2q36.3 is associated with prognosis for oestrogen receptor-negative breast cancer patients treated with chemotherapy - Li, Jingmei; Lindstroem, Linda S.; Foo, Jia N.; Rafiq, Sajjad; Schmidt, Marjanka K.; Pharoah, Paul D. P.; Michailidou, Kyriaki; Dennis, Joe; Bolla, Manjeet K.; Wang, Qin; Van'T Veer, Laura J.; Cornelissen, Sten; et al. (Nature Communications, 2014)
Large population-based registry studies have shown that breast cancer prognosis is inherited. Here we analyse single-nucleotide polymorphisms (SNPs) of genes implicated in human immunology and inflammation as candidates for prognostic markers of breast cancer survival involving 1,804 oestrogen receptor (ER)-negative patients treated with chemotherapy (279 events) from 14 European studies in a prior large-scale genotyping experiment, which is part of the Collaborative Oncological Gene-environment Study (COGS) initiative. We carry out replication using Asian COGS samples (n=522, 53 events) and the Prospective Study of Outcomes in Sporadic versus Hereditary breast cancer (POSH) study (n=315, 108 events). Rs4458204_A near CCL20 (2q36.3) is found to be associated with breast cancer-specific death at a genome-wide significant level (n=2,641, 440 events, combined allelic hazard ratio (HR)=1.81 (1.49-2.19); P for trend=1.90 × 10(-9)). Such survival-associated variants can represent ideal targets for tailored therapeutics, and may also enhance our current prognostic prediction capabilities.
EVALuna2:9232

ABCA transporter gene expression and poor outcome in epithelial ovarian cancer - Hedditch, Ellen L.; Gao, Bo; Russell, Amanda J.; Lu, Yi; Emmanuel, Catherine; Beesley, Jonathan; Johnatty, Sharon E.; Chen, Xiaoqing; Harnett, Paul; George, Joshy; Williams, Rebekka T.; Flemming, Claudia; et al. (Journal of the National Cancer Institute, 2014)
ATP-binding cassette (ABC) transporters play various roles in cancer biology and drug resistance, but their association with outcomes in serous epithelial ovarian cancer (EOC) is unknown.The relationship between clinical outcomes and ABC transporter gene expression in two independent cohorts of high-grade serous EOC tumors was assessed with real-time quantitative polymerase chain reaction, analysis of expression microarray data, and immunohistochemistry. Associations between clinical outcomes and ABCA transporter gene single nucleotide polymorphisms were tested in a genome-wide association study. Impact of short interfering RNA-mediated gene suppression was determined by colony forming and migration assays. Association with survival was assessed with Kaplan-Meier analysis and log-rank tests. All statistical tests were two-sided.Associations with outcome were observed with ABC transporters of the "A" subfamily, but not with multidrug transporters. High-level expression of ABCA1, ABCA6, ABCA8, and ABCA9 in primary tumors was statistically significantly associated with reduced survival in serous ovarian cancer patients. Low levels of ABCA5 and the C-allele of rs536009 were associated with shorter overall survival (hazard ratio for death = 1.50; 95% confidence interval [CI] =1.26 to 1.79; P = 6.5e-6). The combined expression pattern of ABCA1, ABCA5, and either ABCA8 or ABCA9 was associated with particularly poor outcome (mean overall survival in group with adverse ABCA1, ABCA5 and ABCA9 gene expression = 33.2 months, 95% CI = 26.4 to 40.1; vs 55.3 months in the group with favorable ABCA gene expression, 95% CI = 49.8 to 60.8; P = .001), independently of tumor stage or surgical debulking status. Suppression of cholesterol transporter ABCA1 inhibited ovarian cancer cell growth and migration in vitro, and statin treatment reduced ovarian cancer cell migration.Expression of ABCA transporters was associated with poor outcome in serous ovarian cancer, implicating lipid trafficking as a potentially important process in EOC.
EVALuna2:9230

A biallelic truncating AEBP1 variant causes connective tissue disorder in two siblings - Hebebrand, Moritz; Vasileiou, Georgia; Krumbiegel, Mandy; Kraus, Cornelia; Uebe, Steffen; Ekici, Arif Bülent; Thiel, Christian; Reis, André; Popp, Bernt (American Journal of Medical Genetics Part A, 2018)
Biallelic variants in the AEBP1 gene cause a novel autosomal-recessive connective tissue disorder (CTD) reminiscent of Ehlers-Danlos Syndrome (EDS). The four previously reported individuals show considerable clinical variability. Unbiased high-throughput sequencing enables the rapid identification of additional cases for such rare entities. We identified the homozygous nonsense variant c.917dup, p.Tyr306* in AEBP1 using clinical exome sequencing in a female individual with previously unsolved CTD. Segregation testing confirmed homozygosity in the clinically affected brother and heterozygous carrier status in the healthy mother. Chromosomal microarray showed that the variant lies in a run of homozygosity, suggesting a common origin of this genomic segment. RT-PCR analysis in the mother revealed a monoallelic expression of the normal transcript supporting a nonsense-mediated mRNA decay and functional nullizygosity as disease mechanism. We describe two individuals from a fourth family with AEBP1-associated CTD. Our results further verify that autosomal-recessive inherited LOF variants in the AEBP1 gene cause clinical features of different EDS subtypes, but also of the marfanoid spectrum. As identification of further individuals is necessary to inform the clinical characterization, we stress the added value of exome sequencing for such rare diseases.
EVALuna2:35120

A case of autosomal recessive spinocerebellar ataxia type 18 with a novel mutation in GRID2 - Hetzelt, Katalin; Kraus, Cornelia; Kusnik, Stefan; Thiel, C.; Ekici, Arif Bülent; Reis, André; Zweier, Christiane (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

A case of severe autosomal recessive spinocerebellar ataxia type 18 with a novel nonsense variant in GRID2 - Hetzelt, Katalin; Kraus, Cornelia; Kusnik, Stefan; Thiel, Christian; Uebe, Steffen; Ekici, Arif Bülent; Trollmann, Regina; Reis, André; Zweier, Christiane (European Journal of Medical Genetics, 2020)
Autosomal-recessive spinocerebellar ataxia type 18 (SCAR18) is a rare neurologic disorder. It is caused by bi-allelic aberrations in the GRID2 gene, encoding an ionotropic glutamate receptor. In total, 20 affected individuals with mainly homozygous/compound heterozygous intragenic deletions/duplications, two different missense variants and one nonsense variant in GRID2 have been reported, so far. SCAR18 is characterized by delayed psychomotor development, intellectual disability, severely impaired gait due to cerebellar ataxia, ocular movement abnormalities, and cerebellar atrophy in brain imaging. By trio exome sequencing, we now identified a novel homozygous nonsense variant (c.568C > T; p.Gln190*) in GRID2 in a four year old female from a consanguineous family who presented with a particularly severe manifestation of SCAR18. The girl was born after an uneventful pregnancy and showed early-onset, profoundly delayed psychomotor development with no achieved psychomotor milestones at age 4 years. Additionally, she presented with severe muscular hypotonia, progressive truncal and appendicular ataxia, binocular vertical nystagmus, central hearing loss and incomplete loss of sight. She was dystrophic, interacted only very little and had behavioral anomalies such as eating hair and bruxism. Brain imaging showed cerebellar hypoplasia, extended cerebrospinal fluid spaces and beginning reduction of cerebral volume. Our findings further delineate the mutational and clinical spectrum of GRID2-associated spinocerebellar ataxia type 18 and indicate that homozygous nonsense variants are possibly associated with the severe end of the SCAR18 phenotypic spectrum.
CRIS-Team Scopus Importer:2020-07-31
Keywords: Ataxia; Autosomal-recessive; Cerebellar hypoplasia; GRID2; Psychomotor development; SCAR18

A comprehensive evaluation of interaction between genetic variants and use of menopausal hormone therapy on mammographic density - Rudolph, Anja; Fasching, Peter; Behrens, Sabine; Eilber, Ursula; Bolla, Manjeet K.; Wang, Qin; Thompson, Deborah; Czene, Kamila; Brand, Judith S.; Li, Jingmei; Scott, Christopher; Pankratz, V. Shane; et al. (Breast Cancer Research, 2015)
Mammographic density is an established breast cancer risk factor with a strong genetic component and can be increased in women using menopausal hormone therapy (MHT). Here, we aimed to identify genetic variants that may modify the association between MHT use and mammographic density.The study comprised 6,298 postmenopausal women from the Mayo Mammography Health Study and nine studies included in the Breast Cancer Association Consortium. We selected for evaluation 1327 single nucleotide polymorphisms (SNPs) showing the lowest P-values for interaction (P int) in a meta-analysis of genome-wide gene-environment interaction studies with MHT use on risk of breast cancer, 2541 SNPs in candidate genes (AKR1C4, CYP1A1-CYP1A2, CYP1B1, ESR2, PPARG, PRL, SULT1A1-SULT1A2 and TNF) and ten SNPs (AREG-rs10034692, PRDM6-rs186749, ESR1-rs12665607, ZNF365-rs10995190, 8p11.23-rs7816345, LSP1-rs3817198, IGF1-rs703556, 12q24-rs1265507, TMEM184B-rs7289126, and SGSM3-rs17001868) associated with mammographic density in genome-wide studies. We used multiple linear regression models adjusted for potential confounders to evaluate interactions between SNPs and current use of MHT on mammographic density.No significant interactions were identified after adjustment for multiple testing. The strongest SNP-MHT interaction (unadjusted P int <0.0004) was observed with rs9358531 6.5kb 5' of PRL. Furthermore, three SNPs in PLCG2 that had previously been shown to modify the association of MHT use with breast cancer risk were found to modify also the association of MHT use with mammographic density (unadjusted P int <0.002), but solely among cases (unadjusted P int SNP×MHT×case-status <0.02).The study identified potential interactions on mammographic density between current use of MHT and SNPs near PRL and in PLCG2, which require confirmation. Given the moderate size of the interactions observed, larger studies are needed to identify genetic modifiers of the association of MHT use with mammographic density.
EVALuna2:9284

Activation of Epithelial Signal Transducer and Activator of Transcription 1 by Interleukin 28 Controls Mucosal Healing in Mice With Colitis and Is Increased in Mucosa of Patients With Inflammatory Bowel Disease. - Chiriac, Mircea-Teodor; Buchen, Barbara; Wandersee, Alexandra; Hundorfean, Gheorghe; Günther, Claudia; Bourjau, Yvonne; Doyle, Sean E.; Frey, Benjamin; Ekici, Arif Bülent; Büttner, Christian; Weigmann, Benno; Atreya, Raja; et al. (Gastroenterology, 2017)
We investigated the roles of interleukin 28A (also called IL28A or interferon λ2) in intestinal epithelial cell (IEC) activation, studying its effects in mouse models of inflammatory bowel diseases (IBD) and intestinal mucosal healing. and Stat1IEC-KO mice also developed more severe colitis in response to oxazolone than control mice. We found IL28 to induce phosphorylation (activation) of STAT1 in epithelial cells, leading to their proliferation in organoid culture. Administration of IL28 to mice with induced colonic wounds promoted mucosal healing. ). We used high-resolution mini-endoscopy and in vivo imaging methods to assess colitis progression. We used 3-dimensional small intestine and colon organoids, along with RNA-Seq and gene ontology methods, to characterize the effects of IL28 on primary IECs. We studied the effects of IL28 on the human intestinal cancer cell line Caco-2 in a wound-healing assay, and in mice colon wounds. Colonic biopsies and resected tissue from patients with IBD (n = 62) and patients without colon inflammation (controls, n = 23) were analyzed by quantitative polymerase chain rection to measure expression of IL28A, IL28RA, and other related cytokines; biopsy samples were also analyzed by immunofluorescence to identify sources of IL28 production. IECs were isolated from patient tissues and incubated with IL28; signal transducer and activator of transcription 1 (STAT1) phosphorylation was measured by immunoblots and confocal imaging. IL28 controls proliferation of IECs in mice with colitis and accelerates mucosal healing by activating STAT1. IL28 might be developed as a therapeutic agent for patients with IBD. BACKGROUND & AIMS RESULTS METHODS CONCLUSIONS
Keywords: Crohn’s Disease; Interferon λ; Ulcerative Colitis; Wound Healing

Activation of Epithelial Signal Transducer and Activator of Transcription 1 by Interleukin 28 Controls Mucosal Healing in Mice With Colitis and Is Increased in Mucosa of Patients With Inflammatory Bowel Disease - Chiriac, Mircea T.; Buchen, Barbara; Wandersee, Alexandra; Hundorfean, Gheorghe; Günther, Claudia; Bourjau, Yvonne; Doyle, Sean E.; Frey, Benjamin; Ekici, Arif Bülent; Büttner, Christian; Weigmann, Benno; Atreya, Raja; et al. (Gastroenterology, 2017)
We investigated the roles of interleukin 28A (also called IL28A or interferon ?2) in intestinal epithelial cell (IEC) activation, studying its effects in mouse models of inflammatory bowel diseases (IBD) and intestinal mucosal healing.Colitis was induced in C57BL/6JCrl mice (controls), mice with IEC-specific disruption of Stat1 (Stat1IEC-KO), mice with disruption of the interferon ? receptor 1 gene (Il28ra(-/-)), and mice with disruption of the interferon regulatory factor 3 gene (Irf3(-/-)), with or without disruption of Irf7 (Irf7(-/-)). We used high-resolution mini-endoscopy and in vivo imaging methods to assess colitis progression. We used 3-dimensional small intestine and colon organoids, along with RNA-Seq and gene ontology methods, to characterize the effects of IL28 on primary IECs. We studied the effects of IL28 on the human intestinal cancer cell line Caco-2 in a wound-healing assay, and in mice colon wounds. Colonic biopsies and resected tissue from patients with IBD (n = 62) and patients without colon inflammation (controls, n = 23) were analyzed by quantitative polymerase chain rection to measure expression of IL28A, IL28RA, and other related cytokines; biopsy samples were also analyzed by immunofluorescence to identify sources of IL28 production. IECs were isolated from patient tissues and incubated with IL28; signal transducer and activator of transcription 1 (STAT1) phosphorylation was measured by immunoblots and confocal imaging.Lamina propria cells in colon tissues of patients with IBD, and mice with colitis, had increased expression of IL28 compared with controls; levels of IL28R were increased in the colonic epithelium of patients with IBD and mice with colitis. Administration of IL28 induced phosphorylation of STAT1 in primary human and mouse IECs, increasing with dose. Il28ra(-/-), Irf3(-/-), Irf3(-/-)Irf7(-/-), as well as Stat1IEC-KO mice, developed more severe colitis after administration of dextran sulfate sodium than control mice, with reduced epithelial restitution. Il28ra(-/-) and Stat1IEC-KO mice also developed more severe colitis in response to oxazolone than control mice. We found IL28 to induce phosphorylation (activation) of STAT1 in epithelial cells, leading to their proliferation in organoid culture. Administration of IL28 to mice with induced colonic wounds promoted mucosal healing.IL28 controls proliferation of IECs in mice with colitis and accelerates mucosal healing by activating STAT1. IL28 might be developed as a therapeutic agent for patients with IBD.
EVALuna2:9356

Activation of Epithelial Signal Transducer and Activator of Transcription 1 by Interleukin 28 Controls Mucosal Healing in Mice With Colitis and Is Increased in Mucosa of Patients With Inflammatory Bowel Disease - Chiriac, Mircea-Teodor; Buchen, Barbara; Wandersee, Alexandra; Hundorfean, Gheorghe; Günther, Claudia; Bourjau, Yvonne; Doyle, Sean E.; Frey, Benjamin; Ekici, Arif Bülent; Büttner, Christian; Weigmann, Benno; Atreya, Raja; et al. (Gastroenterology, 2017)
We investigated the roles of interleukin 28A (also called IL28A or interferon λ2) in intestinal epithelial cell (IEC) activation, studying its effects in mouse models of inflammatory bowel diseases (IBD) and intestinal mucosal healing. and Stat1IEC-KO mice also developed more severe colitis in response to oxazolone than control mice. We found IL28 to induce phosphorylation (activation) of STAT1 in epithelial cells, leading to their proliferation in organoid culture. Administration of IL28 to mice with induced colonic wounds promoted mucosal healing. ). We used high-resolution mini-endoscopy and in vivo imaging methods to assess colitis progression. We used 3-dimensional small intestine and colon organoids, along with RNA-Seq and gene ontology methods, to characterize the effects of IL28 on primary IECs. We studied the effects of IL28 on the human intestinal cancer cell line Caco-2 in a wound-healing assay, and in mice colon wounds. Colonic biopsies and resected tissue from patients with IBD (n = 62) and patients without colon inflammation (controls, n = 23) were analyzed by quantitative polymerase chain rection to measure expression of IL28A, IL28RA, and other related cytokines; biopsy samples were also analyzed by immunofluorescence to identify sources of IL28 production. IECs were isolated from patient tissues and incubated with IL28; signal transducer and activator of transcription 1 (STAT1) phosphorylation was measured by immunoblots and confocal imaging. IL28 controls proliferation of IECs in mice with colitis and accelerates mucosal healing by activating STAT1. IL28 might be developed as a therapeutic agent for patients with IBD. BACKGROUND & AIMS RESULTS METHODS CONCLUSIONS
Keywords: Crohn’s Disease; Interferon λ; Ulcerative Colitis; Wound Healing

A distinct CD38+CD45RA+ population of CD4+, CD8+, and double-negative T cells is controlled by FAS - Maccari, Maria Elena; Fuchs, Sebastian; Kury, Patrick; Andrieux, Geoffroy; Bengsch, Bertram; Lorenz, Myriam Ricarda; Heeg, Maximilian; Rohr, Jan; Jägle, Sabine; Castro, Carla N.; Groß, Miriam; Warthorst, Ursula; et al. (Journal of Experimental Medicine, 2021)
The identification and characterization of rare immune cell populations in humans can be facilitated by their growth advantage in the context of specific genetic diseases. Here, we use autoimmune lymphoproliferative syndrome to identify a population of FAS-controlled TCRαβ+ T cells. They include CD4+, CD8+, and double-negative T cells and can be defined by a CD38+CD45RA+T-BET- expression pattern. These unconventional T cells are present in healthy individuals, are generated before birth, are enriched in lymphoid tissue, and do not expand during acute viral infection. They are characterized by a unique molecular signature that is unambiguously different from other known T cell differentiation subsets and independent of CD4 or CD8 expression. Functionally, FAS-controlled T cells represent highly proliferative, noncytotoxic T cells with an IL-10 cytokine bias. Mechanistically, regulation of this physiological population is mediated by FAS and CTLA4 signaling, and its survival is enhanced by mTOR and STAT3 signals. Genetic alterations in these pathways result in expansion of FAS-controlled T cells, which can cause significant lymphoproliferative disease.
CRIS-Team Scopus Importer:2020-12-18

Adult alcohol drinking and emotional tone are mediated by neutral sphingomyelinase during development in males - Kalinichenko, Liubov; Mühle, Christiane; Jia, Tianye; Anderheiden, Felix; Datz, Maria; Eberle, Anna-Lisa; Eulenburg, Volker; Granzow, Jonas; Hofer, Martin Jürgen; Hohenschild, Julia; Huber, Sabine; Kämpf, Stefanie; et al. (Cerebral Cortex, 2022)
Alcohol use, abuse, and addiction, and resulting health hazards are highly sex-dependent with unknown mechanisms. Previously, strong links between the SMPD3 gene and its coded protein neutral sphingomyelinase 2 (NSM) and alcohol abuse, emotional behavior, and bone defects were discovered and multiple mechanisms were identified for females. Here we report strong sex-dimorphisms for central, but not for peripheral mechanisms of NSM action in mouse models. Reduced NSM activity resulted in enhanced alcohol consumption in males, but delayed conditioned rewarding effects. It enhanced the acute dopamine response to alcohol, but decreased monoaminergic systems adaptations to chronic alcohol. Reduced NSM activity increased depression- and anxiety-like behavior, but was not involved in alcohol use for the self-management of the emotional state. Constitutively reduced NSM activity impaired structural development in the brain and enhanced lipidomic sensitivity to chronic alcohol. While the central effects were mostly opposite to NSM function in females, similar roles in bone-mediated osteocalcin release and its effects on alcohol drinking and emotional behavior were observed. These findings support the view that the NSM and multiple downstream mechanism may be a source of the sex-differences in alcohol use and emotional behavior.
CRIS-Team WoS Importer:2022-04-15
Keywords: neutral sphingomyelinase; osteocalcin; depression; alcohol; anxiety

Aggregation tests identify new gene associations with breast cancer in populations with diverse ancestry - Mueller, Stefanie H.; Lai, Alvina G.; Valkovskaya, Maria; Michailidou, Kyriaki; Bolla, Manjeet K.; Wang, Qin; Dennis, Joe; Lush, Michael; Abu-Ful, Zomoruda; Ahearn, Thomas U.; Andrulis, Irene L.; Anton-Culver, Hoda; et al. (Genome Medicine, 2023)
Background: Low-frequency variants play an important role in breast cancer (BC) susceptibility. Gene-based methods can increase power by combining multiple variants in the same gene and help identify target genes. Methods: We evaluated the potential of gene-based aggregation in the Breast Cancer Association Consortium cohorts including 83,471 cases and 59,199 controls. Low-frequency variants were aggregated for individual genes’ coding and regulatory regions. Association results in European ancestry samples were compared to single-marker association results in the same cohort. Gene-based associations were also combined in meta-analysis across individuals with European, Asian, African, and Latin American and Hispanic ancestry. Results: In European ancestry samples, 14 genes were significantly associated (q < 0.05) with BC. Of those, two genes, FMNL3 (P = 6.11 × 10−6) and AC058822.1 (P = 1.47 × 10−4), represent new associations. High FMNL3 expression has previously been linked to poor prognosis in several other cancers. Meta-analysis of samples with diverse ancestry discovered further associations including established candidate genes ESR1 and CBLB. Furthermore, literature review and database query found further support for a biologically plausible link with cancer for genes CBLB, FMNL3, FGFR2, LSP1, MAP3K1, and SRGAP2C. Conclusions: Using extended gene-based aggregation tests including coding and regulatory variation, we report identification of plausible target genes for previously identified single-marker associations with BC as well as the discovery of novel genes implicated in BC development. Including multi ancestral cohorts in this study enabled the identification of otherwise missed disease associations as ESR1 (P = 1.31 × 10−5), demonstrating the importance of diversifying study cohorts.
CRIS-Team Scopus Importer:2023-02-10
Keywords: Breast cancer susceptibility; Diverse ancestry; Gene regulation; Genome-wide association study; Rare variants

A Homozygous Mutation in GPT2 Associated with Nonsyndromic Intellectual Disability in a Consanguineous Family from Costa Rica - Lobo-Prada, Tanya; Sticht, Heinrich; Bogantes-Ledezma, Sixto; Ekici, Arif Bülent; Uebe, Steffen; Reis, André; Leal, Alejandro (JIMD reports, 2017)
Intellectual disability is a highly heterogeneous disease that affects the central nervous system and impairs patients' ability to function independently. Despite multiples genes involved in the etiology of disease, most of the genetic background is yet to be discovered. We used runs of homozygosity and exome sequencing to study a large Costa Rican family with four individuals affected with severe intellectual disability and found a novel homozygous missense mutation, p. 96G>R, c. 286G>A, in all affected individuals. This gene encodes for a pyridoxal enzyme involved in the production of the neurotransmitter glutamate and is highly expressed in the white matter of brain and cerebellum. Protein modeling of GPT2 predicted that the mutation is located in a loop where the substrate binds to the active site of the enzyme, therefore, suggesting that the catalytic activity is impaired. With our report of a second mutation we fortify the importance of GPT2 as a novel cause of autosomal recessive nonsyndromic intellectual disability and support the premise that GPT2 is highly important for the neurodevelopment of the central nervous system.The mutation p. 96G>R c. 286G>A in GPT2, located in a loop where the substrate binds to the active site of the enzyme, fortifies the importance of GPT2 in the pathogenesis of nonsyndromic intellectual disability.
EVALuna2:9390

A large-scale assessment of two-way SNP interactions in breast cancer susceptibility using 46 450 cases and 42 461 controls from the breast cancer association consortium - Milne, Roger L.; Herranz, Jesus; Michailidou, Kyriaki; Dennis, Joe; Tyrer, Jonathan P.; Zamora, M. Pilar; Arias-Perez, Jose Ignacio; Gonzalez-Neira, Anna; Pita, Guillermo; Alonso, M. Rosario; Wang, Qin; Bolla, Manjeet K.; et al. (Human Molecular Genetics, 2014)
Part of the substantial unexplained familial aggregation of breast cancer may be due to interactions between common variants, but few studies have had adequate statistical power to detect interactions of realistic magnitude. We aimed to assess all two-way interactions in breast cancer susceptibility between 70 917 single nucleotide polymorphisms (SNPs) selected primarily based on prior evidence of a marginal effect. Thirty-eight international studies contributed data for 46 450 breast cancer cases and 42 461 controls of European origin as part of a multi-consortium project (COGS). First, SNPs were preselected based on evidence (P < 0.01) of a per-allele main effect, and all two-way combinations of those were evaluated by a per-allele (1 d.f.) test for interaction using logistic regression. Second, all 2.5 billion possible two-SNP combinations were evaluated using Boolean operation-based screening and testing, and SNP pairs with the strongest evidence of interaction (P < 10(-4)) were selected for more careful assessment by logistic regression. Under the first approach, 3277 SNPs were preselected, but an evaluation of all possible two-SNP combinations (1 d.f.) identified no interactions at P < 10(-8). Results from the second analytic approach were consistent with those from the first (P > 10(-10)). In summary, we observed little evidence of two-way SNP interactions in breast cancer susceptibility, despite the large number of SNPs with potential marginal effects considered and the very large sample size. This finding may have important implications for risk prediction, simplifying the modelling required. Further comprehensive, large-scale genome-wide interaction studies may identify novel interacting loci if the inherent logistic and computational challenges can be overcome.
EVALuna2:9207

Alport syndrome and autosomal dominant tubulointerstitial kidney disease frequently underlie end-stage renal disease of unknown origin-a single-center analysis - Leenen, Esther; Erger, Florian; Altmuller, Janine; Wenzel, Andrea; Thiele, Holger; Harth, Ana; Tschernoster, Nikolai; Lokhande, Shanti; Joerres, Achim; Becker, Jan-Ulrich; Ekici, Arif Bülent; Huettel, Bruno; et al. (Nephrology Dialysis Transplantation, 2022)
Background The prevalence of end-stage renal disease of unknown etiology in adult patients is globally high and accounts for almost 20% of all dialysis patients. Recent studies have suggested that the percentage of adult patients with a causal genetic variant has been underestimated so far. Despite severe prognostic and therapeutic implications, awareness about prevalence and manifestations of genetic kidney diseases in adult renal patients is still limited. Methods We recruited 58 individuals from 39 families at our transplantation center, fulfilling at least one of the following criteria: (i) unclear etiology of kidney disease, (ii) clinically suspected genetic kidney disease and (iii) positive family history for nephropathies. The cohort consisted of patients waitlisted for kidney transplantation and patients in the follow-up after transplantation. Detailed documentation of family history and phenotype was obtained before initiating gene panel sequencing of 479 nephropathy-associated genes. Results With this study design, a molecular genetic diagnosis was established in one-third of all patients. Mutations in the collagen COL4A genes, and mutations in MUC1 and UMOD were the most frequent among all detected causal variants. Overall, rare genetic variants were detected in more than half of all cases. Conclusion The combination of detailed phenotyping prior to next-generation sequencing diagnostics was highly efficient. Elucidating the underlying genetic causes in a cohort of adult renal patients has considerable clinical impact on medical management.
CRIS-Team WoS Importer:2022-08-12

ALS is imprinted in the chromatin accessibility of blood cells - Kühlwein, Julia K.; Ruf, Wolfgang P.; Kandler, Katharina; Witzel, Simon; Lang, Christina; Mulaw, Medhanie A.; Ekici, Arif Bülent; Weishaupt, Jochen H.; Ludolph, Albert C.; Grozdanov, Veselin; Danzer, Karin M. (Cellular and Molecular Life Sciences, 2023)
Amyotrophic Lateral Sclerosis (ALS) is a complex and incurable neurodegenerative disorder in which genetic and epigenetic factors contribute to the pathogenesis of all forms of ALS. The interplay of genetic predisposition and environmental footprints generates epigenetic signatures in the cells of affected tissues, which then alter transcriptional programs. Epigenetic modifications that arise from genetic predisposition and systemic environmental footprints should in theory be detectable not only in affected CNS tissue but also in the periphery. Here, we identify an ALS-associated epigenetic signature (‘epiChromALS’) by chromatin accessibility analysis of blood cells of ALS patients. In contrast to the blood transcriptome signature, epiChromALS includes also genes that are not expressed in blood cells; it is enriched in CNS neuronal pathways and it is present in the ALS motor cortex. By combining simultaneous ATAC-seq and RNA-seq with single-cell sequencing in PBMCs and motor cortex from ALS patients, we demonstrate that epigenetic changes associated with the neurodegenerative disease can be found in the periphery, thus strongly suggesting a mechanistic link between the epigenetic regulation and disease pathogenesis.
CRIS-Team Scopus Importer:2023-05-05
Keywords: Chromatin remodeling; Epigenome; Integrated analysis; Motor neuron disease; Regulatory elements; Single-nuclei sequencing

Analyses of association of psoriatic arthritis and psoriasis vulgaris with functional NCF1 variants - Löhr, Sabine; Ekici, Arif Bülent; Uebe, Steffen; Büttner, Christian; Köhm, Michaela; Behrens, Frank; Böhm, Beate; Sticherling, Michael; Schett, Georg; Simon, David; Mössner, Rotraut; Nimeh, Ali; et al. (Rheumatology, 2019)
CRIS-Team Scopus Importer:2019-07-02

A new semisynthetic cardenolide analog 3β-[2-(1-amantadine)-1-on-ethylamine]-digitoxigenin (AMANTADIG) affects G2/M cell cycle arrest and miRNA expression profiles and enhances proapoptotic survivin-2B expression in renal cell carcinoma cell lines - Nolte, Elke; Wach, Sven; Silva, Izabella Thais; Lukat, Sabine; Ekici, Arif Bülent; Munkert, Jennifer; Müller-Uri, Frieder; Kreis, Wolfgang; Simões, Cláudia M. O.; Vera González, Julio; Wullich, Bernd; Taubert, Helge; et al. (Oncotarget, 2017)
EVALuna2:9377
Keywords: Cardiac glycoside analog; Cell cycle; 3β-[2-(1-amantadine)-1-on-ethylamine]-digitoxigenin; Human renal cell carcinoma cells; MiRNA

Anti-CD19 CAR T cell therapy for refractory systemic lupus erythematosus - Mackensen, Andreas; Müller, Fabian; Mougiakakos, Dimitrios; Böltz, Sebastian; Wilhelm, Artur; Aigner, Michael; Völkl, Simon; Simon, David; Kleyer, Arnd; Munoz, Luis Enrique; Kretschmann, Sascha; Kharboutli, Soraya; et al. (Nature Medicine, 2022)
Systemic lupus erythematosus (SLE) is a life-threatening autoimmune disease characterized by adaptive immune system activation, formation of double-stranded DNA autoantibodies and organ inflammation. Five patients with SLE (four women and one man) with a median (range) age of 22 (6) years, median (range) disease duration of 4 (8) years and active disease (median (range) SLE disease activity index Systemic Lupus Erythematosus Disease Activity Index: 16 (8)) refractory to several immunosuppressive drug treatments were enrolled in a compassionate-use chimeric antigen receptor (CAR) T cell program. Autologous T cells from patients with SLE were transduced with a lentiviral anti-CD19 CAR vector, expanded and reinfused at a dose of 1 × 106 CAR T cells per kg body weight into the patients after lymphodepletion with fludarabine and cyclophosphamide. CAR T cells expanded in vivo, led to deep depletion of B cells, improvement of clinical symptoms and normalization of laboratory parameters including seroconversion of anti-double-stranded DNA antibodies. Remission of SLE according to DORIS criteria was achieved in all five patients after 3 months and the median (range) Systemic Lupus Erythematosus Disease Activity Index score after 3 months was 0 (2). Drug-free remission was maintained during longer follow-up (median (range) of 8 (12) months after CAR T cell administration) and even after the reappearance of B cells, which was observed after a mean (±s.d.) of 110 ± 32 d after CAR T cell treatment. Reappearing B cells were naïve and showed non-class-switched B cell receptors. CAR T cell treatment was well tolerated with only mild cytokine-release syndrome. These data suggest that CD19 CAR T cell transfer is feasible, tolerable and highly effective in SLE.
CRIS-Team Scopus Importer:2022-09-30

A Peroxisomal Disorder of Severe Intellectual Disability, Epilepsy, and Cataracts Due to Fatty Acyl-CoA Reductase 1 Deficiency - Buchert, Rebecca; Tawamie, Hasan; Smith, Christopher; Uebe, Steffen; Innes, A. Micheil; Al Hallak, Bassam; Ekici, Arif Bülent; Sticht, Heinrich; Schwarze, Bernd; Lamont, Ryan E.; Parboosingh, Jillian S.; Bernier, Francois P.; et al. (American Journal of Human Genetics, 2014)
Rhizomelic chondrodysplasia punctata (RCDP) is a group of disorders with overlapping clinical features including rhizomelia, chondrodysplasia punctata, coronal clefts, cervical dysplasia, congenital cataracts, profound postnatal growth retardation, severe intellectual disability, and seizures. Mutations in PEX7, GNPAT, and AGPS, all involved in the plasmalogen-biosynthesis pathway, have been described in individuals with RCDP. Here, we report the identification of mutations in another gene in plasmalogen biosynthesis, fatty acyl-CoA reductase 1 (FAR1), in two families affected by severe intellectual disability, early-onset epilepsy, microcephaly, congenital cataracts, growth retardation, and spasticity. Exome analyses revealed a homozygous in-frame indel mutation (c.495_507delinsT [p.Glu165_Pro169delinsAsp]) in two siblings from a consanguineous family and compound-heterozygous mutations (c.[787C>T];[1094A>G], p.[Arg263(*)];[Asp365Gly]) in a third unrelated individual. FAR1 reduces fatty acids to their respective fatty alcohols for the plasmalogen-biosynthesis pathway. To assess the pathogenicity of the identified mutations, we transfected human embryonic kidney 293 cells with plasmids encoding FAR1 with either wild-type or mutated constructs and extracted the lipids from the cells. We screened the lipids with gas chromatography and mass spectrometry and found that all three mutations abolished the reductase activity of FAR1, given that no fatty alcohols could be detected. We also observed reduced plasmalogens in red blood cells in one individual to a range similar to that seen in individuals with RCDP, further supporting abolished FAR1 activity. We thus expand the spectrum of clinical features associated with defects in plasmalogen biosynthesis to include FAR1 deficiency as a cause of syndromic severe intellectual disability with cataracts, epilepsy, and growth retardation but without rhizomelia.
EVALuna2:9238

Arginase expression impedes the resolution of intestinal inflammation by altering the fecal microbiome and the metabolome - Baier, Julia; Gänsbauer, Maximilian; Giessler, Claudia; Arnold, Harald; Muske, Mercedes; Schleicher, Ulrike; Lukassen, Sören; Ekici, Arif Bülent; Rauh, Manfred; Daniel, Christoph; Hartmann, Arndt; Schmid, Benjamin; et al. (Journal of Clinical Investigation, 2020)
Arginase 1 (Arg1), which converts L-arginine into ornithine and urea, exerts pleiotropic immunoregulatory effects. However, the function of Arg1 in inflammatory bowel disease (IBD) remains poorly characterized. Here, we found that Arg1 expression correlated with the degree of inflammation in intestinal tissues from IBD patients. In mice, Arg1 was upregulated in an IL-4-/IL-13- and intestinal microbiota-dependent manner. Tie2-Cre+/-Arg1fl/fl mice lacking Arg1 in hematopoietic and endothelial cells recovered faster from experimental colitis than Arg1-expressing littermates. This correlated with decreased vessel density, compositional changes in intestinal microbiota, diminished infiltration by myeloid cells and an accumulation of intraluminal polyamines that promote epithelial healing. The pro-resolving effect of Arg1-deletion was reduced by an L-arginine-free diet, but rescued by simultaneous deletion of other L-arginine-metabolizing enzymes such as Arg2 or Nos2, demonstrating that protection from colitis requires L-arginine. Fecal microbiota transfers from Tie2-Cre+/-Arg1fl/fl mice into wild-type recipients ameliorated intestinal inflammation while transfers from wild-type littermates into Arg1-deficient mice prevented an advanced recovery from colitis. Thus, an increased availability of L-arginine as well as altered intestinal microbiota and metabolic products account for the accelerated resolution from colitis in the absence of Arg1. Consequently, the metabolism of L-arginine may serve as target for clinical intervention in IBD patients.<br

A saturated map of common genetic variants associated with human height - Yengo, Loic; Vedantam, Sailaja; Marouli, Eirini; Sidorenko, Julia; Bartell, Eric; Sakaue, Saori; Graff, Marielisa; Eliasen, Anders U.; Jiang, Yunxuan; Raghavan, Sridharan; Miao, Jenkai; Arias, Joshua D.; et al. (Nature, 2022)
Common single-nucleotide polymorphisms (SNPs) are predicted to collectively explain 40–50% of phenotypic variation in human height, but identifying the specific variants and associated regions requires huge sample sizes1. Here, using data from a genome-wide association study of 5.4 million individuals of diverse ancestries, we show that 12,111 independent SNPs that are significantly associated with height account for nearly all of the common SNP-based heritability. These SNPs are clustered within 7,209 non-overlapping genomic segments with a mean size of around 90 kb, covering about 21% of the genome. The density of independent associations varies across the genome and the regions of increased density are enriched for biologically relevant genes. In out-of-sample estimation and prediction, the 12,111 SNPs (or all SNPs in the HapMap 3 panel2) account for 40% (45%) of phenotypic variance in populations of European ancestry but only around 10–20% (14–24%) in populations of other ancestries. Effect sizes, associated regions and gene prioritization are similar across ancestries, indicating that reduced prediction accuracy is likely to be explained by linkage disequilibrium and differences in allele frequency within associated regions. Finally, we show that the relevant biological pathways are detectable with smaller sample sizes than are needed to implicate causal genes and variants. Overall, this study provides a comprehensive map of specific genomic regions that contain the vast majority of common height-associated variants. Although this map is saturated for populations of European ancestry, further research is needed to achieve equivalent saturation in other ancestries.
CRIS-Team Scopus Importer:2022-10-28

Assessment of variation in immunosuppressive pathway genes reveals TGFBR2 to be associated with prognosis of estrogen receptor-negative breast cancer after chemotherapy - Lei, Jieping; Rudolph, Anja; Moysich, Kirsten B.; Rafiq, Sajjad; Behrens, Sabine; Goode, Ellen L.; Pharoah, Paul Pd; Seibold, Petra; Fasching, Peter; Andrulis, Irene L.; Kristensen, Vessela N.; Couch, Fergus J.; et al. (Breast Cancer Research, 2015)
Tumor lymphocyte infiltration is associated with clinical response to chemotherapy in estrogen receptor (ER) negative breast cancer. To identify variants in immunosuppressive pathway genes associated with prognosis after adjuvant chemotherapy for ER-negative patients, we studied stage I-III invasive breast cancer patients of European ancestry, including 9,334 ER-positive (3,151 treated with chemotherapy) and 2,334 ER-negative patients (1,499 treated with chemotherapy).We pooled data from sixteen studies from the Breast Cancer Association Consortium (BCAC), and employed two independent studies for replications. Overall 3,610 single nucleotide polymorphisms (SNPs) in 133 genes were genotyped as part of the Collaborative Oncological Gene-environment Study, in which phenotype and clinical data were collected and harmonized. Multivariable Cox proportional hazard regression was used to assess genetic associations with overall survival (OS) and breast cancer-specific survival (BCSS). Heterogeneity according to chemotherapy or ER status was evaluated with the log-likelihood ratio test.Three independent SNPs in TGFBR2 and IL12B were associated with OS (P <10?³) solely in ER-negative patients after chemotherapy (267 events). Poorer OS associated with TGFBR2 rs1367610 (G > C) (per allele hazard ratio (HR) 1.54 (95% confidence interval (CI) 1.22 to 1.95), P = 3.08 × 10??) was not found in ER-negative patients without chemotherapy or ER-positive patients with chemotherapy (P for interaction <10-3). Two SNPs in IL12B (r² = 0.20) showed different associations with ER-negative disease after chemotherapy: rs2546892 (G > A) with poorer OS (HR 1.50 (95% CI 1.21 to 1.86), P = 1.81 × 10??), and rs2853694 (A > C) with improved OS (HR 0.73 (95% CI 0.61 to 0.87), P = 3.67 × 10??). Similar associations were observed with BCSS. Association with TGFBR2 rs1367610 but not IL12B variants replicated using BCAC Asian samples and the independent Prospective Study of Outcomes in Sporadic versus Hereditary Breast Cancer Study and yielded a combined HR of 1.57 ((95% CI 1.28 to 1.94), P = 2.05 × 10??) without study heterogeneity.TGFBR2 variants may have prognostic and predictive value in ER-negative breast cancer patients treated with adjuvant chemotherapy. Our findings provide further insights into the development of immunotherapeutic targets for ER-negative breast cancer.
EVALuna2:9270

Assessment of variation in immunosuppressive pathway genes reveals TGFBR2 to be associated with risk of clear cell ovarian cancer - Hampras, Shalaka S.; Sucheston-Campbell, Lara E.; Cannioto, Rikki; Chang-Claude, Jenny; Modugno, Francesmary; Doerk, Thilo; Hillemanns, Peter; Preus, Leah; Knutson, Keith L.; Wallace, Paul K.; Hong, Chi-Chen; Friel, Grace; et al. (Oncotarget, 2016)
Regulatory T (Treg) cells, a subset of CD4+ T lymphocytes, are mediators of immunosuppression in cancer, and, thus, variants in genes encoding Treg cell immune molecules could be associated with ovarian cancer.In a population of 15,596 epithelial ovarian cancer (EOC) cases and 23,236 controls, we measured genetic associations of 1,351 SNPs in Treg cell pathway genes with odds of ovarian cancer and tested pathway and gene-level associations, overall and by histotype, for the 25 genes, using the admixture likelihood (AML) method. The most significant single SNP associations were tested for correlation with expression levels in 44 ovarian cancer patients.The most significant global associations for all genes in the pathway were seen in endometrioid (p = 0.082) and clear cell (p = 0.083), with the most significant gene level association seen with TGFBR2 (p = 0.001) and clear cell EOC. Gene associations with histotypes at p < 0.05 included: IL12 (p = 0.005 and p = 0.008, serous and high-grade serous, respectively), IL8RA (p = 0.035, endometrioid and mucinous), LGALS1 (p = 0.03, mucinous), STAT5B (p = 0.022, clear cell), TGFBR1 (p = 0.021 endometrioid) and TGFBR2 (p = 0.017 and p = 0.025, endometrioid and mucinous, respectively).Common inherited gene variation in Treg cell pathways shows some evidence of germline genetic contribution to odds of EOC that varies by histologic subtype and may be associated with mRNA expression of immune-complex receptor in EOC patients.
EVALuna2:9345

Association analyses of functional NCF1 variants in psoriatic arthritis and psoriasis vulgaris - Hüffmeier, Ulrike; Löhr, Sabine; Ekici, Arif Bülent; Uebe, S.; Koehm, M.; Behrens, F.; Boehm, B.; Sticherling, Michael; Schett, Georg; Moessner, R.; Nimeh, A.; Assmann, G.; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2019)
CRIS-Team WoS Importer:2019-10-25

Association analysis identifies 65 new breast cancer risk loci - Michailidou, Kyriaki; Lindstrom, Sara; Dennis, Joe; Beesley, Jonathan; Hui, Shirley; Kar, Siddhartha; Lemacon, Audrey; Soucy, Penny; Glubb, Dylan; Rostamianfar, Asha; Bolla, Manjeet K.; Wang, Qin; et al. (Nature, 2017)
Breast cancer risk is influenced by rare coding variants in susceptibility genes, such as BRCA1, and many common, mostly non-coding variants. However, much of the genetic contribution to breast cancer risk remains unknown. Here we report the results of a genome-wide association study of breast cancer in 122,977 cases and 105,974 controls of European ancestry and 14,068 cases and 13,104 controls of East Asian ancestry. We identified 65 new loci that are associated with overall breast cancer risk at P < 5 × 10-8. The majority of credible risk single-nucleotide polymorphisms in these loci fall in distal regulatory elements, and by integrating in silico data to predict target genes in breast cells at each locus, we demonstrate a strong overlap between candidate target genes and somatic driver genes in breast tumours. We also find that heritability of breast cancer due to all single-nucleotide polymorphisms in regulatory features was 2-5-fold enriched relative to the genome-wide average, with strong enrichment for particular transcription factor binding sites. These results provide further insight into genetic susceptibility to breast cancer and will improve the use of genetic risk scores for individualized screening and prevention.
EVALuna2:9385

Association of genomic variants at the human leukocyte antigen locus with cervical cancer risk,HPVstatus and gene expression levels - Ramachandran, Dhanya; Schuermann, Peter; Mao, Qianqian; Wang, Yingying; Bretschneider, Lisa-Marie; Speith, Lisa-Marie; Huelse, Fabienne; Enssen, Julia; Bousset, Kristine; Jentschke, Matthias; Boehmer, Gerd; Strauss, Hans-Georg; et al. (International Journal of Cancer, 2020)
The human leukocyte antigen (HLA) locus on chromosome 6 has been reported to be associated with cervical cancer. We investigated two independent single-nucleotide polymorphisms in a large case-control series of cervical dysplasia and carcinoma that has been newly established by the German Cervigen Consortium, comprising a total of 2481 cases and 1556 healthy females. We find significant associations for both variants, rs9272117 atHLA-DQA1and rs2844511 atMICAandHCP5, with cervical disease. Both variants showed evidence of association with invasive cervical cancer (rs9272117: OR 0.89, 95% CI 0.79-0.99,P= .036; rs2844511: OR 1.17, 95% CI 1.04-1.31,P= .008) and with high-grade dysplasia (rs9272117: OR 0.78, 95% CI 0.70-0.87,P= 7.1 x 10(-6); rs2844511: OR 1.13, 95% CI 1.01-1.26,P= .035), as well as in a combined analysis of both groups (rs9272117: OR 0.83, 95% CI 0.75-0.91,P= 6.9 x 10(-5); rs2844511: OR 1.14, 95% CI 1.04-1.26,P= .005). Variant rs2844511, but not rs9272117, also showed modest evidence of association with low-grade dysplasia (OR 1.26, 95% CI 1.04-1.54,P= .019). In case-only analyses, rs2844511 tended to predict HPV status (P= .044) and rs9272117 tended to associate with HPV16 (P= .022). RNA studies in cervical samples showed a significant correlation in the transcript levels ofMICA,HCP5andHLA-DQA1, suggesting extensive co-regulation. All three genes were upregulated in HPV16-positive samples. In stratified analyses, rs9272117 was associated withHLA-DQA1levels, specifically in HPV-positive samples, while rs2844511 was associated withMICAandHCP5levels. The risk allele of rs2844511 was required for correlations betweenMICAorHCP5withHLA-DQA1. Altogether, our results support 6p21.32-33 as the first consistent cervical cancer susceptibility locus and provide evidence for a link between genetic risk variants, HPV16 status and transcript levels ofHLA-DQA1,HCP5andMICA, which may contribute to tumor immune evasion.
CRIS-Team WoS Importer:2020-07-24

Association of germline genetic variants with breast cancer-specific survival in patient subgroups defined by clinic-pathological variables related to tumor biology and type of systemic treatment - Morra, Anna; Escala-Garcia, Maria; Beesley, Jonathan; Keeman, Renske; Canisius, Sander; Ahearn, Thomas U.; Andrulis, Irene L.; Anton-Culver, Hoda; Arndt, Volker; Auer, Paul L.; Augustinsson, Annelie; Freeman, Laura E. Beane; et al. (BREAST CANCER RES, 2021)
Background Given the high heterogeneity among breast tumors, associations between common germline genetic variants and survival that may exist within specific subgroups could go undetected in an unstratified set of breast cancer patients. Methods We performed genome-wide association analyses within 15 subgroups of breast cancer patients based on prognostic factors, including hormone receptors, tumor grade, age, and type of systemic treatment. Analyses were based on 91,686 female patients of European ancestry from the Breast Cancer Association Consortium, including 7531 breast cancer-specific deaths over a median follow-up of 8.1 years. Cox regression was used to assess associations of common germline variants with 15-year and 5-year breast cancer-specific survival. We assessed the probability of these associations being true positives via the Bayesian false discovery probability (BFDP < 0.15). Results Evidence of associations with breast cancer-specific survival was observed in three patient subgroups, with variant rs5934618 in patients with grade 3 tumors (15-year-hazard ratio (HR) [95% confidence interval (CI)] 1.32 [1.20, 1.45], P = 1.4E-08, BFDP = 0.01, per G allele); variant rs4679741 in patients with ER-positive tumors treated with endocrine therapy (15-year-HR [95% CI] 1.18 [1.11, 1.26], P = 1.6E-07, BFDP = 0.09, per G allele); variants rs1106333 (15-year-HR [95% CI] 1.68 [1.39,2.03], P = 5.6E-08, BFDP = 0.12, per A allele) and rs78754389 (5-year-HR [95% CI] 1.79 [1.46,2.20], P = 1.7E-08, BFDP = 0.07, per A allele), in patients with ER-negative tumors treated with chemotherapy. Conclusions We found evidence of four loci associated with breast cancer-specific survival within three patient subgroups. There was limited evidence for the existence of associations in other patient subgroups. However, the power for many subgroups is limited due to the low number of events. Even so, our results suggest that the impact of common germline genetic variants on breast cancer-specific survival might be limited.
CRIS-Team WoS Importer:2021-09-03

Association of mineral and bone biomarkers with adverse cardiovascular outcomes and mortality in the German Chronic Kidney Disease (GCKD) cohort - Reimer, Katharina Charlotte; Nadal, Jennifer; Meiselbach, Heike; Schmid, Matthias; Schultheiss, Ulla T.; Kotsis, Fruzsina; Stockmann, Helena; Friedrich, Nele; Nauck, Matthias; Krane, Vera; Eckardt, Kai-Uwe; Schneider, Markus; et al. (Bone Research, 2023)
Mineral and bone disorder (MBD) in chronic kidney disease (CKD) is tightly linked to cardiovascular disease (CVD). In this study, we aimed to compare the prognostic value of nine MBD biomarkers to determine those associated best with adverse cardiovascular (CV) outcomes and mortality. In 5 217 participants of the German CKD (GCKD) study enrolled with an estimated glomerular filtration rate (eGFR) between 30–60 mL·min−1 per 1.73 m2 or overt proteinuria, serum osteoprotegerin (OPG), C-terminal fibroblast growth factor-23 (FGF23), intact parathyroid hormone (iPTH), bone alkaline phosphatase (BAP), cross-linked C-telopeptide of type 1 collagen (CTX1), procollagen 1 intact N-terminal propeptide (P1NP), phosphate, calcium, and 25-OH vitamin D were measured at baseline. Participants with missing values among these parameters (n = 971) were excluded, leaving a total of 4 246 participants for analysis. During a median follow-up of 6.5 years, 387 non-CV deaths, 173 CV deaths, 645 nonfatal major adverse CV events (MACEs) and 368 hospitalizations for congestive heart failure (CHF) were observed. OPG and FGF23 were associated with all outcomes, with the highest hazard ratios (HRs) for OPG. In the final Cox regression model, adjusted for CV risk factors, including kidney function and all other investigated biomarkers, each standard deviation increase in OPG was associated with non-CV death (HR 1.76, 95% CI: 1.35–2.30), CV death (HR 2.18, 95% CI: 1.50–3.16), MACE (HR 1.38, 95% CI: 1.12–1.71) and hospitalization for CHF (HR 2.05, 95% CI: 1.56–2.69). Out of the nine biomarkers examined, stratification based on serum OPG best identified the CKD patients who were at the highest risk for any adverse CV outcome and mortality.
CRIS-Team Scopus Importer:2023-11-10

Associations between genetic risk variants for kidney diseases and kidney disease etiology - Wunnenburger, Sebastian; Schultheiss, Ulla T.; Walz, Gerd; Hausknecht, Birgit; Ekici, Arif Bülent; Kronenberg, Florian; Eckardt, Kai-Uwe; Kottgen, Anna; Wuttke, Matthias (Scientific Reports, 2017)
Chronic kidney disease (CKD) is a global health problem with a genetic component. Genome-wide association studies have identified variants associated with specific CKD etiologies, but their genetic overlap has not been well studied. This study examined SNP associations across different CKD etiologies and CKD stages using data from 5,034 CKD patients of the German Chronic Kidney Disease study. In addition to confirming known associations, a systemic lupus erythematosus-associated risk variant at TNXB was also associated with CKD attributed to type 1 diabetes (p = 2.5 × 10(-)(7)), a membranous nephropathy-associated variant at HLA-DQA1 was also associated with CKD attributed to systemic lupus erythematosus (p = 5.9 × 10(-)(6)), and an IgA risk variant at HLA-DRB1 was associated with both CKD attributed to granulomatosis with polyangiitis (p = 2.0 × 10(-4)) and to type 1 diabetes (p = 4.6 × 10(-11)). Associations were independent of additional risk variants in the respective genetic regions. Evaluation of CKD stage showed a significant association of the UMOD risk variant, previously identified in population-based studies for association with kidney function, for advanced (stage >=G3b) compared to early-stage CKD (<=stage G2). Shared genetic associations across CKD etiologies and stages highlight the role of the immune response in CKD. Association studies with detailed information on CKD etiology can reveal shared genetic risk variants.
EVALuna2:4033

Astrogenesis in the murine dentate gyrus is a life-long and dynamic process - Schneider, Julia; Weigel, Johannes; Wittmann, Marie-Theres; Svehla, Pavel; Ehrt, Sebastian; Zheng, Fang; Elmzzahi, Tarek; Karpf, Julian; Paniagua-Herranz, Lucia; Basak, Onur; Ekici, Arif Bülent; Wiesmann da Silva Reis, André; et al. (EMBO Journal, 2022)
Astrocytes are highly abundant in the mammalian brain, and their functions are of vital importance for all aspects of development, adaption, and aging of the central nervous system (CNS). Mounting evidence indicates the important contributions of astrocytes to a wide range of neuropathies. Still, our understanding of astrocyte development significantly lags behind that of other CNS cells. We here combine immunohistochemical approaches with genetic fate-mapping, behavioral paradigms, single-cell transcriptomics, and in vivo two-photon imaging, to comprehensively assess the generation and the proliferation of astrocytes in the dentate gyrus (DG) across the life span of a mouse. Astrogenesis in the DG is initiated by radial glia-like neural stem cells giving rise to locally dividing astrocytes that enlarge the astrocyte compartment in an outside-in-pattern. Also in the adult DG, the vast majority of astrogenesis is mediated through the proliferation of local astrocytes. Interestingly, locally dividing astrocytes were able to adapt their proliferation to environmental and behavioral stimuli revealing an unexpected plasticity. Our study establishes astrocytes as enduring plastic elements in DG circuits, implicating a vital contribution of astrocyte dynamics to hippocampal plasticity.
CRIS-Team WoS Importer:2022-04-29

Author Correction: Anti-CD19 CAR T cell therapy for refractory systemic lupus erythematosus. - Mackensen, Andreas; Müller, Fabian; Mougiakakos, Dimitrios; Böltz, Sebastian; Wilhelm, Artur; Aigner, Michael; Völkl, Simon; Simon, David; Kleyer, Arnd; Munoz, Luis Enrique; Kretschmann, Sascha; Kharboutli, Soraya; et al. (Nature Medicine, 2023)
EVALuna2:512812

BDV Syndrome: An Emerging Syndrome with Profound Obesity and Neurodevelopmental Delay Resembling Prader-Willi Syndrome - Bosch, Elisabeth; Hebebrand, Moritz; Popp, Bernt; Penger, Theresa; Behring, Bettina; Cox, Helen; Towner, Shelley; Kraus, Cornelia; Wilson, William G.; Khan, Shagufta; Krumbiegel, Mandy; Ekici, Arif Bülent; et al. (Journal of Clinical Endocrinology and Metabolism, 2021)
Context: CPE encodes carboxypeptidase E, an enzyme that converts proneuropeptides and propeptide hormones to bioactive forms. It is widely expressed in the endocrine and central nervous system. To date, 4 individuals from 2 families with core clinical features including morbid obesity, neurodevelopmental delay, and hypogonadotropic hypogonadism, harboring biallelic loss-of-function (LoF) CPE variants, have been reported. Objective: We describe 4 affected individuals from 3 unrelated consanguineous families, 2 siblings of Syrian, 1 of Egyptian, and 1 of Pakistani descent, all harboring novel homozygous CPE LoF variants. Methods: After excluding Prader-Willi syndrome (PWS), exome sequencing was performed in both Syrian siblings. The variants identified in the other 2 individuals were reported as research variants in a large-scale exome study and in the ClinVar database. Computational modeling of all possible missense alterations allowed assessing CPE tolerance to missense variants. Results: All affected individuals were severely obese with neurodevelopmental delay and other endocrine anomalies. Three individuals from 2 families shared the same CPE homozygous truncating variant c.361Câ€ >â€ T, p.(Arg121∗), while the fourth carried the c.994del, p.(Ser333Alafs∗22) variant. Comparison of clinical features with previously described cases and standardization according to the Human Phenotype Ontology terms indicated a recognizable clinical phenotype, which we termed Blakemore-Durmaz-Vasileiou (BDV) syndrome. Computational analysis indicated high conservation of CPE domains and intolerance to missense changes. Conclusion: Biallelic truncating CPE variants are associated with BDV syndrome, a clinically recognizable monogenic recessive syndrome with childhood-onset obesity, neurodevelopmental delay, hypogonadotropic hypogonadism, and hypothyroidism. BDV syndrome resembles PWS. Our findings suggest missense variants may also be clinically relevant.
CRIS-Team Scopus Importer:2021-12-24
Keywords: BDV syndrome; carboxypeptidase E; CPE; hypogonadotropic hypogonadism; neurodevelopmental disorder; obesity

Biallelic Expression of Mucin-1 in Autosomal Dominant Tubulointerstitial Kidney Disease: Implications for Nongenetic Disease Recognition - Knaup, Karl; Hackenbeck, Thomas; Popp, Bernt; Stoeckert, Johanna; Wenzel, Andrea; Büttner-Herold, Maike; Pfister, Frederick; Schüler, Markus; Seven, Didem; May, Annette M.; Halbritter, Jan; Gröne, Hermann Josef; et al. (Journal of the American Society of Nephrology, 2018)
BACKGROUND: Providing the correct diagnosis for patients with tubulointerstitial kidney disease and secondary degenerative disorders, such as hypertension, remains a challenge. The autosomal dominant tubulointerstitial kidney disease (ADTKD) subtype caused by MUC1 mutations (ADTKD-MUC1) is particularly difficult to diagnose, because the mutational hotspot is a complex repeat domain, inaccessible with routine sequencing techniques. Here, we further evaluated SNaPshot minisequencing as a technique for diagnosing ADTKD-MUC1 and assessed immunodetection of the disease-associated mucin 1 frameshift protein (MUC1-fs) as a nongenetic technique. METHODS: We re-evaluated detection of MUC1 mutations by targeted repeat enrichment and SNaPshot minisequencing by haplotype reconstruction via microsatellite analysis in three independent ADTKD-MUC1 families. Additionally, we generated rabbit polyclonal antibodies against MUC1-fs and evaluated immunodetection of wild-type and mutated allele products in human kidney biopsy specimens. RESULTS: The detection of MUC1 mutations by SNaPshot minisequencing was robust. Immunostaining with our MUC1-fs antibodies and an MUC1 antibody showed that both proteins are readily detectable in human ADTKD-MUC1 kidneys, with mucin 1 localized to the apical membrane and MUC1-fs abundantly distributed throughout the cytoplasm. Notably, immunohistochemical analysis of MUC1-fs expression in clinical kidney samples facilitated reliable prediction of the disease status of individual patients. CONCLUSIONS: Diagnosing ADTKD-MUC1 by molecular genetics is possible, but it is technically demanding and labor intensive. However, immunohistochemistry on kidney biopsy specimens is feasible for nongenetic diagnosis of ADTKD-MUC1 and therefore, a valid method to select families for further diagnostics. Our data are compatible with the hypothesis that specific molecular effects of MUC1-fs underlie the pathogenesis of this disease.
EVALuna2:34428

Biallelic intragenic deletion in MASP1 in an adult female with 3MC syndrome - Graul-Neumann, Luitgard M.; Mensah, Martin A.; Klopocki, Eva; Uebe, Steffen; Ekici, Arif Bülent; Thiel, Christian; Reis, André; Zweier, Christiane (European Journal of Medical Genetics, 2018)
3MC syndrome is a rare autosomal recessive disorder with characteristic craniofacial dysmorphism and multiple anomalies. It is caused by biallelic mutations in one of three genes, MASP1, COLEC11 and COLEC10, all encoding factors of the lectin complement pathway. In MASP1, either truncating mutations or missense variants in exon 12 encoding the C-terminal serine protease domain specific for isoform MASP-3 are causative. By trio exome sequencing we now identified a novel, homozygous 2kb deletion, partially affecting exon 12 in an adult female with the typical facial gestalt of 3MC syndrome and hearing loss, but without the main feature cleft lip/palate, and without intellectual disability, or short stature. We therefore expand the MASP1 associated mutational and clinical spectrum and describe the development of her clinical presentation over a period of 21 years. As the homozygous deletion in our patient was only found by thorough and visual evaluation of the whole exome sequencing data, such deletions might escape detection in some routine diagnostic workflows and might explain a few of the so far molecularly unconfirmed cases of 3MC syndrome.
EVALuna2:34626

Biallelic SEMA3A defects cause a novel type of syndromic short stature - Hofmann, Kristin; Zweier, Markus; Sticht, Heinrich; Zweier, Christiane; Wittmann, Wolfgang; Hoyer, Juliane; Uebe, Steffen; Van Haeringen, Arie; Thiel, Christian; Ekici, Arif Bülent; Reis, André; Rauch, Anita (American Journal of Medical Genetics Part A, 2013)
Chromosomal microarray testing is commonly used to identify disease causing de novo copy number variants in patients with developmental delay and multiple congenital anomalies. In such a patient we now observed an 150 kb deletion on chromosome 7q21.11 affecting the first exon of the axon guidance molecule gene SEMA3A (sema domain, immunoglobulin domain (Ig), short basic domain, secreted, (semaphorin) 3A). This deletion was inherited from the healthy father, but considering the function of SEMA3A and phenotypic similarity to the knock-out mice, we still assumed a pathogenic relevance and tested for a recessive second defect. Sequencing of SEMA3A in the patient indeed revealed the de novo in-frame mutation p.Phe316_Lys317delinsThrSerSerAsnGlu. Cloning of the mutated allele in combination with two informative SNPs confirmed compound heterozygosity in the patient. While the altered protein structure was predicted to be benign, aberrant splicing resulting in a premature stop codon was proven by RT-PCR to occur in about half of the transcripts from this allele. Expression profiling in human fetal and adult cDNA panels, confirmed a high expression of SEMA3A in all brain regions as well as in adult and fetal heart and fetal skeletal muscle. Normal intellectual development in the patient was surprising but may be explained by the remaining 20% of SEMA3A expression level demonstrated by quantitative RT-PCR. We therefore report a novel autosomal recessive syndrome characterized by postnatal short stature with relative macrocephaly, camptodactyly, septal heart defect and several minor anomalies caused by biallelic mutations in SEMA3A.
EVALuna2:9194

Blunted transcriptional response to skeletal muscle ischemia in rats with chronic kidney disease: potential role for impaired ischemia-induced angiogenesis - Heiß, Rafael; Fahlbusch, Fabian B.; Jacobi, Johannes; Daniel, Christoph; Ekici, Arif Bülent; Cordasic, Nada; Amann, Kerstin Ute; Hilgers, Karl Friedrich; Hartner, Andrea (Physiological Genomics, 2017)
Chronic kidney disease (CKD) is associated with increased cardiovascular morbidity and mortality. Previous studies indicated an impairment of ischemia-induced angiogenesis in skeletal muscle of rats with CKD. We performed a systematic comparison of early gene expression in response to ischemia in rats with or without CKD to identify potential molecular mechanisms underlying impaired angiogenesis in CKD. CKD was induced in male rats by 5/6 nephrectomy (SNX); control rats were sham operated (sham). Eight weeks later, ischemia of the right limb was induced by ligation and resection of the femoral artery. Rats were sacrificed 24 hours after the onset of ischemia, and RNA was extracted from the musculus soleus of the ischemic and the nonischemic hindlimb. To identify differentially expressed transcripts, RNA was analyzed employing Affymetrix GeneChip Rat Genome 230 2.0 Arrays. RT-PCR analysis of selected genes was performed to validate observed changes. Hindlimb ischemia up-regulated 239 genes in CKD and 299 genes in control rats (66% overlap) whereas only a few genes were down-regulated (14 in CKD and 34 in controls), compared with the non-ischemic limb of the same animals. Comparison between the ischemic limbs of CKD and controls revealed down-regulation of 65 genes in CKD; 37 of these genes were also among the ischemia-induced genes in controls. Analysis of functional groups (other than angiogenesis) pointed to genes involved in leukocyte recruitment and fatty acid metabolism. Transcript expression profiling points to a relatively small number of differentially expressed genes which may underlie the impaired post-ischemic angiogenesis in CKD.
EVALuna2:3946

Body mass index and breast cancer survival: a Mendelian randomization analysis - Guo, Qi; Burgess, Stephen; Turman, Constance; Bolla, Manjeet K.; Wang, Qin; Lush, Michael; Abraham, Jean; Aittomaki, Kristiina; Andrulis, Irene L.; Apicella, Carmel; Arndt, Volker; Barrdahl, Myrto; et al. (International Journal of Epidemiology, 2017)
Background: There is increasing evidence that elevated body mass index (BMI) is associated with reduced survival for women with breast cancer. However, the underlying reasons remain unclear. We conducted a Mendelian randomization analysis to investigate a possible causal role of BMI in survival from breast cancer. Methods: We used individual-level data from six large breast cancer case-cohorts including a total of 36 210 individuals (2475 events) of European ancestry. We created a BMI genetic risk score (GRS) based on genotypes at 94 known BMI-associated genetic variants. Association between the BMI genetic score and breast cancer survival was analysed by Cox regression for each study separately. Study-specific hazard ratios were pooled using fixed-effect meta-analysis. Results: BMI genetic score was found to be associated with reduced breast cancer-specific survival for estrogen receptor (ER)-positive cases [hazard ratio (HR) = 1.11, per one-unit increment of GRS, 95% confidence interval (CI) 1.01-1.22, P = 0.03). We observed no association for ER-negative cases (HR = 1.00, per one-unit increment of GRS, 95% CI 0.89-1.13, P = 0.95). Conclusions: Our findings suggest a causal effect of increased BMI on reduced breast cancer survival for ER-positive breast cancer. There is no evidence of a causal effect of higher BMI on survival for ER-negative breast cancer cases.
EVALuna2:33863

Bone marrow-derived myeloid progenitors in the leptomeninges of adult mice - Koeniger, Tobias; Bell, Luisa; Mifka, Anika; Enders, Michael; Hautnnann, Valentin; Mekala, Subba Rao; Kirchner, Philipp; Ekici, Arif Bülent; Schulz, Christian; Woersdoerfer, Philipp; Mencl, Stine; Kleinschnitz, Christoph; et al. (Stem Cells, 2020)
Although the bone marrow contains most hematopoietic activity during adulthood, hematopoietic stem and progenitor cells can be recovered from various extramedullary sites. Cells with hematopoietic progenitor properties have even been reported in the adult brain under steady-state conditions, but their nature and localization remain insufficiently defined. Here, we describe a heterogeneous population of myeloid progenitors in the leptomeninges of adult C57BL/6 mice. This cell pool included common myeloid, granulocyte/macrophage, and megakaryocyte/erythrocyte progenitors. Accordingly, it gave rise to all major myelo-erythroid lineages in clonogenic culture assays. Brain-associated progenitors persisted after tissue perfusion and were partially inaccessible to intravenous antibodies, suggesting their localization behind continuous blood vessel endothelium such as the blood-arachnoid barrier. Flt3Cre lineage tracing and bone marrow transplantation showed that the precursors were derived from adult hematopoietic stem cells and were most likely continuously replaced via cell trafficking. Importantly, their occurrence was tied to the immunologic state of the central nervous system (CNS) and was diminished in the context of neuroinflammation and ischemic stroke. Our findings confirm the presence of myeloid progenitors at the meningeal border of the brain and lay the foundation to unravel their possible functions in CNS surveillance and local immune cell production.
CRIS-Team Scopus Importer:2020-12-25
Keywords: hematopoietic; meninges; mouse; myeloid; progenitor

BRCA mutations and their influence on pathological complete response and prognosis in a clinical cohort of neoadjuvantly treated breast cancer patients - Wunderle, Marius; Gaß, Paul; Häberle, Lothar; Flesch, Vivien M.; Rauh, Claudia; Bani, Mayada; Hack, Carolin; Schrauder, Michael G.; Jud, Sebastian; Emons, Julius; Erber, Ramona; Ekici, Arif Bülent; et al. (Breast Cancer Research and Treatment, 2018)
PURPOSE: BRCA1/2 mutations influence the molecular characteristics and the effects of systemic treatment of breast cancer. This study investigates the impact of germline BRCA1/2 mutations on pathological complete response and prognosis in patients receiving neoadjuvant systemic chemotherapy. METHODS: Breast cancer patients were tested for a BRCA1/2 mutation in clinical routine work and were treated with anthracycline-based or platinum-based neoadjuvant chemotherapy between 1997 and 2015. These patients were identified in the tumor registry of the Breast Center of the University of Erlangen (Germany). Logistic regression and Cox regression analyses were performed to investigate the associations between BRCA1/2 mutation status, pathological complete response, disease-free survival, and overall survival. RESULTS: Among 355 patients, 59 had a mutation in BRCA1 or in BRCA2 (16.6%), 43 in BRCA1 (12.1%), and 16 in BRCA2 (4.5%). Pathological complete response defined as "ypT0; ypN0" was observed in 54.3% of BRCA1/2 mutation carriers, but only in 22.6% of non-carriers. The adjusted odds ratio was 2.48 (95% CI 1.26-4.91) for BRCA1/2 carriers versus non-carriers. Patients who achieved a pathological complete response had better disease-free survival and overall survival rates compared with those who did not achieve a pathological complete response, regardless of BRCA1/2 mutation status. CONCLUSIONS: BRCA1/2 mutation status leads to better responses to neoadjuvant chemotherapy in breast cancer. Pathological complete response is the main predictor of disease-free survival and overall survival, independently of BRCA1/2 mutation status.
EVALuna2:34606

Breast cancer risk - From genetics to molecular understanding of pathogenesis - Fasching, Peter; Ekici, Arif Bülent; Wachter, David Lukas; Hein, Alexander; Bayer, Christian M.; Häberle, Lothar; Löhberg, Christian; Schneider, Michael; Jud, Sebastian; Heusinger, K.; Rübner, Matthias; Rauh, Claudia; et al. (Geburtshilfe und Frauenheilkunde, 2013)
Several advancements over the last decade have triggered the developments in the field of breast cancer risk research. One of them is the availability of the human genome sequence along with cheap genotyping possibilities. Another is the globalization of research, which has led to the growth of research collaboration into large international consortia that facilitate the pooling of clinical and genotype data of hundreds of thousands of patients and healthy control individuals. This review concerns with the recent developments in breast cancer risk research and focuses on the discovery of new genetic breast cancer risk factors and their meaning in the context of established non-genetic risk factors. Finally the clinical application is highly dependent on the accuracy of breast cancer risk prediction models, not only for all breast cancer patients, but also for molecular subtypes, preferably for those which are associated with an unfavorable prognosis. Recently risk prediction incorporates all possible risk factors, which include epidemiological risk factors, mammographic density and genetic risk factors. © Georg Thieme Verlag KG Stuttgart• New York•.
CRIS-Team Scopus Importer:2021-07-19
Keywords: BRCA; breast cancer risk; gene-environment interaction; genetic risk factors; prediction models

Breast Cancer Risk Genes - Association Analysis in More than 113,000 Women - Dorling, Leila; Carvalho, Sara; Allen, Jamie; Gonzalez-Neira, Anna; Luccarini, Craig; Wahlstrom, Cecilia; Pooley, Karen A.; Parsons, Michael T.; Fortuno, Cristina; Wang, Qin; Bolla, Manjeet K.; Dennis, Joe; et al. (New England Journal of Medicine, 2021)
BACKGROUND
CRIS-Team WoS Importer:2021-03-26

Breast cancer risk - Genes, environment and clinics Mammakarzinomrisiko - Gene, Umwelt und Klinik - Fasching, Peter; Ekici, Arif Bülent; Adamietz, B. R.; Wachter, David Lukas; Hein, Alexander; Bayer, Christian M.; Häberle, Lothar; Löhberg, Christian; Jud, Sebastian; Heusinger, K.; Rübner, Matthias; Rauh, Claudia; et al. (Geburtshilfe und Frauenheilkunde, 2011)
The information available about breast cancer risk factors has increased dramatically during the last 10 years. In particular, studies of low-penetrance genes and mammographic density have improved our understanding of breast cancer risk. In addition, initial steps have been taken in investigating interactions between genes and environmental factors. This review concerns with actual data on this topic. Several genome-wide association studies (GWASs) with a casecontrol design, as well as large-scale validation studies, have identified and validated more than a dozen single nucleotide polymorphisms (SNPs) associated with breast cancer risk. They are located not only in or close to genes known to be involved in cancer pathogenesis, but also in genes not previously associated with breast cancer pathogenesis, or may even not be related to any genes. SNPs have also been identified that alter the lifetime risk in BRCA mutation carriers. With regard to nongenetic risk factors, studies of postmenopausal hormone replacement therapy (HRT) have revealed important information on how to weigh up the risks and benefits of HRT. Mammographic density (MD) has become an accepted and important breast cancer risk factor. Lifestyle and nutritional considerations have become an integral part of most studies of breast cancer risk, and some improvements have been made in this field as well. More than 10 years after the publication of the first breast cancer prevention studies with tamoxifen, other substances such as raloxifene and aromatase inhibitors have been investigated and have also been shown to have preventive potential. Finally, mammographic screening systems have been implemented in most Western countries during the last decade. These may be developed further by including more individualized methods of predicting the patients breast cancer risk. © Georg Thieme Verlag KG Stuttgart - New York.
CRIS-Team Scopus Importer:2021-07-19
Keywords: BRCA (breast cancer antigen); breast; breast feeding; CAM (Complementary and Alternative medicine); cancer registry; estrogen receptor

Candidate locus analysis of the TERT-CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Carvajal-Carmona, Luis G.; O'Mara, Tracy A.; Painter, Jodie N.; Lose, Felicity A.; Dennis, Joe; Michailidou, Kyriaki; Tyrer, Jonathan P.; Ahmed, Shahana; Ferguson, Kaltin; Healey, Catherine S.; Pooley, Karen; Beesley, Jonathan; et al. (Human genetics, 2015)
Several studies have reported associations between multiple cancer types and single-nucleotide polymorphisms (SNPs) on chromosome 5p15, which harbours TERT and CLPTM1L, but no such association has been reported with endometrial cancer. To evaluate the role of genetic variants at the TERT-CLPTM1L region in endometrial cancer risk, we carried out comprehensive fine-mapping analyses of genotyped and imputed SNPs using a custom Illumina iSelect array which includes dense SNP coverage of this region. We examined 396 SNPs (113 genotyped, 283 imputed) in 4,401 endometrial cancer cases and 28,758 controls. Single-SNP and forward/backward logistic regression models suggested evidence for three variants independently associated with endometrial cancer risk (P = 4.9 × 10(-6) to P = 7.7 × 10(-5)). Only one falls into a haplotype previously associated with other cancer types (rs7705526, in TERT intron 1), and this SNP has been shown to alter TERT promoter activity. One of the novel associations (rs13174814) maps to a second region in the TERT promoter and the other (rs62329728) is in the promoter region of CLPTM1L; neither are correlated with previously reported cancer-associated SNPs. Using TCGA RNASeq data, we found significantly increased expression of both TERT and CLPTM1L in endometrial cancer tissue compared with normal tissue (TERT P = 1.5 × 10(-18), CLPTM1L P = 1.5 × 10(-19)). Our study thus reports a novel endometrial cancer risk locus and expands the spectrum of cancer types associated with genetic variation at 5p15, further highlighting the importance of this region for cancer susceptibility.
EVALuna2:9280

Cardiovascular changes in the NZB/W F1 mouse model of lupus nephritis - Böhme, Romy; Daniel, Christoph; Ferrazzi, Fulvia; Angeloni, Miriam; Ekici, Arif Bülent; Winkler, Thomas; Hilgers, Karl Friedrich; Wellmann, Ute; Voll, Reinhard E.; Amann, Kerstin Ute (Frontiers in Cardiovascular Medicine, 2023)
Background: Patients with systemic lupus erythematosus (SLE), an autoimmune disease, have a higher risk of cardiovascular (CV) disease and death. In addition, up to 40%–50% of SLE patients develop lupus nephritis (LN) and chronic kidney disease, which is an additional CV risk factor. Thus, the individual contributions of LN and other SLE-specific factors to CV events are unclear. Methods: In this study, we investigated the effect of LN on the development of CV changes using the female NZBxNZW F1 (NZB/W) mouse model of lupus-like disease, with female NZW mice as controls. Standard serologic, morphologic, immunohistologic, and molecular analyses were performed. In a separate group of NZB/W mice, systolic blood pressure (BP) was measured during the course of the disease using tail plethysmography. Results: Our data show marked CV changes in NZB/W mice, i.e., increased heart weight, hypertrophy of the left ventricle (LV) and septum, and increased wall thickness of the intramyocardial arteries and the aorta, which correlated with the progression of renal damage, but not with the age of the mice. In addition, systolic BP was increased in NZB/W mice only when kidney damage progressed and proteinuria was present. Pathway analysis based on gene expression data revealed a significant upregulation of the response to interferon beta in NZB/W mice with moderate kidney injury compared with NZB mice. Furthermore, IFI202b and IL-6 mRNA expression is correlated with CV changes. Multiple linear regression analysis demonstrated serum urea as a surrogate marker of kidney function and IFI202b expression as an independent predictor for LV wall thickness. In addition, deposition of complement factors CFD and C3c in hearts from NZB/W mice was seen, which correlated with the severity of kidney disease. Conclusions: Thus, we postulate that the pathogenesis of CV disease in SLE is affected by renal impairment, i.e., LN, but it can also be partly influenced by lupus-specific cardiac expression of pro-inflammatory factors and complement deposition.
CRIS-Team Scopus Importer:2023-08-18
Keywords: autoimmune disease; cardiovascular disease; IL-15; interferon-related; renal disease; systemic lupus erythematosus

CD200+ fibroblasts form a pro-resolving mesenchymal network in arthritis - Rauber, Simon; Mohammadian, Hashem; Schmidkonz, Christian; Atzinger, Armin; Soare, Alina; Treutlein, Christoph; Kemble, Samuel; Mahony, Christopher B.; Geisthoff, Manuel; Angeli, Mario Raphael; Raimondo, Maria Gabriella; Xu, Cong; et al. (Nature Immunology, 2024)
Fibroblasts are important regulators of inflammation, but whether fibroblasts change phenotype during resolution of inflammation is not clear. Here we use positron emission tomography to detect fibroblast activation protein (FAP) as a means to visualize fibroblast activation in vivo during inflammation in humans. While tracer accumulation is high in active arthritis, it decreases after tumor necrosis factor and interleukin-17A inhibition. Biopsy-based single-cell RNA-sequencing analyses in experimental arthritis show that FAP signal reduction reflects a phenotypic switch from pro-inflammatory MMP3+/IL6+ fibroblasts (high FAP internalization) to pro-resolving CD200+DKK3+ fibroblasts (low FAP internalization). Spatial transcriptomics of human joints indicates that pro-resolving niches of CD200+DKK3+ fibroblasts cluster with type 2 innate lymphoid cells, whereas MMP3+/IL6+ fibroblasts colocalize with inflammatory immune cells. CD200+DKK3+ fibroblasts stabilized the type 2 innate lymphoid cell phenotype and induced resolution of arthritis via CD200–CD200R1 signaling. Taken together, these data suggest a dynamic molecular regulation of the mesenchymal compartment during resolution of inflammation.
Created from Fastlane, Scopus look-up

Characterization of germ cell differentiation in the male mouse through single-cell RNA sequencing - Lukassen, Sören; Bosch, Elisabeth; Ekici, Arif Bülent; Winterpacht, Andreas (Scientific Reports, 2018)
Spermatogenesis in the mouse has been extensively studied for decades. Previous methods, such as histological staining or bulk transcriptome analysis, either lacked resolution at the single-cell level or were focused on a very narrowly defined set of factors. Here, we present the first comprehensive, unbiased single-cell transcriptomic view of mouse spermatogenesis. Our single-cell RNA-seq (scRNA-seq) data on over 2,500 cells from the mouse testis improves upon stage marker detection and validation, capturing the continuity of differentiation rather than artificially chosen stages. scRNA-seq also enables the analysis of rare cell populations masked in bulk sequencing data and reveals new insights into the regulation of sex chromosomes during spermatogenesis. Our data provide the basis for further studies in the field, for the first time providing a high-resolution reference of transcriptional processes during mouse spermatogenesis.
EVALuna2:34135

Choline transporter-like1 (CHER1) is crucial for plasmodesmata maturation in Arabidopsis thaliana - Kraner, Max; Link, Katrin; Melzer, Michael; Ekici, Arif Bülent; Uebe, Steffen; Tarazona, Pablo; Feussner, Ivo; Hofmann, Jörg; Sonnewald, Uwe (Plant Journal, 2016)
Plasmodesmata (PD) are microscopic pores connecting plant cells and enable cell-to-cell transport. Currently, little is known about the molecular mechanisms regulating PD formation and development. To uncover components of PD development we made use of the 17 kDa movement protein (MP17) encoded by the Potato leafroll virus (PLRV). The protein is required for cell-to-cell movement of the virus and localises to complex PD. Forward genetic screening for Arabidopsis mutants with altered PD-binding of MP17 revealed several mutant lines, while molecular genetics, biochemical and microscopic studies allowed further characterisation. Map-based cloning of one mutant revealed a point mutation in the choline transporter-like 1 (CHER1) protein, changing glycine(247) into glutamate. Mutation in CHER1 resulted in a starch excess phenotype and stunted growth. Ultrastructure analysis of shoot apical meristems, developing and fully developed leaves showed reduced PD numbers and the absence of complex PD in fully developed leaves. This indicates that cher1 mutants are impaired in PD formation and development. Global lipid profiling revealed only slight modifications in the overall lipid composition, however, altered composition of PD-associated lipids cannot be ruled out. Thus, cher1 is devoid of complex PD in developed leaves and provides insights into the formation of complex PD at the molecular level. This article is protected by copyright. All rights reserved.
EVALuna2:9344

Chromatin-Remodeling-Factor ARID1B Represses Wnt/?-Catenin Signaling - Vasileiou, Georgia; Ekici, Arif Bülent; Urebe, Steffen; Zweier, Christiane; Hoyer, Juliane; Engels, Hartmut; Behrens, Jürgen; Reis, André; Hadjihannas, Michel (American Journal of Human Genetics, 2015)
The link of chromatin remodeling to both neurodevelopment and cancer has recently been highlighted by the identification of mutations affecting BAF chromatin-remodeling components, such as ARID1B, in individuals with intellectual disability and cancer. However, the underlying molecular mechanism(s) remains unknown. Here, we show that ARID1B is a repressor of Wnt/?-catenin signaling. Through whole-transcriptome analysis, we find that in individuals with intellectual disability and ARID1B loss-of-function mutations, Wnt/?-catenin target genes are upregulated. Using cellular models of low and high Wnt/?-catenin activity, we demonstrate that knockdown of ARID1B activates Wnt/?-catenin target genes and Wnt/?-catenin-dependent transcriptional reporters in a ?-catenin-dependent manner. Reciprocally, forced expression of ARID1B inhibits Wnt/?-catenin signaling downstream of the ?-catenin destruction complex. Both endogenous and exogenous ARID1B associate with ?-catenin and repress Wnt/?-catenin-mediated transcription through the BAF core subunit BRG1. Accordingly, mutations in ARID1B leading to partial or complete deletion of its BRG1-binding domain, as is often observed in intellectual disability and cancers, compromise association with ?-catenin, and the resultant ARID1B mutant proteins fail to suppress Wnt/?-catenin signaling. Finally, knockdown of ARID1B in mouse neuroblastoma cells leads to neurite outgrowth through ?-catenin. The data suggest that aberrations in chromatin-remodeling factors, such as ARID1B, might contribute to neurodevelopmental abnormalities and cancer through deregulation of developmental and oncogenic pathways, such as the Wnt/?-catenin signaling pathway.
EVALuna2:9258

Cis-eQTL analysis and functional validation of candidate susceptibility genes for high-grade serous ovarian cancer - Lawrenson, Kate; Li, Qiyan; Kar, Siddhartha; Seo, Ji-Heui; Tyrer, Jonathan; Spindler, Tassja J.; Lee, Janet; Chen, Yibu; Karst, Alison; Drapkin, Ronny; Aben, Katja K. H.; Anton-Culver, Hoda; et al. (Nature Communications, 2015)
Genome-wide association studies have reported 11 regions conferring risk of high-grade serous epithelial ovarian cancer (HGSOC). Expression quantitative trait locus (eQTL) analyses can identify candidate susceptibility genes at risk loci. Here we evaluate cis-eQTL associations at 47 regions associated with HGSOC risk (P<=10(-5)). For three cis-eQTL associations (P<1.4 × 10(-3), FDR<0.05) at 1p36 (CDC42), 1p34 (CDCA8) and 2q31 (HOXD9), we evaluate the functional role of each candidate by perturbing expression of each gene in HGSOC precursor cells. Overexpression of HOXD9 increases anchorage-independent growth, shortens population-doubling time and reduces contact inhibition. Chromosome conformation capture identifies an interaction between rs2857532 and the HOXD9 promoter, suggesting this SNP is a leading causal variant. Transcriptomic profiling after HOXD9 overexpression reveals enrichment of HGSOC risk variants within HOXD9 target genes (P=6 × 10(-10) for risk variants (P<10(-4)) within 10 kb of a HOXD9 target gene in ovarian cells), suggesting a broader role for this network in genetic susceptibility to HGSOC.
EVALuna2:9265

Clinical and experimental evidence suggest a link between KIF7 and C5orf42-related ciliopathies through Sonic Hedgehog signaling - Asadollahi, Reza; Strauss, Justin E.; Zenker, Martin; Beuing, Oliver; Edvardson, Simon; Elpeleg, Orly; Strom, Tim M.; Joset, Pascal; Niedrist, Dunja; Otte, Christine; Oneda, Beatrice; Boonsawat, Paranchai; et al. (European journal of human genetics, 2018)
Acrocallosal syndrome (ACLS) is an autosomal recessive neurodevelopmental disorder caused by KIF7 defects and belongs to the heterogeneous group of ciliopathies related to Joubert syndrome (JBTS). While ACLS is characterized by macrocephaly, prominent forehead, depressed nasal bridge, and hypertelorism, facial dysmorphism has not been emphasized in JBTS cohorts with molecular diagnosis. To evaluate the specificity and etiology of ACLS craniofacial features, we performed whole exome or targeted Sanger sequencing in patients with the aforementioned overlapping craniofacial appearance but variable additional ciliopathy features followed by functional studies. We found (likely) pathogenic variants of KIF7 in 5 out of 9 families, including the original ACLS patients, and delineated 1000 to 4000-year-old Swiss founder alleles. Three of the remaining families had (likely) pathogenic variants in the JBTS gene C5orf42, and one patient had a novel de novo frameshift variant in SHH known to cause autosomal dominant holoprosencephaly. In accordance with the patients' craniofacial anomalies, we showed facial midline widening after silencing of C5orf42 in chicken embryos. We further supported the link between KIF7, SHH, and C5orf42 by demonstrating abnormal primary cilia and diminished response to a SHH agonist in fibroblasts of C5orf42-mutated patients, as well as axonal pathfinding errors in C5orf42-silenced chicken embryos similar to those observed after perturbation of Shh signaling. Our findings, therefore, suggest that beside the neurodevelopmental features, macrocephaly and facial widening are likely more general signs of disturbed SHH signaling. Nevertheless, long-term follow-up revealed that C5orf42-mutated patients showed catch-up development and fainting of facial features contrary to KIF7-mutated patients.
EVALuna2:34140

Clinical and molecular delineation of spondylocostal dysostosis type 3 - Schuhmann, Sarah; Koller, Heiko; Sticht, Heinrich; Kraus, Cornelia; Krumbiegel, Mandy; Uebe, Steffen; Ekici, Arif Bülent; Reis, André; Thiel, Christian (Clinical Genetics, 2021)
CRIS-Team Scopus Importer:2021-03-26

Clinical relevance of systematic phenotyping and exome sequencing in patients with short stature - Hauer, Nadine; Popp, Bernt; Schoeller, Eva; Schuhmann, Sarah; Heath, Karen E.; Hisado-Oliva, Alfonso; Klinger, Patricia; Kraus, Cornelia; Trautmann, Udo; Zenker, Martin; Zweier, Christiane; Wiesener, Antje; et al. (Genetics in Medicine, 2018)
PurposeShort stature is a common condition of great concern to patients and their families. Mostly genetic in origin, the underlying cause often remains elusive due to clinical and genetic heterogeneity.MethodsWe systematically phenotyped 565 patients where common nongenetic causes of short stature were excluded, selected 200 representative patients for whole-exome sequencing, and analyzed the identified variants for pathogenicity and the affected genes regarding their functional relevance for growth.ResultsBy standard targeted diagnostic and phenotype assessment, we identified a known disease cause in only 13.6% of the 565 patients. Whole-exome sequencing in 200 patients identified additional mutations in known short-stature genes in 16.5% of these patients who manifested only part of the symptomatology. In 15.5% of the 200 patients our findings were of significant clinical relevance. Heterozygous carriers of recessive skeletal dysplasia alleles represented 3.5% of the cases.ConclusionA combined approach of systematic phenotyping, targeted genetic testing, and whole-exome sequencing allows the identification of the underlying cause of short stature in at least 33% of cases, enabling physicians to improve diagnosis, treatment, and genetic counseling. Exome sequencing significantly increases the diagnostic yield and consequently care in patients with short stature.
EVALuna2:34628

Clinical validation of genetic variants associated with in vitro chemotherapy-related lymphoblastoid cell toxicity - Fasching, Peter; Häberle, Lothar; Rack, Brigitte; Li, Liang; Hein, Alexander; Ekici, Arif Bülent; Reis, André; Lux, Michael P.; Cunningham, Julie M.; Rübner, Matthias; Jenkins, Gergory; Fridley, Brooke; et al. (Oncotarget, 2017)
Hematotoxicity is one of the major side effects of chemotherapy. The aim of this study was to examine the association between single nucleotide polymorphisms (SNPs) and hematotoxicity in breast cancer patients in a subset of patients of the SUCCESS prospective phase III chemotherapy study. All patients (n = 1678) received three cycles of 5-fluorouracil, epirubicin, and cyclophosphamide (FEC) followed by three cycles of docetaxel or docetaxel/gemcitabine, depending on randomization. Germline DNA was genotyped for 246 SNPs selected from a previous genome-wide association study (GWAS) in a panel of lymphoblastoid cell lines, with gemcitabine toxicity as the phenotype. All SNPs were tested for their value in predicting grade 3 or 4 neutropenic or leukopenic events (NLEs). Their prognostic value in relation to overall survival and disease-free survival was also tested. None of the SNPs was found to be predictive for NLEs during treatment with docetaxel/gemcitabine. Two SNPs in and close to the PIGB gene significantly improved the prediction of NLEs after FEC, in addition to the factors of age and body surface area. The top SNP (rs12050587) had an odds ratio of 1.38 per minor allele (95% confidence interval, 1.17 to 1.62). No associations were identified for predicting disease-free or overall survival. Genetic variance in the PIGB gene may play a role in determining interindividual differences in relation to hematotoxicity after FEC chemotherapy.
EVALuna2:9381

Combined Associations of a Polygenic Risk Score and Classical Risk Factors With Breast Cancer Risk - Kapoor, Pooja Middha; Mavaddat, Nasim; Choudhury, Parichoy Pal; Wilcox, Amber N.; Lindström, Sara; Behrens, Sabine; Michailidou, Kyriaki; Dennis, Joe; Bolla, Manjeet K.; Wang, Qin; Jung, Audrey; Abu-Ful, Zomoroda; et al. (Journal of the National Cancer Institute, 2021)
We evaluated the joint associations between a new 313-variant PRS (PRS313) and questionnaire-based breast cancer risk factors for women of European ancestry, using 72 284 cases and 80 354 controls from the Breast Cancer Association Consortium. Interactions were evaluated using standard logistic regression and a newly developed case-only method for breast cancer risk overall and by estrogen receptor status. After accounting for multiple testing, we did not find evidence that per-standard deviation PRS313 odds ratio differed across strata defined by individual risk factors. Goodness-of-fit tests did not reject the assumption of a multiplicative model between PRS313 and each risk factor. Variation in projected absolute lifetime risk of breast cancer associated with classical risk factors was greater for women with higher genetic risk (PRS313 and family history) and, on average, 17.5% higher in the highest vs lowest deciles of genetic risk. These findings have implications for risk prevention for women at increased risk of breast cancer.
CRIS-Team Scopus Importer:2021-03-26

Common Genetic Variation In Cellular Transport Genes and Epithelial Ovarian Cancer (EOC) Risk - Chornokur, Ganna; Lin, Hui-Yi; Tyrer, Jonathan P.; Lawrenson, Kate; Dennis, Joe; Amankwah, Ernest K.; Qu, Xiaotao; Tsai, Ya-Yu; Jim, Heather S. L.; Chen, Zhihua; Chen, Ann Y.; Permuth-Wey, Jennifer; et al. (PLoS ONE, 2015)
Defective cellular transport processes can lead to aberrant accumulation of trace elements, iron, small molecules and hormones in the cell, which in turn may promote the formation of reactive oxygen species, promoting DNA damage and aberrant expression of key regulatory cancer genes. As DNA damage and uncontrolled proliferation are hallmarks of cancer, including epithelial ovarian cancer (EOC), we hypothesized that inherited variation in the cellular transport genes contributes to EOC risk.In total, DNA samples were obtained from 14,525 case subjects with invasive EOC and from 23,447 controls from 43 sites in the Ovarian Cancer Association Consortium (OCAC). Two hundred seventy nine SNPs, representing 131 genes, were genotyped using an Illumina Infinium iSelect BeadChip as part of the Collaborative Oncological Gene-environment Study (COGS). SNP analyses were conducted using unconditional logistic regression under a log-additive model, and the FDR q<0.2 was applied to adjust for multiple comparisons.The most significant evidence of an association for all invasive cancers combined and for the serous subtype was observed for SNP rs17216603 in the iron transporter gene HEPH (invasive: OR = 0.85, P = 0.00026; serous: OR = 0.81, P = 0.00020); this SNP was also associated with the borderline/low malignant potential (LMP) tumors (P = 0.021). Other genes significantly associated with EOC histological subtypes (p<0.05) included the UGT1A (endometrioid), SLC25A45 (mucinous), SLC39A11 (low malignant potential), and SERPINA7 (clear cell carcinoma). In addition, 1785 SNPs in six genes (HEPH, MGST1, SERPINA, SLC25A45, SLC39A11 and UGT1A) were imputed from the 1000 Genomes Project and examined for association with INV EOC in white-European subjects. The most significant imputed SNP was rs117729793 in SLC39A11 (per allele, OR = 2.55, 95% CI = 1.5-4.35, p = 5.66x10-4).These results, generated on a large cohort of women, revealed associations between inherited cellular transport gene variants and risk of EOC histologic subtypes.
EVALuna2:9283

Common germline polymorphisms associated with breast cancer-specific survival - Pirie, Ailith; Guo, Qi; Kraft, Peter; Canisius, Sander; Eccles, Diana M.; Rahman, Nazneen; Nevanlinna, Heli; Chen, Constance; Khan, Sofia; Tyrer, Jonathan; Bolla, Manjeet K.; Wang, Qin; et al. (Breast Cancer Research, 2015)
Previous studies have identified common germline variants nominally associated with breast cancer survival. These associations have not been widely replicated in further studies. The purpose of this study was to evaluate the association of previously reported SNPs with breast cancer-specific survival using data from a pooled analysis of eight breast cancer survival genome-wide association studies (GWAS) from the Breast Cancer Association Consortium.A literature review was conducted of all previously published associations between common germline variants and three survival outcomes: breast cancer-specific survival, overall survival and disease-free survival. All associations that reached the nominal significance level of P value <0.05 were included. Single nucleotide polymorphisms that had been previously reported as nominally associated with at least one survival outcome were evaluated in the pooled analysis of over 37,000 breast cancer cases for association with breast cancer-specific survival. Previous associations were evaluated using a one-sided test based on the reported direction of effect.Fifty-six variants from 45 previous publications were evaluated in the meta-analysis. Fifty-four of these were evaluated in the full set of 37,954 breast cancer cases with 2,900 events and the two additional variants were evaluated in a reduced sample size of 30,000 samples in order to ensure independence from the previously published studies. Five variants reached nominal significance (P <0.05) in the pooled GWAS data compared to 2.8 expected under the null hypothesis. Seven additional variants were associated (P <0.05) with ER-positive disease.Although no variants reached genome-wide significance (P <5 x 10(-8)), these results suggest that there is some evidence of association between candidate common germline variants and breast cancer prognosis. Larger studies from multinational collaborations are necessary to increase the power to detect associations, between common variants and prognosis, at more stringent significance levels.
EVALuna2:9296

Common non-synonymous SNPs associated with breast cancer susceptibility: findings from the Breast Cancer Association Consortium - Milne, Roger L.; Burwinkel, Barbara; Michailidou, Kyriaki; Arias-Perez, Jose-Ignacio; Pilar Zamora, M.; Menendez-Rodriguez, Primitiva; Hardisson, David; Mendiola, Marta; Gonzalez-Neira, Anna; Pita, Guillermo; Rosario Alonso, M.; Dennis, Joe; et al. (Human Molecular Genetics, 2014)
Candidate variant association studies have been largely unsuccessful in identifying common breast cancer susceptibility variants, although most studies have been underpowered to detect associations of a realistic magnitude. We assessed 41 common non-synonymous single-nucleotide polymorphisms (nsSNPs) for which evidence of association with breast cancer risk had been previously reported. Case-control data were combined from 38 studies of white European women (46 450 cases and 42 600 controls) and analyzed using unconditional logistic regression. Strong evidence of association was observed for three nsSNPs: ATXN7-K264R at 3p21 [rs1053338, per allele OR = 1.07, 95% confidence interval (CI) = 1.04-1.10, P = 2.9 × 10(-6)], AKAP9-M463I at 7q21 (rs6964587, OR = 1.05, 95% CI = 1.03-1.07, P = 1.7 × 10(-6)) and NEK10-L513S at 3p24 (rs10510592, OR = 1.10, 95% CI = 1.07-1.12, P = 5.1 × 10(-17)). The first two associations reached genome-wide statistical significance in a combined analysis of available data, including independent data from nine genome-wide association studies (GWASs): for ATXN7-K264R, OR = 1.07 (95% CI = 1.05-1.10, P = 1.0 × 10(-8)); for AKAP9-M463I, OR = 1.05 (95% CI = 1.04-1.07, P = 2.0 × 10(-10)). Further analysis of other common variants in these two regions suggested that intronic SNPs nearby are more strongly associated with disease risk. We have thus identified a novel susceptibility locus at 3p21, and confirmed previous suggestive evidence that rs6964587 at 7q21 is associated with risk. The third locus, rs10510592, is located in an established breast cancer susceptibility region; the association was substantially attenuated after adjustment for the known GWAS hit. Thus, each of the associated nsSNPs is likely to be a marker for another, non-coding, variant causally related to breast cancer risk. Further fine-mapping and functional studies are required to identify the underlying risk-modifying variants and the genes through which they act.
EVALuna2:9242

Common RUNX3 missense variant contributes to psoriatic arthritis by affecting splicing and modifying signaling, activation and differentiation of T-cells - Hüffmeier, Ulrike; Löhr, Sabine; Uebe, Steffen; Popp, Bernt; Bowes, J.; Kirchner, P.; Giardina, E.; Korendowych, E.; Ekici, Arif Bülent; Ho, P.; Behrens, F.; Koehm, M.; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

Common RUNX3 missense variant contributes to psoriatic arthritis by modifying differentiation of CD8(+) T-cells - Kerker, Iris; Löhr, Sabine; Uebe, Steffen; Popp, Bernt; Vasileiou, Georgia; Bowes, John; Kirchner, Philipp; Becker, Ina; Giardina, Emiliano; Korendowych, Eleanor; Ekici, Arif Bülent; Ho, Pauline; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2022)
CRIS-Team WoS Importer:2022-05-06

Common variants at the CHEK2 gene locus and risk of epithelial ovarian cancer - Lawrenson, Kate; Iversen, Edwin S.; Tyrer, Jonathan; Weber, Rachel Palmieri; Concannon, Patrick; Hazelett, Dennis J.; Li, Qiyuan; Marks, Jeffrey R.; Berchuck, Andrew; Lee, Janet M.; Aben, Katja K. H.; Anton-Culver, Hoda; et al. (Carcinogenesis, 2015)
Genome-wide association studies have identified 20 genomic regions associated with risk of epithelial ovarian cancer (EOC), but many additional risk variants may exist. Here, we evaluated associations between common genetic variants [single nucleotide polymorphisms (SNPs) and indels] in DNA repair genes and EOC risk. We genotyped 2896 common variants at 143 gene loci in DNA samples from 15 397 patients with invasive EOC and controls. We found evidence of associations with EOC risk for variants at FANCA, EXO1, E2F4, E2F2, CREB5 and CHEK2 genes (P <= 0.001). The strongest risk association was for CHEK2 SNP rs17507066 with serous EOC (P = 4.74 x 10(-7)). Additional genotyping and imputation of genotypes from the 1000 genomes project identified a slightly more significant association for CHEK2 SNP rs6005807 (r (2) with rs17507066 = 0.84, odds ratio (OR) 1.17, 95% CI 1.11-1.24, P = 1.1×10(-7)). We identified 293 variants in the region with likelihood ratios of less than 1:100 for representing the causal variant. Functional annotation identified 25 candidate SNPs that alter transcription factor binding sites within regulatory elements active in EOC precursor tissues. In The Cancer Genome Atlas dataset, CHEK2 gene expression was significantly higher in primary EOCs compared to normal fallopian tube tissues (P = 3.72×10(-8)). We also identified an association between genotypes of the candidate causal SNP rs12166475 (r (2) = 0.99 with rs6005807) and CHEK2 expression (P = 2.70×10(-8)). These data suggest that common variants at 22q12.1 are associated with risk of serous EOC and CHEK2 as a plausible target susceptibility gene.
EVALuna2:9297

Comparison of 6q25 breast cancer hits from Asian and European genome wide association studies in the Breast Cancer Association consortium (BCAC) - Hein, Rebecca; Maranian, Melanie; Hopper, John L.; Kapuscinski, Miroslaw K.; Southey, Melissa C.; Park, Daniel J.; Schmidt, Marjanka K.; Broeks, Annegien; Hogervorst, Frans B. L.; Bueno-De-Mesquit, H. Bas; Muir, Kenneth R.; Lophatananon, Artitaya; et al. (PLoS ONE, 2012)
The 6q25.1 locus was first identified via a genome-wide association study (GWAS) in Chinese women and marked by single nucleotide polymorphism (SNP) rs2046210, approximately 180 Kb upstream of ESR1. There have been conflicting reports about the association of this locus with breast cancer in Europeans, and a GWAS in Europeans identified a different SNP, tagged here by rs12662670. We examined the associations of both SNPs in up to 61,689 cases and 58,822 controls from forty-four studies collaborating in the Breast Cancer Association Consortium, of which four studies were of Asian and 39 of European descent. Logistic regression was used to estimate odds ratios (OR) and 95% confidence intervals (CI). Case-only analyses were used to compare SNP effects in Estrogen Receptor positive (ER+) versus negative (ER-) tumours. Models including both SNPs were fitted to investigate whether the SNP effects were independent. Both SNPs are significantly associated with breast cancer risk in both ethnic groups. Per-allele ORs are higher in Asian than in European studies [rs2046210: OR (A/G) = 1.36 (95% CI 1.26-1.48), p = 7.6×10-14 in Asians and 1.09 (95% CI 1.07-1.11), p = 6.8×10-18 in Europeans. rs12662670: OR (G/T) = 1.29 (95% CI 1.19-1.41), p = 1.2×10-9 in Asians and 1.12 (95% CI 1.08-1.17), p = 3.8×10-9 in Europeans]. SNP rs2046210 is associated with a significantly greater risk of ER- than ER+ tumours in Europeans [OR (ER-) = 1.20 (95% CI 1.15-1.25), p = 1.8×10-17 versus OR (ER+) = 1.07 (95% CI 1.04-1.1), p = 1.3×10-7, pheterogeneity = 5.1×10-6]. In these Asian studies, by contrast, there is no clear evidence of a differential association by tumour receptor status. Each SNP is associated with risk after adjustment for the other SNP. These results suggest the presence of two variants at 6q25.1 each independently associated with breast cancer risk in Asians and in Europeans. Of these two, the one tagged by rs2046210 is associated with a greater risk of ER- tumours. © 2012 Hein et al.
CRIS-Team Scopus Importer:2021-07-19

Comparison of methods for isolation and quantification of circulating cell-free DNA from patients with endometriosis - Hübner, Hanna; Lubrich, Hannah; Blum, Simon; Antoniadis, Sophia; Lermann, Johannes; Ekici, Arif Bülent; Fasching, Peter; Beckmann, Matthias; Rübner, Matthias; Burghaus, Stefanie (Reproductive Biomedicine Online, 2021)
Research question: Which is the optimal extraction method for isolating and quantifying circulating cell-free DNA (ccfDNA) from patients with endometriosis? Endometriosis is a common benign disease, associated with pain, infertility and reduced quality of life. Endometriosis is also a known risk factor for various cancers. Robust biomarkers for early detection and prediction of prognosis, however, are lacking. CcfDNA is an easy to obtain biomarker associated with prognosis of cancer patients and enables non-invasive analysis of somatic mutations. Recently, elevated levels of ccfDNA were detected in patients with endometriosis. Design: Two different ccfDNA extraction methods were compared: Maxwell RSC ccfDNA plasma kit (Maxwell) and QiAamp minElute ccfDNA mini kit (QIAamp). The ccfDNA and circulating mitochondrial DNA (mtDNA) quantities from 34 patients diagnosed with endometriosis were analysed. Fluorometric measurement and quantitative reverse transcription polymerase chain reaction (qRT-PCR) of short and long ALU and mtDNA fragments were used to quantiy ccfDNA. Results: The yield of ccfDNA isolated with the Maxwell method was significantly higher compared with the QIAamp method (P < 0.0001). Integrity of ccfDNA was significantly higher in the QIAamp isolate (P < 0.0001). Recovered mtDNA was not significantly different between both extraction methods used. Conclusions: The choice of extraction method can significantly influence the ccfDNA output and integrity. Both methods, however, enabled isolation of sufficient ccfDNA for further downstream applications. With this approach, isolation of ccfDNA could enable the non-invasive detection and analysis of somatic mutation within endometriosis tissue.
CRIS-Team Scopus Importer:2021-09-10
Keywords: CcfDNA; Circulating cell-free DNA; Endometriosis; Mitochondrial DNA; Plasma; Quantification

Comprehensive genetic assessment of the ESR1 locus identifies a risk region for endometrial cancer - O'Mara, Tracy A.; Glubb, Dylan M.; Painter, Jodie N.; Cheng, Timothy; Dennis, Joe; Attia, John; Holliday, Elizabeth G.; Mcevoy, Mark; Scott, Rodney J.; Ashton, Katie; Proietto, Tony; Otton, Geoffrey; et al. (Endocrine-Related Cancer, 2015)
Excessive exposure to estrogen is a well-established risk factor for endometrial cancer (EC), particularly for cancers of endometrioid histology. The physiological function of estrogen is primarily mediated by estrogen receptor alpha, encoded by ESR1. Consequently, several studies have investigated whether variation at the ESR1 locus is associated with risk of EC, with conflicting results. We performed comprehensive fine-mapping analyses of 3633 genotyped and imputed single nucleotide polymorphisms (SNPs) in 6607 EC cases and 37 925 controls. There was evidence of an EC risk signal located at a potential alternative promoter of the ESR1 gene (lead SNP rs79575945, P=1.86×10(-5)), which was stronger for cancers of endometrioid subtype (P=3.76×10(-6)). Bioinformatic analysis suggests that this risk signal is in a functionally important region targeting ESR1, and eQTL analysis found that rs79575945 was associated with expression of SYNE1, a neighbouring gene. In summary, we have identified a single EC risk signal located at ESR1, at study-wide significance. Given SNPs located at this locus have been associated with risk for breast cancer, also a hormonally driven cancer, this study adds weight to the rationale for performing informed candidate fine-scale genetic studies across cancer types.
EVALuna2:9261

Consortium analysis of gene and gene-folate interactions in purine and pyrimidine metabolism pathways with ovarian carcinoma risk - Kelemen, Linda E.; Terry, Kathryn L.; Goodman, Marc T.; Webb, Penelope M.; Bandera, Elisa V.; Mcguire, Valerie; Rossing, Mary Anne; Wang, Qinggang; Dicks, Ed; Tyrer, Jonathan P.; Song, Honglin; Kupryjanczyk, Jolanta; et al. (Molecular Nutrition & Food Research, 2014)
We reevaluated previously reported associations between variants in pathways of one-carbon (1-C) (folate) transfer genes and ovarian carcinoma (OC) risk, and in related pathways of purine and pyrimidine metabolism, and assessed interactions with folate intake.Odds ratios (OR) for 446 genetic variants were estimated among 13,410 OC cases and 22,635 controls, and among 2281 cases and 3444 controls with folate information. Following multiple testing correction, the most significant main effect associations were for dihydropyrimidine dehydrogenase (DPYD) variants rs11587873 (OR = 0.92; p = 6 × 10(-5)) and rs828054 (OR = 1.06; p = 1 × 10(-4)). Thirteen variants in the pyrimidine metabolism genes, DPYD, DPYS, PPAT, and TYMS, also interacted significantly with folate in a multivariant analysis (corrected p = 9.9 × 10(-6)) but collectively explained only 0.2% of OC risk. Although no other associations were significant after multiple testing correction, variants in SHMT1 in 1-C transfer, previously reported with OC, suggested lower risk at higher folate (p(interaction) = 0.03-0.006).Variation in pyrimidine metabolism genes, particularly DPYD, which was previously reported to be associated with OC, may influence risk; however, stratification by folate intake is unlikely to modify disease risk appreciably in these women. SHMT1 SNP-by-folate interactions are plausible but require further validation. Polymorphisms in selected genes in purine metabolism were not associated with OC.
EVALuna2:9231

CRISPR/Cas9-mediated generation of hESC lines with homozygote and heterozygote p.R331W mutation in CTBP1 to model HADDTS syndrome - Akdas, Enes Yagiz; Turan, Sören; Guhathakurta, Debarpan; Ekici, Arif Bülent; Salar, Seda; Lie, Dieter Chichung; Winner, Beate; Fejtová, Anna (Stem Cell Research, 2023)
C-terminal Binding Protein 1 (CTBP1) is a ubiquitously expressed transcriptional co-repressor and membrane trafficking regulator. A recurrent de novo c.991C>T mutation in CTBP1 leads to expression of p.R331W CTBP1 and causes hypotonia, ataxia, developmental delay, and tooth enamel defects syndrome (HADDTS), a rare early onset neurodevelopmental disorder. We generated hESCs lines with heterozygote and homozygote c.991C>T in CTBP1 using CRISPR/Cas9 genome editing and validated them for genetic integrity, off-target mutations, and pluripotency. They will be useful for investigation of HADDTS pathophysiology and for screening for potential therapeutics.
CRIS-Team Scopus Importer:2023-01-20

CRISPR/Cas9-mediated knock-out of krasG12D mutated pancreatic cancer cell lines - Lentsch, Eva; Li, Lifei; Pfeffer, Sina; Ekici, Arif Bülent; Taher, Leila; Pilarsky, Christian; Grützmann, Robert (International Journal of Molecular Sciences, 2019)
In 90% of pancreatic ductal adenocarcinoma cases, genetic alteration of the proto-oncogene Kras has occurred, leading to uncontrolled proliferation of cancerous cells. Targeting Kras has proven to be difficult and the battle against pancreatic cancer is ongoing. A promising approach to combat cancer was the discovery of the clustered regularly interspaced short palindromic repeat (CRISPR)/CRISPR-associated (Cas) system, which can be used to genetically modify cells. To assess the potential of a CRISPR/CRISPR-associated protein 9 (Cas9) method to eliminate Kras mutations in cells, we aimed to knock-out the c.35G>A (p.G12D) Kras mutation. Therefore, three cell lines with a heterozygous Kras mutation (the human cell lines SUIT-2 and Panc-1 and the cell line TB32047 from a KPC mouse model) were used. After transfection, puromycin selection and single-cell cloning, proteins from two negative controls and five to seven clones were isolated to verify the knock-out and to analyze changes in key signal transduction proteins. Western blots showed a specific knock-out in the KrasG12D protein, but wildtype Kras was expressed by all of the cells. Signal transduction analysis (for Erk, Akt, Stat3, AMPKα, and c-myc) revealed expression levels similar to the wildtype. The results described herein indicate that knocking-out the KrasG12D mutation by CRISPR/Cas9 is possible. Additionally, under regular growth conditions, the knock-out clones resembled wildtype cells.
CRIS-Team Scopus Importer:2019-11-26
Keywords: CRISPR/Cas9 system; G12D; Kras; Panc-1; Suit-2; TB32047

Crnkl1 is a highly selective regulator of intron-retaining HIV-1 and cellular mrnas - Xiao, Han; Wyler, Emanuel; Milek, Miha; Grewe, Bastian; Kirchner, Philipp; Ekici, Arif Bülent; Silva, Ana Beatriz Oliveira Villela; Jungnickl, Doris; Full, Florian; Thomas, Marco; Landthaler, Markus; Enßer, Armin; et al. (mBio, 2021)
The HIV-1 Rev protein is a nuclear export factor for unspliced and incom-pletely spliced HIV-1 RNAs. Without Rev, these intron-retaining RNAs are trapped in the nucleus. A genome-wide screen identified nine proteins of the spliceosome, which all enhanced expression from the HIV-1 unspliced RNA after CRISPR/Cas knockdown. Depletion of DHX38, WDR70, and four proteins of the Prp19-associated complex (ISY1, BUD31, XAB2, and CRNKL1) resulted in a more than 20-fold enhancement of unspliced HIV-1 RNA levels in the cytoplasm. Targeting of CRNKL1, DHX38, and BUD31 affected nuclear export efficiencies of the HIV-1 unspliced RNA to a much larger extent than splicing. Transcriptomic analyses further revealed that CRNKL1 also suppresses cyto-plasmic levels of a subset of cellular mRNAs, including some with selectively retained introns. Thus, CRNKL1-dependent nuclear retention is a novel cellular mechanism for the regulation of cytoplasmic levels of intron-retaining HIV-1 mRNAs, which HIV-1 may have harnessed to direct its complex splicing pattern. IMPORTANCE To regulate its complex splicing pattern, HIV-1 uses the adaptor protein Rev to shuttle unspliced or partially spliced mRNA from the nucleus to the cyto-plasm. In the absence of Rev, these RNAs are retained in the nucleus, but it is unclear why. Here we identify cellular proteins whose depletion enhances cytoplas-mic levels of the HIV-1 unspliced RNA. Depletion of one of them, CRNKL1, also increases cytoplasmic levels of a subset of intron-retaining cellular mRNA, suggesting that CRNKL1-dependent nuclear retention may be a basic cellular mechanism exploited by HIV-1.
CRIS-Team Scopus Importer:2021-02-12
Keywords: Association; CRNKL1; Human immunodeficiency virus; Intron-retaining RNA; Nuclear retention; RNA splicing

Cross-Cancer Genome-Wide Association Study of Endometrial Cancer and Epithelial Ovarian Cancer Identifies Genetic Risk Regions Associated with Risk of Both Cancers - Glubb, Dylan M.; Thompson, Deborah J.; Aben, Katja K. H.; Alsulimani, Ahmad; Amant, Frederic; Annibali, Daniela; Attia, John; Barricarte, Aurelio; Beckmann, Matthias; Berchuck, Andrew; Bermisheva, Marina; Bernardini, Marcus Q.; et al. (Cancer Epidemiology Biomarkers & Prevention, 2021)
Background: Accumulating evidence suggests a relationship between endometrial cancer and ovarian cancer. Independent genome-wide association studies (GWAS) for endometrial cancer and ovarian cancer have identified 16 and 27 risk regions, respectively, four of which overlap between the two cancers. We aimed to identify joint endometrial and ovarian cancer risk loci by performing a meta-analysis of GWAS summary statistics from these two cancers.
CRIS-Team WoS Importer:2021-03-12

CYP19A1 fine-mapping and Mendelian randomization: estradiol is causal for endometrial cancer - Thompson, Deborah J.; O'Mara, Tracy A.; Glubb, Dylan M.; Painter, Jodie N.; Cheng, Timothy; Folkerd, Elizabeth; Doody, Deborah; Dennis, Joe; Webb, Penelope M.; Gorman, Maggie; Martin, Lynn; Hodgson, Shirley; et al. (Endocrine-Related Cancer, 2016)
Candidate gene studies have reported CYP19A1 variants to be associated with endometrial cancer and with estradiol (E2) concentrations. We analyzed 2937 single nucleotide polymorphisms (SNPs) in 6608 endometrial cancer cases and 37 925 controls and report the first genome wide-significant association between endometrial cancer and a CYP19A1 SNP (rs727479 in intron 2, P=4.8×10(-11)). SNP rs727479 was also among those most strongly associated with circulating E2 concentrations in 2767 post-menopausal controls (P=7.4×10(-8)). The observed endometrial cancer odds ratio per rs727479 A-allele (1.15, CI=1.11-1.21) is compatible with that predicted by the observed effect on E2 concentrations (1.09, CI=1.03-1.21), consistent with the hypothesis that endometrial cancer risk is driven by E2. From 28 candidate-causal SNPs, 12 co-located with three putative gene-regulatory elements and their risk alleles associated with higher CYP19A1 expression in bioinformatical analyses. For both phenotypes, the associations with rs727479 were stronger among women with a higher BMI (Pinteraction=0.034 and 0.066 respectively), suggesting a biologically plausible gene-environment interaction.
EVALuna2:9315

De novo mutations in the genome organizer CTCF cause intellectual disability - Gregor, Anne; Oti, Martin; Kouwenhoven, Evelyn N.; Hoyer, Juliane; Sticht, Heinrich; Ekici, Arif Bülent; Kjaergaard, Susanne; Rauch, Anita; Stunnenberg, Hendrik G.; Uebe, Steffen; Vasileiou, Georgia; Reis, André; et al. (American Journal of Human Genetics, 2013)
An increasing number of genes involved in chromatin structure and epigenetic regulation has been implicated in a variety of developmental disorders, often including intellectual disability. By trio exome sequencing and subsequent mutational screening we now identified two de novo frameshift mutations and one de novo missense mutation in CTCF in individuals with intellectual disability, microcephaly, and growth retardation. Furthermore, an individual with a larger deletion including CTCF was identified. CTCF (CCCTC-binding factor) is one of the most important chromatin organizers in vertebrates and is involved in various chromatin regulation processes such as higher order of chromatin organization, enhancer function, and maintenance of three-dimensional chromatin structure. Transcriptome analyses in all three individuals with point mutations revealed deregulation of genes involved in signal transduction and emphasized the role of CTCF in enhancer-driven expression of genes. Our findings indicate that haploinsufficiency of CTCF affects genomic interaction of enhancers and their regulated gene promoters that drive developmental processes and cognition.
EVALuna2:9184

Detection rate and re-analysis of exome sequencing data in a cohort of 207 individuals with neurodevelopmental disorders - Hebebrand, Moritz; Thiel, C. T.; Kraus, Cornelia; Ekici, Arif Bülent; Reis, André; Zweier, Christiane (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

DGCR8 deficiency impairs macrophage growth and unleashes the interferon response to mycobacteria - Killy, Barbara; Bodendorfer, Barbara; Mages, Jörg; Ritter, Kristina; Schreiber, Jonathan; Hölscher, Christoph; Pracht, Katharina; Ekici, Arif Bülent; Jäck, Hans-Martin; Lang, Roland (Life Science Alliance, 2021)
The mycobacterial cell wall glycolipid trehalose-6,6-dimycolate (TDM) activates macrophages through the C-type lectin receptor MINCLE. Regulation of innate immune cells relies on miRNAs, which may be exploited by mycobacteria to survive and replicate in macrophages. Here, we have used macrophages deficient in the microprocessor component DGCR8 to investigate the impact of miRNA on the response to TDM. Deletion of DGCR8 in bone marrow progenitors reduced macrophage yield, but did not block macrophage differentiation. DGCR8-deficient macrophages showed reduced constitutive and TDM-inducible miRNA expression. RNAseq analysis revealed that they accumulated primary miRNA transcripts and displayed a modest type I IFN signature at baseline. Stimulation with TDM in the absence of DGCR8 induced overshooting expression of IFNβ and IFN-induced genes, which was blocked by antibodies to type I IFN. In contrast, signaling and transcriptional responses to recombinant IFNβ were unaltered. Infection with live Mycobacterium bovis Bacille Calmette-Guerin replicated the enhanced IFN response. Together, our results reveal an essential role for DGCR8 in curbing IFNβ expression macrophage reprogramming by mycobacteria.
CRIS-Team Scopus Importer:2021-04-16

Diagnostic Yield and Novel Candidate Genes by Exome Sequencing in 152 Consanguineous Families With Neurodevelopmental Disorders - Reuter, Miriam; Tawamie, Hasan; Buchert, Rebecca; Gebril, Ola Hosny; Froukh, Tawfiq; Thiel, Christian; Uebe, Steffen; Ekici, Arif Bülent; Krumbiegel, Mandy; Zweier, Christiane; Hoyer, Juliane; Eberlein, Karolin; et al. (JAMA Psychiatry, 2017)
Autosomal recessive inherited neurodevelopmental disorders are highly heterogeneous, and many, possibly most, of the disease genes are still unknown.To promote the identification of disease genes through confirmation of previously described genes and presentation of novel candidates and provide an overview of the diagnostic yield of exome sequencing in consanguineous families.Autozygosity mapping in families and exome sequencing of index patients were performed in 152 consanguineous families (the parents descended from a same ancestor) with at least 1 offspring with intellectual disability (ID). The study was conducted from July 1, 2008, to June 30, 2015, and data analysis was conducted from July 1, 2015, to August 31, 2016.Of the 152 consanguineous families enrolled, 1 child (in 45 families [29.6%]) or multiple children (107 families [70.4%]) had ID; additional features were present in 140 of the families (92.1%). The mean (SD) age of the children was 10.3 (9.0) years, and 171 of 297 (57.6%) were male. In 109 families (71.7%), potentially protein-disrupting and clinically relevant variants were identified. Of these, a clear clinical genetic diagnosis was made in 56 families (36.8%) owing to 57 (likely) pathogenic variants in 50 genes already established in neurodevelopmental disorders (46 autosomal recessive, 2 X-linked, and 2 de novo) or in 7 previously proposed recessive candidates. In 5 of these families, potentially treatable disorders were diagnosed (mutations in PAH, CBS, MTHFR, CYP27A1, and HIBCH), and in 1 family, 2 disease-causing homozygous variants in different genes were identified. In another 48 families (31.6%), 52 convincing recessive variants in candidate genes that were not previously reported in regard to neurodevelopmental disorders were identified. Of these, 14 were homozygous and truncating in GRM7, STX1A, CCAR2, EEF1D, GALNT2, SLC44A1, LRRIQ3, AMZ2, CLMN, SEC23IP, INIP, NARG2, FAM234B, and TRAP1. The diagnostic yield was higher in individuals with severe ID (35 of 77 [45.5%]), in multiplex families (42 of 107 [39.3%]), in patients with additional features (30 of 70 [42.9%]), and in those with remotely related parents (15 of 34 [44.1%]).Because of the high diagnostic yield of 36.8% and the possibility of identifying treatable diseases or the coexistence of several disease-causing variants, using exome sequencing as a first-line diagnostic approach in consanguineous families with neurodevelopmental disorders is recommended. Furthermore, the literature is enriched with 52 convincing candidate genes that are awaiting confirmation in independent families.
EVALuna2:9388

Differential Effects of Ontamalimab Versus Vedolizumab on Immune Cell Trafficking in Intestinal Inflammation and Inflammatory Bowel Disease - Schulze, Lisa; Becker, Emily; Dedden, Mark; Liu, Lijuan; Van Passen, Chiara; Mohamed Abdou, Mariam; Müller, Tanja; Wiendl, Maximilian; Ullrich, Karen; Atreya, Imke; Leppkes, Moritz; Ekici, Arif Bülent; et al. (Journal of Crohns & Colitis, 2023)
Background and Aims: The anti-MAdCAM-1 antibody ontamalimab demonstrated efficacy in a phase II trial in ulcerative colitis and results of early terminated phase III trials are pending, but its precise mechanisms of action are still unclear. Thus, we explored the mechanisms of action of ontamalimab and compared it to the anti-α4β7 antibody vedolizumab. Methods: We studied MAdCAM-1 expression with RNA sequencing and immunohistochemistry. The mechanisms of action of ontamalimab were assessed with fluorescence microscopy, dynamic adhesion and rolling assays. We performed in vivo cell trafficking studies in mice and compared ontamalimab and vedolizumab surrogate [-s] antibodies in experimental models of colitis and wound healing. We analysed immune cell infiltration under anti-MAdCAM-1 and anti-α4β7 treatment by single-cell transcriptomics and studied compensatory trafficking pathways. Results: MAdCAM-1 expression was increased in active inflammatory bowel disease. Binding of ontamalimab to MAdCAM-1 induced the internalization of the complex. Functionally, ontamalimab blocked T cell adhesion similar to vedolizumab, but also inhibited L-selectin-dependent rolling of innate and adaptive immune cells. Despite conserved mechanisms in mice, the impact of ontamalimab-s and vedolizumab-s on experimental colitis and wound healing was similar. Single-cell RNA sequencing demonstrated enrichment of ontamalimab-s-treated lamina propria cells in specific clusters, and in vitro experiments indicated that redundant adhesion pathways are active in these cells. Conclusions: Ontamalimab has unique and broader mechanisms of action compared to vedolizumab. However, this seems to be compensated for by redundant cell trafficking circuits and leads to similar preclinical efficacy of anti-α4β7 and anti-MAdCAM-1 treatment. These results will be important for the interpretation of pending phase III data.
CRIS-Team Scopus Importer:2023-12-15

Differential Effects of Very-Low-Volume Exercise Modalities on Telomere Length, Inflammation, and Cardiometabolic Health in Obese Metabolic Syndrome Patients: A Subanalysis from Two Randomized Controlled Trials - Reljic, Dejan; Koller, Adriana; Herrmann, Hans J.; Ekici, Arif Bülent; Neurath, Markus; Zopf, Yurdagül (Antioxidants, 2023)
Oxidative stress (OS) and inflammation are features of metabolic syndrome (MetS) that can contribute to the shortening of telomere length (TL), a marker of cellular ageing. Research indicates that exercise can positively influence MetS-associated conditions and TL. However, the effects of low-volume exercise types on TL are still unknown. We investigated the impact of very-low-volume high-intensity interval training (LV-HIIT), one-set resistance training (1-RT), and whole-body electromyostimulation (WB-EMS) on TL, inflammation, and cardiometabolic indices in 167 MetS patients. Data were derived from two randomized controlled trials where patients were allocated to an exercise group (2 sessions/week, for 12 weeks) or a control group. All groups received standard-care nutritional weight loss counselling. TL was determined as the T/S ratio (telomere to single-copy gene amount). All groups significantly reduced body weight (p < 0.05), but the T/S-ratio (p < 0.001) only increased with LV-HIIT. OS-related inflammatory markers (C-reactive protein, interleukin-6, and lipopolysaccharide-binding protein) only decreased (p < 0.05) following LV-HIIT. The MetS severity z-score improved with LV-HIIT (p < 0.001) and 1-RT (p = 0.014) but not with WB-EMS. In conclusion, very-low-volume exercise modalities have differential effects on telomeres, inflammation, and cardiometabolic health. Only LV-HIIT but not strength-based low-volume exercise increased TL in MetS patients, presumably due to superior effects on OS-related inflammatory markers.
CRIS-Team Scopus Importer:2023-11-10
Keywords: anti-aging; cellular age; electromyostimulation; high-intensity interval training; inflammatory markers; metabolic diseases; oxidative stress; resistance training; telomeres

Dissecting TSC2-mutated renal and hepatic angiomyolipomas in an individual with ARID1B-associated intellectual disability - Popp, Bernt; Agaimy, Abbas; Kraus, Cornelia; Knaup, Karl; Ekici, Arif Bülent; Uebe, Steffen; Reis, André; Wiesener, Michael; Zweier, Christiane (BMC Cancer, 2019)
Background: Several subunits of the SWI/SNF chromatin remodeling complex are implicated in both cancer and neurodevelopmental disorders (NDD). Though there is no clinical evidence for an increased tumor risk in individuals with NDDs due to germline mutations in most of these genes so far, this has been repeatedly proposed and discussed. A young woman with NDD due to a de novo mutation in ARID1B now presented with a large renal (> 19 cm in diameter) and multiple hepatic angiomyolipomas (AMLs) but no other signs of tuberous sclerosis complex. Methods: We analyzed tumor and healthy tissue samples with exome and panel sequencing. Results: Additionally to the previously known, germline ARID1B variant we identified a post-zygotic truncating TSC2 variant in both renal and hepatic AMLs but not in any of the healthy tissues. We did not detect any further, obvious tumor driver events. The identification of a passenger variant in SIPA1L3 in both AMLs points to a common clonal origin. Metastasis of the renal AML into the liver is unlikely on the basis of discordant histopathological features. Our findings therefore point to very low-grade mosaicism for the TSC2 variant, possibly in a yet unknown mesenchymal precursor cell that expanded clonally during tumor development. A possible contribution of the germline ARID1B variant to the tumorigenesis remains unclear but cannot be excluded given the absence of any other evident tumor drivers in the AMLs. Conclusion: This unique case highlights the blurred line between tumor genetics and post-zygotic events that can complicate exact molecular diagnoses in patients with rare manifestations. It also demonstrates the relevance of multiple disorders in a single individual, the challenges of detecting low-grade mosaicisms, and the importance of proper diagnosis for treatment and surveillance.
CRIS-Team Scopus Importer:2019-05-21
Keywords: Angiomyolipoma; ARID1B; Mosaic; Neurodevelopmental disorders; TSC2; Tuberous sclerosis complex

Diverse molecular causes of unsolved autosomal dominant tubulointerstitial kidney diseases - Wopperer, Florian; Knaup, Karl; Stanzick, Kira J.; Schneider, Karen; Jobst-Schwan, Tilman; Ekici, Arif Bülent; Uebe, Steffen; Wenzel, Andrea; Schliep, Stefan; Schürfeld, Carsten; Seitz, Randolf; Bernhardt, Wanja; et al. (Kidney International, 2022)
Autosomal Dominant Tubulointerstitial Kidney Disease (ADTKD) is caused by mutations in one of at least five genes and leads to kidney failure usually in mid adulthood. Throughout the literature, variable numbers of families have been reported, where no mutation can be found and therefore termed ADTKD-not otherwise specified. Here, we aim to clarify the genetic cause of their diseases in our ADTKD registry. Sequencing for all known ADTKD genes was performed, followed by SNaPshot minisequencing for the dupC (an additional cytosine within a stretch of seven cytosines) mutation of MUC1. A virtual panel containing 560 genes reported in the context of kidney disease (nephrome) and exome sequencing were then analyzed sequentially. Variants were validated and tested for segregation. In 29 of the 45 registry families, mutations in known ADTKD genes were found, mostly in MUC1. Sixteen families could then be termed ADTKD-not otherwise specified, of which nine showed diagnostic variants in the nephrome (four in COL4A5, two in INF2 and one each in COL4A4, PAX2, SALL1 and PKD2). In the other seven families, exome sequencing analysis yielded potential disease associated variants in novel candidate genes for ADTKD; evaluated by database analyses and genome-wide association studies. For the great majority of our ADTKD registry we were able to reach a molecular genetic diagnosis. However, a small number of families are indeed affected by diseases classically described as a glomerular entity. Thus, incomplete clinical phenotyping and atypical clinical presentation may have led to the classification of ADTKD. The identified novel candidate genes by exome sequencing will require further functional validation.
CRIS-Team Scopus Importer:2022-07-15
Keywords: ADTKD; Alport syndrome; exome; MITKD; MUC1; UMOD

Do telomeres have a higher plasticity than thought? Results from the German Chronic Kidney Disease (GCKD) study as a high-risk population - Raschenberger, Julia; Kollerits, Barbara; Titze, Stephanie; Koettgen, Anna; Bärthlein, Barbara; Ekici, Arif Bülent; Forer, Lukas; Schoenherr, Sebastian; Weissensteiner, Hansi; Haun, Margot; Wanner, Christoph; Eckardt, Kai-Uwe; et al. (Experimental Gerontology, 2015)
Telomere length is considered as a biological marker for aging. It is expected that telomeres shorten with age and with conditions associated with oxidative stress and inflammation. Both are present in patients with chronic kidney disease (CKD) who have a very high cardiovascular risk. We investigated whether CKD duration is associated with relative telomere length (RTL) in 4802 patients from the German Chronic Kidney Disease (GCKD) study. We measured RTL in each sample in quadruplicates using a quantitative polymerase chain reaction (qPCR). We observed a U-shaped association of RTL with CKD duration: the longest RTL was found in those 339 patients who reported the shortest disease duration (<6months) and shorter RTL in 2108 patients with duration between 6months and less than 5years. Most importantly, those 2331 patients who reported a CKD duration of 5years and more had significantly longer RTL compared to those with intermediate CKD duration (6months to less than 5years): mean 0.954, 95%CI 0.946-0.961 versus 0.937, 95%CI 0.929-0.944, p=0.002). Due to the cross-sectional nature of the study these surprising results have to be considered with caution and as hypothesis-generating. Whether the longer RTL in patients with long-lasting disease is caused by an activation of telomerase to counteract the shortening of RTL due to oxidative stress and inflammation or whether they are caused by a survival bias needs to be investigated in longitudinal studies. Our data are in support of a higher plasticity of shortening and elongations of RTL as until recently anticipated.
EVALuna2:138

Dual role of the mycobacterial cord factor TDM in cross-regulation of macrophage responses to IFN gamma - Killy, Barbara; Huber, Angelika; Ekici, Arif Bülent; Wirtz, Stefan; Dalpke, A.; Lang, Roland (2017)
EVALuna2:33888

DYNC2LI1 mutations broaden the clinical spectrum of dynein-2 defects - Keßler, Kristin; Wunderlich, Ina; Uebe, Steffen; Falk, Nathalie; Gießl, Andreas; Brandstätter, Johann Helmut; Popp, Bernt; Klinger, Patricia; Ekici, Arif Bülent; Sticht, Heinrich; Dörr, Helmuth-Günther; Reis, André; et al. (Scientific Reports, 2015)
Skeletal ciliopathies are a heterogeneous group of autosomal recessive osteochondrodysplasias caused by defects in formation, maintenance and function of the primary cilium. Mutations in the underlying genes affect the molecular motors, intraflagellar transport complexes (IFT), or the basal body. The more severe phenotypes are caused by defects of genes of the dynein-2 complex, where mutations in DYNC2H1, WDR34 and WDR60 have been identified. In a patient with a Jeune-like phenotype we performed exome sequencing and identified compound heterozygous missense and nonsense mutations in DYNC2LI1 segregating with the phenotype. DYNC2LI1 is ubiquitously expressed and interacts with DYNC2H1 to form the dynein-2 complex important for retrograde IFT. Using DYNC2LI1 siRNA knockdown in fibroblasts we identified a significantly reduced cilia length proposed to affect cilia function. In addition, depletion of DYNC2LI1 induced altered cilia morphology with broadened ciliary tips and accumulation of IFT-B complex proteins in accordance with retrograde IFT defects. Our results expand the clinical spectrum of ciliopathies caused by defects of the dynein-2 complex.
EVALuna2:9281

Early and late genome-wide gastric epithelial transcriptome response during infection with the human carcinogen Helicobacter pylori - Sharafutdinov, Irshad; Ekici, Arif Bülent; Vieth, Michael; Backert, Steffen; Linz, Bodo (Cell Insight, 2022)
Infection of the stomach by Helicobacter pylori is a major risk factor for the development of gastric cancer. Colonization of the gastric epithelium leads to the activation of multiple disease-related signaling pathways. Serine protease HtrA represents an important secreted virulence factor that mediates cleavage of cellular junctions. However, its potential role in nuclear responses is unknown. Here, we performed a genome-wide RNA-seq analysis of polarized gastric epithelial cells infected by wild-type (wt) and ΔhtrA mutant bacteria. Fluorescence microscopy showed that H. pylori wt, but not ΔhtrA bacteria, preferably localized at cellular junctions. Our results pinpointed early (2 h) and late (6 h) transcriptional responses, with most differentially expressed genes at 6 h post infection. The transcriptomes revealed HtrA-dependent targeting of genes associated with inflammation and apoptosis (e.g. IL8, ZFP36, TNF). Accordingly, infection with the ΔhtrA mutant induced increased apoptosis rates in host cells, which was associated with reduced H. pylori CagA expression. In contrast, transcription of various carcinogenesis-associated genes (e.g. DKK1, DOCK8) was affected by H. pylori independent of HtrA. These findings suggest that H. pylori disturbs previously unknown molecular pathways in an HtrA-dependent and HtrA-independent manner, and provide valuable new insights of this significant pathogen in humans and thus potential targets for better controlling the risk of malignant transformation.<br
Keywords: Helicobacter; Cancer; RNA-seq; HtrA; Apoptosis; Inflammation

Early effects of aldosterone on Na+ transport and the transcriptome of cultured mouse cortical collecting duct cells (mCCDcl1) - Afonso, Sara; Bertog, Marko; Ilyaskin, Alexandr; Büttner, Clara; Ekici, Arif Bülent; Korbmacher, Christoph (ACTA PHYSIOLOGICA, 2022)
CRIS-Team WoS Importer:2022-10-07

Effects of Anti-Integrin Treatment With Vedolizumab on Immune Pathways and Cytokines in Inflammatory Bowel Diseases - Rath, Timo; Billmeier, Ulrike; Ferrazzi, Fulvia; Ekici, Arif Bülent; Neurath, Markus; Atreya, Raja; Vieth, Michael (Frontiers in Immunology, 2018)
Background and aims: Despite proven clinical efficacy of vedolizumab (VDZ) for inducing and maintaining remission in patients with Crohn's disease (CD) and ulcerative colitis (UC), subgroups of patients have no therapeutic benefit from anti-α4β7 integrin therapy with VDZ. Within this study, we aimed to identify genetic, cellular, and immunological mechanisms that define response and failure to VDZ treatment. Methods: Intestinal RNA sequencing was performed in UC and CD patients before and at week 14 of VDZ therapy. α4β7 expression on peripheral and mucosal immune cells was assessed by flow cytometry and immunohistochemistry. Cellular modes of VDZ-mediated action were analyzed ex vivo and in VDZ-treated inflammatory bowel disease patients. Results: Transcriptome analysis showed an impairment of signaling cascades associated with adhesion, diapedesis, and migration of granulocytes and agranulocytes upon VDZ therapy. In non-remitters to VDZ therapy, a tissue destructive and leukocyte-mediated inflammatory activity with activation of TNF-dependent pathways was present, all of which were inhibited in remitters to VDZ. Clinical remission was associated with a significant reduction of α4β7 expression on Th2 and Th17 polarized mucosal CD4+ T cells at week 14 of VDZ therapy and with significantly higher numbers of α4β7-expressing mucosal cells prior to the initiation of VDZ therapy compared with non-remitters. Conclusion: Intestinal α4β7 expression prior to VDZ therapy might represent a biomarker that predicts therapeutic response to subsequent VDZ treatment. Due to high activation of TNF signaling in VDZ non-remitters, anti-TNF treatment might represent a promising therapeutic strategy in VDZ refractory patients.
EVALuna2:34622

EFhd2/Swiprosin-1 is a common genetic determinator for sensation-seeking/low anxiety and alcohol addiction - Mielenz, Dirk; Reichel, Martin; Jia, T.; Quinlan, E. B.; Stöckl, Thomas; Mettang, M.; Zilske, Daniel; Kirmizi Alsan, Elif; Schoenberger, P.; Praetner, M.; Huber, Sabine; Amato, Davide; et al. (Molecular Psychiatry, 2017)
In many societies, the majority of adults regularly consume alcohol. However, only a small proportion develops alcohol addiction. Individuals at risk often show a high sensation-seeking/low-anxiety behavioural phenotype. Here we asked which role EF hand domain containing 2 (EFhd2; Swiprosin-1) plays in the control of alcohol addiction-associated behaviours. EFhd2 knockout (KO) mice drink more alcohol than controls and spontaneously escalate their consumption. This coincided with a sensation-seeking and low-anxiety phenotype. A reversal of the behavioural phenotype with β-carboline, an anxiogenic inverse benzodiazepine receptor agonist, normalized alcohol preference in EFhd2 KO mice, demonstrating an EFhd2-driven relationship between personality traits and alcohol preference. These findings were confirmed in a human sample where we observed a positive association of the EFhd2 single-nucleotide polymorphism rs112146896 with lifetime drinking and a negative association with anxiety in healthy adolescents. The lack of EFhd2 reduced extracellular dopamine levels in the brain, but enhanced responses to alcohol. In confirmation, gene expression analysis revealed reduced tyrosine hydroxylase expression and the regulation of genes involved in cortex development, Eomes and Pax6, in EFhd2 KO cortices. These findings were corroborated in Xenopus tadpoles by EFhd2 knockdown. Magnetic resonance imaging (MRI) in mice showed that a lack of EFhd2 reduces cortical volume in adults. Moreover, human MRI confirmed the negative association between lifetime alcohol drinking and superior frontal gyrus volume. We propose that EFhd2 is a conserved resilience factor against alcohol consumption and its escalation, working through Pax6/Eomes. Reduced EFhd2 function induces high-risk personality traits of sensation-seeking/low anxiety associated with enhanced alcohol consumption, which may be related to cortex function.
EVALuna2:4036

Endometriosis as a risk factor for ovarian or endometrial cancer - results of a hospital-based case-control study - Burghaus, Stefanie; Haeberle, Lothar; Schrauder, Michael G.; Heusinger, Katharina; Thiel, Falk; Hein, Alexander; Wachter, David; Strehl, Johanna; Hartmann, Arndt; Ekici, Arif Bülent; Renner, Stefan; Beckmann, Matthias; et al. (BMC Cancer, 2015)
No screening programs are available for ovarian or endometrial cancer. One reason for this is the low incidence of the conditions, resulting in low positive predictive values for tests, which are not very specific. One way of addressing this problem might be to use risk factors to define subpopulations with a higher incidence. The aim of this study was to investigate the extent to which a medical history of endometriosis can serve as a risk factor for ovarian or endometrial cancer.In a hospital-based case-control analysis, the cases represented patients with endometrial or ovarian cancer who were participating in studies aimed at assessing the risk for these diseases. The controls were women between the age of 40 and 85 who were invited to take part via a newspaper advertisement. A total of 289 cases and 1016 controls were included. Using logistic regression models, it was tested whether self-reported endometriosis is a predictor of case-control status in addition to age, body mass index (BMI), number of pregnancies and previous oral contraceptive (OC) use.Endometriosis was reported in 2.1 % of the controls (n = 21) and 4.8 % of the cases (n = 14). Endometriosis was a relevant predictor for case-control status in addition to other predictive factors (OR 2.63; 95 % CI, 1.28 to 5.41).This case-control study found that self-reported endometriosis may be a risk factor for endometrial or ovarian cancer in women between 40 and 85 years. There have been very few studies addressing this issue, and incorporating it into a clinical prediction model would require a more precise characterization of the risk factor of endometriosis.
EVALuna2:6731

Epigenome-wide association study of serum urate reveals insights into urate co-regulation and the SLC2A9 locus - Tin, Adrienne; Schlosser, Pascal; Matias-Garcia, Pamela R.; Thio, Chris H. L.; Joehanes, Roby; Liu, Hongbo; Yu, Zhi; Weihs, Antoine; Hoppmann, Anselm; Grundner-Culemann, Franziska; Min, Josine L.; Kuhns, Victoria L. Halperin; et al. (Nature Communications, 2021)
Serum urate concentration can be studied in large datasets to find genetic and epigenetic loci that may be related to cardiometabolic traits. Here the authors identify and replicate 100 urate-associated CpGs, which provide insights into urate GWAS loci and shared CpGs of urate and cardiometabolic traits.
CRIS-Team WoS Importer:2021-12-17

Epithelial-Mesenchymal Transition (EMT) Gene Variants and Epithelial Ovarian Cancer (EOC) Risk - Amankwah, Ernest K.; Lin, Hui-Yi; Tyrer, Jonathan P.; Lawrenson, Kate; Dennis, Joe; Chornokur, Ganna; Aben, Katja K. H.; Anton-Culver, Hoda; Antonenkova, Natalia; Bruinsma, Fiona; Bandera, Elisa V.; Bean, Yukie T.; et al. (Genetic Epidemiology, 2015)
Epithelial-mesenchymal transition (EMT) is a process whereby epithelial cells assume mesenchymal characteristics to facilitate cancer metastasis. However, EMT also contributes to the initiation and development of primary tumors. Prior studies that explored the hypothesis that EMT gene variants contribute to epithelial ovarian carcinoma (EOC) risk have been based on small sample sizes and none have sought replication in an independent population. We screened 15,816 single-nucleotide polymorphisms (SNPs) in 296 genes in a discovery phase using data from a genome-wide association study of EOC among women of European ancestry (1,947 cases and 2,009 controls) and identified 793 variants in 278 EMT-related genes that were nominally (P < 0.05) associated with invasive EOC. These SNPs were then genotyped in a larger study of 14,525 invasive-cancer patients and 23,447 controls. A P-value <0.05 and a false discovery rate (FDR) <0.2 were considered statistically significant. In the larger dataset, GPC6/GPC5 rs17702471 was associated with the endometrioid subtype among Caucasians (odds ratio (OR) = 1.16, 95% CI = 1.07-1.25, P = 0.0003, FDR = 0.19), whereas F8 rs7053448 (OR = 1.69, 95% CI = 1.27-2.24, P = 0.0003, FDR = 0.12), F8 rs7058826 (OR = 1.69, 95% CI = 1.27-2.24, P = 0.0003, FDR = 0.12), and CAPN13 rs1983383 (OR = 0.79, 95% CI = 0.69-0.90, P = 0.0005, FDR = 0.12) were associated with combined invasive EOC among Asians. In silico functional analyses revealed that GPC6/GPC5 rs17702471 coincided with DNA regulatory elements. These results suggest that EMT gene variants do not appear to play a significant role in the susceptibility to EOC.
EVALuna2:9299

Estrogen receptor beta rs1271572 polymorphism and invasive ovarian carcinoma risk: Pooled analysis within the ovarian cancer association consortium - Lurie, Galina; Wilkens, Lynne R.; Thompson, Pamela J.; Shvetsov, Yurii B.; Matsuno, Rayna K.; Carney, Michael E.; Palmieri, Rachel T.; Wu, Anna H.; Pike, Malcolm C.; Pearce, Celeste L.; Menon, Usha; Gentry-Maharaj, Aleksandra; et al. (PLoS ONE, 2011)
The association of ovarian carcinoma risk with the polymorphism rs1271572 in the estrogen receptor beta (ESR2) gene was examined in 4946 women with primary invasive ovarian carcinoma and 6582 controls in a pooled analysis of ten case-control studies within the Ovarian Cancer Association Consortium (OCAC). All participants were non-Hispanic white women. Odds ratios (ORs) and 95% confidence intervals (CIs) were estimated using unconditional logistic regression adjusted for site and age. Women with the TT genotype were at increased risk of ovarian carcinoma compared to carriers of the G allele (OR = 1.10; 95%; CI: 1.01-1.21; p = 0.04); the OR was 1.09 (CI: 0.99-1.20; p = 0.07) after excluding data from the center (Hawaii) that nominated this SNP for OCAC genotyping A stronger association of rs1271572 TT versus GT/GG with risk was observed among women aged ≤50 years versus older women (OR = 1.35; CI: 1.12-1.62; p = 0.002; p for interaction = 0.02) that remained statistically significant after excluding Hawaii data (OR = 1.34; CI: 1.11-1.61; p = 0.009). No heterogeneity of the association was observed by study, menopausal status, gravidity, parity, use of contraceptive or menopausal hormones, tumor histological type, or stage at diagnosis. This pooled analysis suggests that rs1271572 might influence the risk of ovarian cancer, in particular among younger women. © 2011 Lurie et al.
CRIS-Team Scopus Importer:2021-07-19

Evaluating the ovarian cancer gonadotropin hypothesis: a candidate gene study - Lee, Alice W.; Tyrer, Jonathan P.; Doherty, Jennifer A.; Stram, Douglas A.; Kupryjanczyk, Jolanta; Dansonka-Mieszkowska, Agnieszka; Plisiecka-Halasa, Joanna; Spiewankiewicz, Beata; Myers, Emily J.; Chenevix-Trench, Georgia; Fasching, Peter A.; Beckmann, Matthias; et al. (Gynecologic Oncology, 2015)
Ovarian cancer is a hormone-related disease with a strong genetic basis. However, none of its high-penetrance susceptibility genes and GWAS-identified variants to date are known to be involved in hormonal pathways. Given the hypothesized etiologic role of gonadotropins, an assessment of how variability in genes involved in the gonadotropin signaling pathway impacts disease risk is warranted.Genetic data from 41 ovarian cancer study sites were pooled and unconditional logistic regression was used to evaluate whether any of the 2185 SNPs from 11 gonadotropin signaling pathway genes was associated with ovarian cancer risk. A burden test using the admixture likelihood (AML) method was also used to evaluate gene-level associations.We did not find any genome-wide significant associations between individual SNPs and ovarian cancer risk. However, there was some suggestion of gene-level associations for four gonadotropin signaling pathway genes: INHBB (p=0.045, mucinous), LHCGR (p=0.046, high-grade serous), GNRH (p=0.041, high-grade serous), and FSHB (p=0.036, overall invasive). There was also suggestive evidence for INHA (p=0.060, overall invasive).Ovarian cancer studies have limited sample numbers, thus fewer genome-wide susceptibility alleles, with only modest associations, have been identified relative to breast and prostate cancers. We have evaluated the majority of ovarian cancer studies with biological samples, to our knowledge, leaving no opportunity for replication. Using both our understanding of biology and powerful gene-level tests, we have identified four putative ovarian cancer loci near INHBB, LHCGR, GNRH, and FSHB that warrant a second look if larger sample sizes and denser genotype chips become available.
EVALuna2:9278

Evaluation of variation in the phosphoinositide-3-kinase catalytic subunit alpha oncogene and breast cancer risk - Stevens, K. N.; Garcia-Closas, Montserrat; Fredericksen, Z.; Kosel, M.; Pankratz, V. S.; Hopper, J. L.; Dite, G. S.; Apicella, C.; Southey, M. C.; Schmidt, M. K.; Broeks, A.; Van 'T Veer, L. J.; et al. (British Journal of Cancer, 2011)
Background: Somatic mutations in phosphoinositide-3-kinase catalytic subunit alpha (PIK3CA) are frequent in breast tumours and have been associated with oestrogen receptor (ER) expression, human epidermal growth factor receptor-2 overexpression, lymph node metastasis and poor survival. The goal of this study was to evaluate the association between inherited variation in this oncogene and risk of breast cancer. Methods: A single-nucleotide polymorphism from the PIK3CA locus that was associated with breast cancer in a study of Caucasian breast cancer cases and controls from the Mayo Clinic (MCBCS) was genotyped in 5436 cases and 5280 controls from the Cancer Genetic Markers of Susceptibility (CGEMS) study and in 30 949 cases and 29 788 controls from the Breast Cancer Association Consortium (BCAC). Results: Rs1607237 was significantly associated with a decreased risk of breast cancer in MCBCS, CGEMS and all studies of white Europeans combined (odds ratio (OR)=0.97, 95% confidence interval (CI) 0.95-0.99, P=4.6 × 10 3), but did not reach significance in the BCAC replication study alone (OR=0.98, 95% CI 0.96-1.01, P=0.139).Conclusion: Common germline variation in PIK3CA does not have a strong influence on the risk of breast cancer. © 2011 Cancer Research UK All rights reserved.
CRIS-Team Scopus Importer:2021-07-19
Keywords: Association study; Genetic susceptibility; Neoplasms

Evidence that breast cancer risk at the 2q35 locus is mediated through IGFBP5 regulation - Ghoussaini, Maya; Edwards, Stacey L.; Michailidou, Kyriaki; Nord, Silje; Lari, Richard Cowper-Sal; Desai, Kinjal; Kar, Siddhartha; Hillman, Kristine M.; Kaufmann, Susanne; Glubb, Dylan M.; Beesley, Jonathan; Dennis, Joe; et al. (Nature Communications, 2014)
GWAS have identified a breast cancer susceptibility locus on 2q35. Here we report the fine mapping of this locus using data from 101,943 subjects from 50 case-control studies. We genotype 276 SNPs using the 'iCOGS' genotyping array and impute genotypes for a further 1,284 using 1000 Genomes Project data. All but two, strongly correlated SNPs (rs4442975 G/T and rs6721996 G/A) are excluded as candidate causal variants at odds against >100:1. The best functional candidate, rs4442975, is associated with oestrogen receptor positive (ER+) disease with an odds ratio (OR) in Europeans of 0.85 (95% confidence interval=0.84-0.87; P=1.7 × 10(-43)) per t-allele. This SNP flanks a transcriptional enhancer that physically interacts with the promoter of IGFBP5 (encoding insulin-like growth factor-binding protein 5) and displays allele-specific gene expression, FOXA1 binding and chromatin looping. Evidence suggests that the g-allele confers increased breast cancer susceptibility through relative downregulation of IGFBP5, a gene with known roles in breast cell biolog
EVALuna2:9236

Evolutionary conserved networks of human height identify multiple Mendelian causes of short stature - Hauer, Nadine; Popp, Bernt; Taher, Leila; Vogl, Carina; Dhandapany, Perundurai S.; Büttner, Christian; Uebe, Steffen; Sticht, Heinrich; Ferrazzi, Fulvia; Ekici, Arif Bülent; De Luca, Alessandro; Klinger, Patricia; et al. (European journal of human genetics, 2019)
Height is a heritable and highly heterogeneous trait. Short stature affects 3% of the population and in most cases is genetic in origin. After excluding known causes, 67% of affected individuals remain without diagnosis. To identify novel candidate genes for short stature, we performed exome sequencing in 254 unrelated families with short stature of unknown cause and identified variants in 63 candidate genes in 92 (36%) independent families. Based on systematic characterization of variants and functional analysis including expression in chondrocytes, we classified 13 genes as strong candidates. Whereas variants in at least two families were detected for all 13 candidates, two genes had variants in 6 (UBR4) and 8 (LAMA5) families, respectively. To facilitate their characterization, we established a clustered network of 1025 known growth and short stature genes, which yielded 29 significantly enriched clusters, including skeletal system development, appendage development, metabolic processes, and ciliopathy. Eleven of the candidate genes mapped to 21 of these clusters, including CPZ, EDEM3, FBRS, IFT81, KCND1, PLXNA3, RASA3, SLC7A8, UBR4, USP45, and ZFHX3. Fifty additional growth-related candidates we identified await confirmation in other affected families. Our study identifies Mendelian forms of growth retardation as an important component of idiopathic short stature.
CRIS-Team Scopus Importer:2019-05-24

Exome Pool-Seq in neurodevelopmental disorders - Popp, Bernt; Ekici, Arif Bülent; Thiel, Christian; Hoyer, Juliane; Wiesener, Antje; Kraus, Cornelia; Reis, André; Zweier, Christiane (European journal of human genetics, 2017)
High throughput sequencing has greatly advanced disease gene identification, especially in heterogeneous entities. Despite falling costs this is still an expensive and laborious technique, particularly when studying large cohorts. To address this problem we applied Exome Pool-Seq as an economic and fast screening technology in neurodevelopmental disorders (NDDs). Sequencing of 96 individuals can be performed in eight pools of 12 samples on less than one Illumina sequencer lane. In a pilot study with 96 cases we identified 27 variants, likely or possibly affecting function. Twenty five of these were identified in 923 established NDD genes (based on SysID database, status November 2016) (ACTB, AHDC1, ANKRD11, ATP6V1B2, ATRX, CASK, CHD8, GNAS, IFIH1, KCNQ2, KMT2A, KRAS, MAOA, MED12, MED13L, RIT1, SETD5, SIN3A, TCF4, TRAPPC11, TUBA1A, WAC, ZBTB18, ZMYND11), two in 543 (SysID) candidate genes (ZNF292, BPTF), and additionally a de novo loss-of-function variant in LRRC7, not previously implicated in NDDs. Most of them were confirmed to be de novo, but we also identified X-linked or autosomal-dominantly or autosomal-recessively inherited variants. With a detection rate of 28%, Exome Pool-Seq achieves comparable results to individual exome analyses but reduces costs by >85%. Compared with other large scale approaches using Molecular Inversion Probes (MIP) or gene panels, it allows flexible re-analysis of data. Exome Pool-Seq is thus well suited for large-scale, cost-efficient and flexible screening in characterized but heterogeneous entities like NDDs.
EVALuna2:9387

Exome Pool-Seq Reloaded - Popp, B.; Vasileiou, G.; Zweier, M.; Ekici, Arif Bülent; Moortgat, S.; Lederer, D.; Maystadt, I.; Destree, A.; Drunat, S.; Verloes, A.; Rauch, A.; Steindl, K.; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

Experimental epileptogenesis in a cell culture model of primary neurons from rat brain: A temporal multi‐scale study - Jablonski, Janos; Hoffmann, Lucas; Blümcke, Ingmar; Fejtová, Anna; Uebe, Steffen; Ekici, Arif Bülent; Gnatkovsky, Vadym; Kobow, Katja (Cells, 2021)
Understanding seizure development requires an integrated knowledge of different scales of organization of epileptic networks. We developed a model of “epilepsy‐in‐a‐dish” based on dissociated primary neuronal cells from neonatal rat hippocampus. We demonstrate how a single application of glutamate stimulated neurons to generate spontaneous synchronous spiking activity with further progression into spontaneous seizure‐like events after a distinct latency period. By computational analysis, we compared the observed neuronal activity in vitro with intracranial electroencephalography (EEG) data recorded from epilepsy patients and identified strong similarities, including a related sequence of events with defined onset, progression, and termination. Next, a link between the neurophysiological changes with network composition and cellular structure down to molecular changes was established. Temporal development of epileptiform network activity correlated with increased neurite outgrowth and altered branching, increased ratio of glutamatergic over GABAergic synapses, and loss of calbindin‐positive interneurons, as well as genome‐wide alterations in DNA methylation. Differentially methylated genes were engaged in various cellular activities related to cellular structure, intracellular signaling, and regulation of gene expression. Our data provide evidence that a single short‐term excess of glutamate is sufficient to induce a cascade of events covering different scales from molecule‐ to network‐level, all of which jointly contribute to seizure development.
CRIS-Team Scopus Importer:2021-11-12
Keywords: DNA methylation; Epigenetic; Epilepsy; In vitro

Exploring the phenotypical spectrum of BRD4 defects - Hauer, Nadine; Vogl, C.; Popp, Bernt; Buettner, C.; Uebe, S.; Sticht, Heinrich; Ekici, Arif Bülent; Klinger, Patricia; Kraus, Cornelia; Krumbiegel, M.; Wiesener, A.; Dörr, Helmuth-Günther; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2019)
CRIS-Team WoS Importer:2019-10-25

FAM13A is associated with non-small cell lung cancer (NSCLC) progression and controls tumor cell proliferation and survival - Eisenhut, Felix; Heim, Lisanne; Trump, Sonja; Mittler, Susanne; Sopel, Nina; Andreev, Katerina; Ferrazzi, Fulvia; Ekici, Arif Bülent; Rieker, Ralf; Springel, Rebekka; Assmann, Vera Elisabeth; Lechmann, Matthias; et al. (OncoImmunology, 2017)
Genome-wide association studies (GWAS) associated Family with sequence similarity 13, member A (FAM13A) with non-small cell lung cancer (NSCLC) occurrence. Here, we found increased numbers of FAM13A protein expressing cells in the tumoral region of lung tissues from a cohort of patients with NSCLC. Moreover, FAM13A inversely correlated with CTLA4 but directly correlated with HIF1? levels in the control region of these patients. Consistently, FAM13A RhoGAP was found to be associated with T cell effector molecules like HIF1? and Tbet and was downregulated in immunosuppressive CD4(+)CD25(+)Foxp3(+)CTLA4(+) T cells. TGF?, a tumor suppressor factor, as well as siRNA to FAM13A, suppressed both isoforms of FAM13A and inhibited tumor cell proliferation. RNA-Seq analysis confirmed this finding. Moreover, siRNA to FAM13A induced TGF? levels. Finally, in experimental tumor cell migration, FAM13A was induced and TGF? accelerated this process by inducing cell migration, HIF1?, and the FAM13A RhoGAP isoform. Furthermore, siRNA to FAM13A inhibited tumor cell proliferation and induced cell migration without affecting HIF1?. In conclusion, FAM13A is involved in tumor cell proliferation and downstream of TGF? and HIF1?, FAM13A RhoGAP is associated with Th1 gene expression and lung tumor cell migration. These findings identify FAM13A as key regulator of NSCLC growth and progression.
EVALuna2:6835

FcγRIIa genotype is associated with acute coronary syndromes as first manifestation of coronary artery disease - Raaz, Dorette; Herrmann, Martin; Ekici, Arif Bülent; Klinghammer, Lutz; Lausen, Berthold; Voll, Reinhard E.; Leusen, Jeanette H.W.; van de Winkel, Jan G.J.; Daniel, Werner; Reis, André; Garlichs, Christoph (Atherosclerosis, 2009)
Objective: Identification of clinically relevant determinants for acute coronary syndromes (ACS) promises reduction of ACS-associated mortality. C-reactive protein (CRP) has proved to be useful identifying people at risk for cardiovascular events. However, it is unknown whether genetic variants at Fcγ receptor IIa (FcγRIIa), the main receptor for CRP, are involved in CRP-related cardiovascular risk. We evaluated the potential impact of FcγRIIa through a genetic association study in patients with ACS. Methods and results: We conducted a genetic association study among 701 consecutive patients with first event of ACS compared to 467 patients with stable angina pectoris. All patients were genotyped for a frequent functional variant at position 131 of the mature FcγRIIa, where the arginine (R) allele results in an increased signal transduction upon CRP binding. In our study, the R/R131 genotype was significantly associated with ACS as the first manifestation of coronary artery disease (P = 1.2 × 10-9, odds ratio 2.86, 95% CI: 2.06-3.99) compared to the non-R/R131 genotype. Conclusions: Our data show a genetic association of the FcγRIIa R/R131 genotype with a more frequent occurrence of ACS as the first manifestation of coronary artery disease, probably mediated via its interaction with CRP. Genotyping of this FcγRIIa variant could help to improve risk stratification in the course of coronary disease in the future. © 2009 Elsevier Ireland Ltd. All rights reserved.
CRIS-Team Scopus Importer:2023-07-10
Keywords: Acute coronary syndrome; Fcγ receptor IIa; Gene polymorphism; Inflammation

FGF receptor genes and breast cancer susceptibility: results from the Breast Cancer Association Consortium - Agarwal, D.; Pineda, S.; Michailidou, K.; Herranz, J.; Pita, G.; Moreno, L. T.; Alonso, M. R.; Dennis, J.; Wang, Q.; Bolla, M. K.; Meyer, K. B.; Menendez-Rodriguez, P.; et al. (British Journal of Cancer, 2014)
Breast cancer is one of the most common malignancies in women. Genome-wide association studies have identified FGFR2 as a breast cancer susceptibility gene. Common variation in other fibroblast growth factor (FGF) receptors might also modify risk. We tested this hypothesis by studying genotyped single-nucleotide polymorphisms (SNPs) and imputed SNPs in FGFR1, FGFR3, FGFR4 and FGFRL1 in the Breast Cancer Association Consortium.Data were combined from 49 studies, including 53 835 cases and 50 156 controls, of which 89 050 (46 450 cases and 42 600 controls) were of European ancestry, 12 893 (6269 cases and 6624 controls) of Asian and 2048 (1116 cases and 932 controls) of African ancestry. Associations with risk of breast cancer, overall and by disease sub-type, were assessed using unconditional logistic regression.Little evidence of association with breast cancer risk was observed for SNPs in the FGF receptor genes. The strongest evidence in European women was for rs743682 in FGFR3; the estimated per-allele odds ratio was 1.05 (95% confidence interval=1.02-1.09, P=0.0020), which is substantially lower than that observed for SNPs in FGFR2.Our results suggest that common variants in the other FGF receptors are not associated with risk of breast cancer to the degree observed for FGFR2.
EVALuna2:9221

Fine-mapping identifies two additional breast cancer susceptibility loci at 9q31.2 - Orr, Nick; Dudbridge, Frank; Dryden, Nicola; Maguire, Sarah; Novo, Daniela; Perrakis, Eleni; Johnson, Nichola; Ghoussaini, Maya; Hopper, John L.; Southey, Melissa C.; Apicella, Carmel; Stone, Jennifer; et al. (Human Molecular Genetics, 2015)
We recently identified a novel susceptibility variant, rs865686, for estrogen-receptor positive breast cancer at 9q31.2. Here, we report a fine-mapping analysis of the 9q31.2 susceptibility locus using 43 160 cases and 42 600 controls of European ancestry ascertained from 52 studies and a further 5795 cases and 6624 controls of Asian ancestry from nine studies. Single nucleotide polymorphism (SNP) rs676256 was most strongly associated with risk in Europeans (odds ratios [OR] = 0.90 [0.88-0.92]; P-value = 1.58 × 10(-25)). This SNP is one of a cluster of highly correlated variants, including rs865686, that spans 14.5 kb. We identified two additional independent association signals demarcated by SNPs rs10816625 (OR = 1.12 [1.08-1.17]; P-value = 7.89 × 10(-09)) and rs13294895 (OR = 1.09 [1.06-1.12]; P-value = 2.97 × 10(-11)). SNP rs10816625, but not rs13294895, was also associated with risk of breast cancer in Asian individuals (OR = 1.12 [1.06-1.18]; P-value = 2.77 × 10(-05)). Functional genomic annotation using data derived from breast cancer cell-line models indicates that these SNPs localise to putative enhancer elements that bind known drivers of hormone-dependent breast cancer, including ER-?, FOXA1 and GATA-3. In vitro analyses indicate that rs10816625 and rs13294895 have allele-specific effects on enhancer activity and suggest chromatin interactions with the KLF4 gene locus. These results demonstrate the power of dense genotyping in large studies to identify independent susceptibility variants. Analysis of associations using subjects with different ancestry, combined with bioinformatic and genomic characterisation, can provide strong evidence for the likely causative alleles and their functional basi
EVALuna2:9279

Fine-mapping of the HNF1B multicancer locus identifies candidate variants that mediate endometrial cancer risk - Painter, Jodie N.; O'Mara, Tracy A.; Batra, Jyotsna; Cheng, Timothy; Lose, Felicity A.; Dennis, Joe; Michailidou, Kyriaki; Tyrer, Jonathan P.; Ahmed, Shahana; Ferguson, Kaltin; Healey, Catherine S.; Kaufmann, Susanne; et al. (Human Molecular Genetics, 2015)
Common variants in the hepatocyte nuclear factor 1 homeobox B (HNF1B) gene are associated with the risk of Type II diabetes and multiple cancers. Evidence to date indicates that cancer risk may be mediated via genetic or epigenetic effects on HNF1B gene expression. We previously found single-nucleotide polymorphisms (SNPs) at the HNF1B locus to be associated with endometrial cancer, and now report extensive fine-mapping and in silico and laboratory analyses of this locus. Analysis of 1184 genotyped and imputed SNPs in 6608 Caucasian cases and 37 925 controls, and 895 Asian cases and 1968 controls, revealed the best signal of association for SNP rs11263763 (P = 8.4 × 10(-14), odds ratio = 0.86, 95% confidence interval = 0.82-0.89), located within HNF1B intron 1. Haplotype analysis and conditional analyses provide no evidence of further independent endometrial cancer risk variants at this locus. SNP rs11263763 genotype was associated with HNF1B mRNA expression but not with HNF1B methylation in endometrial tumor samples from The Cancer Genome Atlas. Genetic analyses prioritized rs11263763 and four other SNPs in high-to-moderate linkage disequilibrium as the most likely causal SNPs. Three of these SNPs map to the extended HNF1B promoter based on chromatin marks extending from the minimal promoter region. Reporter assays demonstrated that this extended region reduces activity in combination with the minimal HNF1B promoter, and that the minor alleles of rs11263763 or rs8064454 are associated with decreased HNF1B promoter activity. Our findings provide evidence for a single signal associated with endometrial cancer risk at the HNF1B locus, and that risk is likely mediated via altered HNF1B gene expression.
EVALuna2:9243

Fine-scale mapping of the 5q11.2 breast cancer locus reveals at least three independent risk variants regulating MAP3K1 - Glubb, Dylan M.; Maranian, Mel J.; Michailidou, Kyriaki; Pooley, Karen A.; Meyer, Kerstin B.; Kar, Siddhartha; Carlebur, Saskia; O'Reilly, Martin; Betts, Joshua A.; Hillman, Kristine M.; Kaufmann, Susanne; Beesley, Jonathan; et al. (American Journal of Human Genetics, 2015)
Genome-wide association studies (GWASs) have revealed SNP rs889312 on 5q11.2 to be associated with breast cancer risk in women of European ancestry. In an attempt to identify the biologically relevant variants, we analyzed 909 genetic variants across 5q11.2 in 103,991 breast cancer individuals and control individuals from 52 studies in the Breast Cancer Association Consortium. Multiple logistic regression analyses identified three independent risk signals: the strongest associations were with 15 correlated variants (iCHAV1), where the minor allele of the best candidate, rs62355902, associated with significantly increased risks of both estrogen-receptor-positive (ER(+): odds ratio [OR] = 1.24, 95% confidence interval [CI] = 1.21-1.27, ptrend = 5.7 × 10(-44)) and estrogen-receptor-negative (ER(-): OR = 1.10, 95% CI = 1.05-1.15, ptrend = 3.0 × 10(-4)) tumors. After adjustment for rs62355902, we found evidence of association of a further 173 variants (iCHAV2) containing three subsets with a range of effects (the strongest was rs113317823 [pcond = 1.61 × 10(-5)]) and five variants composing iCHAV3 (lead rs11949391; ER(+): OR = 0.90, 95% CI = 0.87-0.93, pcond = 1.4 × 10(-4)). Twenty-six percent of the prioritized candidate variants coincided with four putative regulatory elements that interact with the MAP3K1 promoter through chromatin looping and affect MAP3K1 promoter activity. Functional analysis indicated that the cancer risk alleles of four candidates (rs74345699 and rs62355900 [iCHAV1], rs16886397 [iCHAV2a], and rs17432750 [iCHAV3]) increased MAP3K1 transcriptional activity. Chromatin immunoprecipitation analysis revealed diminished GATA3 binding to the minor (cancer-protective) allele of rs17432750, indicating a mechanism for its action. We propose that the cancer risk alleles act to increase MAP3K1 expression in vivo and might promote breast cancer cell surviva
EVALuna2:9276

Five endometrial cancer risk loci identified through genome-wide association analysis - Cheng, Timothy H. T.; Thompson, Deborah J.; O'Mara, Tracy A.; Painter, Jodie N.; Glubb, Dylan M.; Flach, Susanne; Lewis, Annabelle; French, Juliet D.; Freeman-Mills, Luke; Church, David; Gorman, Maggie; Martin, Lynn; et al. (Nature Genetics, 2016)
We conducted a meta-analysis of three endometrial cancer genome-wide association studies (GWAS) and two follow-up phases totaling 7,737 endometrial cancer cases and 37,144 controls of European ancestry. Genome-wide imputation and meta-analysis identified five new risk loci of genome-wide significance at likely regulatory regions on chromosomes 13q22.1 (rs11841589, near KLF5), 6q22.31 (rs13328298, in LOC643623 and near HEY2 and NCOA7), 8q24.21 (rs4733613, telomeric to MYC), 15q15.1 (rs937213, in EIF2AK4, near BMF) and 14q32.33 (rs2498796, in AKT1, near SIVA1). We also found a second independent 8q24.21 signal (rs17232730). Functional studies of the 13q22.1 locus showed that rs9600103 (pairwise r(2) = 0.98 with rs11841589) is located in a region of active chromatin that interacts with the KLF5 promoter region. The rs9600103[T] allele that is protective in endometrial cancer suppressed gene expression in vitro, suggesting that regulation of the expression of KLF5, a gene linked to uterine development, is implicated in tumorigenesis. These findings provide enhanced insight into the genetic and biological basis of endometrial cancer.
EVALuna2:9326

Fra-2 regulates B cell development by enhancing IRF4 and Foxo1 transcription - Ubieta, Kenia; Garcia, Mireia; Groetsch, Bettina; Uebe, Steffen; Stein, Merle; Ekici, Arif Bülent; Schett, Georg; Mielenz, Dirk; Bozec, Aline; Weber, Georg (Journal of Experimental Medicine, 2017)
The role of AP-1 transcription factors in early B cell development and function is still incompletely characterized. Here we address the role of Fra-2 in B cell differentiation. Deletion of Fra-2 leads to impaired B cell proliferation in the bone marrow. In addition, IL-7-stimulated pro-B cell cultures revealed a reduced differentiation from large pre-B cells to small B cells and immature B cells. Gene profiling and chromatin immunoprecipitation sequencing analyses unraveled a transcriptional reduction of the transcription factors Foxo1, Irf4, Ikaros, and Aiolos in Fra-2-deficient B cells. Moreover, expression of IL7R? and Rag 1/2, downstream targets of Irf4 and Foxo1, were also reduced in the absence of Fra-2. Pro-B cell proliferation and small pre-B cell differentiation were fully rescued by expression of Foxo1 and Irf4 in Fra-2-deficient pro-B cells. Hence, Fra-2 is a key upstream regulator of Foxo1 and Irf4 expression and influences proliferation and differentiation of B cells at multiple stages.
EVALuna2:9366

Functional Analysis and Fine Mapping of the 9p22.2 Ovarian Cancer Susceptibility Locus - Buckley, Melissa A.; Woods, Nicholas T.; Tyrer, Jonathan P.; Mendoza-Fandino, Gustavo; Lawrenson, Kate; Hazelett, Dennis J.; Najafabadi, Hamed S.; Gjyshi, Anxhela; Carvalho, Renato S.; Lyra, Paulo C.; Coetzee, Simon G.; Shen, Howard C.; et al. (Cancer Research, 2019)
Genome-wide association studies have identified 40 ovarian cancer risk loci. However, the mechanisms underlying these associations remain elusive. In this study, we conducted a two-pronged approach to identify candidate causal SNPs and assess underlying biological mechanisms at chromosome 9p22.2, the first and most statistically significant associated locus for ovarian cancer susceptibility. Three transcriptional regulatory elements with allele-specific effects and a scaffold/matrix attachment region were characterized and, through physical DNA interactions, BNC2 was established as the most likely target gene. We determined the consensus binding sequence for BNC2 in vitro, verified its enrichment in BNC2 ChIP-seq regions, and validated a set of its downstream target genes. Fine-mapping by dense regional genotyping in over 15,000 ovarian cancer cases and 30,000 controls identified SNPs in the scaffold/ matrix attachment region as among the most likely causal variants. This study reveals a comprehensive regulatory landscape at 9p22.2 and proposes a likely mechanism of susceptibility to ovarian cancer.
CRIS-Team WoS Importer:2019-02-21

Further clinical and molecular delineation of Alazami syndrome associated with variants in LARP7 - Gumuslu, E.; Karaer, K.; Gumus, E.; Ekici, Arif Bülent; Kraus, Cornelia; Reis, André (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

Further clinical and molecular delineation of spondylocostal dysostosis type 3 - Schuhmann, Sarah; Koller, H.; Sticht, Heinrich; Kraus, Cornelia; Krumbiegel, Mandy; Uebe, Steffen; Ekici, Arif Bülent; Reis, André; Thiel, C. T. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

Gene-Environment Interactions Relevant to Estrogen and Risk of Breast Cancer: Can Gene-Environment Interactions Be Detected Only among Candidate SNPs from Genome-Wide Association Studies? - Park, Jooyong; Choi, Ji-Yeob; Choi, Jaesung; Chung, Seokang; Song, Nan; Park, Sue K.; Han, Wonshik; Noh, Dong-Young; Ahn, Sei-Hyun; Lee, Jong Won; Kim, Mi Kyung; Jee, Sun Ha; et al. (Cancers, 2021)
Simple Summary
CRIS-Team WoS Importer:2021-06-04

Genetic Breast Cancer Susceptibility Variants and Prognosis in the Prospectively Randomized SUCCESS A Study - Hein, Alexander; Rack, B.; Li, L.; Ekici, Arif Bülent; Reis, André; Lux, Michael P.; Cunningham, J. M.; Rübner, Matthias; Fridley, B. L.; Schneeweiss, A.; Tesch, H.; Lichtenegger, W.; et al. (Geburtshilfe und Frauenheilkunde, 2017)
Large-scale genotyping studies have identified over 70 single nucleotide polymorphisms (SNPs) associated with breast cancer (BC) risk. However, knowledge regarding genetic risk factors associated with the prognosis is limited. The aim of this study was therefore to investigate the prognostic effect of nine known breast cancer risk SNPs. BC patients (n = 1687) randomly sampled in an adjuvant, randomized phase III trial (SUCCESS A study) were genotyped for nine BC risk SNPs: rs17468277 (CASP8) , rs2981582 (FGFR2) , rs13281615(8q24), rs3817198 (LSP1) , rs889312 (MAP3K1) , rs3803662 (TOX3) , rs13387042(2q35), rs4973768 (SLC4A7) , rs6504950 (COX11) . Cox proportional hazards models were used to test the SNPs' association with overall survival (OS) and progression-free survival (PFS). Additional analyses were carried out for molecular subgroups. rs3817198 in LSP1 (lymphocyte-specific protein 1) was the only SNP that significantly influenced OS (p = 0.01) and PFS (p < 0.01) in the likelihood ratio test comparing the genetic survival model with the clinical survival model. In the molecular subgroups, triple-negative patients with two minor alleles in rs3817198 had a much better prognosis relative to OS (adjusted HR 0.03; 95% CI 0.002 - 0.279) and PFS (HR 0.09; 95% CI 0.02 - 0.36) than patients with the common alleles. The same effect on PFS was shown for patients with luminal A tumors (HR 0.19; 95% CI 0.05 - 0.84), whereas patients with luminal B tumors had a poorer PFS with two minor alleles (HR 2.13; 95% CI 1.02 - 4.40). The variant in rs3817198 has a prognostic effect particularly in the subgroup of patients with triple-negative BC, suggesting a possible link with immunomodulation and BC.
EVALuna2:9355

Genetic interaction screen for severe neurodevelopmental disorders reveals a functional link between Ube3a and Mef2 in Drosophila melanogaster - Straub, Jonas; Gregor, Anne; Sauerer, Tatjana; Fliedner, Anna; Distel, Laila; Suchy, Christine; Ekici, Arif Bülent; Ferrazzi, Fulvia; Zweier, Christiane (Scientific Reports, 2020)
Neurodevelopmental disorders (NDDs) are clinically and genetically extremely heterogeneous with shared phenotypes often associated with genes from the same networks. Mutations in TCF4, MEF2C, UBE3A, ZEB2 or ATRX cause phenotypically overlapping, syndromic forms of NDDs with severe intellectual disability, epilepsy and microcephaly. To characterize potential functional links between these genes/proteins, we screened for genetic interactions in Drosophila melanogaster. We induced ubiquitous or tissue specific knockdown or overexpression of each single orthologous gene (Da, Mef2, Ube3a, Zfh1, XNP) and in pairwise combinations. Subsequently, we assessed parameters such as lethality, wing and eye morphology, neuromuscular junction morphology, bang sensitivity and climbing behaviour in comparison between single and pairwise dosage manipulations. We found most stringent evidence for genetic interaction between Ube3a and Mef2 as simultaneous dosage manipulation in different tissues including glia, wing and eye resulted in multiple phenotype modifications. We subsequently found evidence for physical interaction between UBE3A and MEF2C also in human cells. Systematic pairwise assessment of the Drosophila orthologues of five genes implicated in clinically overlapping, severe NDDs and subsequent confirmation in a human cell line revealed interactions between UBE3A/Ube3a and MEF2C/Mef2, thus contributing to the characterization of the underlying molecular commonalities.<br
Keywords: Genetic interaction; Medical genetics; Molecular medicine; Neurodevelopmental disorders

Genetic Interaction screen for severe neurodevelopmental disorders reveals a functional link between Ube3a and Mef2 in Drosophila melanogaster - Straub, Jonas; Sauerer, Tatjana; Fliedner, Anna; Distel, Laila; Suchy, C.; Ekici, Arif Bülent; Ferrazzi, Fulvia; Gregor, Anne; Zweier, Christiane (52nd Conference of the European-Society-of-Human-Genetics (ESHG), 2019)
CRIS-Team WoS Importer:2019-10-25

Genetic overlap between endometriosis and endometrial cancer: evidence from cross-disease genetic correlation and GWAS meta-analyses - Painter, Jodie N.; O'Mara, Tracy A.; Morris, Andrew P.; Cheng, Timothy H. T.; Gorman, Maggie; Martin, Lynn; Hodson, Shirley; Jones, Angela; Martin, Nicholas G.; Gordon, Scott; Henders, Anjali K.; Attia, John; et al. (Cancer Medicine, 2018)
Epidemiological, biological, and molecular data suggest links between endometriosis and endometrial cancer, with recent epidemiological studies providing evidence for an association between a previous diagnosis of endometriosis and risk of endometrial cancer. We used genetic data as an alternative approach to investigate shared biological etiology of these two diseases. Genetic correlation analysis of summary level statistics from genomewide association studies (GWAS) using LD Score regression revealed moderate but significant genetic correlation (rg = 0.23, P = 9.3 × 10-3 ), and SNP effect concordance analysis provided evidence for significant SNP pleiotropy (P = 6.0 × 10-3 ) and concordance in effect direction (P = 2.0 × 10-3 ) between the two diseases. Cross-disease GWAS meta-analysis highlighted 13 distinct loci associated at P ≤ 10-5 with both endometriosis and endometrial cancer, with one locus (SNP rs2475335) located within PTPRD associated at a genomewide significant level (P = 4.9 × 10-8 , OR = 1.11, 95% CI = 1.07-1.15). PTPRD acts in the STAT3 pathway, which has been implicated in both endometriosis and endometrial cancer. This study demonstrates the value of cross-disease genetic analysis to support epidemiological observations and to identify biological pathways of relevance to multiple diseases.
EVALuna2:34631

Genetic predictors of chemotherapy-related amenorrhea in women with breast cancer - Ruddy, Kathryn J.; Schaid, Daniel J.; Partridge, A. H.; Larson, Nicholas B.; Batzler, Anthony; Häberle, Lothar; Dittrich, Ralf; Widschwendter, P.; Fink, Visnja; Bauer, Emanuel; Schwitulla, Judith; Rübner, Matthias; et al. (Fertility and Sterility, 2019)
Objective: To study how genetics may play a role in determining risk of chemotherapy-related amenorrhea (CRA) in young women with breast cancer. Design: Genome-wide association study. Setting: Not applicable. Patient(s): Premenopausal women ≤45 years of age enrolled in one of these three trials were included if they had at least one menstrual case report form after chemotherapy ended and if they were of European ancestry. Forms during and up to 3 months after receipt of GnRH agonist were excluded. Intervention(s): None. Main Outcome Measure(s): The association of single-nucleotide polymorphisms with post-chemotherapy menstruation adjusted for trial and arm, age, tamoxifen use, and nodal status. Result(s): The median age of the 1,168 women was 41 years (range 19–45). Among these, 457 (39%) never resumed menses after chemotherapy. Older age, tamoxifen use, and node-negative disease were associated with increased risk of CRA. Adjusting for these, rs147451859, in an intron of PPCDC (phosphopantothenoylcysteine decarboxylase), and rs17587029, located 5′ upstream of RPS20P11 (ribosomal protein S20 pseudogene 11), were associated with post-chemotherapy menstruation. Conclusion(s): Genetic variation may contribute to risk of CRA. Better prediction of who will experience CRA may inform reproductive and treatment decision making in young women with cancer.
CRIS-Team Scopus Importer:2019-08-06
Keywords: amenorrhea; Breast neoplasms; drug therapy; toxicity

Genetic predisposition to in situ and invasive lobular carcinoma of the breast - Sawyer, Elinor; Roylance, Rebecca; Petridis, Christos; Brook, Mark N.; Nowinski, Salpie; Papouli, Efterpi; Fletcher, Olivia; Pinder, Sarah; Hanby, Andrew; Kohut, Kelly; Gorman, Patricia; Caneppele, Michele; et al. (PLoS Genetics, 2014)
Invasive lobular breast cancer (ILC) accounts for 10-15% of all invasive breast carcinomas. It is generally ER positive (ER+) and often associated with lobular carcinoma in situ (LCIS). Genome-wide association studies have identified more than 70 common polymorphisms that predispose to breast cancer, but these studies included predominantly ductal (IDC) carcinomas. To identify novel common polymorphisms that predispose to ILC and LCIS, we pooled data from 6,023 cases (5,622 ILC, 401 pure LCIS) and 34,271 controls from 36 studies genotyped using the iCOGS chip. Six novel SNPs most strongly associated with ILC/LCIS in the pooled analysis were genotyped in a further 516 lobular cases (482 ILC, 36 LCIS) and 1,467 controls. These analyses identified a lobular-specific SNP at 7q34 (rs11977670, OR (95%CI) for ILC = 1.13 (1.09-1.18), P = 6.0 × 10(-10); P-het for ILC vs IDC ER+ tumors = 1.8 × 10(-4)). Of the 75 known breast cancer polymorphisms that were genotyped, 56 were associated with ILC and 15 with LCIS at P<0.05. Two SNPs showed significantly stronger associations for ILC than LCIS (rs2981579/10q26/FGFR2, P-het = 0.04 and rs889312/5q11/MAP3K1, P-het = 0.03); and two showed stronger associations for LCIS than ILC (rs6678914/1q32/LGR6, P-het = 0.001 and rs1752911/6q14, P-het = 0.04). In addition, seven of the 75 known loci showed significant differences between ER+ tumors with IDC and ILC histology, three of these showing stronger associations for ILC (rs11249433/1p11, rs2981579/10q26/FGFR2 and rs10995190/10q21/ZNF365) and four associated only with IDC (5p12/rs10941679; rs2588809/14q24/RAD51L1, rs6472903/8q21 and rs1550623/2q31/CDCA7). In conclusion, we have identified one novel lobular breast cancer specific predisposition polymorphism at 7q34, and shown for the first time that common breast cancer polymorphisms predispose to LCIS. We have shown that many of the ER+ breast cancer predisposition loci also predispose to ILC, although there is some heterogeneity between ER+ lobular and ER+ IDC tumors. These data provide evidence for overlapping, but distinct etiological pathways within ER+ breast cancer between morphological subtypes.
EVALuna2:9234

Genetic risk factors for ovarian cancer and their role for endometriosis risk - Burghaus, Stefanie; Fasching, Peter; Haeberle, Lothar; Rübner, Matthias; Buechner, Kathrin; Blum, Simon; Engel, Anne; Ekici, Arif Bülent; Hartmann, Arndt; Hein, Alexander; Beckmann, Matthias; Renner, Stefan (Gynecologic Oncology, 2017)
Several genetic variants have been validated as risk factors for ovarian cancer. Endometriosis has also been described as a risk factor for ovarian cancer. Identifying genetic risk factors that are common to the two diseases might help improve our understanding of the molecular pathogenesis potentially linking the two conditions.In a hospital-based case-control analysis, 12 single nucleotide polymorphisms (SNPs), validated by the Ovarian Cancer Association Consortium (OCAC) and the Collaborative Oncological Gene-environment Study (COGS) project, were genotyped using TaqMan® OpenArray(TM) analysis. The cases consisted of patients with endometriosis, and the controls were healthy individuals without endometriosis. A total of 385 cases and 484 controls were analyzed. Odds ratios and P values were obtained using simple logistic regression models, as well as from multiple logistic regression models with adjustment for clinical predictors.rs11651755 in HNF1B was found to be associated with endometriosis in this case-control study. The OR was 0.66 (95% CI, 0.51 to 0.84) and the P value after correction for multiple testing was 0.01. None of the other genotypes was associated with a risk for endometriosis.As rs11651755 in HNF1B modified both the ovarian cancer risk and also the risk for endometriosis, HNF1B may be causally involved in the pathogenetic pathway leading from endometriosis to ovarian cancer.
EVALuna2:6871

Genetic Risk Score Mendelian Randomization Shows that Obesity Measured as Body Mass Index, but not Waist:Hip Ratio, Is Causal for Endometrial Cancer - Painter, Jodie N.; O'Mara, Tracy A.; Marquart, Louise; Webb, Penelope M.; Attia, John; Medland, Sarah E.; Cheng, Timothy; Dennis, Joe; Holliday, Elizabeth G.; Mcevoy, Mark; Scott, Rodney J.; Ahmed, Shahana; et al. (Cancer Epidemiology Biomarkers & Prevention, 2016)
The strongest known risk factor for endometrial cancer is obesity. To determine whether SNPs associated with increased body mass index (BMI) or waist-hip ratio (WHR) are associated with endometrial cancer risk, independent of measured BMI, we investigated relationships between 77 BMI and 47 WHR SNPs and endometrial cancer in 6,609 cases and 37,926 country-matched controls.Logistic regression analysis and fixed effects meta-analysis were used to test for associations between endometrial cancer risk and (i) individual BMI or WHR SNPs, (ii) a combined weighted genetic risk score (wGRS) for BMI or WHR. Causality of BMI for endometrial cancer was assessed using Mendelian randomization, with BMIwGRS as instrumental variable.The BMIwGRS was significantly associated with endometrial cancer risk (P = 3.4 × 10(-17)). Scaling the effect of the BMIwGRS on endometrial cancer risk by its effect on BMI, the endometrial cancer OR per 5 kg/m(2) of genetically predicted BMI was 2.06 [95% confidence interval (CI), 1.89-2.21], larger than the observed effect of BMI on endometrial cancer risk (OR = 1.55; 95% CI, 1.44-1.68, per 5 kg/m(2)). The association attenuated but remained significant after adjusting for BMI (OR = 1.22; 95% CI, 1.10-1.39; P = 5.3 × 10(-4)). There was evidence of directional pleiotropy (P = 1.5 × 10(-4)). BMI SNP rs2075650 was associated with endometrial cancer at study-wide significance (P < 4.0 × 10(-4)), independent of BMI. Endometrial cancer was not significantly associated with individual WHR SNPs or the WHRwGRS.BMI, but not WHR, is causally associated with endometrial cancer risk, with evidence that some BMI-associated SNPs alter endometrial cancer risk via mechanisms other than measurable BMI.The causal association between BMI SNPs and endometrial cancer has possible implications for endometrial cancer risk modeling. Cancer Epidemiol Biomarkers Prev; 25(11); 1503-10. ©2016 AACR.
EVALuna2:9342

Genetic risk variants for membranous nephropathy: extension of and association with other chronic kidney disease aetiologies - Sekula, Peggy; Li, Yong; Stanescu, Horia C.; Wuttke, Matthias; Ekici, Arif Bülent; Bockenhauer, Detlef; Walz, Gerd; Powis, Stephen H.; Kielstein, Jan T.; Brenchley, Paul; Eckardt, Kai-Uwe; Kronenberg, Florian; et al. (Nephrology Dialysis Transplantation, 2016)
Membranous nephropathy (MN) is a common cause of nephrotic syndrome in adults. Previous genome-wide association studies (GWAS) of 300 000 genotyped variants identified MN-associated loci at HLA-DQA1 and PLA2R1.We used a combined approach of genotype imputation, GWAS, human leucocyte antigen (HLA) imputation and extension to other aetiologies of chronic kidney disease (CKD) to investigate genetic MN risk variants more comprehensively. GWAS using 9 million high-quality imputed genotypes and classical HLA alleles were conducted for 323 MN European-ancestry cases and 345 controls. Additionally, 4960 patients with different CKD aetiologies in the German Chronic Kidney Disease (GCKD) study were genotyped for risk variants at HLA-DQA1 and PLA2R1.In GWAS, lead variants in known loci [rs9272729, HLA-DQA1, odds ratio (OR) = 7.3 per risk allele, P = 5.9 × 10(-27) and rs17830558, PLA2R1, OR = 2.2, P = 1.9 × 10(-8)] were significantly associated with MN. No novel signals emerged in GWAS of X-chromosomal variants or in sex-specific analyses. Classical HLA alleles (DRB1*0301-DQA1*0501-DQB1*0201 haplotype) were associated with MN but provided little additional information beyond rs9272729. Associations were replicated in 137 GCKD patients with MN (HLA-DQA1: P = 6.4 × 10(-24); PLA2R1: P = 5.0 × 10(-4)). MN risk increased steeply for patients with high-risk genotype combinations (OR > 79). While genetic variation in PLA2R1 exclusively associated with MN across 19 CKD aetiologies, the HLA-DQA1 risk allele was also associated with lupus nephritis (P = 2.8 × 10(-6)), type 1 diabetic nephropathy (P = 6.9 × 10(-5)) and focal segmental glomerulosclerosis (P = 5.1 × 10(-5)), but not with immunoglobulin A nephropathy.PLA2R1 and HLA-DQA1 are the predominant risk loci for MN detected by GWAS. While HLA-DQA1 risk variants show an association with other CKD aetiologies, PLA2R1 variants are specific to MN.
EVALuna2:160

Genetic screening confirms heterozygous mutations in ACAN as a major cause of idiopathic short stature - Hauer, Nadine; Sticht, Heinrich; Boppudi, Sangamitra; Büttner, Christian; Kraus, Cornelia; Trautmann, Udo; Zenker, Martin; Zweier, Christiane; Wiesener, Antje; Abou Jamra, Rami; Wieczorek, Dagmar; Kelkel, Jaqueline; et al. (Scientific Reports, 2017)
Short stature is a common pediatric disorder affecting 3% of the population. However, the clinical variability and genetic heterogeneity prevents the identification of the underlying cause in about 80% of the patients. Recently, heterozygous mutations in the ACAN gene coding for the proteoglycan aggrecan, a main component of the cartilage matrix, were associated with idiopathic short stature. To ascertain the prevalence of ACAN mutations and broaden the phenotypic spectrum in patients with idiopathic short stature we performed sequence analyses in 428 families. We identified heterozygous nonsense mutations in four and potentially disease-causing missense variants in two families (1.4%). These patients presented with a mean of -3.2 SDS and some suggestive clinical characteristics. The results suggest heterozygous mutations in ACAN as a common cause of isolated as well as inherited idiopathic short stature.
EVALuna2:9379

Genetics of serum urate concentrations and gout in a high-risk population, patients with chronic kidney disease - Jing, Jiaojiao; Ekici, Arif Bülent; Sitter, Thomas; Schaeffnert, Elke; Li, Yong; Kronenberg, Florian; Koettgen, Anna; Schultheiss, Ulla T.; Eckardt, Kai-Uwe (Scientific Reports, 2018)
We evaluated genetics of hyperuricemia and gout, their interaction with kidney function and medication intake in chronic kidney disease (CKD) patients. Genome-wide association studies (GWAS) of urate and gout were performed in 4941 CKD patients in the German Chronic Kidney Disease (GCKD) study. Effect estimates of 26 known urate-associated population-based single nucleotide polymorphisms (SNPs) were examined. Interactions of urate-associated variants with urate-altering medications and clinical characteristics of gout were evaluated. Genome-wide significant associations with serum urate and gout were identified for known loci at SLC2A9 and ABCG2, but not for novel loci. Effects of the 26 known SNPs were of similar magnitude in CKD patients compared to population-based individuals, except for SNPs at ABCG2 that showed greater effects in CKD. Gene-medication interactions were not significant when accounting for multiple testing. Associations with gout in specific joints were significant for SLC2A9 rs12498742 in wrists and midfoot joints. Known genetic variants in SLC2A9 and ABCG2 were associated with urate and gout in a CKD cohort, with effect sizes for ABCG2 significantly greater in CKD compared to the general population. CKD patients are at high risk of gout due to reduced kidney function, diuretics intake and genetic predisposition, making treatment to target challenging.
EVALuna2:34616

Genetic studies of paired metabolomes reveal enzymatic and transport processes at the interface of plasma and urine - Schlosser, Pascal; Scherer, Nora; Grundner-Culemann, Franziska; Monteiro-Martins, Sara; Haug, Stefan; Steinbrenner, Inga; Uluvar, Burulça; Wuttke, Matthias; Cheng, Yurong; Ekici, Arif Bülent; Gyimesi, Gergely; Karoly, Edward D.; et al. (Nature Genetics, 2023)
The kidneys operate at the interface of plasma and urine by clearing molecular waste products while retaining valuable solutes. Genetic studies of paired plasma and urine metabolomes may identify underlying processes. We conducted genome-wide studies of 1,916 plasma and urine metabolites and detected 1,299 significant associations. Associations with 40% of implicated metabolites would have been missed by studying plasma alone. We detected urine-specific findings that provide information about metabolite reabsorption in the kidney, such as aquaporin (AQP)-7-mediated glycerol transport, and different metabolomic footprints of kidney-expressed proteins in plasma and urine that are consistent with their localization and function, including the transporters NaDC3 (SLC13A3) and ASBT (SLC10A2). Shared genetic determinants of 7,073 metabolite–disease combinations represent a resource to better understand metabolic diseases and revealed connections of dipeptidase 1 with circulating digestive enzymes and with hypertension. Extending genetic studies of the metabolome beyond plasma yields unique insights into processes at the interface of body compartments.
CRIS-Team Scopus Importer:2023-06-16

Genetic studies of urinary metabolites illuminate mechanisms of detoxification and excretion in humans - Schlosser, Pascal; Li, Yong; Sekula, Peggy; Raffler, Johannes; Grundner-Culemann, Franziska; Pietzner, Maik; Cheng, Yurong; Wuttke, Matthias; Steinbrenner, Inga; Schultheiss, Ulla T.; Kotsis, Fruzsina; Kacprowski, Tim; et al. (Nature Genetics, 2020)
The kidneys integrate information from continuous systemic processes related to the absorption, distribution, metabolism and excretion (ADME) of metabolites. To identify underlying molecular mechanisms, we performed genome-wide association studies of the urinary concentrations of 1,172 metabolites among 1,627 patients with reduced kidney function. The 240 unique metabolite–locus associations (metabolite quantitative trait loci, mQTLs) that were identified and replicated highlight novel candidate substrates for transport proteins. The identified genes are enriched in ADME-relevant tissues and cell types, and they reveal novel candidates for biotransformation and detoxification reactions. Fine mapping of mQTLs and integration with single-cell gene expression permitted the prioritization of causal genes, functional variants and target cell types. The combination of mQTLs with genetic and health information from 450,000 UK Biobank participants illuminated metabolic mediators, and hence, novel urinary biomarkers of disease risk. This comprehensive resource of genetic targets and their substrates is informative for ADME processes in humans and is relevant to basic science, clinical medicine and pharmaceutical research.
CRIS-Team Scopus Importer:2020-02-04

Genetic variants in the genes of the sex steroid hormone metabolism and depressive symptoms during and after pregnancy - Schneider, Michael; Pretscher, Jutta; Goecke, Tamme; Häberle, Lothar; Engel, Anne; Kornhuber, Johannes; Eichler, Anna; Ekici, Arif Bülent; Beckmann, Matthias; Fasching, Peter; Schwenke, Eva (Archives of Gynecology and Obstetrics, 2022)
Purpose: The aim of this study was to conduct an association analysis of depressive symptoms and polymorphisms in the ESR1, PGR, CYP19A1, and COMT genes in pregnant and postpartum women. Methods: The Franconian Maternal Health Evaluation Study (FRAMES) recruited healthy pregnant women prospectively for assessment of maternal and fetal health. The German version of the 10-item Edinburgh Postnatal Depression Scale (EPDS) was completed at three time points in this prospective cohort study. Visit 1 was at study entry in the third trimester of pregnancy, visit 2 was shortly after birth, and visit 3 was 6–8 months after birth. Germline DNA and depression measurements from 361 pregnant women were available for analysis. Six single nucleotide polymorphisms (SNPs) in the above-mentioned genes were genotyped. After reconstruction of haplotypes for PGR (rs1042838 and rs10895068) and CYP19A1 (rs10046 and rs4646), a multifactorial linear mixed model was applied to the data to describe the association between haplotypes and depression values. The single SNPs for ESR1 (rs488133) and COMT (rs4680) were analyzed separately using linear mixed models analogously. Results: The mean antepartum EPDS measurement was 5.1, the mean postpartal measurement after 48–72 h was 3.5, and the mean value 6–8 months postpartum was 4.2. The SNPs in PGR were reconstructed into three haplotypes. The most common haplotype was GG, with 63.43% of patients carrying two copies and 33.52% carrying one copy. For haplotype GA, the group of carriers of two copies (0.28%) was combined with the carriers of one copy (9.70%). Haplotype reconstruction using CYP19A1 SNPs resulted in three haplotypes. The most common haplotype was TC, with 25.48% of patients carrying two copies and 51.52% one copy. None of the haplotype blocks and neither of the two single SNPs showed any significant associations with EPDS values. Conclusions: The candidate haplotypes analyzed in PGR and CYP19A1 and single SNPs in ESR1 and COMT did not show any association with depression scores as assessed by EPDS in this cohort of healthy unselected pregnant women.
CRIS-Team Scopus Importer:2022-06-17
Keywords: COMT; CYP19A1; Depression; EPDS; ESR1; PGR; Single nucleotide polymorphisms

Genetic variants in the glucocorticoid pathway genes and birth weight - Schneider, Michael; Hübner, Theresa; Pretscher, Jutta; Goecke, Tamme W.; Schwitulla, Judith; Häberle, Lothar; Kornhuber, Johannes; Ekici, Arif Bülent; Beckmann, Matthias; Fasching, Peter; Schwenke, Eva (Archives of Gynecology and Obstetrics, 2020)
Purpose: The aim of this study was to examine associations between single nucleotide polymorphisms (SNPs) that tag genetic variation in the glucocorticoid pathways (particularly in maternal genes FKBP5, NR3C1, and CRHR1) and birth weight. Methods: The Franconian Maternal Health Evaluation Study (FRAMES) recruited healthy pregnant women prospectively for the assessment of maternal and fetal health. Germline DNA was collected from 375 pregnant women. Nine SNPs in the above-mentioned genes were genotyped. After reconstruction of haplotypes for each gene, a linear regression model was applied to the data to describe the association between haplotypes and birth weight. Results: Female sex in the newborn (compared to male) was associated with lower birth weight, whereas a later week of gestation, higher body mass index pre-pregnancy, and higher parity were associated with higher birth weight. No association with birthweight was shown for the haplotypes of the selected SNPs. Conclusions: In this cohort of healthy unselected pregnant women, the analyzed candidate haplotypes in FKBP5, NR3C1, and CRHR1 did not show any association with birth weight. This might be in line with several other studies that have found no influence of fetal polymorphisms in the glucocorticoid receptor gene or triggers of the maternal HPA axis such as stress and psychosocial problems on birth weight. However, the small sample size in this study and the lack of consideration of individual risk factors and levels of stress in this cohort needs to be taken into account when interpreting the results.
CRIS-Team Scopus Importer:2020-09-11
Keywords: Birth weight; CRHR1; FKBP5; NR3C1; Single nucleotide polymorphisms

Genetic variants in VEGF pathway genes in neoadjuvant breast cancer patients receiving bevacizumab: Results from the randomized phase III GeparQuinto study - Hein, Alexander; Lambrechts, Diether; Von Minckwitz, Gunter; Haeberle, Lothar; Eidtmann, Holger; Tesch, Hans; Untch, Michael; Hilfrich, Joern; Schem, Christian; Rezai, Mahdi; Gerber, Bernd; Costa, Serban Dan; et al. (International Journal of Cancer, 2015)
Studies assessing the effect of bevacizumab (BEV) on breast cancer (BC) outcome have shown different effects on progression-free and overall survival, suggesting that a subgroup of patients may benefit from this treatment. Unfortunately, no biomarkers exist to identify these patients. Here, we investigate whether single nucleotide polymorphisms (SNPs) in VEGF pathway genes correlate with pathological complete response (pCR) in the neoadjuvant GeparQuinto trial. HER2-negative patients were randomized into treatment arms receiving either BEV combined with standard chemotherapy or chemotherapy alone. In a pre-planned biomarker study, DNA was collected from 729 and 724 patients, respectively from both treatment arms, and genotyped for 125 SNPs. Logistic regression assessed interaction between individual SNPs and both treatment arms to predict pCR. Five SNPs may be associated with a better response to BEV, but none of them remained significant after correction for multiple testing. The two SNPs most strongly associated, rs833058 and rs699947, were located upstream of the VEGF-A promoter. Odds ratios for the homozygous common, heterozygous and homozygous rare rs833058 genotypes were 2.36 (95% CI, 1.49-3.75), 1.20 (95% CI, 0.88-1.64) and 0.61 (95% CI, 0.34-1.12). Notably, some SNPs in VEGF-A exhibited a more pronounced effect in the triple-negative subgroup. Several SNPs in VEGF-A may be associated with improved pCR when receiving BEV in the neoadjuvant setting. Although none of the observed effects survived correction for multiple testing, our observations are consistent with previous studies on BEV efficacy in BC. Further research is warranted to clarify the predictive value of these markers.
EVALuna2:9285

Genetic variation at CYP3A is associated with age at menarche and breast cancer risk: a case-control study - Johnson, Nichola; Dudbridge, Frank; Orr, Nick; Gibson, Lorna; Jones, Michael E.; Schoemaker, Minouk J.; Folkerd, Elizabeth J.; Haynes, Ben P.; Hopper, John L.; Southey, Melissa C.; Dite, Gillian S.; Apicella, Carmel; et al. (Breast Cancer Research, 2014)
We have previously shown that a tag single nucleotide polymorphism (rs10235235), which maps to the CYP3A locus (7q22.1), was associated with a reduction in premenopausal urinary estrone glucuronide levels and a modest reduction in risk of breast cancer in women age <=50 years.We further investigated the association of rs10235235 with breast cancer risk in a large case control study of 47,346 cases and 47,570 controls from 52 studies participating in the Breast Cancer Association Consortium. Genotyping of rs10235235 was conducted using a custom Illumina Infinium array. Stratified analyses were conducted to determine whether this association was modified by age at diagnosis, ethnicity, age at menarche or tumor characteristics.We confirmed the association of rs10235235 with breast cancer risk for women of European ancestry but found no evidence that this association differed with age at diagnosis. Heterozygote and homozygote odds ratios (ORs) were OR = 0.98 (95% CI 0.94, 1.01; P = 0.2) and OR = 0.80 (95% CI 0.69, 0.93; P = 0.004), respectively (P(trend) = 0.02). There was no evidence of effect modification by tumor characteristics. rs10235235 was, however, associated with age at menarche in controls (P(trend) = 0.005) but not cases (P(trend) = 0.97). Consequently the association between rs10235235 and breast cancer risk differed according to age at menarche (P(het) = 0.02); the rare allele of rs10235235 was associated with a reduction in breast cancer risk for women who had their menarche age >=15 years (OR(het) = 0.84, 95% CI 0.75, 0.94; OR(hom) = 0.81, 95% CI 0.51, 1.30; P(trend) = 0.002) but not for those who had their menarche age <=11 years (OR(het) = 1.06, 95% CI 0.95, 1.19, OR(hom) = 1.07, 95% CI 0.67, 1.72; P(trend) = 0.29).To our knowledge rs10235235 is the first single nucleotide polymorphism to be associated with both breast cancer risk and age at menarche consistent with the well-documented association between later age at menarche and a reduction in breast cancer risk. These associations are likely mediated via an effect on circulating hormone levels.
EVALuna2:9240

Genetic variation in mitotic regulatory pathway genes is associated with breast tumor grade - Purrington, Kristen S.; Slettedahl, Seth; Bolla, Manjeet K.; Michailidou, Kyriaki; Czene, Kamila; Nevanlinna, Heli; Bojesen, Stig E.; Andrulis, Irene L.; Cox, Angela; Hall, Per; Carpenter, Jane; Yannoukakos, Drakoulis; et al. (Human Molecular Genetics, 2014)
Mitotic index is an important component of histologic grade and has an etiologic role in breast tumorigenesis. Several small candidate gene studies have reported associations between variation in mitotic genes and breast cancer risk. We measured associations between 2156 single nucleotide polymorphisms (SNPs) from 194 mitotic genes and breast cancer risk, overall and by histologic grade, in the Breast Cancer Association Consortium (BCAC) iCOGS study (n = 39 067 cases; n = 42 106 controls). SNPs in TACC2 [rs17550038: odds ratio (OR) = 1.24, 95% confidence interval (CI) 1.16-1.33, P = 4.2 × 10(-10)) and EIF3H (rs799890: OR = 1.07, 95% CI 1.04-1.11, P = 8.7 × 10(-6)) were significantly associated with risk of low-grade breast cancer. The TACC2 signal was retained (rs17550038: OR = 1.15, 95% CI 1.07-1.23, P = 7.9 × 10(-5)) after adjustment for breast cancer risk SNPs in the nearby FGFR2 gene, suggesting that TACC2 is a novel, independent genome-wide significant genetic risk locus for low-grade breast cancer. While no SNPs were individually associated with high-grade disease, a pathway-level gene set analysis showed that variation across the 194 mitotic genes was associated with high-grade breast cancer risk (P = 2.1 × 10(-3)). These observations will provide insight into the contribution of mitotic defects to histological grade and the etiology of breast cancer.
EVALuna2:6629

Genetic variations in estrogen and progesterone pathway genes in preeclampsia patients and controls in Bavaria - Pretscher, Jutta; Rübner, Matthias; Ekici, Arif Bülent; Rödl, Melanie; Hübner, Hanna; Schwitulla, Judith; Titzmann, Adriana; Hartwig, Charlotte; Beckmann, Matthias; Fasching, Peter; Schneider, Michael; Schwenke, Eva (Archives of Gynecology and Obstetrics, 2020)
Purpose: Hypertensive pregnancy disorders and preeclampsia are major causes of maternal and fetal morbidity and mortality worldwide. Many different organs are involved in the diseases’ clinical phenotype. The underlying mechanism is still unknown, with a possible genetic component. This case–control study investigated effects on the risk of preeclampsia of genetic variations (single nucleotide polymorphisms, SNPs) in the estrogen and progesterone pathway genes. Methods: The study included 167 patients with preeclampsia and 115 healthy controls from the “Franconian Maternal Health Evaluation Studies” (FRAMES). All patients completed an epidemiological questionnaire, data from which were correlated with prospective data on pregnancy and labor. DNA was isolated from blood samples and genotyping was done by PCR. Variants in the aromatase gene CYP19A1 (rs10046, rs4646), progesterone receptor gene (rs1042838, rs10895068), and estrogen receptor-α gene (rs488133) were examined, and the genotype distribution in the two groups was analyzed statistically. Results: A significant difference in the distribution frequency of genotypes between preeclampsia patients and controls was identified in one of the five SNPs. For rs10895068 in the progesterone receptor gene, genotype G/A was significantly more frequent among cases than controls (P = 0.023). No significant differences between the two cohorts were found in the other SNPs. Conclusions: This study showed a significant association between only one SNP in the progesterone receptor and preeclampsia. Other studies have also noted genetic aspects of preeclampsia. The underlying mechanism and causal relationship are not yet known, and further research is needed to explain the extent of genetic variations and the causal relationship in preeclampsia.
CRIS-Team Scopus Importer:2020-10-09
Keywords: Genetic marker; Preeclampsia; Pregnancy; Single nucleotide polymorphism (SNP)

Genome-wide analyses identify a role for SLC17A4 and AADAT in thyroid hormone regulation - Teumer, Alexander; Chaker, Layal; Groeneweg, Stefan; Li, Yong; Di Munno, Celia; Barbieri, Caterina; Schultheiss, Ulla T.; Traglia, Michela; Ahluwalia, Tarunveer S.; Akiyama, Masato; Appel, Emil Vincent R.; Arking, Dan E.; et al. (Nature Communications, 2018)
Thyroid dysfunction is an important public health problem, which affects 10% of the general population and increases the risk of cardiovascular morbidity and mortality. Many aspects of thyroid hormone regulation have only partly been elucidated, including its transport, metabolism, and genetic determinants. Here we report a large meta-analysis of genome-wide association studies for thyroid function and dysfunction, testing 8 million genetic variants in up to 72,167 individuals. One-hundred-and-nine independent genetic variants are associated with these traits. A genetic risk score, calculated to assess their combined effects on clinical end points, shows significant associations with increased risk of both overt (Graves' disease) and subclinical thyroid disease, as well as clinical complications. By functional follow-up on selected signals, we identify a novel thyroid hormone transporter (SLC17A4) and a metabolizing enzyme (AADAT). Together, these results provide new knowledge about thyroid hormone physiology and disease, opening new possibilities for therapeutic targets.
EVALuna2:34824

Genome-wide Analysis Identifies Novel Loci Associated with Ovarian Cancer Outcomes: Findings from the Ovarian Cancer Association Consortium - Johnatty, Sharon E.; Tyrer, Jonathan P.; Kar, Siddhartha; Beesley, Jonathan; Lu, Yi; Gao, Bo; Fasching, Peter; Hein, Alexander; Ekici, Arif Bülent; Beckmann, Matthias; Lambrechts, Diether; Van Nieuwenhuysen, Els; et al. (Clinical Cancer Research, 2015)
Chemotherapy resistance remains a major challenge in the treatment of ovarian cancer. We hypothesize that germline polymorphisms might be associated with clinical outcome.We analyzed approximately 2.8 million genotyped and imputed SNPs from the iCOGS experiment for progression-free survival (PFS) and overall survival (OS) in 2,901 European epithelial ovarian cancer (EOC) patients who underwent first-line treatment of cytoreductive surgery and chemotherapy regardless of regimen, and in a subset of 1,098 patients treated with >=4 cycles of paclitaxel and carboplatin at standard doses. We evaluated the top SNPs in 4,434 EOC patients, including patients from The Cancer Genome Atlas. In addition, we conducted pathway analysis of all intragenic SNPs and tested their association with PFS and OS using gene set enrichment analysis.Five SNPs were significantly associated (P <= 1.0 × 10(-5)) with poorer outcomes in at least one of the four analyses, three of which, rs4910232 (11p15.3), rs2549714 (16q23), and rs6674079 (1q22), were located in long noncoding RNAs (lncRNAs) RP11-179A10.1, RP11-314O13.1, and RP11-284F21.8, respectively (P <= 7.1 × 10(-6)). ENCODE ChIP-seq data at 1q22 for normal ovary show evidence of histone modification around RP11-284F21.8, and rs6674079 is perfectly correlated with another SNP within the super-enhancer MEF2D, expression levels of which were reportedly associated with prognosis in another solid tumor. YAP1- and WWTR1 (TAZ)-stimulated gene expression and high-density lipoprotein (HDL)-mediated lipid transport pathways were associated with PFS and OS, respectively, in the cohort who had standard chemotherapy (pGSEA <=6 × 10(-3)).We have identified SNPs in three lncRNAs that might be important targets for novel EOC therapies. Clin Cancer Res; 21(23); 5264-76. ©2015 AACR.
EVALuna2:9298

Genome-wide association analyses define pathogenic signaling pathways and prioritize drug targets for IgA nephropathy - Kiryluk, Krzysztof; Sanchez-Rodriguez, Elena; Zhou, Xu Jie; Zanoni, Francesca; Liu, Lili; Mladkova, Nikol; Khan, Atlas; Marasa, Maddalena; Zhang, Jun Y.; Balderes, Olivia; Sanna-Cherchi, Simone; Bomback, Andrew S.; et al. (Nature Genetics, 2023)
IgA nephropathy (IgAN) is a progressive form of kidney disease defined by glomerular deposition of IgA. Here we performed a genome-wide association study of 10,146 kidney-biopsy-diagnosed IgAN cases and 28,751 controls across 17 international cohorts. We defined 30 genome-wide significant risk loci explaining 11% of disease risk. A total of 16 loci were new, including TNFSF4/TNFSF18, REL, CD28, PF4V1, LY86, LYN, ANXA3, TNFSF8/TNFSF15, REEP3, ZMIZ1, OVOL1/RELA, ETS1, IGH, IRF8, TNFRSF13B and FCAR. The risk loci were enriched in gene orthologs causing abnormal IgA levels when genetically manipulated in mice. We also observed a positive genetic correlation between IgAN and serum IgA levels. High polygenic score for IgAN was associated with earlier onset of kidney failure. In a comprehensive functional annotation analysis of candidate causal genes, we observed convergence of biological candidates on a common set of inflammatory signaling pathways and cytokine ligand–receptor pairs, prioritizing potential new drug targets.
CRIS-Team Scopus Importer:2023-06-30

Genome-wide association analysis identifies three new breast cancer susceptibility loci - Ghoussaini, Maya; Fletcher, Olivia; Michailidou, Kyriaki; Turnbull, Clare; Schmidt, Marjanka K.; Dicks, Ed; Dennis, Joe; Wang, Qin; Humphreys, Manjeet K.; Luccarini, Craig; Baynes, Caroline; Conroy, Don; et al. (Nature Genetics, 2012)
Breast cancer is the most common cancer among women. To date, 22 common breast cancer susceptibility loci have been identified accounting for 8% of the heritability of the disease. We attempted to replicate 72 promising associations from two independent genome-wide association studies (GWAS) in 70,000 cases and 68,000 controls from 41 case-control studies and 9 breast cancer GWAS. We identified three new breast cancer risk loci at 12p11 (rs10771399; P = 2.7 × 10(-35)), 12q24 (rs1292011; P = 4.3 × 10(-19)) and 21q21 (rs2823093; P = 1.1 × 10(-12)). rs10771399 was associated with similar relative risks for both estrogen receptor (ER)-negative and ER-positive breast cancer, whereas the other two loci were associated only with ER-positive disease. Two of the loci lie in regions that contain strong plausible candidate genes: PTHLH (12p11) has a crucial role in mammary gland development and the establishment of bone metastasis in breast cancer, and NRIP1 (21q21) encodes an ER cofactor and has a role in the regulation of breast cancer cell growth.
EVALuna2:9145

Genome-wide association and targeted analysis of copy number variants with psoriatic arthritis in German patients - Uebe, Steffen; Ehrlicher, Maria; Ekici, Arif Bülent; Behrens, Frank; Boehm, Beate; Homuth, Georg; Schurmann, Claudia; Voelker, Uwe; Juenger, Michael; Nauck, Matthias; Voelzke, Henry; Traupe, Heiko; et al. (Bmc Medical Genetics, 2017)
Psoriatic Arthritis (PsA) is a chronic inflammatory disease of the joints. PsA is etiologically complex, and 11 susceptibility loci have been identified so far. Most of these overlap with loci associated with psoriasis vulgaris (PsV), the most common psoriatic skin manifestation which is also frequently seen in PsA patients. In addition, two copy number variants (CNVs) are associated with PsV, one of which, located within the LCE3 gene cluster, is also associated with PsA. Finally, an intergenic deletion has been reported as a PsA-specific CNV.We performed a genome-wide association study (GWAS) of CNVs in PsA and assessed the contribution to disease risk by CNVs at known psoriasis susceptibility loci.After stringent quality assessment and validation of CNVs of the GWAS with an alternative quantitative method, two significantly associated CNVs remained, one near UXS1, the other one at the TRB locus. However, MLPA analysis did not confirm the CN state in 1/3 of individuals, and an analysis of an independent case-control-study failed to confirm the initial associations. Furthermore, detailed PCR-based analysis of the sequence at TRB revealed the existence of a more complex genomic sequence most accurately represented by freeze hg18 which accordingly failed to confirm the hg19 sequence. Only rare CNVs were detected at psoriasis susceptibility loci. At three of 12 susceptibility loci with CNVs (CSMD1, IL12B, RYR2), CN variability was confirmed independently by MLPA. Overall, the rate of CNV confirmation by MLPA was strongly dependent upon CNV type, CNV size and the number of array markers involved in a CNV.Although we identified PsA associations at several loci and confirmed that the common CNVs at these sites were real, 1/3 of the common CNV states could not be reproduced. Furthermore, replication analysis failed to confirm the original association. Furthermore, SNP array-based analyses of CNVs were found to be more reliable for deletions than duplications, independent of the respective CNV allele frequency. CNVs are thus good candidate disease variants, while the methods to detect them should be applied cautiously and reproduced by an independent method.
EVALuna2:9358

Genome-Wide Association Studies of Metabolites in Patients with CKD Identify Multiple Loci and Illuminate Tubular Transport Mechanisms - Li, Yong; Sekula, Peggy; Wuttke, Matthias; Wahrheit, Judith; Hausknecht, Birgit; Schultheiss, Ulla T.; Gronwald, Wolfram; Schlosser, Pascal; Tucci, Sara; Ekici, Arif Bülent; Spiekerkoetter, Ute; Kronenberg, Florian; et al. (Journal of the American Society of Nephrology, 2018)
Background The kidneys have a central role in the generation, turnover, transport, and excretion of metabolites, and these functions can be altered in CKD. Genetic studies of metabolite concentrations can identify proteins performing these functions.Methods We conducted genome-wide association studies and aggregate rare variant tests of the concentrations of 139 serum metabolites and 41 urine metabolites, as well as their pairwise ratios and fractional excretions in up to 1168 patients with CKD.Results After correction for multiple testing, genome-wide significant associations were detected for 25 serum metabolites, two urine metabolites, and 259 serum and 14 urinary metabolite ratios. These included associations already known from population-based studies. Additional findings included an association for the uremic toxin putrescine and variants upstream of an enzyme catalyzing the oxidative deamination of polyamines (AOC1, P-min=2.4×10-12), a relatively high carrier frequency (2%) for rare deleterious missense variants in ACADM that are collectively associated with serum ratios of medium-chain acylcarnitines (P-burden=6.6×10-16), and associations of a common variant in SLC7A9 with several ratios of lysine to neutral amino acids in urine, including the lysine/glutamine ratio (P=2.2×10-23). The associations of this SLC7A9 variant with ratios of lysine to specific neutral amino acids were much stronger than the association with lysine concentration alone. This finding is consistent with SLC7A9 functioning as an exchanger of urinary cationic amino acids against specific intracellular neutral amino acids at the apical membrane of proximal tubular cells.Conclusions Metabolomic indices of specific kidney functions in genetic studies may provide insight into human renal physiology.
EVALuna2:34530

Genome-wide association study identifies 25 known breast cancer susceptibility loci as risk factors for triple-negative breast cancer - Purrington, Kristen S.; Slager, Susan; Eccles, Diana; Yannoukakos, Drakoulis; Fasching, Peter A.; Miron, Penelope; Carpenter, Jane; Chang-Claude, Jenny; Martin, Nicholas G.; Montgomery, Grant W.; Kristensen, Vessela; Anton-Culver, Hoda; et al. (Carcinogenesis, 2014)
Triple-negative (TN) breast cancer is an aggressive subtype of breast cancer associated with a unique set of epidemiologic and genetic risk factors. We conducted a two-stage genome-wide association study of TN breast cancer (stage 1: 1529 TN cases, 3399 controls; stage 2: 2148 cases, 1309 controls) to identify loci that influence TN breast cancer risk. Variants in the 19p13.1 and PTHLH loci showed genome-wide significant associations (P < 5 × 10(-) (8)) in stage 1 and 2 combined. Results also suggested a substantial enrichment of significantly associated variants among the single nucleotide polymorphisms (SNPs) analyzed in stage 2. Variants from 25 of 74 known breast cancer susceptibility loci were also associated with risk of TN breast cancer (P < 0.05). Associations with TN breast cancer were confirmed for 10 loci (LGR6, MDM4, CASP8, 2q35, 2p24.1, TERT-rs10069690, ESR1, TOX3, 19p13.1, RALY), and we identified associations with TN breast cancer for 15 additional breast cancer loci (P < 0.05: PEX14, 2q24.1, 2q31.1, ADAM29, EBF1, TCF7L2, 11q13.1, 11q24.3, 12p13.1, PTHLH, NTN4, 12q24, BRCA2, RAD51L1-rs2588809, MKL1). Further, two SNPs independent of previously reported signals in ESR1 [rs12525163 odds ratio (OR) = 1.15, P = 4.9 × 10(-) (4)] and 19p13.1 (rs1864112 OR = 0.84, P = 1.8 × 10(-) (9)) were associated with TN breast cancer. A polygenic risk score (PRS) for TN breast cancer based on known breast cancer risk variants showed a 4-fold difference in risk between the highest and lowest PRS quintiles (OR = 4.03, 95% confidence interval 3.46-4.70, P = 4.8 × 10(-) (69)). This translates to an absolute risk for TN breast cancer ranging from 0.8% to 3.4%, suggesting that genetic variation may be used for TN breast cancer risk prediction.
EVALuna2:6530

Genome-wide association study identifies a common variant associated with risk of endometrial cancer - Spurdle, Amanda B.; Thompson, Deborah J.; Ahmed, Shahana; Ferguson, Kaltin; Healey, Catherine S.; O'Mara, Tracy; Walker, Logan C.; Montgomery, Stephen B.; Dermitzakis, Emmanouil T.; Fahey, Paul; Montgomery, Grant W.; Webb, Penelope M.; et al. (Nature Genetics, 2011)
Endometrial cancer is the most common malignancy of the female genital tract in developed countries. To identify genetic variants associated with endometrial cancer risk, we performed a genome-wide association study involving 1,265 individuals with endometrial cancer (cases) from Australia and the UK and 5,190 controls from the Wellcome Trust Case Control Consortium. We compared genotype frequencies in cases and controls for 519,655 SNPs. Forty seven SNPs that showed evidence of association with endometrial cancer in stage 1 were genotyped in 3,957 additional cases and 6,886 controls. We identified an endometrial cancer susceptibility locus close to HNF1B at 17q12 (rs4430796, P = 7.1 × 10-10) that is also associated with risk of prostate cancer and is inversely associated with risk of type 2 diabetes. © 2011 Nature America, Inc. All rights reserved.
CRIS-Team Scopus Importer:2021-07-19

Genome-wide association study of germline variants and breast cancer-specific mortality - Escala-Garcia, Maria; Guo, Qi; Doerk, Thilo; Canisius, Sander; Keeman, Renske; Dennis, Joe; Beesley, Jonathan; Lecarpentier, Julie; Bolla, Manjeet K.; Wang, Qin; Abraham, Jean; Andrulis, Irene L.; et al. (British Journal of Cancer, 2019)
BACKGROUND: We examined the associations between germline variants and breast cancer mortality using a large meta-analysis of women of European ancestry.
CRIS-Team WoS Importer:2019-03-29

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Earp, Madalene A.; Kelemen, Linda E.; Magliocco, Anthony M.; Swenerton, Kenneth D.; Chenevix-Trench, Georgia; Lu, Yi; Hein, Alexander; Ekici, Arif Bülent; Beckmann, Matthias; Fasching, Peter; Lambrechts, Diether; Despierre, Evelyn; et al. (Human genetics, 2014)
Epithelial ovarian cancer (EOC) is a heterogeneous cancer with both genetic and environmental risk factors. Variants influencing the risk of developing the less-common EOC subtypes have not been fully investigated. We performed a genome-wide association study (GWAS) of EOC according to subtype by pooling genomic DNA from 545 cases and 398 controls of European descent, and testing for allelic associations. We evaluated for replication 188 variants from the GWAS [56 variants for mucinous, 55 for endometrioid and clear cell, 53 for low-malignant potential (LMP) serous, and 24 for invasive serous EOC], selected using pre-defined criteria. Genotypes from 13,188 cases and 23,164 controls of European descent were used to perform unconditional logistic regression under the log-additive genetic model; odds ratios (OR) and 95 % confidence intervals are reported. Nine variants tagging six loci were associated with subtype-specific EOC risk at P < 0.05, and had an OR that agreed in direction of effect with the GWAS results. Several of these variants are in or near genes with a biological rationale for conferring EOC risk, including ZFP36L1 and RAD51B for mucinous EOC (rs17106154, OR = 1.17, P = 0.029, n = 1,483 cases), GRB10 for endometrioid and clear cell EOC (rs2190503, P = 0.014, n = 2,903 cases), and C22orf26/BPIL2 for LMP serous EOC (rs9609538, OR = 0.86, P = 0.0043, n = 892 cases). In analyses that included the 75 GWAS samples, the association between rs9609538 (OR = 0.84, P = 0.0007) and LMP serous EOC risk remained statistically significant at P < 0.0012 adjusted for multiple testing. Replication in additional samples will be important to verify these results for the less-common EOC subtypes.
EVALuna2:9208

Genome-wide association study with DNA pooling identifies variants at CNTNAP2 associated with pseudoexfoliation syndrome - Krumbiegel, Mandy; Pasutto, Francesca; Schlötzer-Schrehardt, Ursula; Uebe, Steffen; Zenkel, Matthias; Mardin, Christian Y.; Weisschuh, Nicole; Paoli, Daniela; Gramer, Eugen; Becker, Christian; Ekici, Arif Bülent; Weber, Bernhard H. F.; et al. (European journal of human genetics, 2011)
Genetic and nongenetic factors contribute to development of pseudoexfoliation (PEX) syndrome, a complex, age-related, generalized matrix process frequently associated with glaucoma. To identify specific genetic variants underlying its etiology, we performed a genome-wide association study (GWAS) using a DNA-pooling approach. Therefore, equimolar amounts of DNA samples of 80 subjects with PEX syndrome, 80 with PEX glaucoma (PEXG) and 80 controls were combined into separate pools and hybridized to 500K SNP arrays (Affymetrix). Array probe intensity data were analyzed and visualized with expressly developed software tools GPFrontend and GPGraphics in combination with GenePool software. For replication, independent German cohorts of 610 unrelated patients with PEX/PEXG and 364 controls as well as Italian cohorts of 249 patients and 190 controls were used. Of 19, 17 SNPs showing significant allele frequency difference in DNA pools were confirmed by individual genotyping. Further single genotyping at CNTNAP2 locus revealed association between PEX/PEXG for two SNPs, which was confirmed in an independent German but not the Italian cohort. Both SNPs remained significant in the combined German cohorts even after Bonferroni correction (rs2107856: P(c)=0.0108, rs2141388: P(c)=0.0072). CNTNAP2 was found to be ubiquitously expressed in all human ocular tissues, particularly in retina, and localized to cell membranes of epithelial, endothelial, smooth muscle, glial and neuronal cells. Confirming efficiency of GWAS with DNA-pooling approach by detection of the known LOXL1 locus, our study data show evidence for association of CNTNAP2 with PEX syndrome and PEXG in German patients.
EVALuna2:9084

Genome-Wide Meta-Analyses of Breast, Ovarian, and Prostate Cancer Association Studies Identify Multiple New Susceptibility Loci Shared by at Least Two Cancer Types - Kar, Siddhartha P.; Beesley, Jonathan; Al Olama, Ali Amin; Michailidou, Kyriaki; Tyrer, Jonathan; Kote-Jarai, Zsofi A.; Lawrenson, Kate; Lindstrom, Sara; Ramus, Susan J.; Thompson, Deborah J.; Kibel, Adam S.; Dansonka-Mieszkowska, Agnieszka; et al. (Cancer Discovery, 2016)
Breast, ovarian, and prostate cancers are hormone-related and may have a shared genetic basis, but this has not been investigated systematically by genome-wide association (GWA) studies. Meta-analyses combining the largest GWA meta-analysis data sets for these cancers totaling 112,349 cases and 116,421 controls of European ancestry, all together and in pairs, identified at P < 10(-8) seven new cross-cancer loci: three associated with susceptibility to all three cancers (rs17041869/2q13/BCL2L11; rs7937840/11q12/INCENP; rs1469713/19p13/GATAD2A), two breast and ovarian cancer risk loci (rs200182588/9q31/SMC2; rs8037137/15q26/RCCD1), and two breast and prostate cancer risk loci (rs5013329/1p34/NSUN4; rs9375701/6q23/L3MBTL3). Index variants in five additional regions previously associated with only one cancer also showed clear association with a second cancer type. Cell-type-specific expression quantitative trait locus and enhancer-gene interaction annotations suggested target genes with potential cross-cancer roles at the new loci. Pathway analysis revealed significant enrichment of death receptor signaling genes near loci with P < 10(-5) in the three-cancer meta-analysis.We demonstrate that combining large-scale GWA meta-analysis findings across cancer types can identify completely new risk loci common to breast, ovarian, and prostate cancers. We show that the identification of such cross-cancer risk loci has the potential to shed new light on the shared biology underlying these hormone-related cancers. Cancer Discov; 6(9); 1052-67. ©2016 AACR.This article is highlighted in the In This Issue feature, p. 932.
EVALuna2:9322

Genome-wide UPD screening in patients with intellectual disability - Schroeder, Christopher; Ekici, Arif Bülent; Moog, Ute; Grasshoff, Ute; Mau-Holzmann, Ulrike; Sturm, Marc; Vosseler, Vanessa; Poths, Sven; Rappold, Gudrun; Riess, Angelika; Riess, Olaf; Dufke, Andreas; et al. (European journal of human genetics, 2014)
Uniparental disomy (UPD) describes the inheritance of a pair of chromosomes from only one parent. It may occur as isodisomy, heterodisomy or a combination of both and may involve only chromosome segments. UPD can affect each chromosome. The incidence is estimated to be around 1:3500 in live births. Some parts of chromosomes are subject to 'parent-of-origin imprinting' and the phenotypic effect in UPD syndromes is mainly due to functional imbalance of imprinted genes. Isodisomy can result in mutation homozygosity in autosomal-recessive inherited diseases. UPD causes several well-defined imprinting syndromes associated with intellectual disability (ID). Although knowledge on frequency and size of UPDs in patients with unexplained ID remains largely unknown as no efficient genome-wide screening technique was available for detection of both isodisomic and heterodisomic UPDs. SNP microarrays have been proven to be capable to detect UPDs through Mendelian errors. The correct subclassification of UPD requires child-parent trio experiments. To further elucidate the role of UPD in patients with unexplained ID, we analyzed a total of 322 child-parent trios. We were not able to detect UPDs (isodisomies and heterodisomies) within our cohort spanning whole chromosomes or chromosomal segments. We conclude that UPD is rare in patients with unexplained ID.
EVALuna2:9225

Germline polymorphisms in an enhancer of PSIP1 are associated with progression-free survival in epithelial ovarian cancer - French, Juliet D.; Johnatty, Sharon E.; Lu, Yi; Beesley, Jonathan; Gao, Bo; Kalimutho, Murugan; Henderson, Michelle J.; Russell, Amanda J.; Kar, Siddhartha; Chen, Xiaoqing; Hillman, Kristine M.; Kaufmann, Susanne; et al. (Oncotarget, 2016)
Women with epithelial ovarian cancer (EOC) are usually treated with platinum/taxane therapy after cytoreductive surgery but there is considerable inter-individual variation in response. To identify germline single-nucleotide polymorphisms (SNPs) that contribute to variations in individual responses to chemotherapy, we carried out a multi-phase genome-wide association study (GWAS) in 1,244 women diagnosed with serous EOC who were treated with the same first-line chemotherapy, carboplatin and paclitaxel. We identified two SNPs (rs7874043 and rs72700653) in TTC39B (best P=7x10-5, HR=1.90, for rs7874043) associated with progression-free survival (PFS). Functional analyses show that both SNPs lie in a putative regulatory element (PRE) that physically interacts with the promoters of PSIP1, CCDC171 and an alternative promoter of TTC39B. The C allele of rs7874043 is associated with poor PFS and showed increased binding of the Sp1 transcription factor, which is critical for chromatin interactions with PSIP1. Silencing of PSIP1 significantly impaired DNA damage-induced Rad51 nuclear foci and reduced cell viability in ovarian cancer lines. PSIP1 (PC4 and SFRS1 Interacting Protein 1) is known to protect cells from stress-induced apoptosis, and high expression is associated with poor PFS in EOC patients. We therefore suggest that the minor allele of rs7874043 confers poor PFS by increasing PSIP1 expression.
EVALuna2:9320

Germline variants and breast cancer survival in patients with distant metastases at primary breast cancer diagnosis - Escala-Garcia, Maria; Canisius, Sander; Keeman, Renske; Beesley, Jonathan; Anton-Culver, Hoda; Arndt, Volker; Augustinsson, Annelie; Becher, Heiko; Beckmann, Matthias; Behrens, Sabine; Bermisheva, Marina; Bojesen, Stig E.; et al. (Scientific Reports, 2021)
Breast cancer metastasis accounts for most of the deaths from breast cancer. Identification of germline variants associated with survival in aggressive types of breast cancer may inform understanding of breast cancer progression and assist treatment. In this analysis, we studied the associations between germline variants and breast cancer survival for patients with distant metastases at primary breast cancer diagnosis. We used data from the Breast Cancer Association Consortium (BCAC) including 1062 women of European ancestry with metastatic breast cancer, 606 of whom died of breast cancer. We identified two germline variants on chromosome 1, rs138569520 and rs146023652, significantly associated with breast cancer-specific survival (P = 3.19 x 10(-8) and 4.42 x 10(-8)). In silico analysis suggested a potential regulatory effect of the variants on the nearby target genes SDE2 and H3F3A. However, the variants showed no evidence of association in a smaller replication dataset. The validation dataset was obtained from the SNPs to Risk of Metastasis (StoRM) study and included 293 patients with metastatic primary breast cancer at diagnosis. Ultimately, larger replication studies are needed to confirm the identified associations.
CRIS-Team WoS Importer:2021-10-15

GWAS meta-analysis and replication identifies three new susceptibility loci for ovarian cancer - Pharoah, Paul D. P.; Tsai, Ya-Yu; Ramus, Susan J.; Phelan, Catherine M.; Goode, Ellen L.; Lawrenson, Kate; Buckley, Melissa; Fridley, Brooke L.; Tyrer, Jonathan P.; Shen, Howard; Weber, Rachel; Karevan, Rod; et al. (Nature Genetics, 2013)
Genome-wide association studies (GWAS) have identified four susceptibility loci for epithelial ovarian cancer (EOC), with another two suggestive loci reaching near genome-wide significance. We pooled data from a GWAS conducted in North America with another GWAS from the UK. We selected the top 24,551 SNPs for inclusion on the iCOGS custom genotyping array. We performed follow-up genotyping in 18,174 individuals with EOC (cases) and 26,134 controls from 43 studies from the Ovarian Cancer Association Consortium. We validated the two loci at 3q25 and 17q21 that were previously found to have associations close to genome-wide significance and identified three loci newly associated with risk: two loci associated with all EOC subtypes at 8q21 (rs11782652, P = 5.5 × 10-9) and 10p12 (rs1243180, P = 1.8 × 10-8) and another locus specific to the serous subtype at 17q12 (rs757210, P = 8.1 × 10-10). An integrated molecular analysis of genes and regulatory regions at these loci provided evidence for functional mechanisms underlying susceptibility and implicated CHMP4C in the pathogenesis of ovarian cancer.
CRIS-Team Scopus Importer:2021-07-19

Haploinsufficiency of NR4A2 is associated with a neurodevelopmental phenotype with prominent language impairment - Reuter, Miriam; Krumbiegel, Mandy; Schlueter, Gregor; Ekici, Arif Bülent; Reis, André; Zweier, Christiane (American Journal of Medical Genetics Part A, 2017)
Non-recurrent deletions in 2q24.1, minimally overlapping two genes, NR4A2 and GPD2, were recently described in individuals with language impairment and behavioral and cognitive symptoms. We herewith report on a female patient with a similar phenotype of severe language and mild cognitive impairment, in whom we identified a de novo deletion covering only NR4A2. NR4A2 encodes a transcription factor highly expressed in brain regions critical for speech and language and implicated in dopaminergic neuronal development. Our findings of a de novo deletion of NR4A2 in an individual with mild intellectual disability and prominent speech and language impairment provides further evidence for NR4A2 haploinsufficiency being causative for neurodevelopmental and particularly language phenotypes.
EVALuna2:9359

Height and Breast Cancer Risk: Evidence From Prospective Studies and Mendelian Randomization - Zhang, Ben; Shu, Xiao-Ou; Delahanty, Ryan J.; Zeng, Chenjie; Michailidou, Kyriaki; Bolla, Manjeet K.; Wang, Qin; Dennis, Joe; Wen, Wanqing; Long, Jirong; Li, Chun; Dunning, Alison M.; et al. (Journal of the National Cancer Institute, 2015)
Epidemiological studies have linked adult height with breast cancer risk in women. However, the magnitude of the association, particularly by subtypes of breast cancer, has not been established. Furthermore, the mechanisms of the association remain unclear.We performed a meta-analysis to investigate associations between height and breast cancer risk using data from 159 prospective cohorts totaling 5216302 women, including 113178 events. In a consortium with individual-level data from 46325 case patients and 42482 control patients, we conducted a Mendelian randomization analysis using a genetic score that comprised 168 height-associated variants as an instrument. This association was further evaluated in a second consortium using summary statistics data from 16003 case patients and 41335 control patients.The pooled relative risk of breast cancer was 1.17 (95% confidence interval [CI] = 1.15 to 1.19) per 10cm increase in height in the meta-analysis of prospective studies. In Mendelian randomization analysis, the odds ratio of breast cancer per 10cm increase in genetically predicted height was 1.22 (95% CI = 1.13 to 1.32) in the first consortium and 1.21 (95% CI = 1.05 to 1.39) in the second consortium. The association was found in both premenopausal and postmenopausal women but restricted to hormone receptor-positive breast cancer. Analyses of height-associated variants identified eight new loci associated with breast cancer risk after adjusting for multiple comparisons, including three loci at 1q21.2, DNAJC27, and CCDC91 at genome-wide significance level P < 5×10(-8).Our study provides strong evidence that adult height is a risk factor for breast cancer in women and certain genetic factors and biological pathways affecting adult height have an important role in the etiology of breast cancer.
EVALuna2:9301

HER2 and TOP2A amplification in a hospital-based cohort of breast cancer patients: associations with patient and tumor characteristics - Fasching, Peter A.; Weihbrecht, Sebastian; Haeberle, Lothar; Gasparyan, Armen; Villalobos, Ivonne E.; Ma, Yanling; Ekici, Arif Bülent; Wachter, David; Hartmann, Arndt; Beckmann, Matthias; Slamon, Dennis J.; Press, Michael F. (Breast Cancer Research and Treatment, 2014)
Gene amplification is an important factor for altered gene expression in breast cancers. TOP2A-amplification often occurs concomitantly with HER2 amplification, and it has been suggested to be predictive for the response to anthracycline chemotherapy. This study assessed the correlation between HER2 status and TOP2A co-amplification, the possible association of TOP2A single-nucleotide polymorphisms with the frequency of this co-amplification as well as confirmation of association with outcome. HER2 and TOP2A amplification were analyzed in a tissue microarray from a clinical cohort study. Additionally, a common genetic variant (rs13695) in the TOP2A gene was genotyped in germline DNA. HER2 gene amplification was compared with HER2-IHC findings assessed during clinical routine work, and the association between all the biomarkers analyzed and the clinical outcome was determined. As an exploratory aim, rs13695 genotypes were compared with TOP2A amplification status. HER2 amplification was seen in 101 of 628 (16.1 %) and TOP2A amplification in 32 (5.1 %) cancers. No TOP2A amplification occurred without HER2 co-amplification. HER2 amplification was found in 8, 13.6, and 55.1 % of patients with HER2-IHC 0/1+, 2+, and 3+ tumors, respectively. HER2-IHC was not associated with an effect on the prognosis, but HER2-FISH was. There was an association between the rs13695 genotype and TOP2A amplification status (P = 0.03). Although there was a significant correlation between HER2 status determined by IHC and HER2 by FISH, only HER2 gene amplification status by FISH was correlated with outcome indicating greater utility for FISH in routine clinical settings.
EVALuna2:6613

HIBCH deficiency in a patient with phenotypic characteristics of mitochondrial disorders - Reuter, Miriam; Sass, Joern Oliver; Leis, Thomas; Koehler, Julia; Mayr, Johannes A.; Feichtinger, Rene G.; Rauh, Manfred; Schanze, Ina; Baehr, Luzy; Trollmann, Regina; Uebe, Steffen; Ekici, Arif Bülent; et al. (American Journal of Medical Genetics Part A, 2014)
HIBCH (3-hydroxyisobutyryl-CoA hydrolase) deficiency (MIM #250620) is a rare autosomal recessive inborn error of metabolism, leading to a block in the catabolic pathway of the amino acid valine and presumably to accumulation of toxic valine metabolites in mitochondria. Only three families with HIBCH deficiency and biallelic HIBCH mutations have been described. We report on a further patient, first child of healthy consanguineous parents, with severe developmental delay, seizures, hyperintensities of the basal ganglia on magnetic resonance imaging (MRI), progressive brain atrophy, optic nerve atrophy, repeatedly elevated blood lactate, and respiratory chain complexes I, I + III and cytochrome c oxidase deficiencies with borderline depletion of mitochondrial DNA in muscle tissue. Laboratory findings in blood and skeletal muscle were inconsistent and did not allow a definite diagnosis, but supported the hypothesis of mitochondrial dysfunction. Homozygosity mapping and whole-exome sequencing revealed a homozygous one-base pair insertion in HIBCH. Deficiency of enzyme activity was confirmed in cultured fibroblasts. Although relatively unspecific, the clinical features were similar to those of the previously reported cases. Given the clinical variability and large number of differential diagnoses, the prevalence of HIBCH deficiency is probably underestimated. Next-generation sequencing approaches are an effective tool for identifying the underlying genetic basis in patients suspected of mitochondrial disorders. © 2014 Wiley Periodicals, Inc.
EVALuna2:9220

High resolution chromosomal microarray analysis in paediatric obsessive-compulsive disorder - Grünblatt, Edna; Oneda, Beatrice; Ekici, Arif Bülent; Ball, Juliane; Geissler, Julia; Uebe, Steffen; Romanos, Marcel; Rauch, Anita; Walitza, Susanne (Bmc Medical Genomics, 2017)
Obsessive-Compulsive Disorder (OCD) is a common and chronic disorder in which a person has uncontrollable, reoccurring thoughts and behaviours. It is a complex genetic condition and, in case of early onset (EO), the patients manifest a more severe phenotype, and an increased heritability. Large (>500 kb) copy number variations (CNVs) previously associated with autism and schizophrenia have been reported in OCD. Recently, rare CNVs smaller than 500 kb overlapping risk loci for other neurodevelopmental conditions have also been reported in OCD, stressing the importance of examining CNVs of any size range. The aim of this study was to further investigate the role of rare and small CNVs in the aetiology of EO-OCD.We performed high-resolution chromosomal microarray analysis in 121 paediatric OCD patients and in 124 random controls to identify rare CNVs (>50 kb) which might contribute to EO-OCD.The frequencies and the size of the observed rare CNVs in the patients did not differ from the controls. However, we observed a significantly higher frequency of rare CNVs affecting brain related genes, especially deletions, in the patients (OR = 1.98, 95% CI 1.02-3.84; OR = 3.61, 95% CI 1.14-11.41, respectively). Similarly, enrichment-analysis of CNVs gene content, performed with three independent methods, confirmed significant clustering of predefined genes involved in synaptic/brain related functional pathways in the patients but not in the controls. In two patients we detected de-novo CNVs encompassing genes previously associated with different neurodevelopmental disorders (NRXN1, ANKS1B, UHRF1BP1).Our results further strengthen the role of small rare CNVs, particularly deletions, as susceptibility factors for paediatric OCD.
EVALuna2:9389

HLA-G and HLA-F protein isoform expression in breast cancer patients receiving neoadjuvant treatment - Würfel, Franziska; Hübner, Hanna; Häberle, Lothar; Gaß, Paul; Hein, Alexander; Jud, Sebastian; Hack, Carolin; Wunderle, Marius; Schulz-Wendtland, Rüdiger; Erber, Ramona; Hartmann, Arndt; Ekici, Arif Bülent; et al. (Scientific Reports, 2020)
The immunosuppressive human leukocyte antigens HLA-G and HLA-F are expressed on trophoblast and malignant cells. Four membrane-bound and three soluble HLA-G protein isoforms have been described, which have different immunosuppressive potentials. HLA-F has three transcript variants, resulting in three different protein isoforms. The aim of this study was to evaluate the prognostic and predictive value of HLA-G and HLA-F protein isoform expression patterns in patients with breast cancer. Core biopsies were taken at diagnosis in patients with HER2+ (n = 28), luminal B-like (n = 49) and triple-negative (n = 38) breast cancers who received neoadjuvant chemotherapy. Expression levels of HLA-F and -G were correlated with the pathological complete response (pCR). Protein expression was determined by Western blot analysis, using two antibodies for each HLA, specific for different isoforms. The protein expression of HLA isoforms did not significantly differ between breast cancer subtypes. However, some initial indications were found for an association between the soluble HLA-G6 protein isoform and pCR in HER2+ breast cancer. The study provides preliminary evidence for the evaluation of HLA-G isoform expression, in particular HLA-G6, as a possible new marker for pCR in HER2+ breast cancer.
CRIS-Team Scopus Importer:2020-10-02

Hobit- and Blimp-1-driven CD4(+) tissue-resident memory T cells control chronic intestinal inflammation - Zundler, Sebastian; Becker, Emily; Spocinska, Marta; Slawik, Monique; Parga-Vidal, Loreto; Stark, Regina; Wiendl, Maximilian; Atreya, Raja; Rath, Timo; Leppkes, Moritz; Hildner, Kai; Lopez Posadas, Rocío; et al. (Nature Immunology, 2019)
Although tissue-resident memory T cells (T-RM cells) have been shown to regulate host protection in infectious disorders, their function in inflammatory bowel disease (IBD) remains to be investigated. Here we characterized T-RM cells in human IBD and in experimental models of intestinal inflammation. Pro-inflammatory T-RM cells accumulated in the mucosa of patients with IBD, and the presence of CD4(+)CD69(+)CD103(+) T-RM cells was predictive of the development of flares. In vivo, functional impairment of T-RM cells in mice with double knockout of the T-RM-cell-associated transcription factors Hobit and Blimp-1 attenuated disease in several models of colitis, due to impaired cross-talk between the adaptive and innate immune system. Finally, depletion of T-RM cells led to a suppression of colitis activity. Together, our data demonstrate a central role for T-RM cells in the pathogenesis of chronic intestinal inflammation and suggest that these cells could be targets for future therapeutic approaches in IBD.
CRIS-Team WoS Importer:2019-03-06

Hyperandrogenemia and high prolactin in congenital utero-vaginal aplasia patients - Oppelt, Patricia; Mueller, Andreas; Stephan, Liana; Dittrich, Ralf; Lermann, Johannes; Büttner, Christian; Ekici, Arif Bülent; Conzelmann, Gabi; Seeger, Harald; Schoeller, Dorit; Rall, Katharina; Beckmann, Matthias; et al. (Reproduction, 2017)
Patients with the Mayer-Rokitansky-Küster-Hauser syndrome (MRKH) have a congenital utero-vaginal cervical aplasia, but normal or hypoplastic adnexa and develop with normal female phenotype. Some reports mostly demonstrated regular steroid hormone levels in small MRKH cohorts including single MRKH patients with hyperandrogenemia and a clinical presentationof hirsutism and acne has also been shown. Genetically a correlation of WNT4 mutations with singular MRKH patients and hyperandrogenemia was noted. This study analyzed the hormone status of 215 MRKH patients by determining the levels of luteinizing hormone (LH), follicle-stimulating hormone (FSH), estradiol, 17-OH progesterone, testosterone, dehydroepiandrosterone sulfate (DHEAS), sex hormone-binding globulin (SHBG) and prolactin to determine the incidence of hyperandrogenemia and hyperprolactinemia in MRKH patients. Additional calculations and a ratio of free androgen index and biologically active testosterone revealed a hyperandrogenemia rate of 48.3%, hyperprolactinemia of 9.8% and combined hyperandrogenemia and hyperprolactinemia of 4.2% in MRKH patients. The rates of hirsutism, acne and especially polycystic ovary syndrome (PCOS) were in the normal range of the population and showed no correlation with hyperandrogenemia. A weekly hormone assessment over 30 days comparing 5 controls and 7 MRKH patients revealed high androgen and prolactin, but lower LH/FSH and SHBG levels with MRKH patients. The sequencing of WNT4, WNT5A, WNT7A and WNT9B demonstrated no significant mutations correlating with hyperandrogenemia. Taken together, this study shows that over 52% of MRKH patients have hyperandrogenemia without clinical presentation and 14% hyperprolactinemia, which appeals for general hormone assessment and adjustments of MRKH patients.
EVALuna2:9378

Identification and characterization of novel associations in the CASP8/ALS2CR12 region on chromosome 2 with breast cancer risk - Lin, Wei-Yu; Camp, Nicola J.; Ghoussaini, Maya; Beesley, Jonathan; Michailidou, Kyriaki; Hopper, John L.; Apicella, Carmel; Southey, Melissa C.; Stone, Jennifer; Schmidt, Marjanka K.; Broeks, Annegien; Van'T Veer, Laura J.; et al. (Human Molecular Genetics, 2015)
Previous studies have suggested that polymorphisms in CASP8 on chromosome 2 are associated with breast cancer risk. To clarify the role of CASP8 in breast cancer susceptibility, we carried out dense genotyping of this region in the Breast Cancer Association Consortium (BCAC). Single-nucleotide polymorphisms (SNPs) spanning a 1 Mb region around CASP8 were genotyped in 46 450 breast cancer cases and 42 600 controls of European origin from 41 studies participating in the BCAC as part of a custom genotyping array experiment (iCOGS). Missing genotypes and SNPs were imputed and, after quality exclusions, 501 typed and 1232 imputed SNPs were included in logistic regression models adjusting for study and ancestry principal components. The SNPs retained in the final model were investigated further in data from nine genome-wide association studies (GWAS) comprising in total 10 052 case and 12 575 control subjects. The most significant association signal observed in European subjects was for the imputed intronic SNP rs1830298 in ALS2CR12 (telomeric to CASP8), with per allele odds ratio and 95% confidence interval [OR (95% confidence interval, CI)] for the minor allele of 1.05 (1.03-1.07), P = 1 × 10(-5). Three additional independent signals from intronic SNPs were identified, in CASP8 (rs36043647), ALS2CR11 (rs59278883) and CFLAR (rs7558475). The association with rs1830298 was replicated in the imputed results from the combined GWAS (P = 3 × 10(-6)), yielding a combined OR (95% CI) of 1.06 (1.04-1.08), P = 1 × 10(-9). Analyses of gene expression associations in peripheral blood and normal breast tissue indicate that CASP8 might be the target gene, suggesting a mechanism involving apoptosi
EVALuna2:9254

Identification of 12 new susceptibility loci for different histotypes of epithelial ovarian cancer - Phelan, Catherine M.; Kuchenbaecker, Karoline B.; Tyrer, Jonathan P.; Kar, Siddhartha P.; Lawrenson, Kate; Winham, Stacey J.; Dennis, Joe; Pirie, Ailith; Riggan, Marjorie J.; Chornokur, Ganna; Earp, Madalene A.; Lyra, Paulo C.; et al. (Nature Genetics, 2017)
To identify common alleles associated with different histotypes of epithelial ovarian cancer (EOC), we pooled data from multiple genome-wide genotyping projects totaling 25,509 EOC cases and 40,941 controls. We identified nine new susceptibility loci for different EOC histotypes: six for serous EOC histotypes (3q28, 4q32.3, 8q21.11, 10q24.33, 18q11.2 and 22q12.1), two for mucinous EOC (3q22.3 and 9q31.1) and one for endometrioid EOC (5q12.3). We then performed meta-analysis on the results for high-grade serous ovarian cancer with the results from analysis of 31,448 BRCA1 and BRCA2 mutation carriers, including 3,887 mutation carriers with EOC. This identified three additional susceptibility loci at 2q13, 8q24.1 and 12q24.31. Integrated analyses of genes and regulatory biofeatures at each locus predicted candidate susceptibility genes, including OBFC1, a new candidate susceptibility gene for low-grade and borderline serous EOC.
EVALuna2:9375

Identification of four novel susceptibility loci for oestrogen receptor negative breast cancer - Couch, Fergus J.; Kuchenbaecker, Karoline B.; Michailidou, Kyriaki; Mendoza-Fandino, Gustavo A.; Nord, Silje; Lilyquist, Janna; Olswold, Curtis; Hallberg, Emily; Agata, Simona; Ahsan, Habibul; Aittomaeki, Kristiina; Ambrosone, Christine; et al. (Nature Communications, 2016)
Common variants in 94 loci have been associated with breast cancer including 15 loci with genome-wide significant associations (P<5 × 10(-8)) with oestrogen receptor (ER)-negative breast cancer and BRCA1-associated breast cancer risk. In this study, to identify new ER-negative susceptibility loci, we performed a meta-analysis of 11 genome-wide association studies (GWAS) consisting of 4,939 ER-negative cases and 14,352 controls, combined with 7,333 ER-negative cases and 42,468 controls and 15,252 BRCA1 mutation carriers genotyped on the iCOGS array. We identify four previously unidentified loci including two loci at 13q22 near KLF5, a 2p23.2 locus near WDR43 and a 2q33 locus near PPIL3 that display genome-wide significant associations with ER-negative breast cancer. In addition, 19 known breast cancer risk loci have genome-wide significant associations and 40 had moderate associations (P<0.05) with ER-negative disease. Using functional and eQTL studies we implicate TRMT61B and WDR43 at 2p23.2 and PPIL3 at 2q33 in ER-negative breast cancer aetiology. All ER-negative loci combined account for 11% of familial relative risk for ER-negative disease and may contribute to improved ER-negative and BRCA1 breast cancer risk prediction.
EVALuna2:9317

Identification of new genetic susceptibility Loci for breast cancer through consideration of gene-environment interactions - Schoeps, Anja; Rudolph, Anja; Seibold, Petra; Dunning, Alison M.; Milne, Roger L.; Bojesen, Stig E.; Swerdlow, Anthony; Andrulis, Irene; Brenner, Hermann; Behrens, Sabine; Orr, Nicholas; Jones, Michael; et al. (Genetic Epidemiology, 2014)
Genes that alter disease risk only in combination with certain environmental exposures may not be detected in genetic association analysis. By using methods accounting for gene-environment (G × E) interaction, we aimed to identify novel genetic loci associated with breast cancer risk. Up to 34,475 cases and 34,786 controls of European ancestry from up to 23 studies in the Breast Cancer Association Consortium were included. Overall, 71,527 single nucleotide polymorphisms (SNPs), enriched for association with breast cancer, were tested for interaction with 10 environmental risk factors using three recently proposed hybrid methods and a joint test of association and interaction. Analyses were adjusted for age, study, population stratification, and confounding factors as applicable. Three SNPs in two independent loci showed statistically significant association: SNPs rs10483028 and rs2242714 in perfect linkage disequilibrium on chromosome 21 and rs12197388 in ARID1B on chromosome 6. While rs12197388 was identified using the joint test with parity and with age at menarche (P-values = 3 × 10(-07) ), the variants on chromosome 21 q22.12, which showed interaction with adult body mass index (BMI) in 8,891 postmenopausal women, were identified by all methods applied. SNP rs10483028 was associated with breast cancer in women with a BMI below 25 kg/m(2) (OR = 1.26, 95% CI 1.15-1.38) but not in women with a BMI of 30 kg/m(2) or higher (OR = 0.89, 95% CI 0.72-1.11, P for interaction = 3.2 × 10(-05) ). Our findings confirm comparable power of the recent methods for detecting G × E interaction and the utility of using G × E interaction analyses to identify new susceptibility loci.
EVALuna2:9203

Identification of nine new susceptibility loci for endometrial cancer - O'Mara, Tracy A.; Glubb, Dylan M.; Amant, Frederic; Annibali, Daniela; Ashton, Katie; Attia, John; Auer, Paul L.; Beckmann, Matthias; Black, Amanda; Bolla, Manjeet K.; Brauch, Hiltrud; Brenner, Hermann; et al. (Nature Communications, 2018)
Endometrial cancer is the most commonly diagnosed cancer of the female reproductive tract in developed countries. Through genome-wide association studies (GWAS), we have previously identified eight risk loci for endometrial cancer. Here, we present an expanded meta-analysis of 12,906 endometrial cancer cases and 108,979 controls (including new genotype data for 5624 cases) and identify nine novel genome-wide significant loci, including a locus on 12q24.12 previously identified by meta-GWAS of endometrial and colorectal cancer. At five loci, expression quantitative trait locus (eQTL) analyses identify candidate causal genes; risk alleles at two of these loci associate with decreased expression of genes, which encode negative regulators of oncogenic signal transduction proteins (SH2B3 (12q24.12) and NF1 (17q11.2)). In summary, this study has doubled the number of known endometrial cancer risk loci and revealed candidate causal genes for future study.
EVALuna2:34618

Identification of novel candidate genes for idiopathic short stature using whole exome sequencing - Thiel, Christian; Hauer, Nadine; Vogl, C.; Ahmadian, R.; Dhandapany, P. S.; Popp, Bernt; Buettner, C.; Ube, S.; Sticht, Heinrich; Ferrazzi, Fulvia; Ekici, Arif Bülent; De Luca, A.; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2019)
CRIS-Team WoS Importer:2019-10-25

Identification of novel genetic markers of breast cancer survival - Guo, Qi; Schmidt, Marjanka K.; Kraft, Peter; Canisius, Sander; Chen, Constance; Khan, Sofia; Tyrer, Jonathan; Bolla, Manjeet K.; Wang, Qin; Dennis, Joe; Michailidou, Kyriaki; Lush, Michael; et al. (Journal of the National Cancer Institute, 2015)
Survival after a diagnosis of breast cancer varies considerably between patients, and some of this variation may be because of germline genetic variation. We aimed to identify genetic markers associated with breast cancer-specific survival.We conducted a large meta-analysis of studies in populations of European ancestry, including 37954 patients with 2900 deaths from breast cancer. Each study had been genotyped for between 200000 and 900000 single nucleotide polymorphisms (SNPs) across the genome; genotypes for nine million common variants were imputed using a common reference panel from the 1000 Genomes Project. We also carried out subtype-specific analyses based on 6881 estrogen receptor (ER)-negative patients (920 events) and 23059 ER-positive patients (1333 events). All statistical tests were two-sided.We identified one new locus (rs2059614 at 11q24.2) associated with survival in ER-negative breast cancer cases (hazard ratio [HR] = 1.95, 95% confidence interval [CI] = 1.55 to 2.47, P = 1.91 x 10(-8)). Genotyping a subset of 2113 case patients, of which 300 were ER negative, provided supporting evidence for the quality of the imputation. The association in this set of case patients was stronger for the observed genotypes than for the imputed genotypes. A second locus (rs148760487 at 2q24.2) was associated at genome-wide statistical significance in initial analyses; the association was similar in ER-positive and ER-negative case patients. Here the results of genotyping suggested that the finding was less robust.This is currently the largest study investigating genetic variation associated with breast cancer survival. Our results have potential clinical implications, as they confirm that germline genotype can provide prognostic information in addition to standard tumor prognostic factors.
EVALuna2:9260

Identification of six new susceptibility loci for invasive epithelial ovarian cancer - Kuchenbaecker, Karoline B.; Ramus, Susan J.; Tyrer, Jonathan; Lee, Andrew; Shen, Howard C.; Beesley, Jonathan; Lawrenson, Kate; Mcguffog, Lesley; Healey, Sue; Lee, Janet M.; Spindler, Tassja J.; Lin, Yvonne G.; et al. (Nature Genetics, 2015)
Genome-wide association studies (GWAS) have identified 12 epithelial ovarian cancer (EOC) susceptibility alleles. The pattern of association at these loci is consistent in BRCA1 and BRCA2 mutation carriers who are at high risk of EOC. After imputation to 1000 Genomes Project data, we assessed associations of 11 million genetic variants with EOC risk from 15,437 cases unselected for family history and 30,845 controls and from 15,252 BRCA1 mutation carriers and 8,211 BRCA2 mutation carriers (3,096 with ovarian cancer), and we combined the results in a meta-analysis. This new study design yielded increased statistical power, leading to the discovery of six new EOC susceptibility loci. Variants at 1p36 (nearest gene, WNT4), 4q26 (SYNPO2), 9q34.2 (ABO) and 17q11.2 (ATAD5) were associated with EOC risk, and at 1p34.3 (RSPO1) and 6p22.1 (GPX6) variants were specifically associated with the serous EOC subtype, all with P < 5 × 10(-8). Incorporating these variants into risk assessment tools will improve clinical risk predictions for BRCA1 and BRCA2 mutation carriers.
EVALuna2:9273

Identification of ten variants associated with risk of estrogen-receptor-negative breast cancer - Milne, Roger L.; Kuchenbaecker, Karoline B.; Michailidou, Kyriaki; Beesley, Jonathan; Kar, Siddhartha; Lindstrom, Sara; Hui, Shirley; Lemacon, Audrey; Soucy, Penny; Dennis, Joe; Jiang, Xia; Rostamianfar, Asha; et al. (Nature Genetics, 2017)
Most common breast cancer susceptibility variants have been identified through genome-wide association studies (GWAS) of predominantly estrogen receptor (ER)-positive disease. We conducted a GWAS using 21,468 ER-negative cases and 100,594 controls combined with 18,908 BRCA1 mutation carriers (9,414 with breast cancer), all of European origin. We identified independent associations at P < 5 × 10-8 with ten variants at nine new loci. At P < 0.05, we replicated associations with 10 of 11 variants previously reported in ER-negative disease or BRCA1 mutation carrier GWAS and observed consistent associations with ER-negative disease for 105 susceptibility variants identified by other studies. These 125 variants explain approximately 16% of the familial risk of this breast cancer subtype. There was high genetic correlation (0.72) between risk of ER-negative breast cancer and breast cancer risk for BRCA1 mutation carriers. These findings may lead to improved risk prediction and inform further fine-mapping and functional work to better understand the biological basis of ER-negative breast cancer.
EVALuna2:9391

Identification of the deregulated NEK1 protein network in skeletal ciliopathies - Vogl, C.; Keßler, Kristin; Gießl, Andreas; Kirchner, P.; Büttner, Christian; Ekici, Arif Bülent; Reis, André; Thiel, C. T. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

Identification of Two Genetic Loci Associated with Leukopenia after Chemotherapy in Patients with Breast Cancer - Fasching, Peter; Liu, Duan; Scully, Steve; Ingle, James N.; Lyra, Paulo C.; Rack, Brigitte; Hein, Alexander; Ekici, Arif Bülent; Reis, André; Schneeweiss, Andreas; Tesch, Hans; Fehm, Tanja N.; et al. (Clinical Cancer Research, 2022)
Purpose: To identify molecular predictors of grade 3/4 neutropenic or leukopenic events (NLE) after chemotherapy using a genome-wide association study (GWAS). Experimental Design: A GWAS was performed on patients in the phase III chemotherapy study SUCCESS-A (n = 3,322). Genotyping was done using the Illumina HumanOmniExpress-12v1 array. Findings were functionally validated with cell culture models and the genotypes and gene expression of possible causative genes were correlated with clinical treatment response and prognostic outcomes. Results: One locus on chromosome 16 (rs4784750; NLRC5; P = 1.56E-8) and another locus on chromosome 13 (rs16972207; TNFSF13B; P = 3.42E-8) were identified at a genome-wide significance level. Functional validation revealed that expression of these two genes is altered by genotype-dependent and chemotherapy-dependent activity of two transcription factors. Genotypes also showed an association with disease-free survival in patients with an NLE. Conclusions: Two loci in NLRC5 and TNFSF13B are associated with NLEs. The involvement of theMHCI regulator NLRC5 implies the possible involvement of immuno-oncological pathways.
CRIS-Team Scopus Importer:2022-08-19

IL-33-induced metabolic reprogramming controls the differentiation of alternatively activated macrophages and the resolution of inflammation - Faas, Maria; Ipseiz, Natacha; Ackermann, Jochen; Culemann, Stephan; Grüneboom, Anika; Schröder, Fenja; Rothe, Tobias; Scholtysek, Carina; Eberhardt, Martin; Böttcher, Martin; Kirchner, Philipp; Stoll, Cornelia; et al. (Immunity, 2021)
Alternatively activated macrophages (AAMs) contribute to the resolution of inflammation and tissue repair. However, molecular pathways that govern their differentiation have remained incompletely understood. Here, we show that uncoupling protein-2-mediated mitochondrial reprogramming and the transcription factor GATA3 specifically controlled the differentiation of pro-resolving AAMs in response to the alarmin IL-33. In macrophages, IL-33 sequentially triggered early expression of pro-inflammatory genes and subsequent differentiation into AAMs. Global analysis of underlying signaling events revealed that IL-33 induced a rapid metabolic rewiring of macrophages that involved uncoupling of the respiratory chain and increased production of the metabolite itaconate, which subsequently triggered a GATA3-mediated AAM polarization. Conditional deletion of GATA3 in mononuclear phagocytes accordingly abrogated IL-33-induced differentiation of AAMs and tissue repair upon muscle injury. Our data thus identify an IL-4-independent and GATA3-dependent pathway in mononuclear phagocytes that results from mitochondrial rewiring and controls macrophage plasticity and the resolution of inflammation.
CRIS-Team Scopus Importer:2021-11-19
Keywords: alternatively activated macrophage; GATA3; interleukin-33; itaconate; mitochondrial rewiring; resolution of inlammation; UCP2; uncoupling

IL-3 receptor signalling suppresses chronic intestinal inflammation by controlling mechanobiology and tissue egress of regulatory T cells. - Ullrich, Karen; Derdau, Julia; Baltes, Carsten; Battistella, Alice; Rosso, Gonzalo; Uderhardt, Stefan; Schulze, Lisa; Liu, Lijuan; Dedden, Mark; Spocinska, Marta; Kainka, Lucina; Kubánková, Markéta; et al. (Gut, 2023)
IL-3 has been reported to be involved in various inflammatory disorders, but its role in inflammatory bowel disease (IBD) has not been addressed so far. Here, we determined IL-3 expression in samples from patients with IBD and studied the impact of Il3 or Il3r deficiency on T cell-dependent experimental colitis. We explored the mechanical, cytoskeletal and migratory properties of Il3r -/- and Il3r +/+ T cells using real-time deformability cytometry, atomic force microscopy, scanning electron microscopy, fluorescence recovery after photobleaching and in vitro and in vivo cell trafficking assays. We observed that, in patients with IBD, the levels of IL-3 in the inflamed mucosa were increased. In vivo, experimental chronic colitis on T cell transfer was exacerbated in the absence of Il-3 or Il-3r signalling. This was attributable to Il-3r signalling-induced changes in kinase phosphorylation and actin cytoskeleton structure, resulting in increased mechanical deformability and enhanced egress of Tregs from the inflamed colon mucosa. Similarly, IL-3 controlled mechanobiology in human Tregs and was associated with increased mucosal Treg abundance in patients with IBD. Collectively, our data reveal that IL-3 signaling exerts an important regulatory role at the interface of biophysical and migratory T cell features in intestinal inflammation and suggest that this might be an interesting target for future intervention.
EVALuna2:539503

IL-7 Abrogates the Immunosuppressive Function of Human Double-Negative T Cells by Activating Akt/mTOR Signaling - Allgäuer, Andrea; Schreiner, Elisabeth; Ferrazzi, Fulvia; Ekici, Arif Bülent; Gerbitz, Armin; Mackensen, Andreas; Voelkl, Simon (Journal of Immunology, 2015)
Recently, a novel subset of TCR??(+) CD4(-) CD8(-) double-negative (DN) T cells was described to suppress immune responses in both mice and humans. Moreover, in murine models, infusion and/or activation of DN T cells specifically suppressed alloreactive T cells and prevented the development of graft-versus-host disease after allogeneic hematopoietic stem cell transplantation. We demonstrated that human DN T cells, like their murine counterparts, are highly potent suppressor cells of both CD4(+) and CD8(+) T cell responses. After hematopoietic stem cell transplantation and other lymphopenic conditions, IL-7 plays an important role in the reconstitution, survival, and homeostasis of the T cell compartment. Because IL-7 was shown to interfere with T cell functionality, we asked whether IL-7 affects the functionality of human DN T cells. Intriguingly, IL-7 diminished the suppressive activity of DN T cells toward allogeneic CD4(+) effector T cells. Of interest, our studies revealed that IL-7 activates the Akt/mechanistic target of rapamycin (mTOR) pathway in human DN T cells. Importantly, selective inhibition of the protein kinases Akt or mTOR reversed the IL-7 effect, thereby restoring the functionality of DN T cells, whereas inhibition of other central T cell signaling pathways did not. Further analyses suggest that the IL-7/Akt/mTOR signaling cascade downregulates anergy-associated genes and upregulates activation- and proliferation-associated factors that may be crucial for DN T cell functionality. These findings indicate that IL-7 and Akt/mTOR signaling are critical factors for the suppressive capacity of DN T cells. Targeting of these pathways by pharmacological agents may restore and/or enhance DN T cell functionality in graft-versus-host disease.
EVALuna2:9259

Impact of Siponimod on Enteric and Central Nervous System Pathology in Late-Stage Experimental Autoimmune Encephalomyelitis - Weier, Alicia; Enders, Michael; Kirchner, Philipp; Ekici, Arif Bülent; Bigaud, Marc; Kapitza, Christopher; Wörl, Jürgen; Kuerten, Stefanie (International Journal of Molecular Sciences, 2022)
Multiple sclerosis (MS) is an autoimmune disease of the central nervous system (CNS). Although immune modulation and suppression are effective during relapsing-remitting MS, secondary progressive MS (SPMS) requires neuroregenerative therapeutic options that act on the CNS. The sphingosine-1-phosphate receptor modulator siponimod is the only approved drug for SPMS. In the pivotal trial, siponimod reduced disease progression and brain atrophy compared with placebo. The enteric nervous system (ENS) was recently identified as an additional autoimmune target in MS. We investigated the effects of siponimod on the ENS and CNS in the experimental autoimmune encephalomyelitis model of MS. Mice with late-stage disease were treated with siponimod, fingolimod, or sham. The clinical disease was monitored daily, and treatment success was verified using mass spectrometry and flow cytometry, which revealed peripheral lymphopenia in siponimod- and fingolimod-treated mice. We evaluated the mRNA expression, ultrastructure, and histopathology of the ENS and CNS. Single-cell RNA sequencing revealed an upregulation of proinflammatory genes in spinal cord astrocytes and ependymal cells in siponimod-treated mice. However, differences in CNS and ENS histopathology and ultrastructural pathology between the treatment groups were absent. Thus, our data suggest that siponimod and fingolimod act on the peripheral immune system and do not have pronounced direct neuroprotective effects.
CRIS-Team Scopus Importer:2022-12-09
Keywords: central nervous system; enteric nervous system; experimental autoimmune encephalomyelitis; fingolimod; multiple sclerosis; siponimod

Impact of the Voltage-Gated Calcium Channel Antagonist Nimodipine on the Development of Oligodendrocyte Precursor Cells - Enders, Michael; Weier, Alicia; Chunder, Rittika; An, Young; Bremm, Franziska; Feigenspan, Andreas; Büttner, Christian; Ekici, Arif Bülent; Mingardo, Enrico; Odermatt, Benjamin; Kuerten, Stefanie (International Journal of Molecular Sciences, 2023)
Multiple sclerosis (MS) is an inflammatory demyelinating disease of the central nervous system (CNS). While most of the current treatment strategies focus on immune cell regulation, except for the drug siponimod, there is no therapeutic intervention that primarily aims at neuroprotection and remyelination. Recently, nimodipine showed a beneficial and remyelinating effect in experimental autoimmune encephalomyelitis (EAE), a mouse model of MS. Nimodipine also positively affected astrocytes, neurons, and mature oligodendrocytes. Here we investigated the effects of nimodipine, an L-type voltage-gated calcium channel antagonist, on the expression profile of myelin genes and proteins in the oligodendrocyte precursor cell (OPC) line Oli-Neu and in primary OPCs. Our data indicate that nimodipine does not have any effect on myelin-related gene and protein expression. Furthermore, nimodipine treatment did not result in any morphological changes in these cells. However, RNA sequencing and bioinformatic analyses identified potential micro (mi)RNA that could support myelination after nimodipine treatment compared to a dimethyl sulfoxide (DMSO) control. Additionally, we treated zebrafish with nimodipine and observed a significant increase in the number of mature oligodendrocytes (* p≤ 0.05). Taken together, nimodipine seems to have different positive effects on OPCs and mature oligodendrocytes.
CRIS-Team Scopus Importer:2023-03-10
Keywords: dihydropyridines; MS; myelination; neuroprotection; nimodipine; Oli-Neu; OPC; zebrafish

Impaired ATF3 signaling involves SNAP25 in SOD1 mutant ALS patients - Yazar, Volkan; Kühlwein, Julia K.; Knehr, Antje; Grozdanov, Veselin; Ekici, Arif Bülent; Ludolph, Albert C.; Danzer, Karin M. (Scientific Reports, 2023)
Epigenetic remodeling is emerging as a critical process for several neurodegenerative diseases, including amyotrophic lateral sclerosis (ALS). Genetics alone fails to explain the etiology of ALS, the investigation of the epigenome might therefore provide novel insights into the molecular mechanisms of the disease. In this study, we interrogated the epigenetic landscape in peripheral blood mononuclear cells (PBMCs) of familial ALS (fALS) patients with either chromosome 9 open reading frame 72 (C9orf72) or superoxide dismutase 1 (SOD1) mutation and aimed to identify key epigenetic footprints of the disease. To this end, we used an integrative approach that combines chromatin immunoprecipitation targeting H3K27me3 (ChIP-Seq) with the matching gene expression data to gain new insights into the likely impact of blood-specific chromatin remodeling on ALS-related molecular mechanisms. We demonstrated that one of the hub molecules that modulates changes in PBMC transcriptome in SOD1-mutant ALS patients is ATF3, which has been previously reported in an SOD1 G93A mouse model. We also identified potential suppression of SNAP25, with impaired ATF3 signaling in SOD1-mutant ALS blood. Together, our study shed light on the mechanistic underpinnings of SOD1 mutations in ALS.
CRIS-Team Scopus Importer:2023-08-04

Improved Bladder Tumor RNA Isolation from Archived Tissues Using Methylene Blue for Normalization, Multiplex RNA Hybridization, Sequencing and Subtyping - Köhler, Stefanie; Brandl, Lisa; Strissel, Pamela; Glossner, Laura; Ekici, Arif Bülent; Angeloni, Miriam; Ferrazzi, Fulvia; Bahlinger, Veronika; Hartmann, Arndt; Beckmann, Matthias; Eckstein, Markus; Strick, Reiner (International Journal of Molecular Sciences, 2022)
Methylene blue (MB) is a dye used for histology with clinical importance and intercalates into nucleic acids. After MB staining of formalin fixed paraffin embedded (FFPE) muscle invasive bladder cancer (MIBC) and normal urothelium, specific regions could be microdissected. It is not known if MB influences RNA used for gene expression studies. Therefore, we analyzed MIBC using five different RNA isolation methods comparing patient matched FFPE and fresh frozen (FF) tissues pre-stained with or without MB. We demonstrate a positive impact of MB on RNA integrity with FF tissues using real time PCR with no interference of its chemical properties. FFPE tissues showed no improvement of RNA integrity, which we propose is due to formalin induced nucleotide crosslinks. Using direct multiplex RNA hybridization the best genes for normalization of MIBC and control tissues were identified from 34 reference genes. In addition, 5SrRNA and 5.8SrRNA were distinctive reference genes detecting <200 bp fragments important for mRNA analyses. Using these normalized RNAs from MB stained MIBC and applying multiplex RNA hybridization and mRNA sequencing, a minimal gene expression panel precisely identified luminal and basal MIBC tumor subtypes, important for diagnosis, prognosis and chemotherapy response.
CRIS-Team WoS Importer:2022-09-30

Increased PD-1 Expression on Circulating T Cells Correlates with Inferior Outcome after Autologous Stem Cell Transplantation - Richter, Silja; Böttcher, Martin; Stoll, Andrej; Zeremski, Vanja; Völkl, Simon; Mackensen, Andreas; Ekici, Arif Bülent; Jacobs, Benedikt; Mougiakakos, Dimitrios (Transplantation and Cellular Therapy, 2024)
High-dose chemotherapy followed by autologous stem cell transplantation (auto-SCT) is a well-established treatment option for multiple myeloma and malignant lymphoma patients. It is able to induce long-term progression-free survival (PFS) in both patient groups and even provide a cure in patients with aggressive lymphoma. However, relapse is common and has been associated with the pace and quality of immunologic reconstitution after transplantation, as well as with immune cell exhaustion and immunometabolic defects. We aimed to analyze the dynamics of the prototypical exhaustion marker PD-1 on immune cells during reconstitution on high-dose chemotherapy followed by auto-SCT and its impact on PFS. We performed a comprehensive analysis of exhaustion and metabolic markers on immune cells from myeloma and lymphoma patients undergoing auto-SCT using flow cytometry and NanoString technologies. The expression levels of PD-1 were increased during early reconstitution after transplantation on T cells and natural killer (NK) cells, as well as on monocytes. However, while PD-1 expression in NK cells and monocytes normalized over time, PD-1 expression on T cells demonstrated a variable course. Of note, lymphoma patients with continuously increasing PD-1 expression on T cells after auto-SCT had an inferior median PFS of only 146 days, whereas the median PFS was not reached in the lymphoma patients without such a PD-1 expression pattern. T cells from patients with increased PD-1 expression after auto-SCT exhibited an immunometabolic (over)activation and exhausted phenotype compared to T cells from patients with a low PD-1 expression after transplantation, including higher levels of the glycolytic pacemaker enzyme hexokinase 2 and the inhibitory receptor CTLA-4. In addition, proliferating Ki-67+ T cells were more abundant in patients with high PD-1 expression on T cells compared to those with low expression after auto-SCT (11.9% versus 4.2%). PD-1 expression on T cells might serve as an adverse biomarker for lymphoma patients undergoing auto-SCT; however, further validation by larger prospective studies is required.
CRIS-Team Scopus Importer:2024-04-12
Keywords: auto-SCT; exhaustion; PD-1; T cells

Inflammation-induced glycolytic switch controls suppressivity of mesenchymal stem cells via STAT1 glycosylation - Jitschin, R.; Böttcher, Martin; Saul, D.; Lukassen, Sören; Bruns, Heiko; Loschinski, Romy; Ekici, Arif Bülent; Reis, André; Mackensen, Andreas; Mougiakakos, Dimitrios (Leukemia, 2019)
Mesenchymal stem cells (MSCs) represent key contributors to tissue homeostasis and promising therapeutics for hyperinflammatory conditions including graft-versus-host disease. Their immunomodulatory effects are controlled by microenvironmental signals. The MSCs' functional response towards inflammatory cues is known as MSC-"licensing" and includes indoleamine 2,3-dioxygenase (IDO) upregulation. MSCs use tryptophan-depleting IDO to suppress T-cells. Increasing evidence suggests that several functions are (co-)determined by the cells' metabolic commitment. MSCs are capable of both, high levels of glycolysis and of oxidative phosphorylation. Although several studies have addressed alterations of the immune regulatory phenotype elicited by inflammatory priming metabolic mechanisms controlling this process remain unknown. We demonstrate that inflammatory MSC-licensing causes metabolic shifts including enhanced glycolysis and increased fatty acid oxidation. Yet, only interfering with glycolysis impacts IDO upregulation and impedes T-cell-suppressivity. We identified the Janus kinase (JAK)/signal transducer and activator of transcription (STAT)1 pathway as a regulator of both glycolysis and IDO, and show that enhanced glucose turnover is linked to abundant STAT1 glycosylation. Inhibiting the responsible O-acetylglucosamine (O-GlcNAc) transferase abolishes STAT1 activity together with IDO upregulation. Our data suggest that STAT1-O-GlcNAcylation increases its stability towards degradation thus sustaining downstream effects. This pathway could represent a target for interventions aiming to enhance the MSCs' immunoregulatory potency.
EVALuna2:35805

Inherited mutations in 17 breast cancer susceptibility genes among a large triple-negative breast cancer cohort unselected for family history of breast cancer - Couch, Fergus J.; Hart, Steven N.; Sharma, Priyanka; Toland, Amanda Ewart; Wang, Xianshu; Miron, Penelope; Olson, Janet E.; Godwin, Andrew K.; Pankratz, V. Shane; Olswold, Curtis; Slettedahl, Seth; Hallberg, Emily; et al. (Journal of Clinical Oncology, 2015)
Recent advances in DNA sequencing have led to the development of breast cancer susceptibility gene panels for germline genetic testing of patients. We assessed the frequency of mutations in 17 predisposition genes, including BRCA1 and BRCA2, in a large cohort of patients with triple-negative breast cancer (TNBC) unselected for family history of breast or ovarian cancer to determine the utility of germline genetic testing for those with TNBC.Patients with TNBC (N = 1,824) unselected for family history of breast or ovarian cancer were recruited through 12 studies, and germline DNA was sequenced to identify mutations.Deleterious mutations were identified in 14.6% of all patients. Of these, 11.2% had mutations in the BRCA1 (8.5%) and BRCA2 (2.7%) genes. Deleterious mutations in 15 other predisposition genes were detected in 3.7% of patients, with the majority observed in genes involved in homologous recombination, including PALB2 (1.2%) and BARD1, RAD51D, RAD51C, and BRIP1 (0.3% to 0.5%). Patients with TNBC with mutations were diagnosed at an earlier age (P < .001) and had higher-grade tumors (P = .01) than those without mutations.Deleterious mutations in predisposition genes are present at high frequency in patients with TNBC unselected for family history of cancer. Mutation prevalence estimates suggest that patients with TNBC, regardless of age at diagnosis or family history of cancer, should be considered for germline genetic testing of BRCA1 and BRCA2. Although mutations in other predisposition genes are observed among patients with TNBC, better cancer risk estimates are needed before these mutations are used for clinical risk assessment in relatives.
EVALuna2:9246

Inherited variants in the inner centromere protein (INCENP) gene of the chromosomal passenger complex contribute to the susceptibility of ER-negative breast cancer - Kabisch, Maria; Bermejo, Justo Lorenzo; Duennebier, Thomas; Ying, Shibo; Michailidou, Kyriaki; Bolla, Manjeet K.; Wang, Qin; Dennis, Joe; Shah, Mitul; Perkins, Barbara J.; Czene, Kamila; Darabi, Hatef; et al. (Carcinogenesis, 2015)
The chromosomal passenger complex (CPC) plays a pivotal role in the regulation of cell division. Therefore, inherited CPC variability could influence tumor development. The present candidate gene approach investigates the relationship between single nucleotide polymorphisms (SNPs) in genes encoding key CPC components and breast cancer risk. Fifteen SNPs in four CPC genes (INCENP, AURKB, BIRC5 and CDCA8) were genotyped in 88 911 European women from 39 case-control studies of the Breast Cancer Association Consortium. Possible associations were investigated in fixed-effects meta-analyses. The synonymous SNP rs1675126 in exon 7 of INCENP was associated with overall breast cancer risk [per A allele odds ratio (OR) 0.95, 95% confidence interval (CI) 0.92-0.98, P = 0.007] and particularly with estrogen receptor (ER)-negative breast tumors (per A allele OR 0.89, 95% CI 0.83-0.95, P = 0.0005). SNPs not directly genotyped were imputed based on 1000 Genomes. The SNPs rs1047739 in the 3' untranslated region and rs144045115 downstream of INCENP showed the strongest association signals for overall (per T allele OR 1.03, 95% CI 1.00-1.06, P = 0.0009) and ER-negative breast cancer risk (per A allele OR 1.06, 95% CI 1.02-1.10, P = 0.0002). Two genotyped SNPs in BIRC5 were associated with familial breast cancer risk (top SNP rs2071214: per G allele OR 1.12, 95% CI 1.04-1.21, P = 0.002). The data suggest that INCENP in the CPC pathway contributes to ER-negative breast cancer susceptibility in the European population. In spite of a modest contribution of CPC-inherited variants to the total burden of sporadic and familial breast cancer, their potential as novel targets for breast cancer treatment should be further investigated.
EVALuna2:9268

Inhibited Arginase-1 Expression by Fra-1 in Myeloid Cells Enhance Rheumatoid Arthritis Inflammation - Hannemann, Nicole; Schnelzer, A.; Jordan, J.; Eberhardt, Martin; Schleicher, Ulrike; Uebe, Steffen; Ekici, Arif Bülent; Reid, Stephen; Sonnewald, Sophia; Bäuerle, Tobias; Bogdan, Christian; Vera, Julio; et al. (2017)
EVALuna2:33310

Inhibiting Interleukin 36 Receptor Signaling Reduces Fibrosis in Mice with Chronic Intestinal Inflammation - Scheibe, Kristina; Kersten, Christina; Schmied, Anabel; Vieth, Michael; Primbs, Tatjana; Carlé, Birgitta-Elisabeth; Knieling, Ferdinand; Claussen, Jing; Klimowicz, Alexander C.; Zheng, Jie; Baum, Patrick; Meyer, Sebastian; et al. (Gastroenterology, 2018)
BACKGROUND & AIMS: Intestinal fibrosis is a long-term complication in inflammatory bowel diseases (IBD) frequently resulting in functional damage, bowel obstruction, and surgery. Interleukin 36 (IL36) is a group of cytokines in the IL1 family with inflammatory effects. We studied expression of IL36 and its receptor, interleukin 1 receptor like 2 (IL1RL2 or IL36R) in development of intestinal fibrosis in human tissues and mice. METHODS: We obtained intestinal tissues from 92 patients with Crohn´s disease (CD), 48 patients with ulcerative colitis (UC), and 26 patients without inflammatory bowel diseases (controls). Tissues were analyzed by histology to detect fibrosis and immunohistochemistry to determine the distribution of fibroblasts and levels of IL36R ligands. Human and mouse fibroblasts were incubated with IL36 or control medium, and transcriptome-wide RNA sequences were analyzed. Mice were given neutralizing antibodies against IL36R and we studied intestinal tissues from Il1rl2-/- mice; colitis and fibrosis was induced in mice by repetitive administration of DSS or TNBS. Bone marrow cells were transplanted from Il1rl2-/- to irradiated wild-type mice and intestinal tissues were analyzed. Antibodies against IL36R were applied to mice with established chronic colitis and fibrosis and intestinal tissues were studied. RESULTS: Mucosal and submucosal tissues from patients with CD or UC had higher levels of collagens including type VI collagen compared to tissues from controls. In tissues from patients with fibrostenotic CD, significantly higher levels of IL36A were noted, which correlated with high numbers of activated fibroblasts that expressed alpha smooth muscle actin. IL36R activation of mouse and human fibroblasts resulted in expression of genes that regulate fibrosis and tissue remodeling, as well as expression of collagen type VI. Il1rl2-/- mice and mice given injections of an antibody against IL36R developed less severe colitis and fibrosis following administration of DSS or TNBS, but bone marrow cells from Il1rl2-/- mice did not prevent induction of colitis and fibrosis. Injection of antibodies against IL36R significantly reduced established fibrosis in mice with chronic intestinal inflammation. CONCLUSION: We found higher levels of IL36A in fibrotic intestinal tissues from patients with IBD, compared with controls. IL36 induced expression of genes that regulate fibrogenesis in fibroblasts. Inhibition or knockout of the IL36R in mice reduces chronic colitis and intestinal fibrosis. Agents designed to block IL36R signaling could be developed for prevention and treatment of intestinal fibrosis in patients with IBD.
EVALuna2:35123

INHIBITION OF ARGINASE-1 EXPRESSION BY THE TRANSCRIPTION FACTOR FRA-1 IN MACROPHAGES EXACERBATES RHEUMATOID ARTHRITIS INFLAMMATION - Hannemann, Nicole; Cao, Shan; Schnelzer, A.; Jordan, J.; Eberhardt, Martin; Schleicher, Ulrike; Uebe, Steffen; Ekici, Arif Bülent; Rech, Jürgen; Bäuerle, Tobias; Bogdan, Christian; Vera, Julio; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2019)
CRIS-Team WoS Importer:2019-05-17

Integrative bioinformatics analysis characterizing the role of EDC3 in mRNA decay and its association to intellectual disability - Scheller, Ute; Pfisterer, Kathrin; Uebe, Steffen; Ekici, Arif Bülent; Reis, André; Jamra, Rami; Ferrazzi, Fulvia (Bmc Medical Genomics, 2018)
BACKGROUND: Decapping of mRNA is an important step in the regulation of mRNA turnover and therefore of gene expression, which is a key process controlling development and homeostasis of all organisms. It has been shown that EDC3 plays a role in mRNA decapping, however its function is not well understood. Previously, we have associated a homozygous variant in EDC3 with autosomal recessive intellectual disability. Here, we investigate the functional role of EDC3. METHODS: We performed transcriptome analyses in patients' samples. In addition, we established an EDC3 loss-of-function model using siRNA-based knockdown in the human neuroblastoma cell line SKNBE and carried out RNA sequencing. Integrative bioinformatics analyses were performed to identify EDC3-dependent candidate genes and/or pathways. RESULTS: Our analyses revealed that 235 genes were differentially expressed in patients versus controls. In addition, AU-rich element (ARE)-containing mRNAs, whose degradation in humans has been suggested to involve EDC3, had higher fold changes than non-ARE-containing genes. The analysis of RNA sequencing data from the EDC3 in vitro loss-of-function model confirmed the higher fold changes of ARE-containing mRNAs compared to non-ARE-containing mRNAs and further showed an upregulation of long non-coding and coding RNAs. In total, 764 genes were differentially expressed. Integrative bioinformatics analyses of these genes identified dysregulated candidate pathways, including pathways related to synapses/coated vesicles and DNA replication/cell cycle. CONCLUSION: Our data support the involvement of EDC3 in mRNA decay, including ARE-containing mRNAs, and suggest that EDC3 might be preferentially involved in the degradation of long coding and non-coding RNAs. Furthermore, our results associate ECD3 loss-of-function with synapses-related pathways. Collectively, our data provide novel information that might help elucidate the molecular mechanisms underlying the association of intellectual disability with the dysregulation of mRNA degradation.
EVALuna2:34136

Interspecies Single-Cell RNA-Seq Analysis Reveals the Novel Trajectory of Osteoclast Differentiation and Therapeutic Targets - Omata, Yasunori; Okada, Hiroyuki; Uebe, Steffen; Izawa, Naohiro; Ekici, Arif Bülent; Sarter-Zaiss, Kerstin; Saito, Taku; Schett, Georg; Tanaka, Sakae; Zaiss, Mario (JBMR Plus, 2022)
Bone turnover is finely tuned by cells in the bone milieu, including osteoblasts, osteoclasts, and osteocytes. Osteoclasts are multinucleated giant cells with a bone-resorbing function that play a critical role in regulating skeletal homeostasis. Osteoclast differentiation is characterized by dramatic changes in morphology and gene expression following receptor activator of nuclear factor-kappa-Beta ligand (RANKL) stimulation. We performed single-cell RNA-sequencing analyses of human and murine osteoclast-lineage cells (OLCs) and found that OLCs in the mitotic phase do not differentiate into mature osteoclasts. We also identified a guanosine triphosphatase (GTPase) family member, RAB38, as a highly expressed molecule in both human and murine osteoclast clusters; RAB38 gene expression is associated with dynamic changes in histone modification and transcriptional regulation. Silencing Rab38 expression by using short hairpin RNA (shRNA) inhibited osteoclast differentiation and maturation. In summary, we established an integrated fate map of human and murine osteoclastogenesis; this will help identify therapeutic targets in bone diseases. (c) 2022 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research.
CRIS-Team WoS Importer:2022-05-27

Investigating consanguineous families from Turkey to identify autosomal recessive neurodevelopmental disorders - Gumuslu, Esen; Guemues, Evren; Oz, Ozlem; Ozkan, Melis; Karaer, Kadri; Ekici, Arif Bülent; Yildiz, Edibe Pembegul; Aydinli, Nur; Wiesmann da Silva Reis, André (EUROPEAN JOURNAL OF HUMAN GENETICS, 2022)
CRIS-Team WoS Importer:2022-05-06

Investigating PHF13 induced infertility through single cell transcriptomics and non-vertebrate model organisms - Bosch, Elisabeth; Lukassen, S.; Gregor, Anne; Ekici, Arif Bülent; Zweier, Christiane; Winterpacht, Andreas (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

Investigation of gene-environment interactions between 47 newly identified breast cancer susceptibility loci and environmental risk factors - Rudolph, Anja; Milne, Roger L.; Truong, Therese; Knight, Julia A.; Seibold, Petra; Flesch-Janys, Dieter; Behrens, Sabine; Eilber, Ursula; Bolla, Manjeet K.; Wang, Qin; Dennis, Joe; Dunning, Alison M.; et al. (International Journal of Cancer, 2015)
A large genotyping project within the Breast Cancer Association Consortium (BCAC) recently identified 41 associations between single nucleotide polymorphisms (SNPs) and overall breast cancer (BC) risk. We investigated whether the effects of these 41 SNPs, as well as six SNPs associated with estrogen receptor (ER) negative BC risk are modified by 13 environmental risk factors for BC. Data from 22 studies participating in BCAC were pooled, comprising up to 26,633 cases and 30,119 controls. Interactions between SNPs and environmental factors were evaluated using an empirical Bayes-type shrinkage estimator. Six SNPs showed interactions with associated p-values (pint ) <1.1 × 10(-3) . None of the observed interactions was significant after accounting for multiple testing. The Bayesian False Discovery Probability was used to rank the findings, which indicated three interactions as being noteworthy at 1% prior probability of interaction. SNP rs6828523 was associated with increased ER-negative BC risk in women >=170 cm (OR = 1.22, p = 0.017), but inversely associated with ER-negative BC risk in women <160 cm (OR = 0.83, p = 0.039, pint = 1.9 × 10(-4) ). The inverse association between rs4808801 and overall BC risk was stronger for women who had had four or more pregnancies (OR = 0.85, p = 2.0 × 10(-4) ), and absent in women who had had just one (OR = 0.96, p = 0.19, pint = 6.1 × 10(-4) ). SNP rs11242675 was inversely associated with overall BC risk in never/former smokers (OR = 0.93, p = 2.8 × 10(-5) ), but no association was observed in current smokers (OR = 1.07, p = 0.14, pint = 3.4 × 10(-4) ). In conclusion, recently identified BC susceptibility loci are not strongly modified by established risk factors and the observed potential interactions require confirmation in independent studies.
EVALuna2:9245

In Vivo Protein Complementation Demonstrates Presynaptic α-Synuclein Oligomerization and Age-Dependent Accumulation of 8–16-mer Oligomer Species - Kiechle, Martin; von Einem, Bjoern; Höfs, Lennart; Voehringer, Patrizia; Grozdanov, Veselin; Markx, Daniel; Parlato, Rosanna; Wiesner, Diana; Mayer, Benjamin; Sakk, Olena; Baumann, Bernd; Lukassen, Sören; et al. (Cell Reports, 2019)
Kiechle et al. present two transgenic mouse models that allow direct quantitative and spatial detection of α-synuclein (α-syn) oligomers in vivo. They demonstrate α-syn aggregation at the synapse, age-dependent accumulation of 8–16-mer α-syn oligomer species, and trans-cellular oligomer spreading from forebrain to hindbrain neurons.
CRIS-Team Scopus Importer:2019-12-03
Keywords: aging; alpha-synuclein; neurodegeneration; oligomerization; Parkinson's disease; progressive phenotype; protein-fragment complementation; spreading; synaptic oligomers; transgenic mouse model

KNOCK-OUT OF THE HUMAN ENDOGENOUS RETROVIRUS ERV3 USING CRISPR/CAS9 TECHNOLOGY - Hübner, Hanna; Fahlbusch, Fabian B.; Ekici, Arif Bülent; Vasileiou, Georgia; Beckmann, Matthias; Strick, Reiner; Rübner, Matthias (2016)
EVALuna2:9327

Large-scale evaluation of common variation in regulatory T cell-related genes and ovarian cancer outcome - Charbonneau, Bridget; Moysich, Kirsten B.; Kalli, Kimberly R.; Oberg, Ann L.; Vierkant, Robert A.; Fogarty, Zachary C.; Block, Matthew S.; Maurer, Matthew J.; Goergen, Krista M.; Fridley, Brooke L.; Cunningham, Julie M.; Rider, David N.; et al. (Cancer Immunology Research, 2014)
The presence of regulatory T cells (Treg) in solid tumors is known to play a role in patient survival in ovarian cancer and other malignancies. We assessed inherited genetic variations via 749 tag single-nucleotide polymorphisms (SNP) in 25 Treg-associated genes (CD28, CTLA4, FOXP3, IDO1, IL10, IL10RA, IL15, 1L17RA, IL23A, IL23R, IL2RA, IL6, IL6R, IL8, LGALS1, LGALS9, MAP3K8, STAT5A, STAT5B, TGFB1, TGFB2, TGFB3, TGFBR1, TGRBR2, and TGFBR3) in relation to ovarian cancer survival. We analyzed genotype and overall survival in 10,084 women with invasive epithelial ovarian cancer, including 5,248 high-grade serous, 1,452 endometrioid, 795 clear cell, and 661 mucinous carcinoma cases of European descent across 28 studies from the Ovarian Cancer Association Consortium (OCAC). The strongest associations were found for endometrioid carcinoma and IL2RA SNPs rs11256497 [HR, 1.42; 95% confidence interval (CI), 1.22-1.64; P = 5.7 × 10(-6)], rs791587 (HR, 1.36; 95% CI, 1.17-1.57; P = 6.2 × 10(-5)), rs2476491 (HR, = 1.40; 95% CI, 1.19-1.64; P = 5.6 × 10(-5)), and rs10795763 (HR, 1.35; 95% CI, 1.17-1.57; P = 7.9 × 10(-5)), and for clear cell carcinoma and CTLA4 SNP rs231775 (HR, 0.67; 95% CI, 0.54-0.82; P = 9.3 × 10(-5)) after adjustment for age, study site, population stratification, stage, grade, and oral contraceptive use. The rs231775 allele associated with improved survival in our study also results in an amino acid change in CTLA4 and previously has been reported to be associated with autoimmune conditions. Thus, we found evidence that SNPs in genes related to Tregs seem to play a role in ovarian cancer survival, particularly in patients with clear cell and endometrioid epithelial ovarian cance
EVALuna2:9223

Lifetime ovulatory years and risk of epithelial ovarian cancer: a multinational pooled analysis - Fu, Zhuxuan; Brooks, Maria Mori; Irvin, Sarah; Jordan, Susan; Aben, Katja K. H.; Anton-Culver, Hoda; Bandera, Elisa; Beckmann, Matthias; Berchuck, Andrew; Brooks-Wilson, Angela; Chang-Claude, Jenny; Cook, Linda S.; et al. (Journal of the National Cancer Institute, 2023)
Background The role of ovulation in epithelial ovarian cancer (EOC) is supported by the consistent protective effects of parity and oral contraceptive use. Whether these factors protect through anovulation alone remains unclear. We explored the association between lifetime ovulatory years (LOY) and EOC. Methods LOY was calculated using 12 algorithms. Odds ratios (ORs) and 95% confidence intervals (CIs) estimated the association between LOY or LOY components and EOC among 26 204 control participants and 21 267 case patients from 25 studies. To assess whether LOY components act through ovulation suppression alone, we compared beta coefficients obtained from regression models with expected estimates assuming 1 year of ovulation suppression has the same effect regardless of source. Results LOY was associated with increased EOC risk (OR per year increase = 1.014, 95% CI = 1.009 to 1.020 to OR per year increase = 1.044, 95% CI = 1.041 to 1.048). Individual LOY components, except age at menarche, also associated with EOC. The estimated model coefficient for oral contraceptive use and pregnancies were 4.45 times and 12- to 15-fold greater than expected, respectively. LOY was associated with high-grade serous, low-grade serous, endometrioid, and clear cell histotypes (ORs per year increase = 1.054, 1.040, 1.065, and 1.098, respectively) but not mucinous tumors. Estimated coefficients of LOY components were close to expected estimates for high-grade serous but larger than expected for low-grade serous, endometrioid, and clear cell histotypes. Conclusions LOY is positively associated with nonmucinous EOC. Differences between estimated and expected model coefficients for LOY components suggest factors beyond ovulation underlie the associations between LOY components and EOC in general and for non-HGSOC.
CRIS-Team WoS Importer:2023-04-21

Locally renewing resident synovial macrophages provide a protective barrier for the joint - Culemann, Stephan; Grüneboom, Anika; Nicolás-Ávila, José Ángel; Weidner, Daniela; Lämmle, Katrin Franziska; Rothe, Tobias; Quintana, Juan A.; Kirchner, Philipp; Krljanac, Branislav; Eberhardt, Martin; Ferrazzi, Fulvia; Kretzschmar, Elke; et al. (Nature, 2019)
Macrophages are considered to contribute to chronic inflammatory diseases such as rheumatoid arthritis1. However, both the exact origin and the role of macrophages in inflammatory joint disease remain unclear. Here we use fate-mapping approaches in conjunction with three-dimensional light-sheet fluorescence microscopy and single-cell RNA sequencing to perform a comprehensive spatiotemporal analysis of the composition, origin and differentiation of subsets of macrophages within healthy and inflamed joints, and study the roles of these macrophages during arthritis. We find that dynamic membrane-like structures, consisting of a distinct population of CX3CR1+ tissue-resident macrophages, form an internal immunological barrier at the synovial lining and physically seclude the joint. These barrier-forming macrophages display features that are otherwise typical of epithelial cells, and maintain their numbers through a pool of locally proliferating CX3CR1− mononuclear cells that are embedded into the synovial tissue. Unlike recruited monocyte-derived macrophages, which actively contribute to joint inflammation, these epithelial-like CX3CR1+ lining macrophages restrict the inflammatory reaction by providing a tight-junction-mediated shield for intra-articular structures. Our data reveal an unexpected functional diversification among synovial macrophages and have important implications for the general role of macrophages in health and disease.
CRIS-Team Scopus Importer:2019-08-16

Loss of MTUS1/ATIP expression is associated with adverse outcome in advanced bladder carcinomas: data from a retrospective study - Rogler, Anja; Hoja, Sabine; Giedl, Josef; Ekici, Arif Bülent; Wach, Sven; Taubert, Helge; Goebell, Peter; Wullich, Bernd; Stoeckle, Michael; Lehmann, Jan; Petsch, Sabrina; Hartmann, Arndt; et al. (BMC Cancer, 2014)
Seventy percent of all bladder tumours tend to recur and need intensive surveillance, and a subset of tumours progress to muscle-invasive and metastatic disease. However, it is still difficult to find the adequate treatment for every individual patient as it is a very heterogeneous disease and reliable biomarkers are still missing. In our study we searched for new target genes in the critical chromosomal region 8p and investigated the potential tumour suppressor gene candidate MTUS1/ATIP in bladder cancer.MTUS1 was identified to be the most promising deleted target gene at 8p in aCGH analysis with 19 papillary bladder tumours. A correlation with bladder cancer was further validated using immunohistochemistry of 85 papillary and 236 advanced bladder tumours and in functional experiments. Kaplan-Meier analysis and multivariate Cox-regression addressed overall survival (OS) and disease-specific survival (DSS) as a function of MTUS1/ATIP expression. Bivariate correlations investigated associations between MTUS1/ATIP expression, patient characteristics and histopathology. MTUS1 expression was analysed in cell lines and overexpressed in RT112, where impact on viability, proliferation and migration was measured.MTUS1 protein expression was lost in almost 50% of all papillary and advanced bladder cancers. Survival, however, was only influenced in advanced carcinomas, where loss of MTUS1 was associated with adverse OS and DSS. In this cohort, there was also a significant correlation of MTUS1 expression and histological subtype: positive expression was detected in all micropapillary tumours and aberrant nuclear staining was detected in a subset of plasmocytoid urothelial carcinomas. MTUS1 was expressed in all investigated bladder cell lines and overexpression in RT112 led to significantly decreased viability.MTUS1 is a tumour suppressor gene in cultured bladder cancer cells and in advanced bladder tumours. It might represent one new target gene at chromosome 8p and can be used as an independent prognostic factor for advanced bladder cancer patients. The limitation of the study is the retrospective data analysis. Thus, findings should be validated with a prospective advanced bladder tumour cohort.
EVALuna2:6624

Loss of PHF6 leads to aberrant development of human neuron-like cells - Fliedner, Anna; Gregor, Anne; Ferrazzi, Fulvia; Ekici, Arif Bülent; Sticht, Heinrich; Zweier, Christiane (Scientific Reports, 2020)
Pathogenic variants in PHD finger protein 6 (PHF6) cause Borjeson–Forssman–Lehmann syndrome (BFLS), a rare X-linked neurodevelopmental disorder, which manifests variably in both males and females. To investigate the mechanisms behind overlapping but distinct clinical aspects between genders, we assessed the consequences of individual variants with structural modelling and molecular techniques. We found evidence that de novo variants occurring in females are more severe and result in loss of PHF6, while inherited variants identified in males might be hypomorph or have weaker effects on protein stability. This might contribute to the different phenotypes in male versus female individuals with BFLS. Furthermore, we used CRISPR/Cas9 to induce knockout of PHF6 in SK-N-BE (2) cells which were then differentiated to neuron-like cells in order to model nervous system related consequences of PHF6 loss. Transcriptome analysis revealed a broad deregulation of genes involved in chromatin and transcriptional regulation as well as in axon and neuron development. Subsequently, we could demonstrate that PHF6 is indeed required for proper neuron proliferation, neurite outgrowth and migration. Impairment of these processes might therefore contribute to the neurodevelopmental and cognitive dysfunction in BFLS.
CRIS-Team Scopus Importer:2020-11-13

Lymphocyte Immune Response and T Cell Differentiation in Fontan Patients with protein-losing enteropathy - Moosmann, Julia; Toka, Okan; Lukassen, Sören; Ekici, Arif Bülent; Mackensen, Andreas; Dittrich, Sven; Völkl, Simon (Thoracic and Cardiovascular Surgeon, Supplement, 2021)
Background Protein-losing enteropathy (PLE) is a severe complication of the Fontan circulation. There is increasing discussion about whether lymphatic dysregulation is involved as pathomechanism of PLE. This investigation focuses on the interplay between alteration of lymphatic cells and immunologic pathway alterations. Methods Micro-ribonucleic acid (miRNA) expression profiling was performed in 49 patients (n = 10 Fontan patients with PLE, n = 30 Fontan patients without PLE, and n = 9 patients with dextro-transposition of the great arteries (dTGA). miRNA pathway analysis was performed to identify significantly enriched pathways. To determine lymphocyte populations and subtypes multiparameter flow cytometry was used. Results miRNAs pathway analysis of Fontan patients with PLE revealed 20 significantly changed networks of which four of the ten largest were associated with immunologic processes. This finding is supported by significant T cell deficiency with decreased CD4+ count (p = 0.0002), altered CD4 +/CD8+ ratio, and significantly modified CD4+ (p < 0.0001) and CD8+ (p = 0.0002) T cell differentiation toward effector and terminal differentiated T cells in Fontan patients with PLE. Analyses of CD4+ T cell subsets demonstrated significantly increased frequencies of CD4+ CD25+ CD127- regulatory T cells (Treg) in Fontan patients with PLE (p = 0.0011). Conclusion PLE in Fontan patients is associated with severe lymphopenia, T cell deficiency, significant alterations of T cell differentiation, and increased Treg frequency reflecting an immune status of chronic inflammation and shortened protection against pathogens and autoimmunity. These cellular alterations seemed to be dysregulated by several miRNA controlled immunological pathways.
CRIS-Team Scopus Importer:2021-03-05
Keywords: congenital heart disease (CHD); genetics; genomics; inflammation; systemic

Macrophage phosphoproteome analysis reveals MINCLE-dependent and-independent mycobacterial cord factor signaling - Hansen, Madlen; Peltier, Julian; Killy, Barbara; Amin, Bushra; Bodendorfer, Barbara; HäRtlova, Anetta; Uebel, Sebastian; Bosmann, Markus; Hofmann, Jörg; Büttner, Christian; Ekici, Arif Bülent; Kuttke, Mario; et al. (Molecular & Cellular Proteomics, 2019)
Immune sensing of Mycobacterium tuberculosis relies on recognition by macrophages. Mycobacterial cord factor, trehalose-6,6-dimycolate (TDM), is the most abundant cell wall glycolipid and binds to the C-type lectin receptor (CLR) MINCLE. To explore the kinase signaling linking the TDM-MINCLE interaction to gene expression, we employed quantitative phosphoproteome analysis. TDM caused upregulation of 6.7% and suppressed 3.8% of the 14,000 phospho-sites identified on 3727 proteins. MINCLE-dependent phosphorylation was observed for canonical players of CLR signaling (e.g. PLC, PKC), and was enriched for PKC and GSK3 kinase motifs. MINCLE-dependent activation of the PI3K-AKT-GSK3 pathway contributed to inflammatory gene expression and required the PI3K regulatory subunit p85. Unexpectedly, a substantial fraction of TDM-induced phosphorylation was MINCLE-independent, a finding paralleled by transcriptome data. Bioinformatics analysis of both data sets concurred in the requirement for MINCLE for innate immune response pathways and processes. In contrast, MINCLE-independent phosphorylation and transcriptome responses were linked to cell cycle regulation. Collectively, our global analyses show substantial reprogramming of macrophages by TDM and reveal a dichotomy of MINCLE-dependent and-independent signaling linked to distinct biological responses.
CRIS-Team Scopus Importer:2019-05-02

Manifestation of epilepsy in a patient with EED-related overgrowth (Cohen-Gibson syndrome) - Hetzelt, Katalin; Winterholler, Martin; Kerling, Frank; Rauch, Christophe; Ekici, Arif Bülent; Winterpacht, Andreas; Vasileiou, Georgia; Uebe, Steffen; Thiel, Christian; Kraus, Cornelia; Reis, André; Zweier, Christiane (American Journal of Medical Genetics Part A, 2021)
Cohen-Gibson syndrome is a rare genetic disorder, characterized by fetal or early childhood overgrowth and mild to severe intellectual disability. It is caused by heterozygous aberrations in EED, which encodes an evolutionary conserved polycomb group (PcG) protein that forms the polycomb repressive complex-2 (PRC2) together with EZH2, SUZ12, and RBBP7/4. In total, 11 affected individuals with heterozygous pathogenic variants in EED were reported, so far. All variants affect a few key residues within the EED WD40 repeat domain. By trio exome sequencing, we identified the heterozygous missense variant c.581A > G, p.(Asn194Ser) in exon 6 of the EED-gene in an individual with moderate intellectual disability, overgrowth, and epilepsy. The same pathogenic variant was detected in 2 of the 11 previously reported cases. Epilepsy, however, was only diagnosed in one other individual with Cohen-Gibson syndrome before. Our findings further confirm that the WD40 repeat domain represents a mutational hotspot; they also expand the clinical spectrum of Cohen-Gibson syndrome and highlight the clinical variability even in individuals with the same pathogenic variant. Furthermore, they indicate a possible association between Cohen-Gibson syndrome and epilepsy.
CRIS-Team WoS Importer:2021-09-24

MAP4-dependent regulation of microtubule formation affects centrosome, cilia, and golgi architecture as a central mechanism in growth regulation - Zahnleiter, Diana; Hauer, Nadine; Keßler, Kristin; Uebe, Steffen; Sugano, Yuya; Neuhauss, Stephan C. F.; Gießl, Andreas; Ekici, Arif Bülent; Blessing, Holger; Sticht, Heinrich; Dörr, Helmuth-Günther; Reis, André; et al. (Human Mutation, 2015)
Numerous genes are involved in human growth regulation. Recently, autosomal-recessive inherited variants in centrosomal proteins have been identified in Seckel syndrome, primary microcephaly, or microcephalic osteodysplastic primary dwarfism. Common hallmarks of these syndromic forms are severe short stature and microcephaly. In a consanguineous family with two affected children with severe growth retardation and normocephaly, we used homozygosity mapping and next-generation sequencing to identify a homozygous MAP4 variant. MAP4 is a major protein for microtubule assembly during mitosis. High-expression levels in the somite boundaries of zebrafish suggested a role in growth and body segment patterning. The identified variant affects binding sites of kinases necessary for dynamic instability of microtubule formation. We found centrosome amplifications in mitotic fibroblast cells in vivo and in vitro. These numeric centrosomal aberrations were also present during interphase resulting in aberrant ciliogenesis. Furthermore, affected cells showed a dysfunction of the microtubule-dependent assembly of the Golgi apparatus, indicated by a significant lack of compactness of Golgi membranes. These observations demonstrated that MAP4 mutations contribute to the clinical spectrum of centrosomal defects and confirmed the complex role of a centrosomal protein in centrosomal, ciliary, and Golgi regulation associated with severe short stature.
EVALuna2:9244

Mendelian randomization analyses suggest a role for cholesterol in the development of endometrial cancer - Kho, Pik Fang; Amant, Frederic; Annibali, Daniela; Ashton, Katie; Attia, John; Auer, Paul L.; Beckmann, Matthias; Black, Amanda; Brinton, Louise; Buchanan, Daniel D.; Chanock, Stephen J.; Chen, Chu; et al. (International Journal of Cancer, 2020)
Blood lipids have been associated with the development of a range of cancers, including breast, lung and colorectal cancer. For endometrial cancer, observational studies have reported inconsistent associations between blood lipids and cancer risk. To reduce biases from unmeasured confounding, we performed a bidirectional, two-sample Mendelian randomization analysis to investigate the relationship between levels of three blood lipids (low-density lipoprotein [LDL] and high-density lipoprotein [HDL] cholesterol, and triglycerides) and endometrial cancer risk. Genetic variants associated with each of these blood lipid levels (P < 5 × 10−8) were identified as instrumental variables, and assessed using genome-wide association study data from the Endometrial Cancer Association Consortium (12 906 cases and 108 979 controls) and the Global Lipids Genetic Consortium (n = 188 578). Mendelian randomization analyses found genetically raised LDL cholesterol levels to be associated with lower risks of endometrial cancer of all histologies combined, and of endometrioid and non-endometrioid subtypes. Conversely, higher genetically predicted HDL cholesterol levels were associated with increased risk of non-endometrioid endometrial cancer. After accounting for the potential confounding role of obesity (as measured by genetic variants associated with body mass index), the association between genetically predicted increased LDL cholesterol levels and lower endometrial cancer risk remained significant, especially for non-endometrioid endometrial cancer. There was no evidence to support a role for triglycerides in endometrial cancer development. Our study supports a role for LDL and HDL cholesterol in the development of non-endometrioid endometrial cancer. Further studies are required to understand the mechanisms underlying these findings.
CRIS-Team Scopus Importer:2020-08-14
Keywords: endometrial cancer risk; HDL cholesterol; LDL cholesterol; Mendelian randomization; triglycerides

Meta-analyses identify DNA methylation associated with kidney function and damage - Schlosser, Pascal; Tin, Adrienne; Matias-Garcia, Pamela R.; Thio, Chris H. L.; Joehanes, Roby; Liu, Hongbo; Weihs, Antoine; Yu, Zhi; Hoppmann, Anselm; Grundner-Culemann, Franziska; Min, Josine L.; Adeyemo, Adebowale A.; et al. (Nature Communications, 2021)
Chronic kidney disease is a major public health burden. Elevated urinary albumin-to-creatinine ratio is a measure of kidney damage, and used to diagnose and stage chronic kidney disease. To extend the knowledge on regulatory mechanisms related to kidney function and disease, we conducted a blood-based epigenome-wide association study for estimated glomerular filtration rate (n = 33,605) and urinary albumin-to-creatinine ratio (n = 15,068) and detected 69 and seven CpG sites where DNA methylation was associated with the respective trait. The majority of these findings showed directionally consistent associations with the respective clinical outcomes chronic kidney disease and moderately increased albuminuria. Associations of DNA methylation with kidney function, such as CpGs at JAZF1, PELI1 and CHD2 were validated in kidney tissue. Methylation at PHRF1, LDB2, CSRNP1 and IRF5 indicated causal effects on kidney function. Enrichment analyses revealed pathways related to hemostasis and blood cell migration for estimated glomerular filtration rate, and immune cell activation and response for urinary albumin-to-creatinineratio-associated CpGs.
CRIS-Team WoS Importer:2021-12-17

Meta-analysis of genome-wide association studies identifies common susceptibility polymorphisms for colorectal and endometrial cancer near SH2B3 and TSHZ1 - Cheng, Timothy H. T.; Thompson, Deborah; Painter, Jodie; O'Mara, Tracy; Gorman, Maggie; Martin, Lynn; Palles, Claire; Jones, Angela; Buchanan, Daniel D.; Win, Aung Ko; Hopper, John; Jenkins, Mark; et al. (Scientific Reports, 2015)
High-risk mutations in several genes predispose to both colorectal cancer (CRC) and endometrial cancer (EC). We therefore hypothesised that some lower-risk genetic variants might also predispose to both CRC and EC. Using CRC and EC genome-wide association series, totalling 13,265 cancer cases and 40,245 controls, we found that the protective allele [G] at one previously-identified CRC polymorphism, rs2736100 near TERT, was associated with EC risk (odds ratio (OR) = 1.08, P = 0.000167); this polymorphism influences the risk of several other cancers. A further CRC polymorphism near TERC also showed evidence of association with EC (OR = 0.92; P = 0.03). Overall, however, there was no good evidence that the set of CRC polymorphisms was associated with EC risk, and neither of two previously-reported EC polymorphisms was associated with CRC risk. A combined analysis revealed one genome-wide significant polymorphism, rs3184504, on chromosome 12q24 (OR = 1.10, P = 7.23 × 10(-9)) with shared effects on CRC and EC risk. This polymorphism, a missense variant in the gene SH2B3, is also associated with haematological and autoimmune disorders, suggesting that it influences cancer risk through the immune response. Another polymorphism, rs12970291 near gene TSHZ1, was associated with both CRC and EC (OR = 1.26, P = 4.82 × 10(-8)), with the alleles showing opposite effects on the risks of the two cancers.
EVALuna2:9303

Metabolic rewiring controlled by HIF-1α tunes IgA-producing B-cell differentiation and intestinal inflammation - Meng, Xianyi; Asadi Asadabad, Sahar; Cao, Shan; Song, Rui; Lin, Zhen; Safhi, Mohammed; Qin, Yi; Tcheumi Tactoum, Estelle Manuella; Taudte, Verena; Ekici, Arif Bülent; Mielenz, Dirk; Wirtz, Stefan; et al. (Cellular & Molecular Immunology, 2024)
Germinal centers where B cells undergo clonal expansion and antibody affinity maturation are hypoxic microenvironments. However, the function of hypoxia-inducible factor (HIF)-1α in immunoglobulin production remains incompletely characterized. Here, we demonstrated that B cells lacking HIF-1α exhibited significantly lower glycolytic metabolism and impaired IgA production. Loss of HIF-1α in B cells affects IgA-producing B-cell differentiation and exacerbates dextran sodium sulfate (DSS)-induced colitis. Conversely, promoting HIF-1α stabilization via a PHD inhibitor roxadustat enhances IgA class switching and alleviates intestinal inflammation. Mechanistically, HIF-1α facilitates IgA class switching through acetyl-coenzyme A (acetyl-CoA) accumulation, which is essential for histone H3K27 acetylation at the Sα region. Consequently, supplementation with acetyl-CoA improved defective IgA production in Hif1a-deficient B cells and limited experimental colitis. Collectively, these findings highlight the critical importance of HIF-1α in IgA class switching and the potential for targeting the HIF-1α-dependent metabolic‒epigenetic axis to treat inflammatory bowel diseases and other inflammatory disorders.
CRIS-Team Scopus Importer:2024-11-22
Keywords: B cells; HIF-1α; Hypoxia; IgA; Intestinal inflammation

Microphthalmia is not a mandatory finding in X-linked recessive syndromic microphthalmia caused by the recurrent BCOR variant p.Pro85Leu - Kraus, Cornelia; Uebe, Steffen; Thiel, Christian; Ekici, Arif Bülent; Reis, André; Zweier, Christiane (American Journal of Medical Genetics Part A, 2018)
Mutations in BCOR cause X-linked dominant and X-linked recessive forms of syndromic microphthalmia. By exome sequencing, we identified the recurrent BCOR mutation p.Pro85Leu in two brothers and their unaffected mother. While the older brother's phenotype completely fits the described phenotypic spectrum of X-linked recessive BCOR-associated Lenz microphthalmia syndrome, the younger brother showed developmental delay, microcephaly, and skeletal anomalies, but not the key feature of microphthalmia. In contrast to the previously published families, our findings demonstrate a large variability of BCOR-associated, syndromic phenotypes, indicating incomplete penetrance of p.Pro85Leu with regards to microphthalmia in males.
EVALuna2:34843

MicroRNA Related Polymorphisms and Breast Cancer Risk - Khan, Sofia; Greco, Dario; Michailidou, Kyriaki; Milne, Roger L.; Muranen, Taru A.; Heikkinen, Tuomas; Aaltonen, Kirsimari; Dennis, Joe; Bolla, Manjeet K.; Liu, Jianjun; Hall, Per; Irwanto, Astrid; et al. (PLoS ONE, 2014)
Genetic variations, such as single nucleotide polymorphisms (SNPs) in microRNAs (miRNA) or in the miRNA binding sites may affect the miRNA dependent gene expression regulation, which has been implicated in various cancers, including breast cancer, and may alter individual susceptibility to cancer. We investigated associations between miRNA related SNPs and breast cancer risk. First we evaluated 2,196 SNPs in a case-control study combining nine genome wide association studies (GWAS). Second, we further investigated 42 SNPs with suggestive evidence for association using 41,785 cases and 41,880 controls from 41 studies included in the Breast Cancer Association Consortium (BCAC). Combining the GWAS and BCAC data within a meta-analysis, we estimated main effects on breast cancer risk as well as risks for estrogen receptor (ER) and age defined subgroups. Five miRNA binding site SNPs associated significantly with breast cancer risk: rs1045494 (odds ratio (OR) 0.92; 95% confidence interval (CI): 0.88-0.96), rs1052532 (OR 0.97; 95% CI: 0.95-0.99), rs10719 (OR 0.97; 95% CI: 0.94-0.99), rs4687554 (OR 0.97; 95% CI: 0.95-0.99, and rs3134615 (OR 1.03; 95% CI: 1.01-1.05) located in the 3' UTR of CASP8, HDDC3, DROSHA, MUSTN1, and MYCL1, respectively. DROSHA belongs to miRNA machinery genes and has a central role in initial miRNA processing. The remaining genes are involved in different molecular functions, including apoptosis and gene expression regulation. Further studies are warranted to elucidate whether the miRNA binding site SNPs are the causative variants for the observed risk effects.
EVALuna2:9235

MiR-29 related deposition of extracellular matrix in Fuchs endothelial corneal dystrophy - Matthaei, Mario; Clahsen, Thomas; Büttner, Christian; Ekici, Arif Bülent; Siebelmann, Sebastian; Heindl, Ludwig M.; Bachmann, Bjoern; Cursiefen, Claus; Hribek, Agathe (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2020)
CRIS-Team WoS Importer:2020-09-11

Mitochondrial DNA copy number is associated with mortality and infections in a large cohort of patients with chronic kidney disease - Fazzini, Federica; Lamina, Claudia; Fendt, Liane; Schultheiss, Ulla T.; Kotsis, Fruzsina; Hicks, Andrew A.; Meiselbach, Heike; Weissensteiner, Hansi; Forer, Lukas; Krane, Vera; Eckardt, Kai-Uwe; Köttgen, Anna; et al. (Kidney International, 2019)
Damage of mitochondrial DNA (mtDNA) with reduction in copy number has been proposed as a biomarker for mitochondrial dysfunction and oxidative stress. Chronic kidney disease (CKD) is associated with increased mortality and risk of cardiovascular disease, but the underlying mechanisms remain incompletely understood. Here we investigated the prognostic role of mtDNA copy number for cause-specific mortality in 4812 patients from the German Chronic Kidney Disease study, an ongoing prospective observational national cohort study of patients with CKD stage G3 and A1-3 or G1-2 with overt proteinuria (A3) at enrollment. MtDNA was quantified in whole blood using a plasmid-normalized PCR-based assay. At baseline, 1235 patients had prevalent cardiovascular disease. These patients had a significantly lower mtDNA copy number than patients without cardiovascular disease (fully-adjusted model: odds ratio 1.03, 95% confidence interval [CI] 1.01-1.05 per 10 mtDNA copies decrease). After four years of follow-up, we observed a significant inverse association between mtDNA copy number and all-cause mortality, adjusted for kidney function and cardiovascular disease risk factors (hazard ratio 1.37, 95% CI 1.09-1.73 for quartile 1 compared to quartiles 2-4). When grouped by causes of death, estimates pointed in the same direction for all causes but in a fully-adjusted model decreased copy numbers were significantly lower only in infection-related death (hazard ratio 1.82, 95% CI 1.08-3.08). A similar association was observed for hospitalizations due to infections in 644 patients (hazard ratio 1.19, 95% CI 1.00-1.42 in the fully-adjusted model). Thus, our data support a role of mitochondrial dysfunction in increased cardiovascular disease and mortality risks as well as susceptibility to infections in patients with CKD.
CRIS-Team Scopus Importer:2019-07-02
Keywords: chronic kidney disease; infections; mitochondrial DNA copy number; mortality

Mono-allelic deleterious variants in autosomal recessive skeletal dysplasia genes are strongly associated with idiopathic short stature - Thiel, C. T.; Hauer, Nadine; Vogl, C.; Uebe, Steffen; Sticht, Heinrich; Ekici, Arif Bülent; Kraus, Cornelia; Dörr, Helmuth-Günther; Reis, André (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

Mutations in BRCA1/2 and Other Panel Genes in Patients With Metastatic Breast Cancer -Association With Patient and Disease Characteristics and Effect on Prognosis - Fasching, Peter; Yadav, Siddhartha; Hu, Chunling; Wunderle, Marius; Häberle, Lothar; Hart, Steven N.; Rübner, Matthias; Polley, Eric C.; Lee, Kun Y.; Gnanaolivu, Rohan D.; Hadji, Peyman; Hübner, Hanna; et al. (Journal of Clinical Oncology, 2021)
PURPOSE: Among patients with metastatic breast cancer (mBC), the frequency of germline mutations in cancer susceptibility genes and the clinical relevance of these mutations are unclear. In this study, a prospective cohort of patients with mBC was used to determine mutation rates for breast cancer (BC) predisposition genes, to evaluate the clinical characteristics of patients with mutations, and to assess the influence of mutations on patient outcome. PATIENTS AND METHODS: Germline DNA from 2,595 patients with mBC enrolled in the prospective PRAEGNANT registry was evaluated for mutations in cancer predisposition genes. The frequencies of mutations in known BC predisposition genes were compared with results from a prospective registry of patients with nonmetastatic BC sequenced using the same QIAseq method and with public reference controls. Associations between mutation status and tumor characteristics, progression-free survival, and overall survival were assessed. RESULTS: Germline mutations in 12 established BC predisposition genes (including BRCA1 and BRCA2) were detected in 271 (10.4%) patients. A mutation in BRCA1 or BRCA2 was seen in 129 patients (5.0%). BRCA1 mutation carriers had a higher proportion of brain metastasis (27.1%) compared with nonmutation carriers (12.8%). Mutations were significantly enriched in PRAEGNANT patients with mBC compared with patients with nonmetastatic BC (10.4% v 6.6%, P < .01). Mutations did not significantly modify progression-free survival or overall survival for patients with mBC. CONCLUSION: Multigene panel testing may be considered in all patients with mBC because of the high frequency of germline mutations in BRCA1/2 and other BC predisposition genes. Although the prognosis of mutation carriers and nonmutation carriers with mBC was similar, differences observed in tumor characteristics have implications for treatment and for future studies of targeted therapies.
CRIS-Team Scopus Importer:2021-06-04

Mutations in the BAF-Complex Subunit DPF2 Are Associated with Coffin-Siris Syndrome - Vasileiou, Georgia; Vergarajauregui, Silvia; Endele, Sabine; Popp, Bernt; Büttner, Christian; Ekici, Arif Bülent; Gerard, Marion; Bramswig, Nuria C.; Albrecht, Beate; Clayton-Smith, Jill; Morton, Jenny; Tomkins, Susan; et al. (American Journal of Human Genetics, 2018)
Variants affecting the function of different subunits of the BAF chromatin-remodelling complex lead to various neurodevelopmental syndromes, including Coffin-Siris syndrome. Furthermore, variants in proteins containing PHD fingers, motifs recognizing specific histone tail modifications, have been associated with several neurological and developmental-delay disorders. Here, we report eight heterozygous de novo variants (one frameshift, two splice site, and five missense) in the gene encoding the BAF complex subunit double plant homeodomain finger 2 (DPF2). Affected individuals share common clinical features described in individuals with Coffin-Siris syndrome, including coarse facial features, global developmental delay, intellectual disability, speech impairment, and hypoplasia of fingernails and toenails. All variants occur within the highly conserved PHD1 and PHD2 motifs. Moreover, missense variants are situated close to zinc binding sites and are predicted to disrupt these sites. Pull-down assays of recombinant proteins and histone peptides revealed that a subset of the identified missense variants abolish or impaire DPF2 binding to unmodified and modified H3 histone tails. These results suggest an impairment of PHD finger structural integrity and cohesion and most likely an aberrant recognition of histone modifications. Furthermore, the overexpression of these variants in HEK293 and COS7 cell lines was associated with the formation of nuclear aggregates and the recruitment of both wild-type DPF2 and BRG1 to these aggregates. Expression analysis of truncating variants found in the affected individuals indicated that the aberrant transcripts escape nonsense-mediated decay. Altogether, we provide compelling evidence that de novo variants in DPF2 cause Coffin-Siris syndrome and propose a dominant-negative mechanism of pathogenicity.

Mutations in the BAF-complex subunit DPF2 are associated with Coffin-Siris syndrome - Vasileiou, G.; Vergarajauregui, S.; Endele, Sabine; Popp, Bernt; Büttner, Christian; Ekici, Arif Bülent; Gerard, M.; Bramswig, N. C.; Albrecht, B.; Clayton-Smith, J.; Morton, J.; Tomkins, S.; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2019)
CRIS-Team WoS Importer:2019-10-25

Mutual Amplification of GLI2/Hedgehog and Transcription Factor JUN/AP-1 Signaling in Fibroblasts in Systemic Sclerosis: Potential Implications for Combined Therapies - Bergmann, Christina; Chenguiti Fakhouri, Sara; Trinh-Minh, Thuong; Filla, Tim; Rius Rigau, Aleix Rius; Ekici, Arif Bülent; Merlevede, Benita; Hallenberger, Ludwig; Zhu, Honglin; Dees, Clara; Matei, Alexandru Emil; Auth, Janina; et al. (Arthritis and Rheumatology, 2024)
Objective: Deregulation of the cJUN/AP-1 and hedgehog/GLI2 signaling pathways has been implicated in fibroblast activation in systemic sclerosis (SSc). However, the consequences of their concomitant up-regulation are unknown. Here, we tested the hypothesis that mutual amplification of both pathways might drive persistent fibroblast activation. Methods: Cultured fibroblasts and skin sections of patients with diffuse SSc and healthy volunteers were analyzed. cJUN/AP-1 signaling and hedgehog/GLI2 signaling were inhibited using knockdown and pharmacologic approaches. Hedgehog signaling was activated in mice by fibroblast-specific overexpression of constitutively active Smoothened. Results: cJUN and GLI2 are concomitantly up-regulated and colocalize in fibroblasts of patients with SSc compared to healthy controls. Activation of hedgehog/GLI2 signaling induces the expression of cJUN in vitro and in vivo, whereas inactivation of GLI2 inhibits cJUN expression. Likewise, inactivation of cJUN impairs the expression of GLI2. This mutual regulation occurs at the level of transcription with binding of cJUN and GLI2 to specific binding motifs. Interference with this mutual amplification of cJUN signaling and GLI2 signaling inhibits fibroblast activation and collagen release: Inhibition of cJUN/AP-1 signaling ameliorates hedgehog-induced fibroblast activation and skin fibrosis in SmoACT mice with a reduction of skin thickness of 103% (P = 0.0043) in the treatment group compared to the fibrotic control group. Moreover, combined pharmacologic inhibition of cJUN/AP-1 and hedgehog/GLI2 exerts additive antifibrotic effects in a model of TGFβ-driven experimental fibrosis (TBRACT mice). Conclusion: The transcription factors cJUN and GLI2 reinforce each other's activity to promote fibroblast activation in SSc. Interruption of this crosstalk by combined inhibition of both pathways exerts additive antifibrotic effects at well-tolerated doses.
CRIS-Team Scopus Importer:2024-12-06

Mycobacterial Cord Factor Reprograms the Macrophage Response to IFN-γ towards Enhanced Inflammation yet Impaired Antigen Presentation and Expression of GBP1 - Huber, Alexandra; Killy, Barbara; Grummel, Nadine; Bodendorfer, Barbara; Paul, Sushmita; Wiesmann, Veit; Naschberger, Elisabeth; Zimmer, Jana; Wirtz, Stefan; Schleicher, Ulrike; Vera, Julio; Ekici, Arif Bülent; et al. (Journal of Immunology, 2020)
Mycobacteria survive in macrophages despite triggering pattern recognition receptors and T cell-derived IFN-γ production. Mycobacterial cord factor trehalose-6,6-dimycolate (TDM) binds the C-type lectin receptor MINCLE and induces inflammatory gene expression. However, the impact of TDM on IFN-γ-induced macrophage activation is not known. In this study, we have investigated the cross-regulation of the mouse macrophage transcriptome by IFN-γ and by TDM or its synthetic analogue trehalose-6,6-dibehenate (TDB). As expected, IFN-γ induced genes involved in Ag presentation and antimicrobial defense. Transcriptional programs induced by TDM and TDB were highly similar but clearly distinct from the response to IFN-γ. The glycolipids enhanced expression of a subset of IFN-γ-induced genes associated with inflammation. In contrast, TDM/TDB exerted delayed inhibition of IFN-γ-induced genes, including pattern recognition receptors, MHC class II genes, and IFN-γ-induced GTPases, with antimicrobial function. TDM downregulated MHC class II cell surface expression and impaired T cell activation by peptide-pulsed macrophages. Inhibition of the IFN-γ-induced GTPase GBP1 occurred at the level of transcription by a partially MINCLE-dependent mechanism that may target IRF1 activity. Although activation of STAT1 was unaltered, deletion of Socs1 relieved inhibition of GBP1 expression by TDM. Nonnuclear Socs1 was sufficient for inhibition, suggesting a noncanonical, cytoplasmic mechanism. Taken together, unbiased analysis of transcriptional reprogramming revealed a significant degree of negative regulation of IFN-γ-induced Ag presentation and antimicrobial gene expression by the mycobacterial cord factor that may contribute to mycobacterial persistence.
CRIS-Team Scopus Importer:2020-09-18

Myeloperoxidase Modulates Inflammation in Generalized Pustular Psoriasis and Additional Rare Pustular Skin Diseases - Haskamp, Stefan; Bruns, Heiko; Hahn, Madelaine; Hoffmann, Markus; Gregor, Anne; Löhr, Sabine; Hahn, Jonas; Ringer, Mark; Flamann, Cindy; Frey, Benjamin; Lesner, Adam; Thiel, Christian; et al. (American Journal of Human Genetics, 2020)
Generalized pustular psoriasis (GPP) is a severe multi-systemic inflammatory disease characterized by neutrophilic pustulosis and triggered by pro-inflammatory IL-36 cytokines in skin. While 19%–41% of affected individuals harbor bi-allelic mutations in IL36RN, the genetic cause is not known in most cases. To identify and characterize new pathways involved in the pathogenesis of GPP, we performed whole-exome sequencing in 31 individuals with GPP and demonstrated effects of mutations in MPO encoding the neutrophilic enzyme myeloperoxidase (MPO). We discovered eight MPO mutations resulting in MPO -deficiency in neutrophils and monocytes. MPO mutations, primarily those resulting in complete MPO deficiency, cumulatively associated with GPP (p = 1.85E−08; OR = 6.47). The number of mutant MPO alleles significantly differed between 82 affected individuals and >4,900 control subjects (p = 1.04E−09); this effect was stronger when including IL36RN mutations (1.48E−13) and correlated with a younger age of onset (p = 0.0018). The activity of four proteases, previously implicated as activating enzymes of IL-36 precursors, correlated with MPO deficiency. Phorbol-myristate-acetate-induced formation of neutrophil extracellular traps (NETs) was reduced in affected cells (p = 0.015), and phagocytosis assays in MPO-deficient mice and human cells revealed altered neutrophil function and impaired clearance of neutrophils by monocytes (efferocytosis) allowing prolonged neutrophil persistence in inflammatory skin. MPO mutations contribute significantly to GPP's pathogenesis. We implicate MPO as an inflammatory modulator in humans that regulates protease activity and NET formation and modifies efferocytosis. Our findings indicate possible implications for the application of MPO inhibitors in cardiovascular diseases. MPO and affected pathways represent attractive targets for inducing resolution of inflammation in neutrophil-mediated skin diseases.
CRIS-Team Scopus Importer:2020-09-11
Keywords: ACH; acrodermatitis continua suppurativa Hallopeau; activation of IL-36 precursors; acute generalized 4 exanthematous pustulosis; AGEP; efferocytosis; generalized pustular psoriasis; GPP; impaired NETosis; MPO deficiency; myeloperoxidase; oligogenic inheritance

Need for high-resolution Genetic Analysis in iPSC: Results and Lessons from the ForIPS Consortium - Popp, Bernt; Krumbiegel, Mandy; Grosch, Janina; Sommer, Annika; Uebe, Steffen; Kohl, Zacharias; Ploetz, Sonja; Farrell, Michaela; Trautmann, Udo; Kraus, Cornelia; Ekici, Arif Bülent; Asadollahi, Reza; et al. (Scientific Reports, 2018)
Genetic integrity of induced pluripotent stem cells (iPSCs) is essential for their validity as disease models and for potential therapeutic use. We describe the comprehensive analysis in the ForIPS consortium: an iPSC collection from donors with neurological diseases and healthy controls. Characterization included pluripotency confirmation, fingerprinting, conventional and molecular karyotyping in all lines. In the majority, somatic copy number variants (CNVs) were identified. A subset with available matched donor DNA was selected for comparative exome sequencing. We identified single nucleotide variants (SNVs) at different allelic frequencies in each clone with high variability in mutational load. Low frequencies of variants in parental fibroblasts highlight the importance of germline samples. Somatic variant number was independent from reprogramming, cell type and passage. Comparison with disease genes and prediction scores suggest biological relevance for some variants. We show that high-throughput sequencing has value beyond SNV detection and the requirement to individually evaluate each clone.
EVALuna2:34839

Neonatal nephron loss during active nephrogenesis results in altered expression of renal developmental genes and markers of kidney injury - Raming, Roman; Cordasic, Nada; Kirchner, Philipp; Ekici, Arif Bülent; Fahlbusch, Fabian; Wölfle, Joachim; Hilgers, Karl Friedrich; Hartner, Andrea; Menendez-Castro, Carlos (Physiological Genomics, 2021)
Preterm neonates are at a high risk for nephron loss under adverse clinical conditions. Renal damage potentially collides with postnatal nephrogenesis. Recent animal studies suggest that nephron loss within this vulnerable phase leads to renal damage later in life. Nephrogenic pathways are commonly reactivated after kidney injury supporting renal regeneration. We hypothesized that nephron loss during nephrogenesis affects renal development, which, in turn, impairs tissue repair after secondary injury. Neonates prior to 36 wk of gestation show an active nephrogenesis. In rats, nephrogenesis is ongoing until day 10 after birth. Mimicking the situation of severe nephron loss during nephrogenesis, male pups were uninephrectomized at day 1 of life (UNXd1). A second group of males was uninephrectomized at postnatal day 14 (UNXd14), after terminated nephrogenesis. Agematched controls were sham operated. Three days after uninephrectomy transcriptional changes in the right kidney were analyzed by RNA-sequencing, followed by functional pathway analysis. In UNXd1, 1,182 genes were differentially regulated, but only 143 genes showed a regulation both in UNXd1 and UNXd14. The functional groups “renal development” and “kidney injury” were among the most differentially regulated groups and revealed distinctive alterations. Reduced expression of candidate genes concerning renal development (Bmp7, Gdnf, Pdgf-B, Wt1) and injury (nephrin, podocin, Tgf-b 1) were detected. The downregulation of Bmp7 and Gdnf persisted until day 28. In UNXd14, Six2 was upregulated and Pax2 was downregulated. We conclude that nephron loss during nephrogenesis affects renal development and induces a specific regulation of genes that might hinder tissue repair after secondary kidney injury.
CRIS-Team Scopus Importer:2021-12-17
Keywords: Neonatal nephron loss; Neonatal uninephrectomy; Nephrogenesis; Renal regeneration; RNA-sequencing

Network- and systems-based re-engineering of dendritic cells with non-coding RNAs for cancer immunotherapy - Lai, Xin; Dreyer, Florian; Cantone, Martina; Eberhardt, Martin; Gerer, Kerstin F.; Jaitly, Tanushree; Uebe, Steffen; Lischer, Christopher; Ekici, Arif Bülent; Wittmann, Jürgen; Jäck, Hans-Martin; Schaft, Niels; et al. (Theranostics, 2021)
Dendritic cells (DCs) are professional antigen-presenting cells that induce and regulate adaptive immunity by presenting antigens to T cells. Due to their coordinative role in adaptive immune responses, DCs have been used as cell-based therapeutic vaccination against cancer. The capacity of DCs to induce a therapeutic immune response can be enhanced by re-wiring of cellular signalling pathways with microRNAs (miRNAs). Methods: Since the activation and maturation of DCs is controlled by an interconnected signalling network, we deploy an approach that combines RNA sequencing data and systems biology methods to delineate miRNA-based strategies that enhance DC-elicited immune responses. Results: Through RNA sequencing of IKKβ-matured DCs that are currently being tested in a clinical trial on therapeutic anti-cancer vaccination, we identified 44 differentially expressed miRNAs. According to a network analysis, most of these miRNAs regulate targets that are linked to immune pathways, such as cytokine and interleukin signalling. We employed a network topology-oriented scoring model to rank the miRNAs, analysed their impact on immunogenic potency of DCs, and identified dozens of promising miRNA candidates, with miR-15a and miR-16 as the top ones. The results of our analysis are presented in a database that constitutes a tool to identify DC-relevant miRNA-gene interactions with therapeutic potential (www.synmirapy.net/dc-optimization). Conclusions: Our approach enables the systematic analysis and identification of functional miRNA-gene interactions that can be experimentally tested for improving DC immunogenic potenc
CRIS-Team WoS Importer:2020-12-11
Keywords: dendritic cell; therapeutic vaccination in cancer; systems biology; network biology; microRNAs: bioinformatics

Network-Based Integration of GWAS and Gene Expression Identifies a HOX-Centric Network Associated with Serous Ovarian Cancer Risk - Kar, Siddhartha P.; Tyrer, Jonathan P.; Li, Qiyuan; Lawrenson, Kate; Aben, Katja K. H.; Anton-Culver, Hoda; Antonenkova, Natalia; Chenevix-Trench, Georgia; Baker, Helen; Bandera, Elisa V.; Bean, Yukie T.; Beckmann, Matthias; et al. (Cancer Epidemiology Biomarkers & Prevention, 2015)
Genome-wide association studies (GWAS) have so far reported 12 loci associated with serous epithelial ovarian cancer (EOC) risk. We hypothesized that some of these loci function through nearby transcription factor (TF) genes and that putative target genes of these TFs as identified by coexpression may also be enriched for additional EOC risk associations.We selected TF genes within 1 Mb of the top signal at the 12 genome-wide significant risk loci. Mutual information, a form of correlation, was used to build networks of genes strongly coexpressed with each selected TF gene in the unified microarray dataset of 489 serous EOC tumors from The Cancer Genome Atlas. Genes represented in this dataset were subsequently ranked using a gene-level test based on results for germline SNPs from a serous EOC GWAS meta-analysis (2,196 cases/4,396 controls).Gene set enrichment analysis identified six networks centered on TF genes (HOXB2, HOXB5, HOXB6, HOXB7 at 17q21.32 and HOXD1, HOXD3 at 2q31) that were significantly enriched for genes from the risk-associated end of the ranked list (P < 0.05 and FDR < 0.05). These results were replicated (P < 0.05) using an independent association study (7,035 cases/21,693 controls). Genes underlying enrichment in the six networks were pooled into a combined network.We identified a HOX-centric network associated with serous EOC risk containing several genes with known or emerging roles in serous EOC development.Network analysis integrating large, context-specific datasets has the potential to offer mechanistic insights into cancer susceptibility and prioritize genes for experimental characterization. Cancer Epidemiol Biomarkers Prev; 24(10); 1574-84. ©2015 AACR.
EVALuna2:9287

Neutral sphingomyelinase mediates the co-morbidity trias of alcohol abuse, major depression and bone defects - Kalinichenko, Liubov; Mühle, Christiane; Jia, Tianye; Anderheiden, Felix; Datz, Maria; Eberle, Anna-Lisa; Eulenburg, Volker; Granzow, Jonas; Hofer, Martin Jürgen; Hohenschild, Julia; Huber, Sabine; Kämpf, Stefanie; et al. (Molecular Psychiatry, 2021)
Mental disorders are highly comorbid and occur together with physical diseases, which are often considered to arise from separate pathogenic pathways. We observed in alcohol-dependent patients increased serum activity of neutral sphingomyelinase. A genetic association analysis in 456,693 volunteers found associations of haplotypes of SMPD3 coding for NSM-2 (NSM) with alcohol consumption, but also with affective state, and bone mineralisation. Functional analysis in mice showed that NSM controls alcohol consumption, affective behaviour, and their interaction by regulating hippocampal volume, cortical connectivity, and monoaminergic responses. Furthermore, NSM controlled bone–brain communication by enhancing osteocalcin signalling, which can independently supress alcohol consumption and reduce depressive behaviour. Altogether, we identified a single gene source for multiple pathways originating in the brain and bone, which interlink disorders of a mental–physical co-morbidity trias of alcohol abuse—depression/anxiety—bone disorder. Targeting NSM and osteocalcin signalling may, thus, provide a new systems approach in the treatment of a mental–physical co-morbidity trias.
CRIS-Team Scopus Importer:2021-10-08

Nimodipine Exerts Beneficial Effects on the Rat Oligodendrocyte Cell Line OLN-93 - Boltz, Felix; Enders, Michael; Feigenspan, Andreas; Kirchner, Philipp; Ekici, Arif Bülent; Kürten, Stefanie (Brain Sciences, 2022)
Multiple sclerosis (MS) is a chronic autoimmune disease of the central nervous system (CNS). Therapy is currently limited to drugs that interfere with the immune system; treatment options that primarily mediate neuroprotection and prevent neurodegeneration are not available. Here, we studied the effects of nimodipine on the rat cell line OLN-93, which resembles young mature oligodendrocytes. Nimodipine is a dihydropyridine that blocks the voltage-gated L-type calcium channel family members Cav1.2 and Cav1.3. Our data show that the treatment of OLN-93 cells with nimodipine induced the upregulation of myelin genes, in particular of proteolipid protein 1 (Plp1), which was confirmed by a significantly greater expression of PLP1 in immunofluorescence analysis and the presence of myelin structures in the cytoplasm at the ultrastructural level. Whole-genome RNA sequencing additionally revealed the upregulation of genes that are involved in neuroprotection, remyelination, and antioxidation pathways. Interestingly, the observed effects were independent of Cav1.2 and Cav1.3 because OLN-93 cells do not express these channels, and there was no measurable response pattern in patch-clamp analysis. Taking into consideration previous studies that demonstrated a beneficial effect of nimodipine on microglia, our data support the notion that nimodipine is an interesting drug candidate for the treatment of MS and other demyelinating diseases.
CRIS-Team Scopus Importer:2022-05-06
Keywords: dihydropyridines; MS; myelination; neuroprotection; nimodipine; OLN-93

NLRP3 Inhibition Leads to Impaired Mucosal Fibroblast Function in Patients with Inflammatory Bowel Diseases - Weber, Simone; Sitte, Selina; Vögele, Anna-Lena; Sologub, Ludmilla; Wilfer, Angelika; Rath, Timo; Nägel, Andreas; Zundler, Sebastian; Franchi, Luigi; Opipari, Anthony W.; Sonnewald, Sophia; Reid, Stephen; et al. (Journal of Crohns & Colitis, 2023)
Background and Aims: Inflammatory bowel diseases (IBD) are characterized by mucosal inflammation and sequential fibrosis formation, but the exact role of the hyperactive NLRP3 inflammasome in these processes is unclear. Thus, we studied the expression and function of the NLRP3 inflammasome in the context of inflammation and fibrosis in IBD. Methods: We analysed intestinal NLRP3 expression in mucosal immune cells and fibroblasts from IBD patients and NLRP3-associated gene expression via single-cell RNA sequencing and microarray analyses. Furthermore, cytokine secretion of NLRP3 inhibitor treated blood and mucosal cells, as well as proliferation, collagen production, and cell death of NLRP3 inhibitor treated intestinal fibroblasts from IBD patients were studied. Results: We found increased NLRP3 expression in the inflamed mucosa of IBD patients and NLRP3 inhibition led to reduced IL-1β and IL-18 production in blood cells and diminished the bioactive form of mucosal IL-1β. Single cell analysis identified overlapping expression patterns of NLRP3 and IL-1β in classically activated intestinal macrophages and we also detected NLRP3 expression in CD163+ macrophages. In addition, NLRP3 expression was also found in intestinal fibroblasts from IBD patients. Inhibition of NLRP3 led to reduced proliferation of intestinal fibroblasts, which was associated with a marked decrease in production of collagen type I and type VI in IBD patients. Moreover, NLRP3 inhibition in intestinal fibroblasts induced autophagy, a cellular process involved in collagen degradation. Conclusions: In the presented study, we demonstrate that inhibiting NLRP3 might pave the way for novel therapeutic approaches in IBD, especially to prevent the severe complication of intestinal fibrosis formation.
CRIS-Team Scopus Importer:2023-11-17
Keywords: fibroblasts; fibrosis; IL-18; IL-1β; Inflammatory bowel diseases; mucosal immune system; NLRP3 inflammasome; small molecule inhibitor

No clinical utility of KRAS variant rs61764370 for ovarian or breast cancer - Hollestelle, Antoinette; Van Der Baan, Frederieke H.; Berchuck, Andrew; Johnatty, Sharon E.; Aben, Katja K.; Agnarsson, Bjarni A.; Aittomaki, Kristiina; Alducci, Elisa; Andrulis, Irene L.; Anton-Culver, Hoda; Antonenkova, Natalia N.; Antoniou, Antonis C.; et al. (Gynecologic Oncology, 2016)
Clinical genetic testing is commercially available for rs61764370, an inherited variant residing in a KRAS 3' UTR microRNA binding site, based on suggested associations with increased ovarian and breast cancer risk as well as with survival time. However, prior studies, emphasizing particular subgroups, were relatively small. Therefore, we comprehensively evaluated ovarian and breast cancer risks as well as clinical outcome associated with rs61764370.Centralized genotyping and analysis were performed for 140,012 women enrolled in the Ovarian Cancer Association Consortium (15,357 ovarian cancer patients; 30,816 controls), the Breast Cancer Association Consortium (33,530 breast cancer patients; 37,640 controls), and the Consortium of Modifiers of BRCA1 and BRCA2 (14,765 BRCA1 and 7904 BRCA2 mutation carriers).We found no association with risk of ovarian cancer (OR=0.99, 95% CI 0.94-1.04, p=0.74) or breast cancer (OR=0.98, 95% CI 0.94-1.01, p=0.19) and results were consistent among mutation carriers (BRCA1, ovarian cancer HR=1.09, 95% CI 0.97-1.23, p=0.14, breast cancer HR=1.04, 95% CI 0.97-1.12, p=0.27; BRCA2, ovarian cancer HR=0.89, 95% CI 0.71-1.13, p=0.34, breast cancer HR=1.06, 95% CI 0.94-1.19, p=0.35). Null results were also obtained for associations with overall survival following ovarian cancer (HR=0.94, 95% CI 0.83-1.07, p=0.38), breast cancer (HR=0.96, 95% CI 0.87-1.06, p=0.38), and all other previously-reported associations.rs61764370 is not associated with risk of ovarian or breast cancer nor with clinical outcome for patients with these cancers. Therefore, genotyping this variant has no clinical utility related to the prediction or management of these cancers.
EVALuna2:9251

Novel loci for non-syndromic coarctation of the aorta in sporadic and familial cases - Moosmann, Julia; Uebe, Steffen; Dittrich, Sven; Rueffer, Andre; Ekici, Arif Bülent; Toka, Okan (PLoS ONE, 2015)
Coarctation of the aorta (CoA) accounts for 5-8% of all congenital heart defects. CoA can be detected in up to 20% of patients with Ullrich-Turner syndrome (UTS), in which a part or all of one of the X chromosomes is absent. The etiology of non-syndromic CoA is poorly understood. In the present work, we test the hypothesis that rare copy number variation (CNV) especially on the gonosomes, contribute to the etiology of non-syndromic CoA.We performed high-resolution genome-wide CNV analysis using the Affymetrix SNP 6.0 microarray platform for 70 individuals with sporadic CoA, 3 families with inherited CoA (n=13) and 605 controls. Our analysis comprised genome wide association, CNV burden and linkage. CNV was validated by multiplex ligation-dependent probe amplification.We identified a significant abundance of large (>100 kb) CNVs on the X chromosome in males with CoA (p=0.005). 11 out of 51 ( 22%) male cases had these large CNVs. Association analysis in the sporadic cohort revealed 14 novel loci for CoA. The locus on 21q22.3 in the sporadic CoA cohort overlapped with a gene locus identified in all familial cases of CoA (candidate gene TRPM2). We identified one CNV locus within a locus with high multipoint LOD score from a linkage analysis of the familial cases (SEPT9); another locus overlapped with a region implicated in Kabuki syndrome. In the familial cases, we identified a total of 7 CNV loci that were exclusively present in cases but not in unaffected family members.Of all candidate loci identified, the TRPM2 locus was the most frequently implicated autosomal locus in sporadic and familial cases. However, the abundance of large CNVs on the X chromosome of affected males suggests that gonosomal aberrations are not only responsible for syndromic CoA but also involved in the development of sporadic and non-syndromic CoA and their male dominance.
EVALuna2:9256

Novel truncating mutation in CACNA1F in a young male patient diagnosed with optic atrophy - Pasutto, Francesca; Ekici, Arif Bülent; Reis, André; Kremers, Jan; Huchzermeyer, Cord (Ophthalmic Genetics, 2018)
BACKGROUND: Low vision in children can be accompanied by pallor of the optic disc with little or no characteristic morphologic changes of the retina. A variety of diseases can be the underlying cause, including hereditary optic atrophy, Leber's congenital amaurosis (LCA), achromatopsia, and calcium channel, voltage-dependent, L-type, alpha-1F subunit gene (CACNA1F)-associated retinopathy (most widely known as incomplete congenital stationary night blindness: iCSNB). Differentiation at early age is desirable due to large differences in prognosis, but may be difficult because phenotypes overlap and electrophysiological testing is challenging in young patients. We present the case of a 6-year-old boy with unexplained low vision and pallor of the optic disc who originally had been diagnosed with hereditary optic atrophy in the absence of recordable full-field electroretinography (ERG) due to poor patient cooperation. MATERIALS AND METHODS: Standard Sanger sequencing excluded mutations in the OPA1 gene (autosomal-dominant optic atrophy). To identify the underlying genetic cause, whole-exome sequencing was performed on patient's DNA. Recording of the full-field ERG was successfully performed 6 months later. RESULTS: We identified a novel truncating mutation in CACNA1F gene (NM_001256789: c.3895C > T in exon 33) which led to the correct diagnosis of CACNA1F-associated retinopathy in the young boy. ERG recordings showed a negative scotopic mixed response with preserved oscillatory potentials and a flicker ERG with reduced amplitude and biphasic waveform, compatible with a CACNA1F-asssociated phenotype. CONCLUSIONS: We show that genetic testing may help to differentiate between optic atrophy, LCA, and CACNA1F-associated retinopathy at a much earlier age, in absence of electrophysiological examination and by widely overlapping phenotypes.
EVALuna2:34838

Oligodendrocytes regulate the adhesion molecule ICAM-1 in neuroinflammation - Alvarado, M. N. Gonzalez; Aprato, J.; Baumeister, M.; Ekici, Arif Bülent; Kirchner, P.; Hoffmann, Alana; Winkler, Jürgen; Wegner, M.; Haase, S.; Linker, R. (Glia, 2021)
Recently, oligodendrocytes (Ol) have been attributed potential immunomodulatory effects. Yet, the exact mode of interaction with pathogenic CNS infiltrating lymphocytes remains unclear. Here, we attempt to dissect mechanisms of Ol modulation during neuroinflammation and characterize the interaction of Ol with pathogenic T cells. RNA expression analysis revealed an upregulation of immune-modulatory genes and adhesion molecules (AMs), ICAM-1 and VCAM-1, in Ol when isolated from mice undergoing experimental autoimmune encephalomyelitis (EAE). To explore whether AMs are involved in the interaction of Ol with infiltrating T cells, we performed co-culture studies on mature Ol and Th1 cells. Live cell imaging analysis showed direct interaction between both cell types. Eighty percentage of Th1 cells created contacts with Ol that lasted longer than 15 min, which may be regarded as physiologically relevant. Exposure of Ol to Th1 cells or their supernatant resulted in a significant extension of Ol processes, and upregulation of AMs as well as other immunomodulatory genes. Our observations indicate that blocking of oligodendroglial ICAM-1 can reduce the number of Th1 cells initially contacting the Ol. These results suggest that AMs may play a role in the interaction between Ol and Th1 cells. We identified Ol interacting with CD4+ cells in vivo in spinal cord tissue of EAE diseased mice indicating that our in vitro findings are of interest to further scientific research in this field. Further characterization and understanding of Ol interaction with infiltrating cells may lead to new therapeutic strategies enhancing Ol protection and remyelination potential. Oligodendrocytes regulate immune modulatory genes and adhesion molecules during autoimmune neuroinflammation Oligodendrocytes interact with Th1 cells in vitro in a physiologically relevant manner Adhesion molecules may be involved in Ol-Th1 cell interaction.
CRIS-Team WoS Importer:2021-07-16
Keywords: adhesion molecules; autoimmune neuroinflammation; EAE; oligodendrocytes; Th1 cells

PALB2, CHEK2 and ATM rare variants and cancer risk: data from COGS - Southey, Melissa C.; Goldgar, David E.; Winqvist, Robert; Pylkas, Katri; Couch, Fergus; Tischkowitz, Marc; Foulkes, William D.; Dennis, Joe; Michailidou, Kyriaki; Van Rensburg, Elizabeth J.; Heikkinen, Tuomas; Nevanlinna, Heli; et al. (Journal of Medical Genetics, 2016)
The rarity of mutations in PALB2, CHEK2 and ATM make it difficult to estimate precisely associated cancer risks. Population-based family studies have provided evidence that at least some of these mutations are associated with breast cancer risk as high as those associated with rare BRCA2 mutations. We aimed to estimate the relative risks associated with specific rare variants in PALB2, CHEK2 and ATM via a multicentre case-control study.We genotyped 10 rare mutations using the custom iCOGS array: PALB2 c.1592delT, c.2816T>G and c.3113G>A, CHEK2 c.349A>G, c.538C>T, c.715G>A, c.1036C>T, c.1312G>T, and c.1343T>G and ATM c.7271T>G. We assessed associations with breast cancer risk (42 671 cases and 42 164 controls), as well as prostate (22 301 cases and 22 320 controls) and ovarian (14 542 cases and 23 491 controls) cancer risk, for each variant.For European women, strong evidence of association with breast cancer risk was observed for PALB2 c.1592delT OR 3.44 (95% CI 1.39 to 8.52, p=7.1×10(-5)), PALB2 c.3113G>A OR 4.21 (95% CI 1.84 to 9.60, p=6.9×10(-8)) and ATM c.7271T>G OR 11.0 (95% CI 1.42 to 85.7, p=0.0012). We also found evidence of association with breast cancer risk for three variants in CHEK2, c.349A>G OR 2.26 (95% CI 1.29 to 3.95), c.1036C>T OR 5.06 (95% CI 1.09 to 23.5) and c.538C>T OR 1.33 (95% CI 1.05 to 1.67) (p<=0.017). Evidence for prostate cancer risk was observed for CHEK2 c.1343T>G OR 3.03 (95% CI 1.53 to 6.03, p=0.0006) for African men and CHEK2 c.1312G>T OR 2.21 (95% CI 1.06 to 4.63, p=0.030) for European men. No evidence of association with ovarian cancer was found for any of these variants.This report adds to accumulating evidence that at least some variants in these genes are associated with an increased risk of breast cancer that is clinically important.
EVALuna2:6832

Paradoxical antidepressant effects of alcohol are related to acid sphingomyelinase and its control of sphingolipid homeostasis - Müller, Christiane; Kalinichenko, Liubov; Tiesel, Jens; Witt, Matthias; Stöckl, Thomas; Sprenger, Eva; Fuchser, Jens; Beckmann, Janine; Praetner, Marc; Huber, Sabine; Amato, Davide; Mühle, Christiane; et al. (Acta Neuropathologica, 2016)
Alcohol is a widely consumed drug that can lead to addiction and severe brain damage. However, alcohol is also used as self-medication for psychiatric problems, such as depression, frequently resulting in depression-alcoholism comorbidity. Here, we identify the first molecular mechanism for alcohol use with the goal to self-medicate and ameliorate the behavioral symptoms of a genetically induced innate depression. An induced over-expression of acid sphingomyelinase (ASM), as was observed in depressed patients, enhanced the consumption of alcohol in a mouse model of depression. ASM hyperactivity facilitates the establishment of the conditioned behavioral effects of alcohol, and thus drug memories. Opposite effects on drinking and alcohol reward learning were observed in animals with reduced ASM function. Importantly, free-choice alcohol drinking-but not forced alcohol exposure-reduces depression-like behavior selectively in depressed animals through the normalization of brain ASM activity. No such effects were observed in normal mice. ASM hyperactivity caused sphingolipid and subsequent monoamine transmitter hypo-activity in the brain. Free-choice alcohol drinking restores nucleus accumbens sphingolipid- and monoamine homeostasis selectively in depressed mice. A gene expression analysis suggested strong control of ASM on the expression of genes related to the regulation of pH, ion transmembrane transport, behavioral fear response, neuroprotection and neuropeptide signaling pathways. These findings suggest that the paradoxical antidepressant effects of alcohol in depressed organisms are mediated by ASM and its control of sphingolipid homeostasis. Both emerge as a new treatment target specifically for depression-induced alcoholism.
EVALuna2:3919

Patients with unstable angina pectoris show an increased frequency of the Fc gamma RIIa R131 allele - Raaz-Schrauder, Dorette; Ekici, Arif Bülent; Munoz, Luis Enrique; Klinghammer, Lutz; Voll, Reinhard E.; Leusen, Jeanette H.W.; Van De Winkel, Jan G.J.; Reis, André; Schett, Georg; Garlichs, Christoph; Herrmann, Martin (Autoimmunity, 2012)
Patients with Systemic Lupus Erythematosus (SLE) carry an increased risk for the development of coronary artery disease (CAD). The R131 allele of the Fc gamma receptor IIa (FcγRIIa) is associated with SLE incidence and disease severity but also with CAD. Compared to stable angina pectoris (SAP) the unstable angina (UAP), as a manifestation of destabilizing CAD, is associated with increased risk of persistent instability, myocardial infarction, and death. Identification of clinically relevant determinants for unstable angina promises reduction of UAP-associated mortality in patients with SLE. We conducted a clinical study among 553 consecutive patients with stable angina pectoris (n 330) and unstable angina pectoris (n 223). All patients were genotyped for a frequent functional variant at position 131 of the mature FcγRIIa. UAP, but not SAP was significantly associated with the R/R131 genotype (P < 0.001). In troponin-negative patients with angina carrying the R/R131 genotype the odds ratio for suffering from UAP was 4.02 (95% confidence interval, 2.526.41) compared to those with non-R/R131 genotypes. In a multivariable analysis, the R/R131 genotype independently predicted the risk for development of UAP in a model adjusted for classical atherogenic risk factors. Our data imply that risk stratification of SLE- and other high risk patients with troponin-negative angina could be significantly improved by FcγRIIa genotyping. © Informa UK, Ltd.
CRIS-Team Scopus Importer:2023-07-10
Keywords: Allele R131; Coronary disease; Fc gamma receptor IIa; SLE; Stable; Unstable angina pectoris

PAX5 biallelic genomic alterations define a novel subgroup of B-cell precursor acute lymphoblastic leukemia - Bastian, Lorenz; Schroeder, Michael P.; Eckert, Cornelia; Schlee, Cornelia; Tanchez, Jutta Ortiz; Kämpf, Sebastian; Wagner, Dimitrios L.; Schulze, Veronika; Isaakidis, Konstandina; Lázaro-Navarro, Juan; Hänzelmann, Sonja; James, Alva Rani; et al. (Leukemia, 2019)
Chromosomal rearrangements and specific aneuploidy patterns are initiating events and define subgroups in B-cell precursor acute lymphoblastic leukemia (BCP-ALL). Here we analyzed 250 BCP-ALL cases and identified a novel subgroup (‘PAX5-plus’, n = 19) by distinct DNA methylation and gene expression profiles. All patients in this subgroup harbored mutations in the B-lineage transcription factor PAX5, with p.P80R as hotspot. Mutations either affected two independent codons, consistent with compound heterozygosity, or suffered LOH predominantly through chromosome 9p aberrations. These biallelic events resulted in disruption of PAX5 transcriptional programs regulating B-cell differentiation and tumor suppressor functions. Homozygous CDKN2A/B deletions and RAS-activating hotspot mutations were highly enriched as cooperating events in the genomic profile of PAX5-plus ALL. Together, this defined a specific pattern of triple alterations, exclusive to the novel subgroup. PAX5-plus ALL was observed in pediatric and adult patients. Although restricted by the limited sample size, a tendency for more favorable clinical outcome was observed, with 10 of 12 adult PAX5-plus patients achieving long-term survival. PAX5-plus represents the first BCP-ALL subgroup defined by sequence alterations in contrast to gross chromosomal events and exemplifies how deregulated differentiation (PAX5), impaired cell cycle control (CDKN2A/B) and sustained proliferative signaling (RAS) cooperatively drive leukemogenesis.
CRIS-Team Scopus Importer:2019-07-26

PEDF Is Associated with the Termination of Chondrocyte Phenotype and Catabolism of Cartilage Tissue - Klinger, Patricia; Lukassen, Sören; Ferrazzi, Fulvia; Ekici, Arif Bülent; Hotfiel, Thilo; Swoboda, Bernd; Aigner, T.; Gelse, Kolja (BioMed Research International, 2017)
Objective. To investigate the expression and target genes of pigment epithelium-derived factor (PEDF) in cartilage and chondrocytes, respectively. Methods. We analyzed the expression pattern of PEDF in different human cartilaginous tissues including articular cartilage, osteophytic cartilage, and fetal epiphyseal and growth plate cartilage, by immunohistochemistry and quantitative real-time (qRT) PCR. Transcriptome analysis after stimulation of human articular chondrocytes with rhPEDF was performed by RNA sequencing (RNA-Seq) and confirmed by qRT-PCR. Results. Immunohistochemically, PEDF could be detected in transient cartilaginous tissue that is prone to undergo endochondral ossification, including epiphyseal cartilage, growth plate cartilage, and osteophytic cartilage. In contrast, PEDF was hardly detected in healthy articular cartilage and in the superficial zone of epiphyses, regions that are characterized by a permanent stable chondrocyte phenotype. RNA-Seq analysis and qRT-PCR demonstrated that rhPEDF significantly induced the expression of a number of matrix-degrading factors including SAA1, MMP1, MMP3, and MMP13. Simultaneously, a number of cartilage-specific genes including COL2A1, COL9A2, COMP, and LECT were among the most significantly downregulated genes. Conclusions. PEDF represents a marker for transient cartilage during all neonatal and postnatal developmental stages and promotes the termination of cartilage tissue by upregulation of matrix-degrading factors and downregulation of cartilage-specific genes. These data provide the basis for novel strategies to stabilize the phenotype of articular cartilage and prevent its degradation.
EVALuna2:9364

Percent mammographic density and dense area as risk factors for breast cancer - Rauh, C.; Hack, Caroline; Häberle, Lothar; Hein, Alexander; Engel, Anne; Schrauder, Michael G.; Fasching, Peter; Jud, Sebastian; Ekici, Arif Bülent; Loehberg, C. R.; Meier-Meitinger, Martina; Ozan-Mergner, Sevil Julia; et al. (Geburtshilfe und Frauenheilkunde, 2012)
Purpose: Mammographic characteristics are known to be correlated to breast cancer risk. Percent mammographic density (PMD), as assessed by computer-assisted methods, is an established risk factor for breast cancer. Along with this assessment the absolute dense area (DA) of the breast is reported as well. Aim of this study was to assess the predictive value of DA concerning breast cancer risk in addition to other risk factors and in addition to PMD. Methods: We conducted a case control study with hospital-based patients with a diagnosis of invasive breast cancer and healthy women as controls. A total of 561 patients and 376 controls with available mammographic density were included into this study. We describe the differences concerning the common risk factors BMI, parital status, use of hormone replacement therapy (HRT) and menopause between cases and controls and estimate the odds ratios for PMD and DA, adjusted for the mentioned risk factors. Furthermore we compare the prediction models with each other to find out whether the addition of DA improves the model. Results: Mammographic density and DA were highly correlated with each other. Both variables were as well correlated to the commonly known risk factors with an expected direction and strength, however PMD (ρ = 0.56) was stronger correlated to BMI than DA (ρ = 0.11). The group of women within the highest quartil of PMD had an OR of 2.12 (95 % CI: 1.25-3.62). This could not be seen for the fourth quartile concerning DA. However the assessment of breast cancer risk could be improved by including DA in a prediction model in addition to common risk factors and PMD. Conclusions: The inclusion of the parameter DA into a prediction model for breast cancer in addition to established risk factors and PMD could improve the breast cancer risk assessment. As DA is measured together with PMD in the process of computer-assisted assessment of PMD it might be considered to include it as one additional breast cancer risk factor that is obtained from breast imaging. © Georg Thieme Verlag KG Stuttgart · New York.
CRIS-Team Scopus Importer:2021-07-19
Keywords: breast cancer; mammographic density; risk

PHENOTYPE OF VULNERABLE ATHEROSCLEROTIC PLAQUES SHOWS STRONG ASSOCIATION WITH SINGLE NUCLEOTIDE POLYMORPHISM ALLELES OF COMMON RISK VARIANTS FOR CORONARY ARTERY DISEASE - Furtmair, R.; Kühn, Charlotte; Koenig, C.; Ekici, Arif Bülent; Klinghammer, Lutz; Achenbach, Stephan; Reis, André; Tauchi, M.; Dietel, B. (2016)
EVALuna2:33679

Polygenic Risk Scores for Prediction of Breast Cancer and Breast Cancer Subtypes - Mavaddat, Nasim; Michailidou, Kyriaki; Dennis, Joe; Lush, Michael; Fachal, Laura; Lee, Andrew; Tyrer, Jonathan P.; Chen, Ting-Huei; Wang, Qin; Bolla, Manjeet K.; Yang, Xin; Adank, Muriel A.; et al. (American Journal of Human Genetics, 2019)
Stratification of women according to their risk of breast cancer based on polygenic risk scores (PRSs) could improve screening and prevention strategies. Our aim was to develop PRSs, optimized for prediction of estrogen receptor (ER)-specific disease, from the largest available genome-wide association dataset and to empirically validate the PRSs in prospective studies. The development dataset comprised 94,075 case subjects and 75,017 control subjects of European ancestry from 69 studies, divided into training and validation sets. Samples were genotyped using genome-wide arrays, and single-nucleotide polymorphisms (SNPs) were selected by stepwise regression or lasso penalized regression. The best performing PRSs were validated in an independent test set comprising 11,428 case subjects and 18,323 control subjects from 10 prospective studies and 190,040 women from UK Biobank (3,215 incident breast cancers). For the best PRSs (313 SNPs), the odds ratio for overall disease per 1 standard deviation in ten prospective studies was 1.61 (95%CI: 1.57-1.65) with area under receiver-operator curve (AUC) = 0.630 (95%CI: 0.628-0.651). The lifetime risk of overall breast cancer in the top centile of the PRSs was 32.6%. Compared with women in the middle quintile, those in the highest 1% of risk had 4.37- and 2.78-fold risks, and those in the lowest 1% of risk had 0.16- and 0.27-fold risks, of developing ER-positive and ER-negative disease, respectively. Goodness-of-fit tests indicated that this PRS was well calibrated and predicts disease risk accurately in the tails of the distribution. This PRS is a powerful and reliable predictor of breast cancer risk that may improve breast cancer prevention programs.
EVALuna2:35122

Polymorphisms in a Putative Enhancer at the 10q21.2 Breast Cancer Risk Locus Regulate NRBF2 Expression - Darabi, Hatef; Mccue, Karen; Beesley, Jonathan; Michailidou, Kyriaki; Nord, Silje; Kar, Siddhartha; Humphreys, Keith; Thompson, Deborah; Ghoussaini, Maya; Bolla, Manjeet K.; Dennis, Joe; Wang, Qin; et al. (American Journal of Human Genetics, 2015)
Genome-wide association studies have identified SNPs near ZNF365 at 10q21.2 that are associated with both breast cancer risk and mammographic density. To identify the most likely causal SNPs, we fine mapped the association signal by genotyping 428 SNPs across the region in 89,050 European and 12,893 Asian case and control subjects from the Breast Cancer Association Consortium. We identified four independent sets of correlated, highly trait-associated variants (iCHAVs), three of which were located within ZNF365. The most strongly risk-associated SNP, rs10995201 in iCHAV1, showed clear evidence of association with both estrogen receptor (ER)-positive (OR = 0.85 [0.82-0.88]) and ER-negative (OR = 0.87 [0.82-0.91]) disease, and was also the SNP most strongly associated with percent mammographic density. iCHAV2 (lead SNP, chr10: 64,258,684:D) and iCHAV3 (lead SNP, rs7922449) were also associated with ER-positive (OR = 0.93 [0.91-0.95] and OR = 1.06 [1.03-1.09]) and ER-negative (OR = 0.95 [0.91-0.98] and OR = 1.08 [1.04-1.13]) disease. There was weaker evidence for iCHAV4, located 5' of ADO, associated only with ER-positive breast cancer (OR = 0.93 [0.90-0.96]). We found 12, 17, 18, and 2 candidate causal SNPs for breast cancer in iCHAVs 1-4, respectively. Chromosome conformation capture analysis showed that iCHAV2 interacts with the ZNF365 and NRBF2 (more than 600 kb away) promoters in normal and cancerous breast epithelial cells. Luciferase assays did not identify SNPs that affect transactivation of ZNF365, but identified a protective haplotype in iCHAV2, associated with silencing of the NRBF2 promoter, implicating this gene in the etiology of breast cancer.
EVALuna2:9266

Polymorphisms in inflammation pathway genes and endometrial cancer risk - Delahanty, Ryan J.; Xiang, Yong-Bing; Spurdle, Amanda; Beeghly-Fadiel, Alicia; Long, Jirong; Thompson, Deborah; Tomlinson, Ian; Yu, Herbert; Lambrechts, Diether; Doerk, Thilo; Goodman, Marc T.; Zheng, Ying; et al. (Cancer Epidemiology Biomarkers & Prevention, 2013)
Background: Experimental and epidemiologic evidence have suggested that chronic inflammation may play a critical role in endometrial carcinogenesis. Methods: To investigate this hypothesis, a two-stage study was carried out to evaluate single-nucleotide polymorphisms (SNP) in inflammatory pathway genes in association with endometrial cancer risk. In stage I, 64 candidate pathway genes were identified and 4,542 directly genotyped or imputed SNPs were analyzed among 832 endometrial cancer cases and 2,049 controls, using data from the Shanghai Endometrial Cancer Genetics Study. Linkage disequilibrium of stage I SNPs significantly associated with endometrial cancer (P < 0.05) indicated that the majority of associations could be linked to one of 24 distinct loci. One SNP from each of the 24 loci was then selected for follow-up genotyping. Of these, 21 SNPs were successfully designed and genotyped in stage II, which consisted of 10 additional studies including 6,604 endometrial cancer cases and 8,511 controls. Results: Five of the 21 SNPs had significant allelic odds ratios (ORs) and 95% confidence intervals (CI) as follows: FABP1, 0.92 (0.85-0.99); CXCL3, 1.16 (1.05-1.29); IL6, 1.08 (1.00-1.17); MSR1, 0.90 (0.82-0.98); and MMP9, 0.91 (0.87-0.97). Two of these polymorphisms were independently significant in the replication sample (rs352038 in CXCL3 and rs3918249 in MMP9). The association for the MMP9 polymorphism remained significant after Bonferroni correction and showed a significant association with endometrial cancer in both Asian- and European-ancestry samples. Conclusions: These findings lend support to the hypothesis that genetic polymorphisms in genes involved in the inflammatory pathway may contribute to genetic susceptibility to endometrial cancer. Impact statement: This study adds to the growing evidence that inflammation plays an important role in endometrial carcinogenesis. © 2012 American Association for Cancer Research.
CRIS-Team Scopus Importer:2021-07-19

Polymorphisms in the RANK/RANKL genes and their effect on bone specific prognosis in breast cancer patients - Hein, Alexander; Bayer, Christian M.; Schrauder, Michael G.; Haeberle, Lothar; Heusinger, Katharina; Strick, Reiner; Ruebner, Matthias; Lux, Michael P.; Renner, Stefan; Schulz-Wendtland, Rüdiger; Ekici, Arif Bülent; Hartmann, Arndt; et al. (BioMed Research International, 2014)
The receptor activator of NF-?B (RANK) pathway is involved in bone health as well as breast cancer (BC) pathogenesis and progression. Whereas the therapeutic implication of this pathway is established for the treatment of osteoporosis and bone metastases, the application in adjuvant BC is currently investigated. As genetic variants in this pathway have been described to influence bone health, aim of this study was the prognostic relevance of genetic variants in RANK and RANKL. Single nucleotide polymorphisms in RANK(L) (rs1054016/rs1805034/rs35211496) were genotyped and analyzed with regard to bone metastasis-free survival (BMFS), disease-free survival, and overall survival for a retrospective cohort of 1251 patients. Cox proportional hazard models were built to examine the prognostic influence in addition to commonly established prognostic factors. The SNP rs1054016 seems to influence BMFS. Patients with two minor alleles had a more favorable prognosis than patients with at least one common allele (HR 0.37 (95% CI: 0.17, 0.84)), whereas other outcome parameters remained unaffected. rs1805034 and rs35211496 had no prognostic relevance. The effect of rs1054016(RANKL) adds to the evidence that the RANK pathway plays a role in BC pathogenesis and progression with respect to BMFS, emphasizing the connection between BC and bone health.
EVALuna2:6628

Polyol pathway links glucose metabolism to the aggressiveness of cancer cells - Schwab, Annemarie; Siddiqui, Aarif; Vazakidou, Maria Eleni; Napoli, Francesca; Böttcher, Martin; Menchicchi, Bianca; Raza, Umar; Saatci, Ozge; Krebs, Angela; Ferrazzi, Fulvia; Rapa, Ida; Dettmer-Wilde, Katja; et al. (Cancer Research, 2018)
Cancer cells alter their metabolism to support their malignant properties. In this study, we report that the glucose-transforming polyol pathway (PP) gene aldo-keto-reductase-1-member-B1 (AKR1B1) strongly correlates with epithelial-to-mesenchymal transition (EMT). This association was confirmed in samples from lung cancer patients and from an EMT-driven colon cancer mouse model with p53 deletion. In vitro, mesenchymal-like cancer cells showed increased AKR1B1 levels, and AKR1B1 knockdown was sufficient to revert EMT. An equivalent level of EMT suppression was measured by targeting the downstream enzyme sorbitol-dehydrogenase (SORD), further pointing at the involvement of the PP. Comparative RNA sequencing confirmed a profound alteration of EMT in PP-deficient cells, revealing a strong repression of TGF-? signature genes. Excess glucose was found to promote EMT through autocrine TGF-? stimulation, while PP-deficient cells were refractory to glucose-induced EMT. These data show that PP represents a molecular link between glucose metabolism, cancer differentiation, and aggressiveness, and may serve as a novel therapeutic target.
EVALuna2:10237

Predicting Triple-Negative Breast Cancer Subtype Using Multiple Single Nucleotide Polymorphisms for Breast Cancer Risk and Several Variable Selection Methods - Häberle, Lothar; Hein, Alexander; Rübner, Matthias; Schneider, Michael; Ekici, Arif Bülent; Gaß, Paul; Hartmann, Arndt; Schulz-Wendtland, Rüdiger; Beckmann, Matthias; Lo, Wing-Yee; Schroth, Werner; Brauch, Hiltrud; et al. (Geburtshilfe und Frauenheilkunde, 2017)
Studies of triple-negative breast cancer have recently been extending the inclusion criteria and incorporating additional molecular markers into the selection criteria, opening up scope for targeted therapies. The screening phases required for studies of this type are often prolonged, since the process of determining the molecular subtype and carrying out additional biomarker assessment is time-consuming. Parameters such as germline genotypes capable of predicting the molecular subtype before it becomes available from pathology might be helpful for treatment planning and optimizing the timing and cost of screening phases. This appears to be feasible, as rapid and low-cost genotyping methods are becoming increasingly available. The aim of this study was to identify single nucleotide polymorphisms (SNPs) for breast cancer risk capable of predicting triple negativity, in addition to clinical predictors, in breast cancer patients.This cross-sectional observational study included 1271 women with invasive breast cancer who were treated at a university hospital. A total of 76 validated breast cancer risk SNPs were successfully genotyped. Univariate associations between each SNP and triple negativity were explored using logistic regression analyses. Several variable selection and regression techniques were applied to identify a set of SNPs that together improve the prediction of triple negativity in addition to the clinical predictors of age at diagnosis and body mass index (BMI). The most accurate prediction method was determined by cross-validation.The SNP rs10069690 (TERT, CLPTM1L) was the only significant SNP (corrected p = 0.02) after correction of p values for multiple testing in the univariate analyses. This SNP and three additional SNPs from the genes RAD51B, CCND1, and FGFR2 were selected for prediction of triple negativity. The addition of these SNPs to clinical predictors increased the cross-validated area under the curve (AUC) from 0.618 to 0.625. Age at diagnosis was the strongest predictor, stronger than any genetic characteristics.Prediction of triple-negative breast cancer can be improved if SNPs associated with breast cancer risk are added to a prediction rule based on age at diagnosis and BMI. This finding could be used for prescreening purposes in complex molecular therapy studies for triple-negative breast cancer.
EVALuna2:6850

Prediction of breast cancer risk based on profiling with common genetic variants - Mavaddat, Nasim; Pharoah, Paul D. P.; Michailidou, Kyriaki; Tyrer, Jonathan; Brook, Mark N.; Bolla, Manjeet K.; Wang, Qin; Dennis, Joe; Dunning, Alison M.; Shah, Mitul; Luben, Robert; Brown, Judith; et al. (Journal of the National Cancer Institute, 2015)
Data for multiple common susceptibility alleles for breast cancer may be combined to identify women at different levels of breast cancer risk. Such stratification could guide preventive and screening strategies. However, empirical evidence for genetic risk stratification is lacking.We investigated the value of using 77 breast cancer-associated single nucleotide polymorphisms (SNPs) for risk stratification, in a study of 33 673 breast cancer cases and 33 381 control women of European origin. We tested all possible pair-wise multiplicative interactions and constructed a 77-SNP polygenic risk score (PRS) for breast cancer overall and by estrogen receptor (ER) status. Absolute risks of breast cancer by PRS were derived from relative risk estimates and UK incidence and mortality rates.There was no strong evidence for departure from a multiplicative model for any SNP pair. Women in the highest 1% of the PRS had a three-fold increased risk of developing breast cancer compared with women in the middle quintile (odds ratio [OR] = 3.36, 95% confidence interval [CI] = 2.95 to 3.83). The ORs for ER-positive and ER-negative disease were 3.73 (95% CI = 3.24 to 4.30) and 2.80 (95% CI = 2.26 to 3.46), respectively. Lifetime risk of breast cancer for women in the lowest and highest quintiles of the PRS were 5.2% and 16.6% for a woman without family history, and 8.6% and 24.4% for a woman with a first-degree family history of breast cancer.The PRS stratifies breast cancer risk in women both with and without a family history of breast cancer. The observed level of risk discrimination could inform targeted screening and prevention strategies. Further discrimination may be achievable through combining the PRS with lifestyle/environmental factors, although these were not considered in this repor
EVALuna2:9271

Premature Osteoarthritis as Presenting Sign of Type II Collagenopathy: A Case Report and Literature Review - Husar-Memmer, Emma; Ekici, Arif Bülent; Al Kaissi, Ali; Sticht, Heinrich; Manger, Bernhard; Schett, Georg; Zwerina, Jochen (Seminars in Arthritis and Rheumatism, 2013)
Osteoarthritis (OA) is a frequent, chronic, and often disabling disease. Early-onset OA should prompt rheumatologists to search for underlying causes. We describe the clinical presentation and diagnosis of a patient with severe premature OA.We report a patient with severe polyarticular OA starting in young adulthood due to a heterozygous mutation in the COL2A1 gene. We discuss the clinical features, diagnosis, and known mutations of previously reported cases identified through a PubMed literature review.A 43-year-old Caucasian woman of normal stature presented with a 24-year history of symmetrical polyarticular OA involving both large and small joints. At the time of presentation, the patient already underwent 6 joint replacement surgeries. Family history was unremarkable. Clinical, serologic, radiographic, and histologic studies did not reveal any specific cause for this unusual clinical presentation. Genetic analysis revealed a heterozygous COL2A1 mutation (R519C) consistent with the clinical phenotype. Reviewing the literature, we discuss the clinical spectrum of type II collagenopathies emphasizing premature OA as the sole clinical manifestation.Unusual clinical presentations of OA should prompt investigations to search for an underlying cause. Type II collagenopathy should be considered in young adults with severe symmetrical OA even in the absence of other clinical features. A correct diagnosis allows classification and genetic counseling of the patient.
EVALuna2:9163

Prenatal androgen receptor activation determines adult alcohol and water drinking in a sex-specific way - Huber, Sabine; Zoicas, Iulia; Reichel, Martin; Mühle, Christiane; Büttner, Christian; Ekici, Arif Bülent; Eulenburg, Volker; Lenz, Bernd; Kornhuber, Johannes; Müller, Christian P. (Addiction Biology, 2017)
Alcohol use disorders are major psychiatric disorders. Correlational studies in humans suggested organizational hormonal effects during embryonic development as a risk factor for adult alcohol dependence. Permanent changes can be induced by the activity of sex hormones, like testosterone. Here, we demonstrate a relationship between prenatal androgen receptor (AR)-activation and adult alcohol as well as water drinking in mice in a sex-dependent fashion. Prenatal AR inhibition using the antagonist flutamide decreased adult male alcohol consumption. In contrast, prenatal AR activation by dihydrotestosterone (DHT) led to an increase in adult alcohol consumption in females. These effects were different in adult water drinking, flutamide increased water consumption in females and DHT increased water consumption in males. Prenatal flutamide reduced locomotion and anxiety in adult males but was ineffective in females. We found that prenatal AR activation controls adult levels of monoaminergic modulatory transmitters in the brain and blood hormone levels in a sex-specific way. RNA-Seq analysis confirmed a prenatal AR mediated control of adult expression of alcohol drinking-related genes like Bdnf and Per2. These findings demonstrate that prenatal androgen activity is a risk factor for the establishment of alcohol consumption in adults by its organizational effects.
EVALuna2:4035

Prenatal diagnosis of HNF1B-associated renal cysts: Is there a need to differentiate intragenic variants from 17q12 microdeletion syndrome? - Vasileiou, Georgia; Hoyer, Juliane; Thiel, Christian; Schaefer, Jan Thomas; Zapke, Maren; Krumbiegel, Mandy; Kraus, Cornelia; Zweier, Markus; Uebe, Steffen; Ekici, Arif Bülent; Schneider, Michael; Wiesener, Michael; et al. (Prenatal Diagnosis, 2019)
Objective 17q12 microdeletions containing HNF1B and intragenic variants within this gene are associated with variable developmental, endocrine, and renal anomalies, often already noted prenatally as hyperechogenic/cystic kidneys. Here, we describe prenatal and postnatal phenotypes of seven individuals with HNF1B aberrations and compare their clinical and genetic data to those of previous studies. Methods Prenatal sequencing and postnatal chromosomal microarray analysis were performed in seven individuals with renal and/or neurodevelopmental phenotypes. We evaluated HNF1B-related clinical features from 82 studies and reclassified 192 reported intragenic HNF1B variants. Results In a prenatal case, we identified a novel in-frame deletion p.(Gly239del) within the HNF1B DNA-binding domain, a mutational hot spot as demonstrated by spatial clustering analysis and high computational prediction scores. The six postnatally diagnosed individuals harbored 17q12 microdeletions. Literature screening revealed variable reporting of HNF1B-associated clinical traits. Overall, both mutation groups showed a high phenotypic heterogeneity. The reclassification of all previously reported intragenic HNF1B variants provided an up-to-date overview of the mutational spectrum. Conclusions We highlight the value of prenatal HNF1B screening in renal developmental diseases. Standardized clinical reporting and systematic classification of HNF1B variants are necessary for a more accurate risk quantification of prenatal and postnatal clinical features, improving genetic counseling and prenatal decision making.
CRIS-Team WoS Importer:2019-11-08

Prevalence of hereditary tubulointerstitial kidney diseases in the German Chronic Kidney Disease study - Popp, Bernt; Ekici, Arif Bülent; Knaup, Karl; Schneider, Karen; Uebe, Steffen; Park, Jonghun; Bafna, Vineet; Meiselbach, Heike; Eckardt, Kai-Uwe; Schiffer, Mario; Wiesmann da Silva Reis, André; Kraus, Cornelia; et al. (European Journal of Human Genetics, 2022)
Hereditary chronic kidney disease (CKD) appears to be more frequent than the clinical perception. Exome sequencing (ES) studies in CKD cohorts could identify pathogenic variants in similar to 10% of individuals. Tubulointerstitial kidney diseases, showing no typical clinical/histologic finding but tubulointerstitial fibrosis, are particularly difficult to diagnose. We used a targeted panel (29 genes) and MUC1-SNaPshot to sequence 271 DNAs, selected in defined disease entities and age cutoffs from 5217 individuals in the German Chronic Kidney Disease cohort. We identified 33 pathogenic variants. Of these 27 (81.8%) were in COL4A3/4/5, the largest group being 15 COL4A5 variants with nine unrelated individuals carrying c.1871G>A, p.(Gly624Asp). We found three cysteine variants in UMOD, a novel missense and a novel splice variant in HNF1B and the homoplastic MTTF variant m.616T>C. Copy-number analysis identified a heterozygous COL4A5 deletion, and a HNF1B duplication/deletion, respectively. Overall, pathogenic variants were present in 12.5% (34/271) and variants of unknown significance in 9.6% (26/271) of selected individuals. Bioinformatic predictions paired with gold standard diagnostics for MUC1 (SNaPshot) could not identify the typical cytosine duplication ("c.428dupC") in any individual, implying that ADTKD-MUC1 is rare. Our study shows that >10% of selected individuals carry disease-causing variants in genes partly associated with tubulointerstitial kidney diseases. COL4A3/4/5 genes constitute the largest fraction, implying they are regularly overlooked using clinical Alport syndrome criteria and displaying the existence of phenocopies. We identified variants easily missed by some ES pipelines. The clinical filtering criteria applied enriched for an underlying genetic disorder.
CRIS-Team WoS Importer:2022-09-23

PU.1 controls fibroblast polarization and tissue fibrosis - Wohlfahrt, Thomas; Rauber, Simon; Uebe, Steffen; Luber, Markus; Soare, Alina; Ekici, Arif Bülent; Weber, Stefanie; Matei, Alexandru-Emil; Chen, Chih-Wei; Maier, Christiane; Karouzakis, Emmanuel; Kiener, Hans P.; et al. (Nature, 2019)
Fibroblasts are polymorphic cells with pleiotropic roles in organ morphogenesis, tissue homeostasis and immune responses. In fibrotic diseases, fibroblasts synthesize abundant amounts of extracellular matrix, which induces scarring and organ failure. By contrast, a hallmark feature of fibroblasts in arthritis is degradation of the extracellular matrix because of the release of metalloproteinases and degrading enzymes, and subsequent tissue destruction. The mechanisms that drive these functionally opposing pro-fibrotic and pro-inflammatory phenotypes of fibroblasts remain unknown. Here we identify the transcription factor PU.1 as an essential regulator of the pro-fibrotic gene expression program. The interplay between transcriptional and post-transcriptional mechanisms that normally control the expression of PU.1 expression is perturbed in various fibrotic diseases, resulting in the upregulation of PU.1, induction of fibrosis-associated gene sets and a phenotypic switch in extracellular matrix-producing pro-fibrotic fibroblasts. By contrast, pharmacological and genetic inactivation of PU.1 disrupts the fibrotic network and enables reprogramming of fibrotic fibroblasts into resting fibroblasts, leading to regression of fibrosis in several organs.
EVALuna2:35476

Rare frameshift mutation in SERPINA3 contributes to generalized pustular psoriasis - Hüffmeier, Ulrike; Sticht, Heinrich; Wenzel, J.; Wilsmann-Theis, D.; Wolff, K.; Löhr, Sabine; Frey, Benjamin; Hahn, M.; Ekici, Arif Bülent; Uebe, S.; Thiel, Christian; Wiesmann da Silva Reis, André; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2019)
CRIS-Team WoS Importer:2019-10-25

Rare Loss-of-Function Mutation in SERPINA3 in Generalized Pustular Psoriasis - Frey, Silke; Sticht, Heinrich; Wilsmann-Theis, Dagmar; Gerschütz, Anne; Wolf, Katharina; Löhr, Sabine; Haskamp, Stefan; Frey, Benjamin; Hahn, Madelaine; Ekici, Arif Bülent; Uebe, Steffen; Thiel, Christian; et al. (Journal of Investigative Dermatology, 2020)
CRIS-Team Scopus Importer:2020-03-06

Refined histopathological predictors of BRCA1 and BRCA2 mutation status: a large-scale analysis of breast cancer characteristics from the BCAC, CIMBA, and ENIGMA consortia - Spurdle, Amanda B.; Couch, Fergus J.; Parsons, Michael T.; Mcguffog, Lesley; Barrowdale, Daniel; Bolla, Manjeet K.; Wang, Qin; Healey, Sue; Schmutzler, Rita Katharina; Wappenschmidt, Barbara; Rhiem, Kerstin; Hahnen, Eric; et al. (Breast Cancer Research, 2014)
The distribution of histopathological features of invasive breast tumors in BRCA1 or BRCA2 germline mutation carriers differs from that of individuals with no known mutation. Histopathological features thus have utility for mutation prediction, including statistical modeling to assess pathogenicity of BRCA1 or BRCA2 variants of uncertain clinical significance. We analyzed large pathology datasets accrued by the Consortium of Investigators of Modifiers of BRCA1/2 (CIMBA) and the Breast Cancer Association Consortium (BCAC) to reassess histopathological predictors of BRCA1 and BRCA2 mutation status, and provide robust likelihood ratio (LR) estimates for statistical modeling.Selection criteria for study/center inclusion were estrogen receptor (ER) status or grade data available for invasive breast cancer diagnosed younger than 70 years. The dataset included 4,477 BRCA1 mutation carriers, 2,565 BRCA2 mutation carriers, and 47,565 BCAC breast cancer cases. Country-stratified estimates of the likelihood of mutation status by histopathological markers were derived using a Mantel-Haenszel approach.ER-positive phenotype negatively predicted BRCA1 mutation status, irrespective of grade (LRs from 0.08 to 0.90). ER-negative grade 3 histopathology was more predictive of positive BRCA1 mutation status in women 50 years or older (LR = 4.13 (3.70 to 4.62)) versus younger than 50 years (LR = 3.16 (2.96 to 3.37)). For BRCA2, ER-positive grade 3 phenotype modestly predicted positive mutation status irrespective of age (LR = 1.7-fold), whereas ER-negative grade 3 features modestly predicted positive mutation status at 50 years or older (LR = 1.54 (1.27 to 1.88)). Triple-negative tumor status was highly predictive of BRCA1 mutation status for women younger than 50 years (LR = 3.73 (3.43 to 4.05)) and 50 years or older (LR = 4.41 (3.86 to 5.04)), and modestly predictive of positive BRCA2 mutation status in women 50 years or older (LR = 1.79 (1.42 to 2.24)).These results refine likelihood-ratio estimates for predicting BRCA1 and BRCA2 mutation status by using commonly measured histopathological features. Age at diagnosis is an important variable for most analyses, and grade is more informative than ER status for BRCA2 mutation carrier prediction. The estimates will improve BRCA1 and BRCA2 variant classification and inform patient mutation testing and clinical management.
EVALuna2:9304

Regulatory eosinophils induce the resolution of experimental arthritis and appear in remission state of human rheumatoid arthritis - Andreev, Darja; Liu, Mengdan; Kachler, Katerina; Llerins Perez, Mireia; Kirchner, Philipp; Kölle, Julia; Gießl, Andreas; Rauber, Simon; Song, Rui; Aust, Oliver; Grüneboom, Anika; Kleyer, Arnd; et al. (Annals of the Rheumatic Diseases, 2020)
Objectives: Eosinophils possess pro-inflammatory functions in asthma. However, our recent studies have suggested that innate lymphoid cells type 2 (ILC2s) and eosinophils have proresolving properties in rheumatoid arthritis (RA). Nothing is known yet about the mechanisms determining the double-edged role of eosinophils. Therefore, we investigated whether asthma, a paradigm eosinophilic disease, can elicit resolution of chronic arthritis. Methods: Ovalbumin-triggered eosinophilic asthma was combined with K/BxN serum-induced arthritis, where lung and synovial eosinophil subsets were compared by single-cell RNA sequencing (scRNA-seq). To investigate the involvement of the ILC2-interleukin-5 (IL-5) axis, hydrodynamic injection (HDI) of IL-25 and IL-33 plasmids, IL-5 reporter mice and anti-IL-5 antibody treatment were used. In patients with RA, the presence of distinct eosinophil subsets was examined in peripheral blood and synovial tissue. Disease activity of patients with RA with concomitant asthma was monitored before and after mepolizumab (anti-IL-5 antibody) therapy. Results: The induction of eosinophilic asthma caused resolution of murine arthritis and joint tissue protection. ScRNA-seq revealed a specific subset of regulatory eosinophils (rEos) in the joints, distinct from inflammatory eosinophils in the lungs. Mechanistically, synovial rEos expanded on systemic upregulation of IL-5 released by lung ILC2s. Eosinophil depletion abolished the beneficial effect of asthma on arthritis. rEos were consistently present in the synovium of patients with RA in remission, but not in active stage. Remarkably, in patients with RA with concomitant asthma, mepolizumab treatment induced relapse of arthritis. Conclusion: These findings point to a hitherto undiscovered proresolving signature in an eosinophil subset that stimulates arthritis resolution.
CRIS-Team Scopus Importer:2020-11-20
Keywords: arthritis; autoimmune diseases; cytokines; immune system diseases; inflammation; rheumatoid

Renal fibrosis is the common feature of autosomal dominant tubulointerstitial kidney diseases caused by mutations in mucin 1 or uromodulin - Ekici, Arif Bülent; Hackenbeck, Thomas; Moriniere, Vincent; Panness, Andrea; Büttner, Maike; Uebe, Steffen; Janka, Rolf Matthias; Wiesener, Antje; Hermann, Ingo; Grupp, Sina; Hornberger, Martin; Huber, Tobias B.; et al. (Kidney International, 2014)
For decades, ill-defined autosomal dominant renal diseases have been reported, which originate from tubular cells and lead to tubular atrophy and interstitial fibrosis. These diseases are clinically indistinguishable, but caused by mutations in at least four different genes: UMOD, HNF1B, REN, and, as recently described, MUC1. Affected family members show renal fibrosis in the biopsy and gradually declining renal function, with renal failure usually occurring between the third and sixth decade of life. Here we describe 10 families and define eligibility criteria to consider this type of inherited disease, as well as propose a practicable approach for diagnosis. In contrast to what the frequently used term 'Medullary Cystic Kidney Disease' implies, development of (medullary) cysts is neither an early nor a typical feature, as determined by MRI. In addition to Sanger and gene panel sequencing of the four genes, we established SNaPshot minisequencing for the predescribed cytosine duplication within a distinct repeat region of MUC1 causing a frameshift. A mutation was found in 7 of 9 families (3 in UMOD and 4 in MUC1), with one indeterminate (UMOD p.T62P). On the basis of clinical and pathological characteristics we propose the term 'Autosomal Dominant Tubulointerstitial Kidney Disease' as an improved terminology. This should enhance recognition and correct diagnosis of affected individuals, facilitate genetic counseling, and stimulate research into the underlying pathophysiology.
EVALuna2:3695

Reset of inflammatory priming of joint tissue and reduction of the severity of arthritis flares by bromodomain inhibition - Friščić, Jasna; Reinwald, Christiane; Böttcher, Martin; Houtman, Miranda; Euler, Maximilien; Chen, Xi; Walker, Kellie I.; Kirchner, Philipp; Zhu, Honglin; Wirth, Benjamin; Weidner, Daniela; Krüger, René; et al. (Arthritis and Rheumatology, 2023)
Objective: We have recently shown that priming of synovial fibroblasts (SFs) drives arthritis flares. Pathogenic priming of SFs is essentially mediated by epigenetic reprogramming. Bromodomain and extra-terminal motif (BET) proteins translate epigenetic changes into transcription. Here we used a BET inhibitor to target inflammatory tissue priming and reduce flare severity in experimental arthritis. Methods: BALB/c mice were treated intraperitoneally or locally into the paw with I-BET151, which blocks interaction of BET proteins with acetylated histones. Effect of I-BET151 on acute arthritis and/or inflammatory tissue priming was assessed in a model of repeated injections of monosodium urate crystals or zymosan into the paw. I-BET151 was given either from before arthritis induction, at peak inflammation, or after healing of the first arthritis bout. Transcriptomic (RNA-Seq), epigenomic (ATAC-Seq) and functional analysis (invasion, cytokine production, migration, senescence, metabolic flux) was performed on murine and human SFs treated with I-BET151 in vitro or in vivo. Results: Systemic I-BET151 administration did not affect acute inflammation but abolished inflammatory tissue priming and diminished flare severity in both preventive and therapeutic treatment settings. I-BET151 was also effective when applied locally in the joint. BET inhibition also inhibited osteoclast differentiation, while macrophage activation in the joint was not affected. Flare reduction after BET inhibition was mediated, at least in part, by rolling back the primed transcriptional, metabolic and pathogenic phenotype of SFs. Conclusion: Inflammatory tissue priming is dependent on transcriptional regulation by BET proteins, which makes them promising therapeutic targets for preventing arthritis flares in previously affected joints.
CRIS-Team Scopus Importer:2023-01-27

Residual homing of alpha 4 beta 7-expressing beta 1(+)PI16(+) regulatory T cells with potent suppressive activity correlates with exposure-efficacy of vedolizumab - Becker, Emily; Dedden, Mark; Gall, Christine; Wiendl, Maximilian; Ekici, Arif Bülent; Schulz-Kuhnt, Anja; Schweda, Anna; Bosch-Voskens, Caroline; Hegazy, Ahmed; Vitali, Francesco; Atreya, Raja; Müller, Tanja; et al. (Gut, 2021)
Objective The anti-alpha 4 beta 7 integrin antibody vedolizumab is administered at a fixed dose for the treatment of IBDs. This leads to a wide range of serum concentrations in patients and previous studies had suggested that highest exposure levels are associated with suboptimal clinical response. We aimed to determine the mechanisms underlying these non-linear exposure-efficacy characteristics of vedolizumab. Design We characterised over 500 samples from more than 300 subjects. We studied the binding of vedolizumab to T cells and investigated the functional consequences for dynamic adhesion, transmigration, gut homing and free binding sites in vivo. Employing single-cell RNA sequencing, we characterised alpha 4 beta 7 integrin-expressing T cell populations 'resistant' to vedolizumab and validated our findings in vitro and in samples from vedolizumab-treated patients with IBD. We also correlated our findings with a post-hoc analysis of the Gemini II and III studies. Results Regulatory T (T-Reg) cells exhibited a right-shifted vedolizumab binding profile compared with effector T (T-Eff) cells. Consistently, in a certain concentration range, the residual adhesion, transmigration, homing of and availability of functional alpha 4 beta 7 on T-Reg cells in vivo was higher than that of/on T-Eff cells. We identified a vedolizumab-'resistant' alpha 4 beta 7-expressing beta 1(+)PI16(+) T-Reg cell subset with pronounced regulatory properties as the substrate for this effect. Our observations correlated with exposure-efficacy data from Gemini II and III trials. Conclusion Completely blocking T-Eff cell trafficking with vedolizumab, while simultaneously permitting residual homing of powerful T-Reg cells in an optimal 'therapeutic window' based on target exposure levels might be a strategy to optimise treatment outcomes in patients with IBD.
CRIS-Team WoS Importer:2021-12-10

Rhinovirus inhibits IL-17A and the downstream immune responses in allergic asthma - Graser, Anna; Ekici, Arif Bülent; Sopel, Nina; Melichar, V. O.; Zimmermann, Theodor; Papadopoulos, N. G.; Taka, S.; Ferrazzi, Fulvia; Vuorinen, T.; Finotto, Susetta (Mucosal Immunology, 2016)
The proinflammatory cytokine interleukin-17A (IL-17A) is known to mediate antimicrobial activity, but its role during rhinovirus (RV) infections and in asthma needs further investigation. Therefore, we addressed the role of IL-17A during allergic asthma and antiviral immune response in human and murine immunocompetent cells. In this study we found that asthmatic children with a RV infection in their upper airways have upregulated mRNA levels of the antiviral cytokine interferon type I (IFN)-? and the transcription factor T-box 21 (TBX21) and reduced levels of IL-17A protein in their peripheral blood mononuclear cells (PBMCs). We also found that IL-17A inhibited RV1b replication in infected human lung epithelial cells A549. Furthermore, by using gene array analysis we discovered that targeted deletion of Il17a in murine lung CD4(+) T cells impaired Oas1g mRNA downstream of Ifn?, independently from RV infection. Additionally, in PBMCs of children with a RV infection in their nasalpharyngeal fluid OAS1 gene expression was found downregulated. Finally RV1b inhibited IL-17A production in lung CD4(+) T cells in a setting of experimental asthma. These results indicate that the RV1b inhibits IL-17A in T helper type 17 cells and IL-17A clears RV1b infection in epithelial cells. In both cases IL-17A contributes to fend off RV1b infection by inducing genes downstream of interferon type I pathway.
EVALuna2:9312

Risk of Ovarian Cancer and the NF-?B Pathway: Genetic Association with IL1A and TNFSF10 - Charbonneau, Bridget; Block, Matthew S.; Bamlet, William R.; Vierkant, Robert A.; Kalli, Kimberly R.; Fogarty, Zachary; Rider, David N.; Sellers, Thomas A.; Tworoger, Shelley S.; Poole, Elizabeth; Risch, Harvey A.; Salvesen, Helga B.; et al. (Cancer Research, 2014)
A missense single-nucleotide polymorphism (SNP) in the immune modulatory gene IL1A has been associated with ovarian cancer risk (rs17561). Although the exact mechanism through which this SNP alters risk of ovarian cancer is not clearly understood, rs17561 has also been associated with risk of endometriosis, an epidemiologic risk factor for ovarian cancer. Interleukin-1? (IL1A) is both regulated by and able to activate NF-?B, a transcription factor family that induces transcription of many proinflammatory genes and may be an important mediator in carcinogenesis. We therefore tagged SNPs in more than 200 genes in the NF-?B pathway for a total of 2,282 SNPs (including rs17561) for genotype analysis of 15,604 cases of ovarian cancer in patients of European descent, including 6,179 of high-grade serous (HGS), 2,100 endometrioid, 1,591 mucinous, 1,034 clear cell, and 1,016 low-grade serous, including 23,235 control cases spanning 40 studies in the Ovarian Cancer Association Consortium. In this large population, we confirmed the association between rs17561 and clear cell ovarian cancer [OR, 0.84; 95% confidence interval (CI), 0.76-0.93; P = 0.00075], which remained intact even after excluding participants in the prior study (OR, 0.85; 95% CI, 0.75-0.95; P = 0.006). Considering a multiple-testing-corrected significance threshold of P < 2.5 × 10(-5), only one other variant, the TNFSF10 SNP rs6785617, was associated significantly with a risk of ovarian cancer (low malignant potential tumors OR, 0.85; 95% CI, 0.79-0.91; P = 0.00002). Our results extend the evidence that borderline tumors may have a distinct genetic etiology. Further investigation of how these SNPs might modify ovarian cancer associations with other inflammation-related risk factors is warranted. Cancer Res; 74(3); 852-61. ©2013 AACR.
EVALuna2:9204

Risk, Prediction and Prevention of Hereditary Breast Cancer - Large-Scale Genomic Studies in Times of Big and Smart Data - Wunderle, Marius; Olmes, Gregor; Nabieva, Naiba; Häberle, Lothar; Jud, Sebastian; Hein, Alexander; Rauh, Claudia; Hack, Carolin; Erber, Ramona; Ekici, Arif Bülent; Hoyer, Juliane; Vasileiou, Georgia; et al. (Geburtshilfe und Frauenheilkunde, 2018)
Over the last two decades genetic testing for mutations in BRCA1 and BRCA2 has become standard of care for women and men who are at familial risk for breast or ovarian cancer. Currently, genetic testing more often also includes so-called panel genes, which are assumed to be moderate-risk genes for breast cancer. Recently, new large-scale studies provided more information about the risk estimation of those genes. The utilization of information on panel genes with regard to their association with the individual breast cancer risk might become part of future clinical practice. Furthermore, large efforts have been made to understand the influence of common genetic variants with a low impact on breast cancer risk. For this purpose, almost 450 000 individuals have been genotyped for almost 500 000 genetic variants in the OncoArray project. Based on first results it can be assumed that - together with previously identified common variants - more than 170 breast cancer risk single nucleotide polymorphisms can explain up to 18% of familial breast cancer risk. The knowledge about genetic and non-genetic risk factors and its implementation in clinical practice could especially be of use for individualized prevention. This includes an individualized risk prediction as well as the individualized selection of screening methods regarding imaging and possible lifestyle interventions. The aim of this review is to summarize the most recent developments in this area and to provide an overview on breast cancer risk genes, risk prediction models and their utilization for the individual patient.
EVALuna2:34612

RNA-seq and pathway analysis of ocular tissues in PEX patients and healthy subjects - Pasutto, Francesca; Zenkel, Matthias; Berner, Daniel; Uebe, Steffen; Ekici, Arif Bülent; Kruse, Friedrich; Reis, André; Schlötzer-Schrehardt, Ursula (2018)
EVALuna2:34745

RNA sequencing reveals induction of specific renal inflammatory pathways in a rat model of malignant hypertension - Menendez-Castro, Carlos; Cordasic, Nada; Fahlbusch, Fabian; Ekici, Arif Bülent; Kirchner, Philipp; Daniel, Christoph; Amann, Kerstin Ute; Velkeen, Roland; Wölfle, Joachim; Schiffer, Mario; Hartner, Andrea; Hilgers, Karl Friedrich (Journal of Molecular Medicine, 2021)
Abstract: In malignant hypertension, far more severe kidney injury occurs than in the “benign” form of the disease. The role of high blood pressure and the renin–angiotensin–aldosterone system is well recognized, but the pathogenesis of the renal injury of malignant hypertension (MH) remains incompletely understood. Using the rat model of two-kidney, one-clip renovascular hypertension in which some but not all animals develop MH, we performed a transcriptomic analysis of gene expression by RNA sequencing to identify transcriptional changes in the kidney cortex specific for MH. Differential gene expression was assessed in three groups: MH, non-malignant hypertension (NMH), and normotensive, sham-operated controls. To distinguish MH from NMH, we considered two factors: weight loss and typical renovascular lesions. Mean blood pressure measured intraarterially was elevated in MH (220 ± 6.5 mmHg) as well as in NMH (192 ± 6.4 mmHg), compared to controls (119 ± 1.7 mmHg, p < 0.05). Eight hundred eighty-six genes were exclusively regulated in MH only. Principal component analysis revealed a separated clustering of the three groups. The data pointed to an upregulation of many inflammatory mechanisms in MH including pathways which previously attracted relatively little attention in the setting of hypertensive kidney injury: Transcripts from all three complement activation pathways were upregulated in MH compared to NMH but not in NMH compared with controls; immunohistochemistry confirmed complement deposition in MH exclusively. The expression of chemokines attracting neutrophil granulocytes (CXCL6) and infiltration of myeloperoxidase-positive cells were increased only in MH rats. The data suggest that these pathways, especially complement deposition, may contribute to kidney injury under MH. Key messages: The most severe hypertension-induced kidney injury occurs in malignant hypertension.In a rat model of malignant hypertension, we assessed transcriptional responses in the kidney exposed to high blood pressure. A broad stimulation of inflammatory mechanisms was observed, but a few specific pathways were activated only in the malignant form of the disease, notably activation of the complement cascades.Complement inhibitors may alleviate the thrombotic microangiopathy of malignant hypertension even in the absence of primary complement abnormalities.
CRIS-Team Scopus Importer:2021-09-24
Keywords: Complement activation; Inflammation; Kidney injury; Malignant hypertension; RNA-Seq; Two-kidney one-clip renovascular hypertension (2K1C)

Roflumilast inhibits tumor growth and migration in STK11/LKB1 deficient pancreatic cancer - Zhang, Shuman; Yun, Duo; Yang, Hao; Eckstein, Markus; Elbait, Gihan Daw; Zhou, Yaxing; Lu, Yanxi; Yang, Hai; Zhang, Jinping; Dörflein, Isabella; Britzen-Laurent, Nathalie; Pfeffer, Susanne; et al. (Cell Death Discovery, 2024)
Pancreatic cancer is a malignant tumor of the digestive system. It is highly aggressive, easily metastasizes, and extremely difficult to treat. This study aimed to analyze the genes that might regulate pancreatic cancer migration to provide an essential basis for the prognostic assessment of pancreatic cancer and individualized treatment. A CRISPR knockout library directed against 915 murine genes was transfected into TB 32047 cell line to screen which gene loss promoted cell migration. Next-generation sequencing and PinAPL.py- analysis was performed to identify candidate genes. We then assessed the effect of serine/threonine kinase 11 (STK11) knockout on pancreatic cancer by wound-healing assay, chick agnosia (CAM) assay, and orthotopic mouse pancreatic cancer model. We performed RNA sequence and Western blotting for mechanistic studies to identify and verify the pathways. After accelerated Transwell migration screening, STK11 was identified as one of the top candidate genes. Further experiments showed that targeted knockout of STK11 promoted the cell migration and increased liver metastasis in mice. Mechanistic analyses revealed that STK11 knockout influences blood vessel morphogenesis and is closely associated with the enhanced expression of phosphodiesterases (PDEs), especially PDE4D, PDE4B, and PDE10A. PDE4 inhibitor Roflumilast inhibited STK11-KO cell migration and tumor size, further demonstrating that PDEs are essential for STK11-deficient cell migration. Our findings support the adoption of therapeutic strategies, including Roflumilast, for patients with STK11-mutated pancreatic cancer in order to improve treatment efficacy and ultimately prolong survival.
CRIS-Team Scopus Importer:2024-04-12

rs495139 in the TYMS-ENOSF1 Region and Risk of Ovarian Carcinoma of Mucinous Histology - Kelemen, Linda E.; Earp, Madalene; Fridley, Brooke L.; Chenevix-Trench, Georgia; Fasching, Peter; Beckmann, Matthias; Ekici, Arif Bülent; Hein, Alexander; Lambrechts, Diether; Lambrechts, Sandrina; Van Nieuwenhuysen, Els; Vergote, Ignace; et al. (International Journal of Molecular Sciences, 2018)
Thymidylate synthase (TYMS) is a crucial enzyme for DNA synthesis. TYMS expression is regulated by its antisense mRNA, ENOSF1. Disrupted regulation may promote uncontrolled DNA synthesis and tumor growth. We sought to replicate our previously reported association between rs495139 in the TYMS-ENOSF1 3' gene region and increased risk of mucinous ovarian carcinoma (MOC) in an independent sample. Genotypes from 24,351 controls to 15,000 women with invasive OC, including 665 MOC, were available. We estimated per-allele odds ratios (OR) and 95% confidence intervals (CI) using unconditional logistic regression, and meta-analysis when combining these data with our previous report. The association between rs495139 and MOC was not significant in the independent sample (OR = 1.09; 95% CI = 0.97⁻1.22; p = 0.15; N = 665 cases). Meta-analysis suggested a weak association (OR = 1.13; 95% CI = 1.03⁻1.24; p = 0.01; N = 1019 cases). No significant association with risk of other OC histologic types was observed (p = 0.05 for tumor heterogeneity). In expression quantitative trait locus (eQTL) analysis, the rs495139 allele was positively associated with ENOSF1 mRNA expression in normal tissues of the gastrointestinal system, particularly esophageal mucosa (r = 0.51, p = 1.7 × 10-28), and nonsignificantly in five MOC tumors. The association results, along with inconclusive tumor eQTL findings, suggest that a true effect of rs495139 might be small.
EVALuna2:35118

Saliva samples as a source of DNA for high throughput genotyping: an acceptable and sufficient means in improvement of risk estimation throughout mammographic diagnostics - Poehls, U. G.; Hack, Caroline; Ekici, Arif Bülent; Beckmann, Matthias; Fasching, Peter; Rübner, Matthias; Hübner, Hanna (European Journal of Medical Research, 2018)
BACKGROUND: Breast cancer screening programs seem to be an insufficient tool for women at high genetic risk for breast cancer. These women are not adequately monitored yet. Genetic testing may improve clearly the quality of breast cancer prevention programs. At present, blood samples are favored for obtaining high-quality DNA; however, DNA can also be obtained by collecting saliva. The aim of this study was, on the one hand, to determine whether saliva sampling is a practicable means to obtain sufficient quantity and quality of DNA and, on the other hand, whether it is accepted by patients throughout mammographic diagnostics. METHODS: 67 consecutive women with diagnostic need for mammography with or without a family history for breast cancer were asked for their basic willingness to undergo a genetic testing by saliva sample in addition to standard diagnostics. Saliva samples were analyzed in terms of DNA quantity and quality. RESULTS: 64 (95.6%) women agreed to provide a saliva sample; 3 of them denied participation. And even 63 out of 64 (98.4%) were interested in their specific results. 45 out of 64 samples contained a DNA concentration above 50 ng/µl, 12 samples were between 25 and 50 ng/µl and only 7 of them were under 25 ng/µl with the standard extraction procedure. CONCLUSION: A high number of patients seem to accept salvia samples as a risk assessment tool in breast diagnostics and are interested in their specific risk situation. At the same time, it could be demonstrated that it is an effective way to provide high-quality DNA for breast cancer gene analysis. However, it remains to be shown whether it would be possible to integrate it with the same acceptance in a nationwide breast cancer screening program.
EVALuna2:34632

SCAF4 loss of function in humans and Drosophila implicates mRNA transcriptional termination in neuro-developmental disorders - Fliedner, Anna; Kirchner, P.; Agre, K. E.; De Graaf-Van De Laar, I.; Clarke, M. Dutra; Davis-Keppen, L.; Ekici, Arif Bülent; Gregor, Anne; Lippa, N.; Mcwalter, K.; Mirzaa, G.; Noh, G.; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

scRNA sequencing uncovers a TCF4-dependent transcription factor network regulating commissure development in mouse - Wittmann, Marie-Theres; Katada, Sayako; Sock, Elisabeth; Kirchner, Philipp; Ekici, Arif Bülent; Wegner, Michael; Nakashima, Kinichi; Lie, Dieter Chichung; Reis, André (Development, 2021)
Transcription factor 4 (TCF4) is a crucial regulator of neurodevelopment and has been linked to the pathogenesis of autism, intellectual disability and schizophrenia. As a class I bHLH transcription factor (TF), it is assumed that TCF4 exerts its neurodevelopmental functions through dimerization with proneural class II bHLH TFs. Here, we aim to identify TF partners of TCF4 in the control of interhemispheric connectivity formation. Using a new bioinformatic strategy integrating TF expression levels and regulon activities from single cell RNA-sequencing data, we find evidence that TCF4 interacts with non-bHLH TFs and modulates their transcriptional activity in Satb2+ intercortical projection neurons. Notably, this network comprises regulators linked to the pathogenesis of neurodevelopmental disorders, e.g. FOXG1, SOX11 and BRG1. In support of the functional interaction of TCF4 with non-bHLH TFs, we find that TCF4 and SOX11 biochemically interact and cooperatively control commissure formation in vivo, and regulate the transcription of genes implicated in this process. In addition to identifying new candidate interactors of TCF4 in neurodevelopment, this study illustrates how scRNA-Seq data can be leveraged to predict TF networks in neurodevelopmental processes.
CRIS-Team Scopus Importer:2021-08-13
Keywords: Commissure development; Gene regulatory networks; Mouse; Protein-protein interaction; Single-cell RNA sequencing; SOX11; TCF4

Serum levels of miR-320 family members are associated with clinical parameters and diagnosis in prostate cancer patients - Lieb, Verena; Weigelt, Katrin; Scheinost, Lena; Fischer, Kersten; Greither, Thomas; Marcou, Marios; Theil, Gerit; Klocker, Helmut; Holzhausen, Hans Juergen; Lai, Xin; Vera, Julio; Ekici, Arif Bülent; et al. (Oncotarget, 2018)
We studied the association of the serum levels of the microRNA family members miR-320a/-b/-c with clinico-pathological data to assess their applicability as diagnostic biomarker in prostate cancer (PCa) patients. The levels of miR-320a/-b/-c in 3 groups were evaluated by qRT-PCR (145 patients with PCa, 31 patients with benign prostatic hyperplasia (BPH) and 19 healthy controls). The levels of the three family members of miR-320 were directly correlated within each group (P < 0.001), but they differed significantly among the three groups (P < 0.001). The serum levels of the miR-320 family members were significantly increased in older patients compared to younger patients (≤ 66 years vs. > 66 years, P ≤ 0.001). In addition, the levels of all three miR-320 family members were significantly different in patients with low tumor stage compared with those with high tumor stage (miR-320a: P = 0.034; miR-320b: P = 0.006; miR-320c: P = 0.007) and in patients with low serum PSA compared with those with high serum PSA (≤ 4 ng vs. > 4 ng; miR-320a: P = 0.003; miR-320b: P = 0.003; miR-320c: P = 0.006). The levels of these miRNAs were inversely correlated with serum PSA levels. Detection in the serum samples of PCa patients with or without PSA relapse revealed higher levels of miR-320a/-b/-c in the group without PSA relapse before/after radical prostatectomy than in that with PCa relapse. In summary, the differences among the PCa/BPH/healthy control groups with respect to miR-320a/-b/-c levels in conjunction with higher levels in patients without a PSA relapse than in those with a relapse suggest the diagnostic potential of these miRNA-320 family members in PCa patients.
EVALuna2:35121

Single-cell RNA sequencing of adult mouse testes - Lukassen, Sören; Bosch, Elisabeth; Ekici, Arif Bülent; Winterpacht, Andreas (Scientific Data, 2018)
Spermatogenesis is an efficient and complex system of continuous cell differentiation. Previous studies investigating the transcriptomes of different cell populations in the testis relied either on sorting cells, cell depletion, or juvenile animals where not all stages of spermatogenesis have been completed. We present single-cell RNA sequencing (scRNA-Seq) data of 2,500 cells from the testes of two 8-week-old C57Bl/6J mice. Our dataset includes all spermatogenic stages from preleptotene to condensing spermatids as well as individual spermatogonia, Sertoli and Leydig cells. The data capture the full continuity of the meiotic and postmeiotic stages of spermatogenesis, and is thus ideally suited for marker discovery, network inference and similar analyses for which temporal ordering of differentiation processes can be exploited. Furthermore, it can serve as a reference for future studies involving single-cell RNA-Seq in mice where spermatogenesis is perturbed.
EVALuna2:34826

Single molecule real time sequencing in ADTKD-MUC1 allows complete assembly of the VNTR and exact positioning of causative mutations - Wenzel, Andrea; Altmueller, Janine; Ekici, Arif Bülent; Popp, Bernt; Stueber, Kurt; Thiele, Holger; Pannes, Alois; Staubach, Simon; Salido, Eduardo; Nuernberg, Peter; Reinhardt, Richard; Reis, André; et al. (Scientific Reports, 2018)
Recently, the Mucin-1 (MUC1) gene has been identified as a causal gene of autosomal dominant tubulointerstitial kidney disease (ADTKD). Most causative mutations are buried within a GC-rich 60 basepair variable number of tandem repeat (VNTR), which escapes identification by massive parallel sequencing methods due to the complexity of the VNTR. We established long read single molecule real time sequencing (SMRT) targeted to the MUC1-VNTR as an alternative strategy to the snapshot assay. Our approach allows complete VNTR assembly, thereby enabling the detection of all variants residing within the VNTR and simultaneous determination of VNTR length. We present high resolution data on the VNTR architecture for a cohort of snapshot positive (n = 9) and negative (n = 7) ADTKD families. By SMRT sequencing we could confirm the diagnosis in all previously tested cases, reconstruct both VNTR alleles and determine the exact position of the causative variant in eight of nine families. This study demonstrates that precise positioning of the causative mutation(s) and identification of other coding and noncoding sequence variants in ADTKD-MUC1 is feasible. SMRT sequencing could provide a powerful tool to uncover potential factors encoded within the VNTR that associate with intra- and interfamilial phenotype variability of MUC1 related kidney disease.
EVALuna2:34138

Sox11 is an Activity-Regulated Gene with Dentate-Gyrus-Specific Expression Upon General Neural Activation - von Wittgenstein, Julia; Zheng, Fang; Wittmann, Marie-Theres; Balta, Elli-Anna; Ferrazzi, Fulvia; Schäffner, Iris; Häberle, Benjamin; Valero Aracama, Maria Jesus; Koehl, Muriel; Miranda, Carlos J.; Kaspar, Brian K.; Ekici, Arif Bülent; et al. (Cerebral Cortex, 2020)
Neuronal activity initiates transcriptional programs that shape long-term changes in plasticity. Although neuron subtypes differ in their plasticity response, most activity-dependent transcription factors (TFs) are broadly expressed across neuron subtypes and brain regions. Thus, how region- and neuronal subtype-specific plasticity are established on the transcriptional level remains poorly understood. We report that in young adult (i.e., 6-8 weeks old) mice, the developmental TF SOX11 is induced in neurons within 6 h either by electroconvulsive stimulation or by exploration of a novel environment. Strikingly, SOX11 induction was restricted to the dentate gyrus (DG) of the hippocampus. In the novel environment paradigm, SOX11 was observed in a subset of c-FOS expressing neurons (ca. 15%); whereas around 75% of SOX11+ DG granule neurons were c-FOS+, indicating that SOX11 was induced in an activity-dependent fashion in a subset of neurons. Environmental enrichment or virus-mediated overexpression of SOX11 enhanced the excitability of DG granule cells and downregulated the expression of different potassium channel subunits, whereas conditional Sox11/4 knock-out mice presented the opposite phenotype. We propose that Sox11 is regulated in an activity-dependent fashion, which is specific to the DG, and speculate that activity-dependent Sox11 expression may participate in the modulation of DG neuron plasticity.
CRIS-Team Scopus Importer:2020-05-29
Keywords: dentate gyrus; hippocampus; immediate early gene; plasticity; Sox11

Specific phenotype and function of CD56-expressing innate immune cell subsets in human thymus - Gerstner, Stephanie; Köhler, Wolfgang; Heidkamp, Gordon Frederik; Purbojo, Ariawan; Uchida, Shizuka; Ekici, Arif Bülent; Heger, Lukas; Luetke-Eversloh, Merlin; Schubert, Ralf; Bader, Peter; Klingebiel, Thomas; Koehl, Ulrike; et al. (Journal of Leukocyte Biology, 2016)
Whereas innate immune cells, such as NK and innate lymphoid cells (ILCs), have been characterized in different human tissues, knowledge on the thymic CD56-expressing cell subsets is limited. In this study, the rare subpopulations of thymic CD56(+)CD3(-) cells from samples of >100 patients have been successfully analyzed. The results revealed fundamental differences between thymic and peripheral blood (PB) CD56(+)CD3(-) cells. Thymic tissues lacked immunoregulatory CD56(high)CD16(dim) NK cells but showed two Eomes(+)CD56(dim) subsets on which common NK cell markers were significantly altered. CD56(dim)CD16(high) cells expressed high amounts of NKG2A, NKG2D, and CD27 with low CD57. Conversely, CD56(dim)CD16(dim) cells displayed high CD127 but low expression of KIR, NKG2D, and natural cytotoxicity receptors (NCRs). Thymic CD56(+)CD3(-) cells were able to gain cytotoxicity but were especially immunoregulatory cells, producing a broad range of cytokines. Finally, one population of thymic CD56(+) cells resembled conventional NK cells, whereas the other represented a novel, noncanonical NK subset.
EVALuna2:9311

SRD5A3-CDG: Twins with an intragenic tandem duplication - Rieger, Melissa; Türk, Matthias; Kraus, Cornelia; Uebe, Steffen; Ekici, Arif Bülent; Krumbiegel, Mandy; Huchzermeyer, Cord; Wiesmann da Silva Reis, André; Thiel, Christian (European Journal of Medical Genetics, 2022)
Steroid 5α-reductase type 3 congenital disorder of glycosylation (SRD5A3-CDG) is a rare metabolic disease mainly characterized by psychomotor disability, visual impairment, and variable eye malformations caused by bi-allelic pathogenic variants in SRD5A3. So far, only 23 distinct mutations were described. Exome sequencing in 32-year old monozygotic male twins revealed only the heterozygous splice variant c.562+3delG in SRD5A3, but no second variant. The twins presented with psychomotor deficit and a complex eye disease including retinal dystrophy, pallor of the papilla, nystagmus, and strabismus suggestive of SRD5A3-CDG. Only when applying exome-based copy number analysis, we identified as a second compound heterozygous variant a previously not reported tandem duplication of exons 2–4 in SRD5A3. Next to the typical skeletal anomalies of SRD5A3-CDG such as kyphosis and scoliosis, extension deficits of the proximal interphalangeal (PIP) joints IV were observed. Since similar contractures were described once in a patient with SRD5A3-CDG, we suggest that this rare symptom is possibly associated with SRD5A3-CDG. Our findings further expand the mutational and clinical spectrum of SRD5A3-CDG and emphasize the importance of an intragenic copy number analysis in patients with strong clinical suspicion of SRD5A3-CDG and only one detectable sequence variant.
CRIS-Team Scopus Importer:2022-04-15
Keywords: CDG; Exon duplication; SRD5A3

Susceptibility gene mutations in germline and tumors of patients with HER2-negative advanced breast cancer - Fasching, Peter; Hu, Chunling; Hart, Steven N.; Rübner, Matthias; Polley, Eric C.; Gnanaolivu, Rohan D.; Hartkopf, Andreas D.; Hübner, Hanna; Janni, Wolfgang; Hadji, Peyman; Tesch, Hans; Uhrig, Sabrina; et al. (npj Breast Cancer, 2024)
Germline mutations in BRCA1 and BRCA2 (gBRCA1/2) are required for a PARP inhibitor therapy in patients with HER2-negative (HER2−) advanced breast cancer (aBC). However, little is known about the prognostic impact of gBRCA1/2 mutations in aBC patients treated with chemotherapy. This study aimed to investigate the frequencies and prognosis of germline and somatic BRCA1/2 mutations in HER2- aBC patients receiving the first chemotherapy in the advanced setting. Patients receiving their first chemotherapy for HER2- aBC were retrospectively selected from the prospective PRAEGNANT registry (NCT02338167). Genotyping of 26 cancer predisposition genes was performed with germline DNA of 471 patients and somatic tumor DNA of 94 patients. Mutation frequencies, progression-free and overall survival (PFS, OS) according to germline mutation status were assessed. gBRCA1/2 mutations were present in 23 patients (4.9%), and 33 patients (7.0%) had mutations in other cancer risk genes. Patients with a gBRCA1/2 mutation had a better OS compared to non-mutation carriers (HR: 0.38; 95%CI: 0.17–0.86). PFS comparison was not statistically significant. Mutations in other risk genes did not affect prognosis. Two somatic BRCA2 mutations were found in 94 patients without gBRCA1/2 mutations. Most frequently somatic mutated genes were TP53 (44.7%), CDH1 (10.6%) and PTEN (6.4%). In conclusion, aBC patients with gBRCA1/2 mutations had a more favorable prognosis under chemotherapy compared to non-mutation carriers. The mutation frequency of 5% with gBRCA1/2 mutations together with improved outcome indicates that germline genotyping of all metastatic patients for whom a PARP inhibitor therapy is indicated should be considered.
CRIS-Team Scopus Importer:2024-07-19

?-Synuclein-induced myelination deficit defines a novel interventional target for multiple system atrophy - Ettle, Benjamin; Kerman, Bilal E.; Valera, Elvira; Gillmann, Clarissa; Schlachetzki, Johannes; Reiprich, Simone; Büttner, Christian; Ekici, Arif Bülent; Reis, André; Wegner, Michael; Bäuerle, Tobias; Riemenschneider, Markus J.; et al. (Acta Neuropathologica, 2016)
Multiple system atrophy (MSA) is a rare atypical parkinsonian disorder characterized by a rapidly progressing clinical course and at present without any efficient therapy. Neuropathologically, myelin loss and neurodegeneration are associated with ?-synuclein accumulation in oligodendrocytes, but underlying pathomechanisms are poorly understood. Here, we analyzed the impact of oligodendrocytic ?-synuclein on the formation of myelin sheaths to define a potential interventional target for MSA. Post-mortem analyses of MSA patients and controls were performed to quantify myelin and oligodendrocyte numbers. As pre-clinical models, we used transgenic MSA mice, a myelinating stem cell-derived oligodendrocyte-neuron co-culture, and primary oligodendrocytes to determine functional consequences of oligodendrocytic ?-synuclein overexpression on myelination. We detected myelin loss accompanied by preserved or even increased numbers of oligodendrocytes in post-mortem MSA brains or transgenic mouse forebrains, respectively, indicating an oligodendrocytic dysfunction in myelin formation. Corroborating this observation, overexpression of ?-synuclein in primary and stem cell-derived oligodendrocytes severely impaired myelin formation, defining a novel ?-synuclein-linked pathomechanism in MSA. We used the pro-myelinating activity of the muscarinic acetylcholine receptor antagonist benztropine to analyze the reversibility of the myelination deficit. Transcriptome profiling of primary pre-myelinating oligodendrocytes demonstrated that benztropine readjusts myelination-related processes such as cholesterol and membrane biogenesis, being compromised by oligodendrocytic ?-synuclein. Additionally, benztropine restored the ?-synuclein-induced myelination deficit of stem cell-derived oligodendrocytes. Strikingly, benztropine also ameliorated the myelin deficit in transgenic MSA mice, resulting in a prevention of neuronal cell loss. In conclusion, this study defines the ?-synuclein-induced myelination deficit as a novel and crucial pathomechanism in MSA. Importantly, the reversible nature of this oligodendrocytic dysfunction opens a novel avenue for an intervention in MSA.
EVALuna2:4991

Tetrasomy of SCN2A associated with refractory neonatal epileptic encephalopathy - Krumbiegel, Mandy; Trollmann, Regina; Mammadova, Dilbar; Schnell, Alexander; Kraus, Cornelia; Ekici, Arif Bülent; Reis, André; Zweier, Christiane (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

Th2 single-cell heterogeneity and clonal distribution at distant sites in helminth-infected mice - Radtke, Daniel; Thuma, Natalie; Schülein, Christine; Kirchner, Philipp; Ekici, Arif Bülent; Schober, Kilian; Vöhringer, David (eLife, 2022)
Th2 cells provide effector functions in type 2 immune responses to helminths and allergens. Despite knowledge about molecular mechanisms of Th2 cell differentiation, there is little information on Th2 cell heterogeneity and clonal distribution between organs. To address this, we performed combined single-cell transcriptome and T-cell receptor (TCR) clonotype analysis on murine Th2 cells in mesenteric lymph nodes (MLNs) and lung after infection with Nippostrongylus brasiliensis (Nb) as a human hookworm infection model. We find organ-specific expression profiles, but also populations with conserved migration or effector/resident memory signatures that unexpectedly cluster with potentially regulatory Il10(pos)Foxp3(neg) cells. A substantial MLN subpopulation with an interferon response signature suggests a role for interferon signaling in Th2 differentiation or diversification. Further RNA-inferred developmental directions indicate proliferation as a hub for differentiation decisions. Although the TCR repertoire is highly heterogeneous, we identified expanded clones and CDR3 motifs. Clonal relatedness between distant organs confirmed effective exchange of Th2 effector cells, although locally expanded clones dominated the response. We further cloned an Nb-specific TCR from an expanded clone in the lung effector cluster and describe surface markers that distinguish transcriptionally defined clusters. These results provide insights in Th2 cell subset diversity and clonal relatedness in distant organs.
CRIS-Team WoS Importer:2022-09-02

The anti-viral properties of IL-17A in allergic asthma - Graser, Anna; Ekici, Arif Bülent; Melichar, Volker O.; Zimmermann, Theodor; Papadopoulos, Nikolaos G.; Taka, Stella; Ferrazzi, Fulvia; Vuorinen, Tytti; Finotto, Susetta (2015)
EVALuna2:25975

The clinical significance of small copy number variants in neurodevelopmental disorders - Asadollahi, Reza; Oneda, Beatrice; Joset, Pascal; Azzarello-Burri, Silvia; Bartholdi, Deborah; Steindl, Katharina; Vincent, Marie; Cobilanschi, Joana; Sticht, Heinrich; Baldinger, Rosa; Reissmann, Regina; Sudholt, Irene; et al. (Journal of Medical Genetics, 2014)
Despite abundant evidence for pathogenicity of large copy number variants (CNVs) in neurodevelopmental disorders (NDDs), the individual significance of genome-wide rare CNVs <500 kb has not been well elucidated in a clinical context.By high-resolution chromosomal microarray analysis, we investigated the clinical significance of all rare non-polymorphic exonic CNVs sizing 1-500 kb in a cohort of 714 patients with undiagnosed NDDs.We detected 96 rare CNVs <500 kb affecting coding regions, of which 58 (60.4%) were confirmed. 6 of 14 confirmed de novo, one of two homozygous and four heterozygous inherited CNVs affected the known microdeletion regions 17q21.31, 16p11.2 and 2p21 or OMIM morbid genes (CASK, CREBBP, PAFAH1B1, SATB2; AUTS2, NRXN3, GRM8). Two further de novo CNVs affecting single genes (MED13L, CTNND2) were instrumental in delineating novel recurrent conditions. For the first time, we here report exonic deletions of CTNND2 causing low normal IQ with learning difficulties with or without autism spectrum disorder. Additionally, we discovered a homozygous out-of-frame deletion of ACOT7 associated with features comparable to the published mouse model. In total, 24.1% of the confirmed small CNVs were categorised as pathogenic or likely pathogenic (median size 130 kb), 17.2% as likely benign, 3.4% represented incidental findings and 55.2% remained unclear.These results verify the diagnostic relevance of genome-wide rare CNVs <500 kb, which were found pathogenic in 2% (14/714) of cases (1.1% de novo, 0.3% homozygous, 0.6% inherited) and highlight their inherent potential for discovery of new conditions.
EVALuna2:9237

The complement system drives local inflammatory tissue priming by metabolic reprogramming of synovial fibroblasts - Friščić, Jasna; Böttcher, Martin; Reinwald, Christiane; Bruns, Heiko; Wirth, Benjamin; Popp, Sebastian; Walker, Kellie Irene; Ackermann, Jochen A.; Chen, Xi; Turner, Jason; Zhu, Honglin; Seyler, Lisa; et al. (Immunity, 2021)
Arthritis typically involves recurrence and progressive worsening at specific predilection sites, but the checkpoints between remission and persistence remain unknown. Here, we defined the molecular and cellular mechanisms of this inflammation-mediated tissue priming. Re-exposure to inflammatory stimuli caused aggravated arthritis in rodent models. Tissue priming developed locally and independently of adaptive immunity. Repeatedly stimulated primed synovial fibroblasts (SFs) exhibited enhanced metabolic activity inducing functional changes with intensified migration, invasiveness and osteoclastogenesis. Meanwhile, human SF from patients with established arthritis displayed a similar primed phenotype. Transcriptomic and epigenomic analyses as well as genetic and pharmacological targeting demonstrated that inflammatory tissue priming relies on intracellular complement C3- and C3a receptor-activation and downstream mammalian target of rapamycin- and hypoxia-inducible factor 1α-mediated metabolic SF invigoration that prevents activation-induced senescence, enhances NLRP3 inflammasome activity, and in consequence sensitizes tissue for inflammation. Our study suggests possibilities for therapeutic intervention abrogating tissue priming without immunosuppression.
CRIS-Team Scopus Importer:2021-04-19
Keywords: arthritis; cell metabolism; cellular senescence; complement system; inflammasome; inflammation; mechanistic target of rapamycin; synovial fibroblasts; tissue priming; trained immunity

The FANCM:p.Arg658* truncating variant is associated with risk of triple-negative breast cancer - Figlioli, Gisella; Bogliolo, Massimo; Catucci, Irene; Caleca, Laura; Lasheras, Sandra Viz; Pujol, Roser; Kiiski, Johanna I.; Muranen, Taru A.; Barnes, Daniel R.; Dennis, Joe; Michailidou, Kyriaki; Bolla, Manjeet K.; et al. (npj Breast Cancer, 2019)
Breast cancer is a common disease partially caused by genetic risk factors. Germline pathogenic variants in DNA repair genes BRCA1, BRCA2, PALB2, ATM, and CHEK2 are associated with breast cancer risk. FANCM, which encodes for a DNA translocase, has been proposed as a breast cancer predisposition gene, with greater effects for the ER-negative and triple-negative breast cancer (TNBC) subtypes. We tested the three recurrent protein-truncating variants FANCM:p.Arg658*, p.Gln1701*, and p.Arg1931* for association with breast cancer risk in 67,112 cases, 53,766 controls, and 26,662 carriers of pathogenic variants of BRCA1 or BRCA2. These three variants were also studied functionally by measuring survival and chromosome fragility in FANCM−/− patient-derived immortalized fibroblasts treated with diepoxybutane or olaparib. We observed that FANCM:p.Arg658* was associated with increased risk of ER-negative disease and TNBC (OR = 2.44, P = 0.034 and OR = 3.79; P = 0.009, respectively). In a country-restricted analysis, we confirmed the associations detected for FANCM:p.Arg658* and found that also FANCM:p.Arg1931* was associated with ER-negative breast cancer risk (OR = 1.96; P = 0.006). The functional results indicated that all three variants were deleterious affecting cell survival and chromosome stability with FANCM:p.Arg658* causing more severe phenotypes. In conclusion, we confirmed that the two rare FANCM deleterious variants p.Arg658* and p.Arg1931* are risk factors for ER-negative and TNBC subtypes. Overall our data suggest that the effect of truncating variants on breast cancer risk may depend on their position in the gene. Cell sensitivity to olaparib exposure, identifies a possible therapeutic option to treat FANCM-associated tumors.
CRIS-Team Scopus Importer:2019-11-12

The missing link: ARID1B non-truncating variants causing Coffin-Siris syndrome due to protein aggregation - Bosch, Elisabeth; Güse, Esther; Kirchner, Philipp; Winterpacht, Andreas; Walther, Mona; Alders, Marielle; Kerkhof, Jennifer; Ekici, Arif Bülent; Sticht, Heinrich; Sadikovic, Bekim; Reis, André; Vasileiou, Georgia (Human genetics, 2024)
ARID1B is the most frequently mutated gene in Coffin-Siris syndrome (CSS). To date, the vast majority of causative variants reported in ARID1B are truncating, leading to nonsense-mediated mRNA decay. In the absence of experimental data, only few ARID1B amino acid substitutions have been classified as pathogenic, mainly based on clinical data and their de novo occurrence, while most others are currently interpreted as variants of unknown significance. The present study substantiates the pathogenesis of ARID1B non-truncating/NMD-escaping variants located in the SMARCA4-interacting EHD2 and DNA-binding ARID domains. Overexpression assays in cell lines revealed that the majority of EHD2 variants lead to protein misfolding and formation of cytoplasmic aggresomes surrounded by vimentin cage-like structures and co-localizing with the microtubule organisation center. ARID domain variants exhibited not only aggresomes, but also nuclear aggregates, demonstrating robust pathological effects. Protein levels were not compromised, as shown by quantitative western blot analysis. In silico structural analysis predicted the exposure of amylogenic segments in both domains due to the nearby variants, likely causing this aggregation. Genome-wide transcriptome and methylation analysis in affected individuals revealed expression and methylome patterns consistent with those of the pathogenic haploinsufficiency ARID1B alterations in CSS cases. These results further support pathogenicity and indicate two approaches for disambiguation of such variants in everyday practice. The few affected individuals harbouring EHD2 non-truncating variants described to date exhibit mild CSS clinical traits. In summary, this study paves the way for the re-evaluation of previously unclear ARID1B non-truncating variants and opens a new era in CSS genetic diagnosis.
CRIS-Team Scopus Importer:2024-07-26

The mutational and phenotypic spectrum of TUBA1A-associated tubulinopathy - Hebebrand, Moritz; Hüffmeier, Ulrike; Trollmann, Regina; Hehr, Ute; Uebe, Steffen; Ekici, Arif Bülent; Kraus, Cornelia; Krumbiegel, Mandy; Reis, André; Thiel, Christian; Popp, Bernt (Orphanet Journal of Rare Diseases, 2019)
BackgroundThe TUBA1A-associated tubulinopathy is clinically heterogeneous with brain malformations, microcephaly, developmental delay and epilepsy being the main clinical features. It is an autosomal dominant disorder mostly caused by de novo variants in TUBA1A.ResultsIn three individuals with developmental delay we identified heterozygous de novo missense variants in TUBA1A using exome sequencing. While the c.1307G>A, p.(Gly436Asp) variant was novel, the two variants c.518C>T, p.(Pro173Leu) and c.641G>A, p.(Arg214His) were previously described. We compared the variable phenotype observed in these individuals with a carefully conducted review of the current literature and identified 166 individuals, 146 born and 20 fetuses with a TUBA1A variant. In 107 cases with available clinical information we standardized the reported phenotypes according to the Human Phenotype Ontology. The most commonly reported features were developmental delay (98%), anomalies of the corpus callosum (96%), microcephaly (76%) and lissencephaly (agyria-pachygyria) (70%), although reporting was incomplete in the different studies. We identified a total of 121 specific variants, including 15 recurrent ones. Missense variants cluster in the C-terminal region around the most commonly affected amino acid position Arg402 (13.3%). In a three-dimensional protein model, 38.6% of all disease-causing variants including those in the C-terminal region are predicted to affect the binding of microtubule-associated proteins or motor proteins. Genotype-phenotype analysis for recurrent variants showed an overrepresentation of certain clinical features. However, individuals with these variants are often reported in the same publication.ConclusionsWith 166 individuals, we present the most comprehensive phenotypic and genotypic standardized synopsis for clinical interpretation of TUBA1A variants. Despite this considerable number, a detailed genotype-phenotype characterization is limited by large inter-study variability in reporting.
CRIS-Team WoS Importer:2019-02-27

The polynucleotide kinase 3'-phosphatase gene (PNKP) is involved in Charcot-Marie-Tooth disease (CMT2B2) previously related to MED25 - Leal, Alejandro; Bogantes-Ledezma, Sixto; Ekici, Arif Bülent; Uebe, Steffen; Thiel, Christian; Sticht, Heinrich; Berghoff, Martin; Berghoff, Corinna; Morera, Bernal; Meisterernst, Michael; Reis, André (Neurogenetics, 2018)
Charcot-Marie-Tooth disease (CMT) represents a heterogeneous group of hereditary peripheral neuropathies. We previously reported a CMT locus on chromosome 19q13.3 segregating with the disease in a large Costa Rican family with axonal neuropathy and autosomal recessive pattern of inheritance (CMT2B2). We proposed a homozygous missense variant in the Mediator complex 25 (MED25) gene as causative of the disease. Nevertheless, the fact that no other CMT individuals with MED25 variants were reported to date led us to reevaluate the original family. Using exome sequencing, we now identified a homozygous nonsense variant (p.Gln517ter) in the last exon of an adjacent gene, the polynucleotide kinase 3'-phosphatase (PNKP) gene. It encodes a DNA repair protein recently associated with recessive ataxia with oculomotor apraxia type 4 (AOA4) and microcephaly, seizures, and developmental delay (MCSZ). Subsequently, five unrelated Costa Rican CMT2 subjects initially identified as being heterozygous for the same MED25 variant were found to be also compound heterozygote for PNKP. All were heterozygous for the same variant found homozygous in the large family and a second one previously associated with ataxia (p.Thr408del). Detailed clinical reassessment of the initial family and the new individuals revealed in all an adult-onset slowly progressive CMT2 associated with signs of cerebellar dysfunction such as slurred speech and oculomotor involvement, but neither microcephaly, seizures, nor developmental delay. We propose that PKNP variants are the major causative variant for the CMT2 phenotype in these individuals and that the milder clinical manifestation is due to an allelic effect.
EVALuna2:35117

The proinflammatory effect of C-reactive protein on human endothelial cells depends on the Fc?RIIa genotype - Raaz-Schrauder, Dorette; Ekici, Arif Bülent; Klinghammer, Lutz; Stumpf, Christian; Achenbach, Stephan; Herrmann, Martin; Reis, André; Garlichs, Christoph (Thrombosis Research, 2014)
The stimulatory effects of CRP (C-reactive protein) on endothelial cells are mainly mediated via Fc?RIIa. This receptor exists in two different allotypes bearing either arginine (R131) or histidine (H131) at the extracellular amino acid position 131 of the mature protein, but only Fc?RIIa-R131 displays high avidity for CRP. This study investigated the role of the Fc?RIIa genotype in CRP-stimulated endothelial cells.We tested the effects of CRP on expression of the adhesion molecules ICAM-1, VCAM-1, and E-selectin, as well as the endothelial release of pro-inflammatory molecules as a function of the Fc?RIIa-genotype (Fc?RIIa-H/H131, Fc?RIIa-H/R131, Fc?RIIa-R/R131) in HUVEC (Human Umbilical Vein Endothelial Cells). HUVEC were grouped according to their Fc?RIIa status by genotyping with an allele specific nested-PCR. The expression of ICAM-1, VCAM-1, and E-selectin on HUVEC was detected by flow cytometry. The release of soluble markers (sCD40L, IL-6, IL-8, MCP-1, tPA, sP-selectin, and sVCAM-1) was measured using a multiplex assay for flow cytometry.CRP-stimulated expression of ICAM-1 and E-selectin was dependent on the specific Fc?RIIa-genotype, with most pronounced induction in HUVEC with the Fc?RIIa-R/R genotype, followed by H/R and H/H. In accordance with this finding, the supernatants of stimulated HUVEC with the R/R genotype showed significantly higher levels of tPA, MCP-1, and IL-6. Our data show that CRP stimulates the expression of adhesion molecules and the release of soluble markers by HUVEC as a function of the Fc?RIIa-genotype. These findings could be relevant in the context of risk stratification in patients with cardiovascular disease.
EVALuna2:9209

The pseudokinase MLKL mediates programmed hepatocellular necrosis independently of RIPK3 during hepatitis - Lopez Posadas, Rocío; Becker, Christoph; Günther, Claudia; Tenzer, Stefan; Amann, Kerstin Ute; Billmeier, Ulrike; Atreya, Raja; Fiorino, Gionata; Vetrano, Stefania; Danese, Silvio; Ekici, Arif Bülent; Wirtz, Stefan; et al. (Journal of Clinical Investigation, 2016)
Although necrosis and necroinflammation are central features of many liver diseases, the role of programmed necrosis in the context of inflammation-dependent hepatocellular death remains to be fully determined. Here, we have demonstrated that the pseudokinase mixed lineage kinase domain-like protein (MLKL), which plays a key role in the execution of receptor-interacting protein (RIP) kinase-dependent necroptosis, is upregulated and activated in human autoimmune hepatitis and in a murine model of inflammation-dependent hepatitis. Using genetic and pharmacologic approaches, we determined that hepatocellular necrosis in experimental hepatitis is driven by an MLKL-dependent pathway that occurs independently of RIPK3. Moreover, we have provided evidence that the cytotoxic activity of the proinflammatory cytokine IFN-? in hepatic inflammation is strongly connected to induction of MLKL expression via activation of the transcription factor STAT1. In summary, our results reveal a pathway for MLKL-dependent programmed necrosis that is executed in the absence of RIPK3 and potentially drives the pathogenesis of severe liver diseases.
EVALuna2:2178

Transcription factor Fra-1 targets arginase-1 to enhance macrophage-mediated inflammation in arthritis - Hannemann, Nicole; Cao, Shan; Eriksson, Daniel; Schnelzer, Anne; Jordan, Jutta; Eberhardt, Martin; Schleicher, Ulrike; Rech, Jürgen; Uebe, Steffen; Ekici, Arif Bülent; Canete, Juan D.; Chen, Xiaoxiang; et al. (Journal of Clinical Investigation, 2019)
The polarization of macrophages is regulated by transcription factors, such as NF-κB and activator protein 1 (AP-1). In this manuscript, we delineated the role of the transcription factor Fos-related antigen 1 (Fra-1) during macrophage activation and development of arthritis. Network level interaction analysis of microarray data derived from Fra-1- or Fra-2-deficient macrophages revealed a central role of Fra-1, but not of Fra-2, in orchestrating the expression of genes related to wound response, Toll-like receptor activation, and interleukin signaling. ChIP sequencing and standard ChIP analyses of macrophages identified arginase 1 (Arg1) as a target of Fra-1. Luciferase reporter assays revealed that Fra-1 downregulated Arg1 expression by direct binding to the promoter region. Using macrophage-specific Fra-1- or Fra-2-deficient mice, we observed enhanced expression and activity of Arg1 and a reduction of arthritis in the absence of Fra-1, but not of Fra-2. This phenotype was reversed by treatment with the arginase inhibitor Nω-hydroxy-nor-arginine, while -arginine supplementation increased arginase activity and alleviated arthritis, supporting the notion that reduced arthritis in macrophage-specific Fra-1-deficient mice resulted from enhanced Arg1 expression and activity. Moreover, patients with active rheumatoid arthritis (RA) showed increased Fra-1 expression in the peripheral blood and elevated Fra-1 protein in synovial macrophages compared with RA patients in remission. In addition, the Fra-1/ARG1 ratio in synovial macrophages was related to RA disease activity. In conclusion, these data suggest that Fra-1 orchestrates the inflammatory state of macrophages by inhibition of Arg1 expression and thereby impedes the resolution of inflammation.
CRIS-Team Scopus Importer:2019-07-16

Transcriptome sequencing reveals maelstrom as a novel target gene of the terminal system in the red flour beetle Tribolium castaneum - Pridöhl, Fabian; Weißkopf, Matthias; Koniszewski, Nikolaus; Sulzmaier, Andreas; Uebe, Steffen; Ekici, Arif Bülent; Schoppmeier, Michael (Development, 2017)
Terminal regions of the Drosophila embryo are patterned by the localized activation of the Torso-RTK pathway, which promotes the downregulation of Capicua. In the short-germ beetle Tribolium, the function of the terminal system appears to be rather different, as the pathway promotes axis elongation and, in addition, is required for patterning the extra-embryonic serosa at the anterior. Here, we show that Torso signalling also induces gene expression by relieving Capicua-mediated repression in Tribolium Given that the majority of Torso target genes remain to be identified, we established a differential gene-expression screen. A subset of 50 putative terminal target genes was screened for functions in early embryonic patterning. Of those, 13 genes show early terminal expression domains and also phenotypes were related to terminal patterning. Among others, we found the PIWI-interacting RNA factor Maelstrom to be crucial for early embryonic polarization. Tc-mael is required for proper serosal size regulation and head morphogenesis. Moreover, Tc-mael promotes growth-zone formation and axis elongation. Our results suggest that posterior patterning by Torso may be realized through Maelstrom-dependent activation of posterior Wnt domains.
EVALuna2:9357

Transcriptomes of MPO-Deficient Patients with Generalized Pustular Psoriasis Reveals Expansion of CD4+ Cytotoxic T Cells and an Involvement of the Complement System - Haskamp, Stefan; Frey, Benjamin; Becker, Ina; Schulz-Kuhnt, Anja; Atreya, Imke; Berking, Carola; Pauli, David; Ekici, Arif Bülent; Berges, Johannes; Mößner, Rotraut; Wilsmann-Theis, Dagmar; Sticherling, Michael; et al. (Journal of Investigative Dermatology, 2022)
Generalized pustular psoriasis is a severe psoriatic subtype characterized by epidermal neutrophil infiltration. Although variants in IL36RN and MPO have been shown to affect immune cells, a systematic analysis of neutrophils and PBMC subsets and their differential gene expression dependent on MPO genotypes was not performed yet. We assessed the transcriptomes of MPO-deficient patients using single-cell RNA sequencing of PBMCs and RNA sequencing of neutrophils in a stable disease state. Cell-type annotation by multimodal reference mapping of single-cell RNA-sequencing data was verified by flow cytometry of surface and intracellular markers; the proportions of CD4+ cytotoxic T lymphocytes and other CD4+ effector cells were increased in generalized pustular psoriasis, whereas the frequencies of naïve CD4+ T cells were significantly lower. The expression of FGFBP2 marking CD4+ cytotoxic T lymphocytes and CD8+ effector memory T cells was elevated in patients with generalized pustular psoriasis with disease-contributing variants compared with that in noncarriers (P = 0.0015). In neutrophils, differentially expressed genes were significantly enriched in genes of the classical complement activation pathway. Future studies assessing affected cell types and pathways will show their contribution to generalized pustular psoriasis's pathogenesis and indicate whether findings can be transferred to the acute epidermal situation and whether depletion or inactivation of CD4+ cytotoxic T lymphocytes may be a reasonable therapeutic approach.
CRIS-Team Scopus Importer:2022-07-08

TRIM28 haploinsufficiency predisposes to Wilms tumor - Diets, Illja J.; Hoyer, Juliane; Ekici, Arif Bülent; Popp, Bernt; Hoogerbrugge, Nicoline; van Reijmersdal, Simon V.; Bhaskaran, Rajith; Hadjihannas, Michel; Vasileiou, Georgia; Thiel, Christian; Seven, Didem; Uebe, Steffen; et al. (International Journal of Cancer, 2019)
Two percent of patients with Wilms tumors have a positive family history. In many of these cases the genetic cause remains unresolved. By applying germline exome sequencing in two families with two affected individuals with Wilms tumors, we identified truncating mutations in TRIM28. Subsequent mutational screening of germline and tumor DNA of 269 children affected by Wilms tumor was performed, and revealed seven additional individuals with germline truncating mutations, and one individual with a somatic truncating mutation in TRIM28. TRIM28 encodes a complex scaffold protein involved in many different processes, including gene silencing, DNA repair and maintenance of genomic integrity. Expression studies on mRNA and protein level showed reduction of TRIM28, confirming a loss-of-function effect of the mutations identified. The tumors showed an epithelial-type histology that stained negative for TRIM28 by immunohistochemistry. The tumors were bilateral in six patients, and 10/11 tumors are accompanied by perilobar nephrogenic rests. Exome sequencing on eight tumor DNA samples from six individuals showed loss-of-heterozygosity (LOH) of the TRIM28-locus by mitotic recombination in seven tumors, suggesting that TRIM28 functions as a tumor suppressor gene in Wilms tumor development. Additionally, the tumors showed very few mutations in known Wilms tumor driver genes, suggesting that loss of TRIM28 is the main driver of tumorigenesis. In conclusion, we identified heterozygous germline truncating mutations in TRIM28 in 11 children with mainly epithelial-type Wilms tumors, which become homozygous in tumor tissue. These data establish TRIM28 as a novel Wilms tumor predisposition gene, acting as a tumor suppressor gene by LOH.
CRIS-Team Scopus Importer:2019-05-02
Keywords: genetic predisposition; haploinsufficiency; TRIM28; Wilms tumor

Tumor microenvironment-dependent epigenetic imprinting in the vasculature predicts colon cancer outcome - Naschberger, Elisabeth; Fuchs, Maximilian; Dickel, Nicholas; Kunz, Meik; Popp, Bernt; Anchang, Charles Gwellem; Demmler, Richard; Lyu, Yanmin; Uebe, Steffen; Ekici, Arif Bülent; Geppert, Carol-Immanuel; Hartmann, Arndt; et al. (Cancer Communications, 2023)
CRIS-Team Scopus Importer:2023-10-27

Two truncating variants in FANCC and breast cancer risk - Dork, Thilo; Peterlongo, Paolo; Mannermaa, Arto; Bolla, Manjeet K.; Wang, Qin; Dennis, Joe; Ahearn, Thomas; Andrulis, Irene L.; Anton-Culver, Hoda; Arndt, Volker; Aronson, Kristan J.; Augustinsson, Annelie; et al. (Scientific Reports, 2019)
Fanconi anemia (FA) is a genetically heterogeneous disorder with 22 disease-causing genes reported to date. In some FA genes, monoallelic mutations have been found to be associated with breast cancer risk, while the risk associations of others remain unknown. The gene for FA type C, FANCC, has been proposed as a breast cancer susceptibility gene based on epidemiological and sequencing studies. We used the Oncoarray project to genotype two truncating FANCC variants (p.R185X and p.R548X) in 64,760 breast cancer cases and 49,793 controls of European descent. FANCC mutations were observed in 25 cases (14 with p.R185X, 11 with p.R548X) and 26 controls (18 with p.R185X, 8 with p.R548X). There was no evidence of an association with the risk of breast cancer, neither overall (odds ratio 0.77, 95%CI 0.44–1.33, p = 0.4) nor by histology, hormone receptor status, age or family history. We conclude that the breast cancer risk association of these two FANCC variants, if any, is much smaller than for BRCA1, BRCA2 or PALB2 mutations. If this applies to all truncating variants in FANCC it would suggest there are differences between FA genes in their roles on breast cancer risk and demonstrates the merit of large consortia for clarifying risk associations of rare variants.
CRIS-Team Scopus Importer:2019-09-17

Unexpected phenotypic variability in a family with epilepsy explained by independent segregation of biparental CACNA1A loss-of-function variants - Kraus, Cornelia; Mammadova, Dilbar; Leis, T.; Ekici, Arif Bülent; Thiel, C.; Reis, André; Trollmann, Regina (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

Variants in genes encoding small GTPases and association with epithelial ovarian cancer susceptibility - Earp, Madalene; Tyrer, Jonathan P.; Winham, Stacey J.; Lin, Hui-Yi; Chornokur, Ganna; Dennis, Joe; Aben, Katja K. H.; Anton-Culver, Hoda; Antonenkova, Natalia; Bandera, Elisa V.; Bean, Yukie T.; Beckmann, Matthias; et al. (PLoS ONE, 2018)
Epithelial ovarian cancer (EOC) is the fifth leading cause of cancer mortality in American women. Normal ovarian physiology is intricately connected to small GTP binding proteins of the Ras superfamily (Ras, Rho, Rab, Arf, and Ran) which govern processes such as signal transduction, cell proliferation, cell motility, and vesicle transport. We hypothesized that common germline variation in genes encoding small GTPases is associated with EOC risk. We investigated 322 variants in 88 small GTPase genes in germline DNA of 18,736 EOC patients and 26,138 controls of European ancestry using a custom genotype array and logistic regression fitting log-additive models. Functional annotation was used to identify biofeatures and expression quantitative trait loci that intersect with risk variants. One variant, ARHGEF10L (Rho guanine nucleotide exchange factor 10 like) rs2256787, was associated with increased endometrioid EOC risk (OR = 1.33, p = 4.46 x 10-6). Other variants of interest included another in ARHGEF10L, rs10788679, which was associated with invasive serous EOC risk (OR = 1.07, p = 0.00026) and two variants in AKAP6 (A-kinase anchoring protein 6) which were associated with risk of invasive EOC (rs1955513, OR = 0.90, p = 0.00033; rs927062, OR = 0.94, p = 0.00059). Functional annotation revealed that the two ARHGEF10L variants were located in super-enhancer regions and that AKAP6 rs927062 was associated with expression of GTPase gene ARHGAP5 (Rho GTPase activating protein 5). Inherited variants in ARHGEF10L and AKAP6, with potential transcriptional regulatory function and association with EOC risk, warrant investigation in independent EOC study populations.
EVALuna2:34624

Variants in SCAF4 Cause a Neurodevelopmental Disorder and Are Associated with Impaired mRNA Processing - Fliedner, Anna; Kirchner, Philipp; Wiesener, Antje; van de Beek, Irma; Waisfisz, Quinten; van Haelst, Mieke; Scott, Daryl A.; Lalani, Seema R.; Rosenfeld, Jill A.; Azamian, Mahshid S.; Xia, Fan; Dutra-Clarke, Marina; et al. (American Journal of Human Genetics, 2020)
RNA polymerase II interacts with various other complexes and factors to ensure correct initiation, elongation, and termination of mRNA transcription. One of these proteins is SR-related CTD-associated factor 4 (SCAF4), which is important for correct usage of polyA sites for mRNA termination. Using exome sequencing and international matchmaking, we identified nine likely pathogenic germline variants in SCAF4 including two splice-site and seven truncating variants, all residing in the N-terminal two thirds of the protein. Eight of these variants occurred de novo, and one was inherited. Affected individuals demonstrated a variable neurodevelopmental disorder characterized by mild intellectual disability, seizures, behavioral abnormalities, and various skeletal and structural anomalies. Paired-end RNA sequencing on blood lymphocytes of SCAF4-deficient individuals revealed a broad deregulation of more than 9,000 genes and significant differential splicing of more than 2,900 genes, indicating an important role of SCAF4 in mRNA processing. Knockdown of the SCAF4 ortholog CG4266 in the model organism Drosophila melanogaster resulted in impaired locomotor function, learning, and short-term memory. Furthermore, we observed an increased number of active zones in larval neuromuscular junctions, representing large glutamatergic synapses. These observations indicate a role of CG4266 in nervous system development and function and support the implication of SCAF4 in neurodevelopmental phenotypes. In summary, our data show that heterozygous, likely gene-disrupting variants in SCAF4 are causative for a variable neurodevelopmental disorder associated with impaired mRNA processing.
CRIS-Team Scopus Importer:2020-08-21
Keywords: epilepsy; intellectual disability; mRNA processing; neurodevelopmental disorder; SCAF4; seizures

Variation in NF-?B signaling pathways and survival in invasive epithelial ovarian cancer - Block, Matthew S.; Charbonneau, Bridget; Vierkant, Robert A.; Fogarty, Zachary; Bamlet, William R.; Pharoah, Paul D. P.; Chenevix-Trench, Georgia; Rossing, Mary Anne; Cramer, Daniel; Pearce, Celeste Leigh; Schildkraut, Joellen; Menon, Usha; et al. (Cancer Epidemiology Biomarkers & Prevention, 2014)
Survival in epithelial ovarian cancer (EOC) is influenced by the host immune response, yet the key genetic determinants of inflammation and immunity that affect prognosis are not known. The nuclear factor-?B (NF-?B) transcription factor family plays an important role in many immune and inflammatory responses, including the response to cancer. We studied common inherited variation in 210 genes in the NF-?B family in 10,084 patients with invasive EOC (5,248 high-grade serous, 1,452 endometrioid, 795 clear cell, and 661 mucinous) from the Ovarian Cancer Association Consortium. Associations between genotype and overall survival were assessed using Cox regression for all patients and by major histology, adjusting for known prognostic factors and correcting for multiple testing (threshold for statistical significance, P < 2.5 × 10(-5)). Results were statistically significant when assessed for patients of a single histology. Key associations were with caspase recruitment domain family, member 11 (CARD11) rs41324349 in patients with mucinous EOC [HR, 1.82; 95% confidence interval (CI), 1.41-2.35; P = 4.13 × 10(-6)] and tumor necrosis factor receptor superfamily, member 13B (TNFRSF13B) rs7501462 in patients with endometrioid EOC (HR, 0.68; 95% CI, 0.56-0.82; P = 2.33 × 10(-5)). Other associations of note included TNF receptor-associated factor 2 (TRAF2) rs17250239 in patients with high-grade serous EOC (HR, 0.84; 95% CI, 0.77-0.92; P = 6.49 × 10(-5)) and phospholipase C, gamma 1 (PLCG1) rs11696662 in patients with clear cell EOC (HR, 0.43; 95% CI, 0.26-0.73; P = 4.56 × 10(-4)). These associations highlight the potential importance of genes associated with host inflammation and immunity in modulating clinical outcomes in distinct EOC histologies.
EVALuna2:9241

Whole exome sequencing reveals a novel de novo FOXC1 mutation in a patient with unrecognized Axenfeld-Rieger syndrome and glaucoma - Pasutto, F.; Mauri, L.; Popp, Bernt; Sticht, Heinrich; Ekici, Arif Bülent; Piozzi, E.; Bonfante, A.; Penco, Silvana; Schlötzer-Schrehardt, Ursula; Reis, André (Gene, 2015)
We report the identification of a novel mutation in the fork-head box C1 (FOXC1) gene which occurred de novo in an Italian patient with unrecognized Axenfeld-Rieger syndrome. He was previously diagnosed as having late recognized primary congenital glaucoma at the age of 14 years and was subsequently subjected to multiple surgical interventions due to uncontrolled intraocular pressure and progressive visual field loss. After exclusion of mutations in CYP1B1 and MYOC, trio-whole-exome sequencing revealed de novo in frame deletion in the coding region of the FOXC1 gene (c.407_409delGTC, p.V137del) leading to a deletion of the evolutionary conserved amino acid Valine at position 137 of the protein. Molecular modeling predicted that Val137 deletion impairs FOXC1 DNA-binding capacity and transcriptional activation. Since loss-of-function mutations in FOXC1 are associated with Axenfeld-Rieger syndrome, the genetic findings in combination with re-evaluation of the patient's clinical data resulted in a corrected diagnosis of Axenfeld-Rieger syndrome with developmental glaucoma. We therefore suggest that in addition to CYP1B1 and MYOC, FOXC1 should be included in the genetic analysis of cases with unclear glaucomatous phenotypes to ensure proper diagnosis, adequate treatment and appropriate genetic counseling.
EVALuna2:9257